Le droit de l'OHADA à l’ère du numérique : réflexion à la lumière de l’acte uniforme organisant le droit commercial général du 15 décembre 2010 dans les 17 pays membres - Mbazi, Grâce Beda; Mbasoni, Séraphin Christian; Iragi Ntwali, Valéry (Studia Universitatis Babeș-Bolyai Studia Europaea, 2025)
Ohbla Law in the Digital Age: Reflections in Light of the Uniform Act Organizing General Commercial Law of 15 December 2010 in the 17 Member Countries. The digitalization of commercial law within the OHBLA area represents a major step toward adapting the legal framework to the digital economy. The 2010 reform introduced key innovations, including the recognition of electronic documents, digital signatures, and the digitalization of the RCCM, thereby improving transaction speed and transparency. However, several challenges persist: unequal digital infrastructure, limited cybersecurity, low digital literacy, and the need for harmonized practices among member States. The success of this reform will therefore require strong technical and institutional support.
Keywords: Commercial law; Cybersecurity; Cybersécurité; Digital infrastructure; Digitalisation; Digitalization; Droit commercial; Legal certainty; OHADA; OHBLA; Sécurité juridique

Le Contrôle des Prix de transfert par les Administrations Fiscales des États de l'Afrique de l'Ouest - Diallo, Mamadou Dian (Université Côte d'Azur, 2025)
Les prix de transfert sont les prix auxquels une entreprise transfère des biens corporels, des actifs incorporels ou rend des services à des entreprises associées situées dans différents pays. En Afrique de l'Ouest, la question des prix de transfert est devenue un enjeu majeur pour les autorités fiscales, dès lors que ces pratiques peuvent être utilisées pour transférer artificiellement des bénéfices vers des juridictions à faible fiscalité, réduisant ainsi les recettes fiscales locales. Les pays de l'Afrique de l'Ouest connaissent une forte présence d'entreprises multinationales, en particulier, dans les secteurs des mines, du pétrole, des télécommunications etc. La faiblesse des capacités de contrôle fiscal, combinée à la complexité des montages fiscaux, rendent difficile la lutte contre l'érosion de la base d'imposition et le transfert de bénéfices à l'étranger.L'imposition des entreprises multinationales est gouvernée par les principes dits, de « territorialité » et de « pleine concurrence ». Il résulte des standards internationaux, que chaque entité d'un groupe multinational doit s'acquitter de l'impôt dans son pays d'implantation, en déterminant son bénéfice local comme si ses transactions avec les autres entités qui lui sont liées étaient effectuées avec des entreprises indépendantes.La présente thèse a pour objectif de traiter du contrôle des prix de transfert par les autorités fiscales des pays de l'Afrique de l'Ouest, dans un contexte où la lutte contre l'évasion fiscale internationale est devenue un enjeu mondial. A cet égard, le projet BEPS initié en 2013 par le G20 a formulé des recommandations à l'endroit des autorités fiscales permettant de traiter efficacement les questions liées aux pratiques BEPS. Ce projet a été intégré dans les principes de l'OCDE applicables en matière de prix de transfert à l'intention des entreprises multinationales et des administrations fiscales, renforcé par le Manuel Pratique de l'ONU sur les prix de transfert à l'intention des pays en voie de développement. Il replace le principe de pleine concurrence au centre de la lutte contre les pratiques BEPS. Transfer pricing refers to the price at which a company transfers tangible or intangible assets, or provides services to associated companies located in different countries. In West Africa, the issue of transfer pricing has become a major challenge for tax authorities, as these practices can be used to artificially shift profits to low-tax jurisdictions, thereby reducing local tax revenues. West African countries have a strong presence of multinational companies, particularly in the mining, oil, and telecommunications sectors. Weak tax audit capacities, combined with the complexity of tax arrangements, make it difficult to combat base erosion and profit shifting abroad.The taxation of multinational companies is governed by the so-called ''territoriality'' and ''arm's length'' principles. International standards stipulate that each entity within a multinational group must pay tax in its country of establishment, determining its local profit as if its transactions with other related entities were conducted with independent companies.This thesis aims to address transfer pricing controls by tax authorities in West African countries, in a context where the fight against international tax evasion has become a global issue. In this regard, the BEPS project initiated in 2013 by the G20 has formulated recommendations for tax authorities to effectively address issues related to BEPS practices. This project was incorporated into the OECD Transfer Pricing Guidelines for Multinational Enterprises and Tax Administrations, reinforced by the UN Practical Handbook on Transfer Pricing for Developing Countries. It places the arm's length principle at the center of the fight against BEPS practices.
Keywords: Administration fiscale; Afrique de l'Ouest; Afrique occidentale; Arm's length principle; BEPS; Base d’imposition; Control; Contrôle; Entreprises multinationales; Indirect profit shifting; Multinational enterprises; Pricing; Principe de pleine concurrence; Prix; Prix de cession interne; Prix de transfert (manipulation); Procédures fiscales; Tax authorities; Transfer; Transfer pricing; Transfert; Transfert indirect de bénéfices; West Africa

L'abus de droit en matière fiscale - Silberman, Lauren (Université Paris 12, 2025)
La théorie de l’abus de droit se présente comme un correctif essentiel à l’exercice des droits et un outil pour rétablir l’équilibre entre les intérêts en présence qui sont, en matière fiscale, ceux des contribuables, de l’administration fiscale et de la collectivité. L’abus de droit dépend du droit auquel une limite est apportée, limite pouvant être fixée par le législateur et selon une politique déterminée. Le législateur français a autonomisé la notion d’abus de droit en matière fiscale par la création d’une procédure spéciale de rectification assortie d’une majoration automatique punitive. La multiplication des dispositifs anti-abus d’assiette, qui s’applique dans le cadre de la procédure de rectification de droit commun, et qui n’entrainent pas l’application automatique d’une pénalité, a mené à une évolution de la notion d’abus de droit en matière fiscale. Ces dispositifs encadrent l’exercice de la liberté de choisir la voie la moins imposée, et se distinguent par leur régime et leur sanction. Corrélativement, l’Union européenne a développé sa propre notion d’abus de droit en matière fiscale, d’abord pour apprécier la compatibilité des dispositifs nationaux au droit primaire de l’Union, puis pour encadrer l’exercice des avantages offerts par le droit dérivé. Elle a ainsi dégagé une définition de l’abus de droit dont les critères diffèrent selon le droit abusé. L’OCDE s’est également intéressée à la notion d’abus en matière fiscale dans le cadre de la lutte contre l’érosion de la base d’imposition et le transfert de bénéfices. Son approche, plus pragmatique, se concentre sur les comportements des contribuables et de redevables qui doit être conforme non pas à la législation, mais à la politique fiscale et à l’équité fiscale entre les Etats et les opérateurs sur le marché mondial. L’Union européenne a adopté la même conception de l’abus de droit en matière fiscale par l’adoption d’un paquet de mesures de lutte contre la fraude et l’évasion fiscales. L’approche comportementale et économique de l’abus de droit coexiste aujourd’hui avec l’approche stricte et répressive du droit fiscal français. Cette coexistence a mené à la multiplication des dispositifs anti-abus d’assiette qui font entrer dans le champ de l’abus des comportements identifiés comme abusifs parce que non conformes à la conception internationale et européenne de l’équité fiscale. La notion de fictivité s’est élargie au profit de la notion de validité pour faire entrer dans son champ des comportements autrefois considérés comme de l’optimisation fiscale. Cette nouvelle approche de l’abus de droit en matière fiscale est source d’incertitudes pour les contribuables et les redevables et permet de s’interroger sur l’étendue de la notion d’abus de droit en matière fiscale. The theory of abuse of rights is an essential corrective to the exercise of rights, and a tool for restoring the balance between the interests involved, which, in tax matters, are those of the taxpayer, the tax authorities and the community. Abuse of rights depends on the law to which a limit has been set, a limit that can be set by the legislator according to a specific policy. The French legislator has given autonomy to the notion of abuse of rights in tax matters. It has created a provision to penalize abuse of rights, with a special rectification procedure and an automatic punitive surcharge. But it has also created anti-abuse provisions which apply within the framework of the ordinary rectification procedure and which do not entail the automatic application of a penalty. While all of these measures provide a framework for exercising the freedom to choose the path of least resistance to taxation, they differ in terms of their regimes and penalties. The European Union has also developed its own concept of abuse of rights in tax matters, firstly to assess the compatibility of national provisions with EU primary law, and then to provide a framework for the exercise of the advantages offered by secondary legislation. It has thus established a definition of abuse of rights, the criteria for which differ according to the law being abused. The OECD has also turned its attention to the notion of tax abuse as part of the fight against tax base erosion and profit shifting. Its more pragmatic approach focuses on the behavior of taxpayers and liables, which must be consistent not with legislation, but with tax policy and tax fairness between countries and operators on the global market. The European Union has adopted the same concept of abuse of rights in tax matters, with the adoption of a package of measures to combat tax fraud and evasion. Today, the behavioral and economic approach to abuse of rights coexists with the strict and repressive approach of French tax law. This coexistence has led to a proliferation of anti-abuse provisions that bring into the scope of abuse behaviors identified as abusive because they do not conform to international and European concepts of tax fairness. The notion of fictitiousness has been broadened in favor of the notion of validity, bringing within its scope behaviors previously considered as tax planning. This new approach to abuse of rights in tax matters is a source of uncertainty for taxpayers and liables and raises questions about the scope of the notion of abuse of rights in tax matters.
Keywords: Abus de droit; Abuse of rights; Anti-Abuse mesures; Choice of the path of least taxation; Choix de la voie la moins imposée; Dispositifs anti-Abus; Droit fiscal; Fraude et évasion fiscales; Fraude fiscale; Freedom of movement; Liberté de circulation; Optimisation fiscale; Tax fraud and evasion; Tax planning

La sécurité alimentaire à l'épreuve du droit foncier rural en Côte d'Ivoire - Ekra, Kanga Mireille (Université Côte d'Azur, 2025)
La sécurité alimentaire est un enjeu primaire pour tous les pays du monde en particulier les pays en développement. À ce propos, le foncier rural joue un rôle fondamental dans l'effectivité de la sécurité alimentaire. Ce rôle peut s'apprécier en fonction du régime juridique qui s'applique aux terres rurales.La Côte d'Ivoire s'est dotée de la loi de 1998 sur le droit foncier rural. Cette loi reconnaît le régime de propriété privée et le libéralisme économique comme des fondamentaux à la protection et surtout à la sécurisation du foncier rural ivoirien longtemps marqué par les règles coutumières. Or, ces normes -régime de propriété privée et libéralisme économique- telles qu'elles sont conçues et exécutées lèsent les petits exploitants-agriculteurs au profit d'une élite de personnes et des investisseurs. En effet, les objectifs recherchés par ces derniers sont en contradiction avec ceux soutenus par les petits agriculteurs-exploitants. Ainsi, les règles du droit foncier rural ivoirien constituent des facteurs de risques pour la sécurité alimentaire en Côte d'Ivoire, car elles sont plutôt favorables à une mise à disposition durable des terres à des personnes peu enclines à faire de la sécurité alimentaire une priorité.Afin de pallier la généralisation du régime de propriété privée, il serait possible d'envisager l'instauration potentielle d'un régime de propriété coutumière. Un tel régime se distingue par des caractères particuliers, respectueux des droits fondamentaux des peuples autochtones et à même de répondre aux besoins alimentaires des petits exploitants-agriculteurs et de leurs communautés. Ces dernières années, la propriété coutumière se présente comme une alternative aux cas d'accaparements de terres, de violations des droits des peuples autochtones et de l'épuisement de leurs ressources naturelles. Food security is a primary issue for all countries of the world, particularly developing countries. In this regard, rural land plays a fundamental role in the effectiveness of food security. This role can be assessed in terms of the legal regime that applies to all rural land.Côte d'Ivoire has adopted the Rural Land Law of 1998. This law recognizes the private property regime and economic liberalism as fundamental rules for the protection and, above all, for the security of Ivorian rural land, which has long been marked by customary rules. Yet these standards - private property and economic liberalism - as they are enforced turn their backs on smallholder farmers to the benefit of an elite of people and investors. Based on this observation, the economic objectives pursued by these ''privileged'' are at odds with those defended by smallholder farmers. Thus, the rules of rural land law pose a risk factor for food security in Côte d'Ivoire.In order to compensate for the generalization of the private property regime and its variations must be mitigated by the possible introduction of a customary property regime. Such a regime has special characteristics, respectful of the human rights of indigenous peoples and responsive to the food needs of smallholder farmers and their communities. In recent years, it has been presented as an alternative to cases of land grabbing, violations of the rights of indigenous peoples and the depletion of their natural resources
Keywords: Autochtone; Coutumier; Customary; Côte d'Ivoire; Droit foncier rural; Droit rural; Food security; National production; Production nationale; Propriété foncière (droit); Rural land law; Sécurité alimentaire

La monnaie électronique dans les espaces bancaires européens, sous régionaux africains et OHADA - Fougou, Pierre Damien (Université de Bordeaux, 2025)
En tant qu’innovation majeure, la monnaie électronique s’est imposée dans l’écosystème financier en permettant aux agents économiques de répondre à des besoins distincts mais complémentaires tant en Europe qu’en Afrique. A cet effet, l’analyse de la monnaie électronique à l’aune de ces deux espaces géographiques, et précisément de trois espaces bancaires que sont l’UE, l’UMOA et la CEMAC, a notamment permis de mettre en lumière les différentes dynamiques qu’entraîne cet instrument moderne. En Europe, la monnaie électronique constitue une réponse pragmatique aux micropaiements dans une économie largement bancarisée. En Afrique, elle représente, bien plus qu’une simple solution aux micropaiements, un levier essentiel d'inclusion financière pour des populations majoritairement non bancarisées. Cette thèse propose une analyse juridique comparative de la monnaie électronique dans ces deux espaces géographiques, révélant des contextes socio-économiques contrastés ainsi que des perspectives radicalement différentes malgré une appréhension juridique commune. Afin de mener une analyse intégrant à la fois l’évolution juridique et technologique de la monnaie électronique et des moyens de paiements numériques, l’on consacrera la première partie de l’analyse à étudier les critères de qualification de la monnaie électronique, ce qui permettra de souligner que les espaces bancaires concernés par l’étude disposent d’une appréhension juridique commune en la matière, tout en ayant des appropriations technologiques différentes qui s’illustrent par des formes de monnaie électronique distinctes selon que l’on se trouve en Europe ou dans les espaces bancaires UMOA et CEMAC. Ensuite, l’analyse se poursuivra avec l’étude des innovations technologiques et des mutations juridiques qui ont eu lieu avec l’émergence de la monnaie électronique. Cette analyse sera également le pilier de la posture prospective dans laquelle s’inscrit cette thèse car elle permettra non seulement d’asseoir les réflexions sur la nécessaire évolution des critères monétaires face à l’émergence des moyens de paiements numériques, mais également de plaider pour un changement de paradigme qui consistera principalement à réduire l’ampleur du monopole monétaire traditionnel, et à instaurer une concurrence plus dynamique entre moyens de paiement. Dans cette démarche prospective ayant pour objectif d’améliorer l’efficacité des moyens de paiement et de garantir une inclusion financière plus optimale, l’on proposera également que soit attribué un cours légal à la monnaie électronique en Afrique, et que soit mis sur pied un jeton de monnaie électronique de banque centrale s’appuyant sur la technologie des registres distribués, et ce, afin de favoriser l’intégration économique africaine. En somme, la monnaie électronique constitue bien plus qu'une simple innovation technique. Elle est et peut devenir un véritable vecteur de transformation profonde des systèmes financiers et du droit monétaire. Son encadrement juridique doit donc continuer à évoluer pour accompagner son développement exponentiel. En Afrique particulièrement, les régulateurs gagneraient à en faire un instrument privilégié d'inclusion financière et d'intégration économique régionale, et ce, en optant pour des réformes juridiques et institutionnelles ambitieuses. Cette recherche propose ainsi de repenser les fondements du droit bancaire et monétaire non seulement afin d’adapter la monnaie électronique aux réalités d’une économie de plus en plus numérisée et moins centralisée, mais surtout afin de faire de cet instrument moderne un outil propice aux besoins d’intégration économique en Afrique. As a major innovation, electronic money has established itself in the financial ecosystem by enabling economic agents to meet distinct yet complementary needs in both Europe and Africa. To this end, the analysis of electronic money through the lens of these two geographical areas, and specifically of three banking zones – the EU, WAMU, and CEMAC – has notably highlighted the various dynamics generated by this modern instrument. In Europe, electronic money represents a pragmatic response to micropayments in a largely banked economy. In Africa, it constitutes far more than a simple solution for micropayments; it serves as an essential lever for financial inclusion among predominantly unbanked populations. This thesis offers a comparative legal analysis of electronic money in these two geographical areas, revealing contrasting socio-economic contexts as well as radically different perspectives despite a common legal understanding. In order to conduct an analysis that integrates both the legal and technological evolution of electronic money and digital payment methods, the first part of the analysis will be devoted to examining the qualification criteria for electronic money. This will underscore that the banking zones covered by the study share a common legal understanding of the matter, while having different technological appropriations that are illustrated by distinct forms of electronic money depending on whether one is in Europe or in the WAEMU and CEMAC banking zones. Subsequently, the analysis will continue with the study of technological innovations and legal transformations that have occurred with the emergence of electronic money. This analysis will also serve as the cornerstone of the forward-looking approach that underpins this thesis, as it will not only ground reflections on the necessary evolution of monetary criteria in the face of emerging digital payment methods, but will also advocate for a paradigm shift consisting primarily of reducing the scope of the traditional monetary monopoly and establishing more dynamic competition among payment methods. Within this forward-looking approach aimed at improving the efficiency of payment methods and ensuring more optimal financial inclusion, it will also be proposed that electronic money be granted legal tender status in Africa, and that a central bank electronic money token be established based on distributed ledger technology, in order to promote African economic integration. In sum, electronic money represents far more than a mere technical innovation. It is and can become a genuine vector for profound transformation of financial systems and monetary law. Its legal framework must therefore continue to evolve to support its exponential development. In Africa particularly, regulators would benefit from making it a privileged instrument for financial inclusion and regional economic integration, by opting for ambitious legal and institutional reforms. This research thus proposes to rethink the foundations of banking and monetary law not only to adapt electronic money to the realities of an increasingly digitized and less centralized economy, but especially to make this modern instrument a tool conducive to the needs of economic integration in Africa.
Issue: 2025BORD0334
Keywords: Afrique; Bank; CEMAC; Communauté Economique et Monétaire de l'Afrique Centrale; EU; Electronic money; Espace bancaire; Monnaie électonique; OHADA; Organisation pour l'harmonisation en Afrique du droit des affaires; Pays de l'Union européenne; UE; UMOA; Union économique et monétaire Ouest africaine; WAMU

Réflexion sur la procédure de médiation de l’acte uniforme de l’OHADA relatif à la Médiation (AUM) - Adjita, Shamsidine Akrawati (Revue Internationale de Droit et Science Politique, 2025)
La médiation n’est pas une invention du législateur de l’OHADA. Elle est aussi vieille que le monde. Sa consécration légale à travers l’Acte uniforme relatif à la médiation met en évidence son importance dans la résolution des litiges à l’amiable dans l’ordonnancement juridique de l’OHADA. Cela s’explique car la médiation renvoie à l’idée de justice. Le sentiment de justice n’est pas lié à une époque, il est plutôt inhérent à l’existence humaine et porte en lui-même une exigence, une valeur fondamentale universellement reconnue. Il s’agit du droit à la justice dont le respect permet d’apprécier de façon efficiente les valeurs auxquelles une société est attachée. Toute société a besoin de justice, mais elle ne peut la rendre de façon satisfaisante avec le procédé traditionnel qu’est le jugement. Le juge ne peut pas tout. Le bon sens dicte de l’éviter. Selon un adage populaire, « un mauvais accord vaut mieux qu’un bon procès ». Là où il y a une société, il y a des différends. Là où il y a des différends, il y a des modes de règlement des différends parmi lesquels la médiation occupe une place de choix. Avatar médiatisé de la justice consensuelle, panacée de la déjudiciarisation et de la déjuridicisation, la médiation est parée de toutes les vertus pour éviter le procès. Elle apparaît donc comme une alternative à laquelle peuvent recourir les parties en conflit pour régler leur malentendu à l’amiable tout en préservant leurs relations d’affaires. Elle n’est pas une procédure laissée à l’appréciation du juge, mais plutôt à celle des parties en conflit qui en sont les principales actrices. Cependant elles ne peuvent parvenir à la résolution de leur litige que par l’intermédiaire d’un tiers appelée médiateur et sans lequel la procédure serait incomplète. On a donc, d’un côté, les parties à la médiation qui la considèrent comme étant leur affaire et, de l’autre, le médiateur qui est considéré comme le chef d’orchestre de la procédure. Mediation is not an invention of the OHADA legislator. It is as old as the world itself. Its legal recognition through the Uniform Act on Mediation highlights its importance in the amicable resolution of disputes within the OHADA legal system. This is because mediation refers to the idea of justice. The sense of justice is not tied to a particular era; rather, it is inherent to human existence and carries with it a requirement, a universally recognized fundamental value. It is the right to justice, respect for which allows for the efficient appreciation of the values to which a society is attached. Every society needs justice, but it cannot deliver it satisfactorily through the traditional process of judgment. Judges cannot do everything. Common sense dictates that it should be avoided. According to a popular saying, “a bad agreement is better than a good trial.” Where there is society, there are disputes. Where there are disputes, there are ways of resolving them, among which mediation occupies a prominent place. As the media-friendly face of consensual justice and the panacea for reducing court cases and legal proceedings, mediation is seen as the ideal way to avoid litigation. It therefore appears to be an alternative that parties in conflict can use to settle their differences amicably while preserving their business relationships. It is not a procedure left to the discretion of the judge, but rather to that of the parties in conflict, who are the main actors. However, they can only resolve their dispute through a third party called a mediator, without whom the procedure would be incomplete. On the one hand, therefore, we have the parties to the mediation, who consider it to be their business, and on the other, the mediator, who is considered to be the conductor of the procedure.
Keywords: Acte uniforme; Judge; Juge; Mediation; Mediator; Médiateur; Médiation; Parties en conflit; Parties to the dispute; Uniform Act

Les actions en responsabilité médicale pour faute de diagnostic en droit ivoirien au regard du droit français - Agbodo, Attemene Jean Paul (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2025)
Si l’erreur de diagnostic ne constitue pas en elle-même une faute pénale, il en est tout autre de la faute de diagnostic qui prouvée, permet au patient d’engager la responsabilité du médecin- auteur du diagnostic, tant devant les juridictions judiciaires qu’administratives, outre les voies de règlement amiable du litige. Cette efficacité avec laquelle le législateur français entend prendre en compte les actions des patients-victimes contre les professionnels de santé pour la réparation des préjudices subis, reste inexistante en droit ivoirien, malgré les multiples dénonciations des manquements fautifs des médecins dans la prise en charge de leurs patients. Toute chose qui appelle aujourd’hui, à l’impérieuse nécessité d’une réforme du droit de la santé ivoirien au regard du droit français. Afin de garantir au patient un traitement sérieux de sa pathologie conformément aux données acquises par la science. If the error of diagnosis does not constitute in itself a penal fault, it is quite different for the fault of diagnosis which, once proven, allows the patient to engage the responsibility of the doctor-author of the diagnosis, as well before the judicial jurisdictions as administrative, in addition to the ways of amicable settlement of the litigation. This efficiency with which the French legislator intends to take into account the actions of patient-victims against health professionals for the reparation of the prejudices suffered, remains non-existent in Ivorian law, in spite of the multiple denunciations of the faulty failings of doctors in the care of their patients. All this calls for the urgent need to reform Ivorian health law in line with French law. In order to guarantee the patient a serious treatment of his pathology in accordance with the data acquired by science.
Keywords: Compensation; Consolidation; Doctor; Indemnisation; Médecin; Patient; Victim; Victime

La rupture conventionnelle du contrat de travail au Togo - Alipoe, Pierre-Paul Kossi (Revue Internationale de Droit et Science Politique, 2025)
La rupture conventionnelle du contrat de travail est introduite dans le Code du travail par la loi du 18 juin 2021 portant Code du travail. C’est un mode de rupture négocié et homologué par l’inspecteur du travail. Il vient s’ajouter aux modes traditionnels de rupture du contrat de travail que sont la démission, le licenciement et la rupture par consentement mutuel. Il garantit une sécurité financière au travailleur tout en évitant les risques et les coûts d’un licenciement pour l'employeur. S’il faut bien louer ces avantages, les risques qu’il renferme ne doivent pas être oubliés. Le nouveau mode de rupture peut servir de moyen pour contourner des règles protectrices des droits des travailleurs. Ces faiblesses du dispositif peuvent être corrigées par un affinement de la procédure de rupture. Ces ajustements concernent aussi bien la procédure de la rupture que les pouvoirs du juge du travail. Il faudra également clarifier le domaine de la rupture. Ainsi, les travailleurs dont les contrats sont éligibles à la rupture conventionnelle devront être identifiés et l’articulation entre le nouveau mode de rupture et les modes traditionnels de cessation du contrat de travail devra également être précisée. The mutual termination of the employment contract was introduced into the Labour Code by the Act of 18 June 2021 enacting the Labour Code. It constitutes a negotiated mode of termination subject to approval by the labour inspector. This mechanism complements the traditional forms of termination of the employment contract, namely resignation, dismissal, and termination by mutual consent. It offers financial security to the employee while enabling the employer to avoid the risks and costs associated with dismissal. While these advantages deserve recognition, the risks inherent in this new form of termination should not be overlooked. Indeed, mutual termination may serve as a means of circumventing certain rules designed to protect workers’ rights. These weaknesses in the system may be addressed through a refinement of the termination procedure. Such adjustments should concern both the procedural framework governing mutual termination and the powers of the labour judge. Furthermore, the scope of application of mutual termination must be clarified. In this regard, the categories of workers whose contracts are eligible for mutual termination must be clearly identified, and the relationship between this new mode of termination and the traditional forms of termination of the employment contract must also be clearly articulated.
Keywords: Administrative approval; Contractualisation; Contractualization; Contrat de travail; Droit du travail; Employment contract; Homologation; Labour law; Legal certainty; Mutual termination; Rupture conventionnelle; Sécurité juridique

Les préoccupations environnementales en droit OHADA des sociétés commerciales - Amougou, Max Aristide (Revue Internationale de Droit et Science Politique, 2025)
De plus en plus, à travers le monde, il est demandé et attendu des entreprises d’aller au-delà de la seule finalité économique et financière au profit des associés et intégrer, entre autres, des considérations environnementales dans leurs décisions. Cette dynamique, est certes lente et timide, mais en construction dans le droit OHADA des sociétés commerciales. Ce droit reçoit implicitement les préoccupations environnementales. Il n’est donc pas totalement indifférent face à l’impérieuse nécessité de protection et de restauration de la nature. Or, l’environnement se vend et fait vendre. Il pourrait alors constituer un facteur de renforcement de l’attractivité du droit OHADA dans son ensemble et faire des sociétés commerciales des entités philanthropiques. L’intégration explicite des préoccupations environnementales dans le droit OHADA des sociétés serait alors requise. Elle accroitrait autant la compétitivité que la crédibilité des entreprises africaines au plan national et international. Increasingly, around the world, companies are being asked and expected to go beyond purely economic and financial objectives for the benefit of their shareholders and to integrate environmental considerations into their decision-making. This dynamic, while admittedly slow and tentative, is taking shape within OHADA business law. This law implicitly acknowledges environmental concerns. It is therefore not entirely indifferent to the pressing need to protect and restore nature. The environment is a marketable commodity and a driver of sales. It could thus become a factor in strengthening the attractiveness of OHADA law as a whole and transform businesses into philanthropic entities. The explicit integration of environmental concerns into OHADA business law would therefore be necessary. This would enhance both the competitiveness and the credibility of African companies at the national and international levels.
Keywords: Business law; CSR; Droit des sociétés commerciales; Environment; Environmental concerns; Environnement; Préoccupations environnementales; RSE

La femme sous l'angle des droits fondamentaux - Barsali, Jeanne (Université de Bordeaux, 2025)
Les droits fondamentaux, par leur universalité, visent à protéger les valeurs les plus essentielles de tout individu. Leur effectivité suppose cependant le respect du principe d’égalité, lequel ne se limite pas à un traitement uniforme : il implique que des situations différentes appellent un traitement différencié, afin d’assurer une égalité réelle. Or, les femmes, en raison de spécificités biologiques et sociales qui leur sont propres, se trouvent souvent dans des situations particulières qui justifient une protection accrue. Cette spécificité conduit à distinguer deux formes de protection. La première, explicite, consiste à prévoir des dispositifs visant directement les femmes dans les situations qui ne les concernent qu’elles, comme la grossesse ou la maternité. La seconde, implicite, agit par l’intermédiaire de normes générales applicables à tous, mais dont les femmes demeurent les principales bénéficiaires en raison de leur exposition particulière à certains phénomènes sociaux. Tel est notamment le cas des violences conjugales, où les femmes représentent la grande majorité des victimes. L’articulation de ces deux formes de protection révèle néanmoins des insuffisances structurelles. Les textes, bien que nombreux, se heurtent à une application imparfaite, qui laisse subsister un écart significatif entre la proclamation des droits et leur effectivité concrète. De plus, certaines problématiques spécifiques aux femmes demeurent insuffisamment encadrées ou ignorées par le législateur, ce qui entretient des discriminations persistantes dans des domaines essentiels tels que l’économie ou la santé. L’analyse met ainsi en lumière la nécessité d’un double mouvement : d’une part, renforcer l’application et l’efficacité des dispositifs existants afin d’assurer leur pleine effectivité ; d’autre part, envisager de nouvelles pistes d’amélioration pour combler les lacunes actuelles et garantir une protection plus complète et plus équitable des droits fondamentaux des femmes. By their universality, fundamental rights aim to protect the most essential values of any individual. However, their efficiency presupposes respect of the principle of equality, which is not only limited to an uniform treatment : it implies different situations call for different treatments, in order to ensure real equality. Fundamental rights, by their universality, aim to protect the most essential values of every individual. Their effectiveness presupposes, however, respect for the principle of equality, which is not limited to uniform treatment: it implies that different situations call for differential treatment, in order to ensure real equality. However, women, because of their own biological and social specificities, often find themselves in special situations that justify increased protection. Yet women often end up, because of their own biological and social specificities, in special situations that justify an increased protection. This specificity leads to a distinction between two forms of protection. The first one, which is explicit, consists in providing devices designed directly for women in situations that only concern them, such as pregnancy or motherhood. The second one is implicit and acts through general rules applicable to all, but of which women end up being the main beneficiaries because of their particular exposure to certain social phenomena such as domestic violence, where women represent the vast majority of victims. Nevertheless the articulation of these two forms of protection reveals structural insufficiencies. Although numerous, the texts come up against an incomplete application and this leaves a significant gap between the proclamation of rights and their concrete effectiveness. On top of that, certain issues specific to women remain insufficiently supervised or ignored by the legislator, which maintains persistent discrimination in essential areas such as the economy or health. The analysis thus highlights the need for a two-fold approach : on one hand, strengthening the application and effectiveness of existing schemes in order to ensure their full effectiveness, and on the other hand, considering new ways for improvement to fill the current gaps and ensure a more complete and equitable protection of women's fundamental rights.
Issue: 2025BORD0408
Keywords: Discrimination; Droits fondamentaux; Equality; Femme; Fundamental rights; Protection; Woman; Égalité

L’émergence d’une dualité de la figure du consommateur en droit CEMAC de la consommation : entre vulnérabilité normative et réactance fonctionnelle - Boussakoumdi, Pierre (Revue Internationale de Droit et Science Politique, 2025)
Le droit CEMAC de la consommation repose classiquement sur une logique de protection du consommateur, appréhendé comme la partie structurellement vulnérable dans les relations de marché. Cette vulnérabilité, consacrée tant par la directive n°02/19-UEAC-639-CM-33 harmonisant la protection du consommateur au sein de la CEMAC que par les législations nationales des États membres, justifie une intervention normative visant à corriger les déséquilibres contractuels au profit du consommateur. Toutefois, l’évolution des pratiques de consommation, la judiciarisation croissante des relations contractuelles et l’émergence de préoccupations environnementales et sociétales révèlent une transformation progressive de la figure du consommateur. Celui-ci apparaît désormais comme un acteur revendicatif et engagé, assumant des charges procédurales et participant à l’orientation des modes de production et de consommation. L’article met ainsi en lumière l’émergence d’une dualité de la figure du consommateur en droit CEMAC de la consommation, oscillant entre vulnérabilité normative et réactance fonctionnelle, et interroge la capacité du droit positif à concilier protection et responsabilisation du consommateur. CEMAC consumer law has traditionally been based on the protection of the consumer, regarded as the structurally weaker party in market relations. This vulnerability, enshrined both in Directive No. 02/19-UEAC-639-CM-33 harmonizing consumer protection within CEMAC and in the national legislations of Member States, justifies regulatory intervention aimed at correcting contractual imbalances. However, the evolution of consumption practices, the increasing judicialization of consumer relations, and the rise of environmental and social concerns reveal a gradual transformation of the consumer’s role. The consumer now appears as a more assertive and engaged actor, bearing procedural obligations and influencing production and consumption patterns. This article highlights the emergence of a dual figure of the consumer in CEMAC consumer law, oscillating between normative vulnerability and functional reactance, and questions the ability of positive law to reconcile consumer protection with growing consumer responsibility.
Keywords: CEMAC law; Consommateur; Consumer; Droit CEMAC; Reactance; Réactance; Vulnerability; Vulnérabilité

Problématique des apports non capitalisables : une focale sur l’apport en industrie en droit des sociétés OHADA - Chouarupouo Ndassa, Moussa Kallil (Revue Internationale de Droit et Science Politique, 2025)
Les apports non capitalisables, en particulier l’apport en industrie, révèlent une difficulté majeure du droit des sociétés : intégrer dans le capital social des contributions immatérielles dont la valeur est essentielle, mais difficile à quantifier. À travers le « visage des apports non capitalisables émergé ». Cet article, analyse met en évidence les limites structurelles du régime actuel notamment l’absence de capitalisation, les difficultés d’évaluation, la participation restreinte de l’apporteur et l’insécurité juridique. Le « visage immergé », quant à lui, permettent ensuite d’identifier les perspectives d’évolution à l’instar de la valorisation accrue des contributions immatérielles, de la création de mécanismes d’évaluation adaptés, de la contractualisation des engagements et de la reconnaissance renforcée du rôle économique de l’apporteur en industrie. Parions, au final, que la modernisation de ce régime constitue une étape nécessaire pour aligner le droit des sociétés sur les standards de l’économie immatérielle contemporaine.
Keywords: AUSCGIE; Apport en industrie; Apport non capitalisable; Bien immatériel; Capital social; Droit des sociétés; Evaluation des apports

Les insuffisances du droit des sociétés de l'OHADA : analyse critique des tensions paradoxales entre innovations réformatrices et pratiques locales, à la lumière du droit français, allemand et de l'Union européenne - Diallo, Mamadou Alimou (Université de Perpignan Via Domitia, 2025)
Il est désormais bien établi que le 17 avril 1997, en application des articles 1 et 2 du Traité portant Organisation pour l’Harmonisation en Afrique du Droit des Affaires (désigné ci-dessous sous l’acronyme OHADA), signé en octobre 1993 à Port-Louis, en l’île Maurice, l’Acte Uniforme relatif au Droit des Sociétés Commerciales et du Groupement d’Intérêt Économique (ci-après AUSCGIE) a été adopté. Présenté à la fin du XXᵉ siècle comme une avancée législative majeure, cet instrument juridique avait pour ambition d’instaurer des dispositions uniformes régissant les sociétés commerciales opérant dans les États membres de l’Organisation. Quinze ans après son adoption, l’AUSCGIE a fait l’objet d’une première révision substantielle. Cette réforme se distingue par son envergure sans précédent en ce sens que plus de 450 dispositions ont été modifiées, tandis que de nouvelles ont été introduites, témoignant ainsi d’une intervention législative d’une rare intensité. Néanmoins, érigée par le discours institutionnel en symbole de modernisation et d’adaptation du droit aux exigences contemporaines, cette réforme soulève de multiples interrogations quant à sa pertinence véritable et à son efficacité pratique. L’étendue des modifications interroge également sur l’adéquation des ajustements aux réalités économiques et juridiques des États membres. En effet, quelques années à peine après cette réforme, des interrogations substantielles ont émergé quant à la reconfiguration du droit des sociétés et aux modalités de sa mise en œuvre. Ces préoccupations révèlent les failles structurelles du nouvel AUSCGIE, en ce qu’elles conduisent à s’interroger sur sa capacité véritable à instaurer un ordre juridique cohérent au sein de l’espace de l’OHADA, apte à discipliner les entreprises dans la réalisation de leur objet social, tout en intégrant les impératifs contemporains de gouvernance durable. Par ailleurs, l’AUSCGIE reflète les tensions structurelles inhérentes à l’idée même d’harmonisation dans un espace caractérisé par des disparités économiques, politiques et institutionnelles persistantes. Cette tension prend une acuité particulière au regard des rapports normatifs que l’OHADA entretient avec d’autres instances régionales, notamment l’UEMOA et la CEMAC. L’uniformisation des règles, loin d’être un processus fluide et homogène, semble entravée par ces clivages qui fragmentent encore l’espace juridique et judiciaire de l’OHADA. L’objectif de ces travaux n’est pas de livrer une exégèse doctrinale purement descriptive de l’AUSCGIE, ni d’en proposer une critique systématique, encore moins dans une dénégation gratuite de l’œuvre normative du législateur de l’OHADA. Il s’agit plutôt, en mobilisant principalement le droit français, allemand et celui de l’Union européenne (UE), d’analyser la pertinence de cette réforme à l’aune des réalités locales et internationales du droit des affaires, afin d’en apprécier l’efficacité et la capacité à répondre aux défis contemporains auxquels les économies africaines sont confrontées. Cette étude s’attache à apprécier la mesure dans laquelle l’Acte uniforme révisé parvient à véritablement répondre aux attentes qu’il a suscitées. Elle vise à confronter la performativité du discours réformateur à la réalité de sa mise en œuvre, en évaluant la capacité effective du texte à encadrer rationnellement l’activité des entreprises, à catalyser les investissements endogènes et à susciter une confiance durable des investisseurs. Ces axes d’investigation, qui articulent la normativité proclamée et la normativité vécue de l’AUSCGIE révisé, constituent le cœur théorique de la présente recherche. Celle-ci se positionne dans une démarche résolument dé-constructive, tendant à dévoiler les apories structurelles, les incohérences téléologiques et les effets de dissonance entre le modèle prescriptif et les pratiques institutionnelles effectives. It is now well established that on April 17, 1997, pursuant to Articles 1 and 2 of the Treaty on the Organization for the Harmonization of Business Law in Africa (OHADA), signed in October 1993 in Port-Louis, Mauritius, the Uniform Act on Commercial Companies and Economic Interest Groups (AUSCGIE) was adopted. Presented at the end of the twentieth century as a major legislative achievement, this legal instrument aimed to establish uniform provisions governing commercial companies and economic interest groups operating within the OHADA member states. Fifteen years post-adoption, the AUSCGIE underwent its first substantial revision during the 35th session of the OHADA Council of Ministers, convened on January 30, 2014, in Ouagadougou, Burkina Faso. This reform, promulgated in the OHADA Official Journal on February 4, 2014, and entering into force on May 5 of the same year, distinguished itself by its unprecedented scope – over 450 provisions were amended, while numerous new stipulations were introduced, reflecting an intervention of exceptional legislative magnitude. Nevertheless, this revision, ostensibly designed to respond to contemporary imperatives for a legal framework balancing modernity, originality, legal certainty, and flexibility, has engendered significant concerns regarding its substantive relevance and practical efficacy. The breadth of these amendments raises critical questions not only about the coherence and stability of the legal framework but also about the congruence of these adjustments with the economic and juridical realities of the member states. Indeed, only a few years after this reform, significant questions emerged concerning the transformation of company law (the AUSCGIE) and the modalities of its implementation. These concerns reveal the structural shortcomings of the new AUSCGIE, as they lead to doubts about its real capacity to establish a coherent legal order within the OHADA area, capable of regulating companies in the pursuit of their corporate purpose while integrating contemporary imperatives of sustainable governance. Furthermore, the AUSCGIE reflects the structural tensions inherent in the very idea of harmonization within a space characterized by persistent economic, political, and institutional disparities. This tension becomes particularly acute when considering the normative relationships that OHADA maintains with other regional organizations, notably UEMOA and CEMAC. The uniformization of rules, far from being a smooth and homogeneous process, appears hindered by these divisions, which continue to fragment the legal and judicial space of OHADA. The purpose of this research is neither to offer a purely descriptive doctrinal exegesis of the AUSCGIE nor to propose a systematic critique, let alone to deny gratuitously the normative achievements of the OHADA legislator. Rather, by drawing mainly on French, German, and European Union (EU) law, it aims to analyze the relevance of this reform in light of both local and international realities of business law, in order to assess its effectiveness and its ability to respond to the contemporary challenges facing African economies. This study seeks to assess the extent to which the revised Uniform Act truly meets the expectations it generated. It aims to confront the performativity of the reformist discourse with the reality of its implementation, by evaluating the text’s actual capacity to rationally regulate corporate activity, to catalyze endogenous investment, and to foster sustainable investor confidence. These areas of investigation, which connect the proclaimed and the lived normativity of the revised AUSCGIE, constitute the theoretical core of the present research. The study adopts a rigorously deconstructive approach, intended to unveil the structural aporias, teleological inconsistencies, and dissonant effects that emerge between the prescriptive model and the institutional practices effectively shaping it
Keywords: AUSCGIE; Acte uniforme révisé; Allemagne; Critical study of the new reform; Droit OHADA; Droit allemand; Droit de l'Union européenne; Droit des sociétés; Droit français; ESG; EU law; France; French law; German law; Organisation pour l'harmonisation en Afrique du droit des affaires; Pays de l'OHADA; Pays de l'Union européenne; Uniform Act on Commercial Companies and Economic Interest Groupings

Vulnérabilité et détresse du chef de TPE-PME : Aspects juridiques et sociétaux - Duplan, Jhonny (Université de Limoges, 2025)
À travers une lecture critique du droit positif, cette thèse propose une analyse de la vulnérabilité des dirigeants de TPE-PME mettant en lumière les limites du droit face aux multiples contraintes de la réalité entrepreneuriale. Il est démontré que la protection juridique actuellement offerte à ces dirigeants demeure partielle, conditionnelle et fragmentaire alors même qu’ils sont confrontés à des faiblesses et à des risques systémiques qui excèdent largement le simple aléa économique. En croisant les enjeux juridiques, économiques et humains, cette recherche vise à parfaire la place du chef de TPE-PME dans l’ordre juridique. Elle appelle à la mise en place d’un cadre plus lisible, équitable, protecteur, accessible et stratégiquement cohérent. Ce cadre doit permettre de restaurer la confiance, prévenir l’effondrement, favoriser le rebond et offrir à ces dirigeants les conditions d’un engagement entrepreneurial à la fois responsable, digne et sécurisé. En mettant en évidence les sources multiples de cette vulnérabilité, ainsi que les faiblesses et risques particuliers auxquels ces opérateurs économiques sont exposés dans la gestion quotidienne de leurs activités, cette analyse constitue un plaidoyer en faveur de la reconnaissance et/ou de l’attribution de la qualité de personne vulnérable à ces sujets de droit. Through a critical reading of positive law, this thesis offers an analysis of the vulnerability of SME (Small and Medium-sized Enterprise) leaders, highlighting the limitations of the legal system in addressing the numerous constraints of entrepreneurial reality. It demonstrates that the current legal protection afforded to these leaders remains partial, conditional, and fragmented, even though they face weaknesses and systemic risks that go far beyond mere economic uncertainty. By interweaving legal, economic, and human dimensions, this research seeks to redefine the role of the SME leader within the legal order. It calls for the establishment of a clearer, fairer, more protective, accessible, and strategically coherent legal framework. Such a framework should help restore confidence, prevent collapse, support recovery, and provide these leaders with the conditions for responsible, dignified, and secure entrepreneurial engagement. By shedding light on the multiple sources of this vulnerability, as well as the specific weaknesses and risks faced by SME leaders in the day-to-day management of their businesses, this analysis serves as an argument in favor of recognizing – or granting – the status of legally vulnerable persons to these economic actors.
Keywords: Bounce back; Chef de TPE-PME; Distress; Détresse; Head of the company; Petites et moyennes entreprises; Rebond; Resilience; Résilience; Small business owner; TPE-PME; Vulnerability; Vulnérabilité

La prévention de la pénibilité au travail - El Allagui, Khaoula (Université de Limoges, 2025)
La pénibilité au travail, objet en France de débat social depuis une vingtaine d’année est une notion protéiforme et complexe, qui sous-tend des enjeux, approches et des actions différentes suivant les définitions et critères retenus pour des objectifs de compensation ou de réparation. Mais avant même la notion de pénibilité, les questions de prévention et de santé au travail sont présentes depuis longtemps dans les différentes sources normatives qui encadrent l’activité salariée. Les deux notions de pénibilité et de prévention ne trouvent une portée règlementaire concrète que depuis la loi du 9 novembre 2010 portant réforme des retraites. Ainsi, l’obligation de prévention de l’employeur est étendue à la pénibilité au travail au même titre que la prévention des risques professionnels et une définition légale de la notion de pénibilité est formulée. C’est conformément à cette définition que le le Compte Personnel de Prévention de la Pénibilité (C3P) est entré en vigueur dans un objectif de renforcer la culture de prévention de l’entreprise. Il est supprimé en 2017 pour laisser la place au Compte Professionnel de Prévention (C2P).Si la dimension préventive est bien présente, elle reste marquée par une logique de réparation ou de compensation. Une véritable réflexion doit être menée en termes de définition et de prévention pour dépasser cette approche à la lumière des enjeux humains, juridiques et financiers qui s’y attachent.Par ailleurs, les nouvelles organisations du travail ont des conséquences sur la santé des salariés et leur espérance de vie sans incapacité. L’objectif recherché serait d’améliorer la réactivité du dispositif de prévention existant pour l’étendre à certaines formes de pénibilité jusque-là exclues, notamment la pénibilité psychique.Aussi, à plus long terme, c’est une démarche globale et positive de la prévention de la pénibilité qu’il faudra intégrer et promouvoir pour une amélioration pérenne de la santé des travailleurs en entreprise. L’effectivité d’une telle démarche dépend de la volonté et de la capacité des différents acteurs à dépasser les enjeux réglementaires et nécessite l’intervention coordonnée de l’employeur, des partenaires sociaux et des salariés pour engager des actions collectives et durables. La loi du 2 août 2021 dite « santé au travail » traduit juridiquement cette nouvelle approche. Hardship at work which has been the subject of social debate in France for the past twenty years, is a complex concept, which underpins different issues, approaches and actions, depending on the definitions and criteria adopted for compensation or reparation purposes. But even before the notion of "arduousness", questions of prevention and health at work have long been present in the various normative sources that provide a framework for salaried activity. The two concepts of hardship and prevention have only been given concrete regulatory scope since the Pension Reform Act of November 9, 2010. The employer's duty of prevention was thus extended to cover arduous work in the same way as the prevention of occupational risks, and a legal definition of the notion of arduous work was formulated. It was in line with this definition that the “Compte Personnel de Prévention de la Pénibilité (C3P)” came into force, with the aim of reinforcing the company's prevention culture. It was abolished in 2017 to make way for the “Compte Professionnel de Prévention (C2P)”.Although the preventive dimension is clearly present, it remains marked by a logic of reparation or compensation. We need to think hard in terms of definition and prevention, to move beyond this approach in the light of the human, legal and financial stakes involved.In addition, new work organizations are having an impact on employees' health and disability-free life expectancy. The aim is to improve the responsiveness of the existing prevention system and extend it to cover certain forms of hitherto excluded hardship, notably mental hardship.In the longer term, therefore, a comprehensive and positive approach to the prevention of arduous work will need to be integrated and promoted, in order to bring about a lasting improvement in the health of workers in the workplace. The effectiveness of such an approach depends on the willingness and ability of the various players to go beyond regulatory issues, and requires the coordinated intervention of the company, social partners and employees to initiate collective and sustainable actions. The law of August 2, 2021, known as the "health at work" law, gives legal expression to this new approach to prevention in labor law.
Issue: 2025LIMO0076
Keywords: Conditions de travail; Hardness at work; Prevention; Prévention; Pénibilité; Pénibilité du travail; Risqs; Risque; Working conditions

La réglementation de l'intelligence artificielle dans le secteur de la conformité bancaire : approche européenne et canadienne - Gérard, Lorène (Université de Montréal, 2025)
Ce mémoire propose une analyse comparative de l'intégration de l'intelligence artificielle (IA) dans le secteur de la conformité bancaire, en s'intéressant aux approches européennes et canadiennes. Tandis que l'Union européenne a choisi de structurer cet encadrement à travers un règlement spécifique, le Canada avance de manière plus fragmentée, particulièrement depuis l'abandon du projet de loi C-27. Au fil de l'étude, plusieurs défis communs émergent : multiplication des normes, chevauchement des obligations, et insécurité juridique, autant de facteurs qui compliquent l'adoption d'outils d'IA dans le respect des exigences de conformité. L'analyse met en lumière les conséquences concrètes de cette fragmentation, notamment la hausse des coûts de conformité et un frein à l'innovation technologique. À partir de ces constats, ce travail propose des pistes pour clarifier et mieux articuler les règles existantes, en vue de bâtir un cadre plus lisible, cohérent et propice à l'innovation. En définitive, l’objectif poursuivi est d’esquisser les contours d’une régulation de l’IA adaptée aux défis du secteur bancaire, dans un contexte technologique en perpétuelle évolution. This thesis offers a comparative analysis of the integration of artificial intelligence (AI) into the field of banking compliance, focusing on the European and Canadian approaches. While the European Union has chosen to frame this integration through a specific regulation, Canada is advancing in a more fragmented manner, particularly following the abandonment of Bill C-27. Throughout the study, several common challenges emerge: the multiplication of standards, overlapping obligations, and legal uncertainty, all of which complicate the adoption of AI tools while ensuring regulatory compliance. The analysis highlights the concrete consequences of this fragmentation, including rising compliance costs and a potential slowdown in technological innovation. Based on these findings, this work proposes avenues for clarifying and better coordinating existing regulations, aiming to build a more coherent, understandable, and innovation-friendly framework. Ultimately, the goal is to outline a regulatory model for AI that meets the evolving challenges faced by the banking sector in an ever-changing technological landscape
Keywords: Artificial Intelligence; Banking Compliance; Cadre réglementaire canadien de l’IA; Cadre réglementaire européen de l’IA; Canadian Regulatory Framework for AI; Conformité bancaire; European regulatory framework for AI; Intelligence artificielle

La réglementation de l’intelligence artificielle dans le secteur de la conformité bancaire : approche européenne et canadienne - Gérard, Lorène (Université de Montréal, 2025)
Ce mémoire propose une analyse comparative de l'intégration de l'intelligence artificielle (IA) dans le secteur de la conformité bancaire, en s'intéressant aux approches européennes et canadiennes. Tandis que l'Union européenne a choisi de structurer cet encadrement à travers un règlement spécifique, le Canada avance de manière plus fragmentée, particulièrement depuis l'abandon du projet de loi C-27. Au fil de l'étude, plusieurs défis communs émergent : multiplication des normes, chevauchement des obligations, et insécurité juridique, autant de facteurs qui compliquent l'adoption d'outils d'IA dans le respect des exigences de conformité. L'analyse met en lumière les conséquences concrètes de cette fragmentation, notamment la hausse des coûts de conformité et un frein à l'innovation technologique. À partir de ces constats, ce travail propose des pistes pour clarifier et mieux articuler les règles existantes, en vue de bâtir un cadre plus lisible, cohérent et propice à l'innovation. En définitive, l’objectif poursuivi est d’esquisser les contours d’une régulation de l’IA adaptée aux défis du secteur bancaire, dans un contexte technologique en perpétuelle évolution. This thesis offers a comparative analysis of the integration of artificial intelligence (AI) into the field of banking compliance, focusing on the European and Canadian approaches. While the European Union has chosen to frame this integration through a specific regulation, Canada is advancing in a more fragmented manner, particularly following the abandonment of Bill C-27. Throughout the study, several common challenges emerge: the multiplication of standards, overlapping obligations, and legal uncertainty, all of which complicate the adoption of AI tools while ensuring regulatory compliance. The analysis highlights the concrete consequences of this fragmentation, including rising compliance costs and a potential slowdown in technological innovation. Based on these findings, this work proposes avenues for clarifying and better coordinating existing regulations, aiming to build a more coherent, understandable, and innovation-friendly framework. Ultimately, the goal is to outline a regulatory model for AI that meets the evolving challenges faced by the banking sector in an ever-changing technological landscape.
Keywords: AI; Artificial Intelligence; Banking Compliance; Cadre réglementaire canadien; Cadre réglementaire européen; Canadian Regulatory Framework; Conformité bancaire; European regulatory framework; IA; Intelligence artificielle

Social media and structural injustice : a critical analysis of EU platform regulation - Griffin, Rachel (Institut d'études politiques de Paris - Sciences Po, 2025)
Cette thèse examine le traitement par la régulation européenne de la problématique des injustices structurelles sociales liées aux grands réseaux sociaux. Pour ce faire, elle opère une synthèse de nombreuses recherches empiriques qui mettent en évidence les inégalités dans la gouvernance des contenus, et s'appuie sur des perspectives théoriques tirées de la philosophie politique, de la théorie juridique féministe, et des recherches en droit et économie politique. Elle présente trois lignes d'argumentation principales. Premièrement, le droit européen n'empêche pas les injustices telles que la discrimination dans la modération, les violences en ligne, ou la visibilité inégale des différents groupes sociaux, parce qu'il conceptualise ces inégalités d'une manière individualiste et formaliste, visant à protéger les droits d'individus particuliers et à assurer l'application des règles prédéfinies, tout en ignorant la nature systémique des inégalitésDeuxièmement, le droit contribue souvent activement aux injustices : par exemple, en permettant aux agences policières de demander la suppression des contenus pour des raisons politiques. Troisièmement, les aspects du cadre réglementaire qui sont perçus comme les plus à même de combattre les inégalités systémiques, à savoir les obligations autour de la gestion des risques et les principes des droits de l'homme, se révèlent en réalité peu capables d'empêcher les injustices structurelles. Ces deux éléments restent en effet inscrits dans un paradigme de régulation technocratique, dépolitisée, et favorable au marché, et excluent toute contestation réelle du pouvoir ou des pratiques commerciales des plateformes de « big tech ». This thesis analyses EU regulation of social media content governance, focusing on how the law addresses the impacts of the largest platforms on structural social injustice. To do so, it draws on theoretical perspectives from political philosophy, feminist and queer legal theory, and law and political economy, and synthesises a wide range of empirical scholarship that illuminates the unjust impacts of social media platforms' content governance. It makes three main arguments.First, EU law cannot effectively address unjust impacts - such as discriminatory content moderation, online violence, or the unequal visibility of different social groups - because it regulates them in a highly individualistic and formalistic way, focused on protecting individual rights and consistently applying predefined rules, which overlooks systemic inequalities and their connections to underlying political-economic structures. Second, moreover, the law often actively contributes to injustice: for example, by excluding minority perspectives from platform governance, or by making it easier for state institutions to target politically disfavoured content for removal. Third, the two aspects of the legal framework which are widely seen by experts as the most promising levers to address systemic inequalities and power disparities - risk management obligations, and human rights principles - are also incapable of counteracting these problems. They remain limited by a technocratic, depoliticised and marketised regulatory paradigm, which excludes genuine political contestation of the power of 'big tech' platforms to organise online content in line with their own commercial interests.
Issue: 2025IEPP0034
Keywords: Digital law; Droit des technologies de l'information et de la communication; Droit européen; Droit numérique; Eu law; Feminism; Féminisme; Platform regulation; Régulation des plateformes; Réseaux sociaux

La fonction du capital social en droit Ohada - Harouna, Mohamed Albachar; Maïga, Assalia Tiébory; Diallo, Mahamoudou Bazzi (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
Le capital social joue un rôle déterminant au sein de la société commerciale. Traditionnellement, une fonction essentielle lui était reconnue : celle de conférer des privilèges, tant politiques que financiers, à ceux qui y participent. Aujourd’hui, toutefois, sa portée dépasse largement ces conceptions classiques. À l’instar du patrimoine du débiteur, il constitue désormais un véritable instrument de crédit au bénéfice des créanciers sociaux. L’objet de la présente analyse est de mettre en évidence l’importance du capital social et la nécessité de sa protection, dans la mesure où de nombreux partenaires fondent leurs attentes sur sa consistance. Les approches empirique et théorique que nous avons adoptées dans le cadre de cette réflexion nous ont permis d’examiner la notion sous ses divers aspects. Nous espérons que les résultats de cette étude seront d’une utilité considérable, non seulement pour le monde des affaires, mais également pour l’ensemble des partenaires soucieux de préserver l’intégrité du capital social. Social capital plays a determining function within the commercial society. Classically, a function is allocated to it, that of the privileges (political and financial) attached to it. Today, this capital occupies a function beyond traditional conceptions. Like the debtor's assets, it is a credit instrument for social creditors. The object of such an analysis is to determine the importance of social capital to be able to protect it at all costs because many partners base their hope on it. The empirical and theoretical methods that we adopt as part of this reflection will allow us to carry out an in-depth analysis of the concept in all its contours and we hope that the results that will emerge will be of immeasurable usefulness not only for the business world. but also partners in the preservation of capital.
Keywords: Capital; Droit Ohada; Droit des sociétés; Fonction; Function; Society

Commentaire de l’affaire Makondo C/ dame Ngo Hongnoyo ou la préservation de l’unité conjugale - Mekoul, Israël Jacob Baruc (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2025)
Un époux marié sous le régime monogamique abandonne son foyer et décide d’aller vivre chez une femme qu’il décide d’épouser sans avoir rompu avec la première épouse. Attrait en justice par la première épouse, l’époux s’engage à lui verser une pension alimentaire en contrepartie de son abandon de foyer. Les juges de la cour Suprême du Cameroun ont rejeté l’octroi de la pension alimentaire, soulignant fort à propos que la bigamie ne se résout pas par une pension alimentaire de l’acte querellé. Elle se résout par une annulation du second mariage. Dans le but de sanctionner la violation de l’engagement de monogamie, les juges de la Haute Cour n’ont pas retenu l’adultère de l’homme (qui aurait conduit au divorce). Ils ont eu pour souci de préserver l’unité conjugale et l’unité de famille. A husband married under a monogamous regime abandoned his home and decided to live with a woman he married without having divorced his first wife. Sued by his first wife, the husband agreed to pay her alimony in exchange for his abandonment of the home. The judges of the Supreme Court of Cameroon rejected the award of alimony, rightly emphasizing that bigamy is not resolved by alimony for the disputed act. It is resolved by the annulment of the second marriage. In order to penalize the violation of the monogamous commitment, the High Court judges did not consider the man’s adultery (which would have led to divorce). Their concern was to preserve marital and family unity.
Keywords: Adultère; Bigamie; Dommages et intérêts; Pension alimentaire; Unité du foyer

Le contrat intelligent, au secours du consommateur numérique - Mujangi, Mbombo (Université de Montréal, 2025)
Internet a révolutionné le commerce à distance en abolissant littéralement les barrières territoriales qui existaient entre le commerçant et le consommateur pour permettre des échanges dans un environnement dématérialisé. La pandémie de la Covid19 a été un tournant important pour le e-Commerce puisque le confinement qui s’en est suivi a presque obligé le monde à se tourner vers le virtuel qui a connu un boom spectaculaire. Presque tout se fait virtuellement au point que les épiceries aussi offrent la possibilité d’achat en ligne. Mais force est de constater que même dans le cyberespace, la relation entre le consommateur et le commerçant demeure déséquilibrée puisque ce-dernier reste celui qui édicte les règles du jeu. Dans ce travail, nous posons la question de savoir si les protections et garanties du consommateur, consacrées notamment par le Code Civil du Québec et la Loi sur la protection du consommateur, ont survécu avec le e-Commerce ou faut-il d’autres protections pour le consommateur dans le cyberespace? Nous postulons que le contrat intelligent peut être un moyen de sécuriser le consommateur dans le cadre du e-Commerce puisqu’il oblige le commerçant à clarifier les termes du contrat, offrant ainsi une prévisibilité de la relation contractuelle. Dans le cadre de notre travail, nous allons analyser les protections offertes actuellement au consommateur du commerce électronique en procédant à une analyse de droit comparé entre le Québec et la France dans le cadre de l’Union européenne. Puis nous verrons les avantages et inconvénients du contrat intelligent ce qui nous permettra de répondre à la question que nous posons à savoir s’il est un procédé salutaire qui remettrait l’équilibre dans la relation entre commerçant et le consommateur en assurant ainsi une protection adéquate à ce dernier. The Internet has revolutionized e-Commerce by literally abolishing the territorial barriers that existed between the merchant and the consumer to allow exchanges in a dematerialized environment. The Covid19 pandemic was an important turning point for e-Commerce since the subsequent lockdown almost forced the world to turn to the virtual, which experienced a spectacular boom. Almost everything is done virtually. Even grocery stores offer the possibility of online shopping. But even in cyberspace, the relationship between the consumer and the merchant remains unbalanced since the latter remains the one who dictates the rules of the game. In this work, we ask the question of whether consumer protections and guarantees, enshrined by the Quebec Civil Code and the Consumer Protection Act, have survived with e-Commerce or are there other consumer protections needed in cyberspace? We postulate that the smart contract can be a way to secure the consumer in the context of Ecommerce since it requires the merchant to clarify the terms of the contract. As part of our work, we will analyze the protections currently offered to consumers in electronic commerce by conducting a comparative law analysis between Quebec and France in the context of the European Union. Then we will see the advantages and disadvantages of the smart contract, which will allow us to answer the question whether it is a beneficial process that would restore balance in the relationship between merchant and consumer by ensuring adequate protection for the latter.
Keywords: Blockchain; Commerce électronique; Commerçant; Consommateur; Consumer; Consumer Protection Act; Consumer protection; Contrat en ligne; Contrat intelligent; Cyberespace; Cyberspace; Distance selling; Electronic commerce; Loi sur la protection du consommateur; Merchant; Online contract; Protection du consommateur; Smart contract; Vente à distance

Regulating the Legal Quagmire of Artificial Intelligence and Copyright Infringement in Cameroon and Across Africa - Nyadjroh Gabsa, Lidwina (Revue Internationale de Droit et Science Politique, 2025)
The rapid advancement of artificial intelligence (AI) technologies presents unprecedented prospects and plight within the realm of copyright law. This article investigates the strained interplay between AI-generated content and copyright infringement in Cameroon and across Africa, where legal frameworks often lag behind technological innovations. The concern arises from the ambiguity surrounding authorship, ownership, and the applicability of existing copyright laws to AI-generated works, which poses significant risks for creators and innovators. The question on how does current copyright legislation in Cameroon and broader African jurisdictions address the challenges posed by AI is the core of this work. Legal gaps exist, thereby creating the need to address the constrains introduced by AI, necessitating a reevaluation and reform of copyright laws. Employing a doctrinal and extensive online search, findings of this work reveal that many African nations, including Cameroon, a member of OAPI, lack specific regulations addressing AI's implications for copyright, resulting in uncertainty for creators. The results show a pressing need for revisiting of copyright laws in Cameroon and across Africa, to ensure robust protection for AI-generated works while promoting technological advancement. This article recommends adapting copyright laws for AI-generated works, the need for regional cooperation to explicitly adopt standard definitions of AI and AI operations to circumvent infringement claims, and also incorporate a unified approach to resolve the debate on copyright protection on AI status recognition of authorship and ownership, to enhance legal certainty, creativity and innovation. Le développement rapide des technologies d'intelligence artificielle (IA) ouvre des perspectives inédites, mais soulève également des défis majeurs en matière de droit d'auteur. Cet article examine les interactions complexes entre les contenus générés par l'IA et la contrefaçon au Cameroun et en Afrique, où les cadres juridiques sont souvent en retard sur les innovations technologiques. L'ambiguïté entourant la paternité, la propriété et l'applicabilité du droit d'auteur aux œuvres générées par l'IA est source d'inquiétude, car elle représente un risque important pour les créateurs et les innovateurs. La question de savoir comment la législation actuelle sur le droit d'auteur au Cameroun et, plus largement, dans les juridictions africaines, appréhende les défis posés par l'IA est au cœur de cette étude. Des lacunes juridiques existent, d'où la nécessité de remédier aux contraintes introduites par l'IA et, par conséquent, de réévaluer et de réformer le droit d'auteur. S’appuyant sur une recherche doctrinale et en ligne exhaustive, cette étude révèle que de nombreux pays africains, dont le Cameroun, membre de l’OAPI, ne disposent pas de réglementations spécifiques concernant les implications de l’IA en matière de droit d’auteur, ce qui engendre une incertitude pour les créateurs. Les résultats soulignent l’urgence de revoir les lois sur le droit d’auteur au Cameroun et dans toute l’Afrique, afin de garantir une protection solide des œuvres générées par l’IA tout en favorisant le progrès technologique. Cet article recommande d’adapter les lois sur le droit d’auteur aux œuvres générées par l’IA, de renforcer la coopération régionale pour adopter explicitement des définitions standardisées de l’IA et de ses opérations afin de prévenir les actions en contrefaçon, et d’intégrer une approche unifiée pour résoudre le débat sur la protection du droit d’auteur concernant le statut de l’IA, la reconnaissance de la paternité et de la propriété intellectuelle, afin d’améliorer la sécurité juridique, la créativité et l’innovation.
Keywords: AI; Contrefaçon; Copyright; Droit d'auteur; IA; Impasse juridique; Infringement; Intellectual property; Legal Quagmire; Propriété intellectuelle; Regulation; Réglementation

Le contentieux disciplinaire : Plaidoyer pour une harmonisation du droit disciplinaire dans les prisons de la zone CEMAC - O'Bounou, Eric (Université de Pau et des Pays de l'Adour, 2025)
En février 1995 la situation des prisonniers connait une ouverture vers une prison de droit suite à un revirement de jurisprudence consacré par l'arrêt ''Marie''. Cette décision fixe le cadre de l'érection d'un procès en droit, autorisant le juge à connaitre des recours formulés par les détenus contre l'administration pénitentiaire. Le contentieux disciplinaire pénitentiaire augure alors une nouvelle discipline qui va enrichir la matière pénitentiaire. Plusieurs années après l'établissement de cette jurisprudence, les pays de l'Afrique centrale en général et de la zone CEMAC en particulier, qui ont adopté en copie collée les règles du droit administratif français et son contentieux, tournent le dos à la pénétration du principe de légalité en milieu carcéral, laissant ainsi les mesures intérieures imposées une dictature dans les établissements pénitentiaires de cet espace. Pour que le droit trouve enfin une place au sein de l'univers carcéral, le plaidoyer pour une harmonisation du droit disciplinaire, nous offre une ouverture pour garantir une protection des droits des détenus par l'instauration des règles qui gouvernent l'accès à une procès équitable. In February 1995, the situation of prisoners saw an opening towards a rights-based prison following a change in case law established by the 'Marie' ruling. This decision sets the framework for the establishment of a legal process, allowing judges to hear appeals made by inmates against the prison administration. The disciplinary litigation in prisons heralds a new discipline that will enrich the field of incarceration. Several years after the establishment of this case law, countries in Central Africa in general, and the CEMAC zone in particular, which have adopted a copy of French administrative law and its disputes, turn their backs on the penetration of the principle of legality within the prison environment, thus allowing internal measures to impose a dictatorship within the penitentiary establishments of this area. For law to finally find a place within the prison universe, advocacy for the harmonization of law.
Issue: 2025PAUU2013
Keywords: CEMAC; Communauté Economique et Monétaire de l'Afrique Centrale; Contentieux; Disciplinary; Discipline; Harmonisation; Harmonization; Litigation; Prison; Prisons; Prisons (discipline); Prisons (droit)

La situation des travailleurs dans les entreprises en difficulté : étude de droit comparé entre le droit OHADA et le droit français - Sy, Adama Lamine (Université Paris 12, 2025)
Cette thèse procède à une étude de droit comparé, entre le droit de l’OHADA et le droit français, concernant les droits des travailleurs ou salariés dans les entreprises en difficulté. En droit de l’OHADA comme en droit français, les droits des travailleurs sont garantis même si ces droits nécessiteraient des améliorations considérables. Les droits des travailleurs sont garantis dans les entreprises en difficulté notamment en ce qui concerne la garantie de l'emploi et des salaires. Dans les procédures collectives, le droit de l’OHADA comme le droit français, entendent préserver les emplois des salariés et protéger leurs créances salariales. L’Acte uniforme portant organisation des procédures collectives d’apurement du passif, les Codes du travail des pays membres de l’OHADA, ainsi que le Code de commerce français, prévoient la poursuite des contrats de travail en présence d’une procédure collective et la garantie leurs créances de salaire. Également, contrairement aux législateurs de l’OHADA, afin de remédier aux carences du système du privilège et super privilège, le législateur français a adopté le 27 juillet 1973 une loi tendant à assurer le paiement des créances résultant du contrat de travail, laquelle institue également l’association pour la gestion du régime de garantie des créances des salariés (AGS).Toutefois, malgré les mesures prévues par les législateurs de l’OHADA et français, les droits des travailleurs dans les entreprises en difficulté demeurent insuffisamment garantis. Des licenciements pour motif économiques peuvent être prononcés lorsque les difficultés de l’entreprise persistent. Les travailleurs ou les salariés occupent une place importante dans l’entreprise surtout lorsque celle-ci connaît des difficultés. Pour assurer l’efficacité de la garantie de leurs droits, les salariés doivent s’impliquer davantage dans la conduite des procédures collectives. Partant, une réforme du droit des entreprises en difficulté, tant en droit de l’OHADA qu’en droit français, pourrait être préconisée, tenant davantage compte des aspects sociaux des procédures collectives. This thesis conducts a comparative law study, between OHADA law and French law,concerning the rights of workers or employees in companies in difficulty.In OHADA law as in French law, workers' rights are guaranteed even if these rights wouldrequire considerable improvements. Workers' rights are guaranteed in companies indifficulty, particularly with regard to the guarantee of employment and wages. Incollective proceedings, OHADA law as in French law, intend to preserve the jobs ofemployees and protect their salary claims. The Uniform Act organizing collectiveprocedures for the settlement of liabilities, the Labor Codes of OHADA membercountries, as well as the French Commercial Code, provide for the continuation ofemployment contracts in the presence of collective proceedings and the guarantee of theirsalary claims.Also, unlike the OHADA legislators, in order to remedy the shortcomings of the privilegeand super privilege system, the French legislator adopted on July 27, 1973 a law aimedat ensuring the payment of claims resulting from the employment contract, which alsoestablishes the association for the management of the guarantee scheme for employeeclaims (AGS). However, despite the measures provided by the OHADA and Frenchlegislators, the rights of workers in companies in difficulty remain insufficientlyguaranteed. Redundancies for economic reasons may be pronounced when the company'sdifficulties persist. Workers or employees occupy an important place in the company,especially when it is experiencing difficulties. To ensure the effectiveness of the guaranteeof their rights, employees must be more involved in the conduct of collective procedures.Therefore, a reform of the law on companies in difficulty, both in OHADA law and inFrench law, could be recommended, taking greater account of the social aspects ofcollective procedures.
Issue: 2025PA120044
Keywords: Créances de salaires; Créances salariales; Droit OHADA; Droit comparé; Droit français; Entreprises en difficulté; Entreprises en difficulté (droit); Firms in difficulty; French law; Law OHADA; Procédures collectives; Travailleurs; Worker

La contractualisation de l’exercice de l’autorité parentale - Thoo, Kossi Albert Francis (Revue Internationale de Droit et Science Politique, 2025)
Ce travail explore la contractualisation de l’autorité parentale dans le Code des Personnes et de la Famille, en analysant les évolutions législatives historiques et contemporaines. La notion de contractualisation dans les relations familiales s’est développée dans le contexte de l’autonomisation et de l’égalité accrue entre les époux. Elle est illustrée par la transition de la puissance paternelle à une autorité parentale partagée. Cette évolution a été influencée par des avancées législatives en matière de droits des enfants et d’égalité des sexes qui ont redéfini la dynamique familiale à l’échelle mondiale. Cependant, dans les contextes africains, comme au Bénin, ces changements rencontrent une forte résistance culturelle. Les coutumes traditionnelles valorisent l’autorité paternelle comme un pilier de stabilité sociale et de cohésion familiale, rendant difficile l’adoption complète des lois de co-autorité parentale. L’article met en lumière les tensions entre ces cadres juridiques importés et les pratiques locales, questionnant leur pertinence dans les sociétés africaines. Il propose une contractualisation explicite qui permettrait aux époux, avant le mariage, de convenir de la délégation de l’autorité parentale à l’un des parents, chef de famille, qu’il s’agisse du père ou de la mère, en fonction des réalités culturelles. Cette approche vise à concilier l’égalité juridique avec la préservation des valeurs traditionnelles pour maintenir l’harmonie familiale. This paper deals with the contractualization of parental authority within family law, examining both historical and contemporary legislative developments. The concept of contractualization in family matters emerged from the evolution of family law towards greater autonomy and equality between spouses, exemplified by the transition from paternal power to shared parental authority. This shift has been influenced by legislative advancements, including children's rights and gender equality, which have redefined family dynamics globally. However, in African contexts, such as Benin, these changes face significant cultural resistance. Traditional customs uphold paternal authority as foundational for social stability and family coherence, complicating the full adoption of shared parental authority laws. The article highlights how these imported legal frameworks may conflict with local practices, questioning the relevance and adaptability of such foreign-influenced family codes in African societies. It proposes an explicit contractualization approach that would allow parents, prior to marriage, to agree on the delegation of parental authority to one parent as a family leader, whether the mother or the father, based on cultural realities. This approach aims at reconciling legal equality with the preservation of traditional values, maintaining family harmony, while respecting the diverse social contexts of African communities.
Keywords: African customs; Autorité parentale; Contractualisation; Contractualization; Coutumes africaines; Droit familial; Egalité des sexes; Family law; Gender equality; Parental authority; Paternal power; Puissance paternelle

Le droit mou en entreprise - Wane, Sadou (Revue Internationale de Droit et Science Politique, 2025)
La norme est partout dans toute société : ce n’est pas parce qu’elle englobe tout comme l’auraient pensé les tenants du panjurisme, mais qu’elle se dissémine en bigarrant ses sources par l’effet de la privatisation de la création du droit. Les transfigurations rayonnantes du monde des affaires ont entraîné des mutations et des difformités profondes de l’environnement économique, social, juridique, entre autres. Cette transmutation a généré une nouvelle conception de la norme non coercitive, un glissement du droit dur vers un droit mou, influant significativement la gouvernance des entreprises. La réflexion centrée autour du droit mou, pris dans son déploiement au sein de l’entreprise privée, contribue à identifier justement les traits caractéristiques de ces normes, très souvent opposées aux dispositions du droit dur, même si l’on a tendance à minimiser l’intérêt de la distinction jugée filiforme, où les concepts s’entremêlent, se cumulent et se succèdent. La réception du droit mou en entreprise, œuvre, d’ailleurs, inachevée, est peu ou prou contrastée, en ce sens qu’il n’est pas réfutable que certaines composantes du droit souple soient reconnues comme faisant corps avec le droit, tandis que d'autres seraient désagrégées au droit dur. The norm is ubiquitous in every society, not because it encompasses everything, as proponents of panjurism might have thought, but because it disseminates itself by diversifying its sources through the privatization of lawmaking. The radiant transformations of the business world have led to profound mutations and distortions in the economic, social, and legal environment, among others. This transformation has generated a new conception of the non-coercive norm, a shift from hard law to soft law, significantly influencing corporate governance. Reflection focused on soft law, considered in its deployment within private enterprise, helps to precisely identify the characteristic features of these norms, very often contrasted with the provisions of hard law, even if there is a tendency to minimize the importance of this distinction, considered subtle, where concepts intertwine, accumulate, and succeed one another. The reception of soft law in business, a work which is, moreover, unfinished, is more or less contrasted, in the sense that it is undeniable that some components of soft law are recognized as forming part of the law, while others would be disintegrated into hard law.
Keywords: Coercion; Coercition; Droit dur; Enterprise; Entreprise; Hard law; Normativity; Normativité; Regulation; Régulation; Sanction; Soft law

Le déni de justice en matière civile : étude comparative des droits français, égyptien et koweïtien - Alkhudhair, Abdlrahman (Université de Strasbourg, 2025)
Cette étude s’attache à analyser, de manière chronologique, l’évolution du concept de déni de justice. La problématique qu’elle soulève prend racine dans l’ambiguïté entourant cette notion et dans l’absence de consensus quant à sa définition. Menée selon une approche comparative, cette recherche vise à cerner la portée du déni de justice, à en préciser la signification et à retracer les étapes de son évolution, en examinant tout à la fois le rôle du législateur dans l’apparition de ce concept et l’apport de la doctrine ainsi que de la jurisprudence - tant nationale que supranationale - dans l’extension de son champ d’application.L’étude conclut que l’interdiction du déni de justice a d’abord été perçue comme un simple instrument de transfert du pouvoir interprétatif et créateur du législateur vers le juge, puis comprise comme une violation des devoirs fondamentaux incombant à ce dernier en raison de sa fonction, avant d’être considérée comme une atteinte au droit au juge. Enfin, il apparaît que la compréhension approfondie et la définition précise de la notion de déni de justice peuvent inciter les chercheurs à s’interroger sur les causes juridiques et factuelles de ce phénomène, et à proposer des solutions efficaces afin d’en réduire l’occurrence ou d’en atténuer l’impact dans la pratique. This study analyzes, in chronological order, the evolution of the concept of denial of justice. The issue addressed arises from the ambiguity surrounding this notion and the lack of consensus regarding its definition.Conducted using a comparative approach, this research seeks to delineate the scope of denial of justice, clarify its meaning, and trace the stages of its evolution by examining both the role of the legislator in the emergence of this concept and the contribution of legal doctrine as well as case law -at both national and supranational levels -in broadening its field of application.The study concludes that the prohibition of denial of justice was initially perceived as a mere instrument for transferring the legislator’s interpretive and creative power to the judge, then understood as a violation of the fundamental duties incumbent upon the latter by virtue of judicial office, before being regarded as an infringement of the right to a judge.Finally, it appears that a thorough understanding and precise definition of the notion of denial of justice may prompt researchers to examine the legal and factual causes of this phenomenon, and to propose effective solutions to reduce its occurrence or mitigate its practical impact.
Keywords: Droit au juge; Droit civil; Droit comparé; Droit d’accès à un tribunal; Délai raisonnable; Déni de justice; Fonction juridictionnelle; Interprétation; Pouvoir créateur; Référé législatif; Tribunal des conflits

La prescription extinctive en droit patrimonial de la famille - Faugeras, Sarah (Université de Limoges, 2025)
La réflexion sur le temps, qu’il soit mesuré ou vécu, fait toute la singularité du droit patrimonial de la famille. Là où le temps objectif assure rigueur et sécurité, le temps subjectif révèle les lenteurs et hésitations propres aux parcours familiaux.La prescription en matière familiale doit assumer sa spécificité. Elle est à la fois tributaire d’un droit commun modernisé par la loi du 17 juin 2008, et le fruit d’un ensemble de prescriptions spéciales destinées à tenir compte des particularismes de la matière. Ainsi, il convient de réfléchir sur le rôle que doit occuper le droit commun en la matière et sur la cohérence de son articulation avec les prescriptions spéciales. Reflection on time, whether measured or lived, lies at the heart of what makes patrimonial family law unique. While objective time ensures rigor and legal certainty, subjective time reveals the delays and hesitations inherent in family dynamics.Prescription in family matters must therefore embrace its specificity. It is both shaped by a body of common law modernized by the Act of 17 June 2008 and the product of a set of special limitation rules designed to account for the particular features of this field. Accordingly, it is necessary to reflect on the role that common law should play in this area and on the coherence of its interaction with special limitation regimes.
Keywords: Co-Ownership; Droit patrimonial; Famille; Forclusion; Forfeiture; Indivisions; Limitation periods; Patrimoine; Preclusion periods; Preclusive periods; Prescription; Régimes matrimoniaux; Successions

Le code de conduite, instrument de soumission des entreprises multinationales au droit international public - Lambard, Mary (Université de Lille, 2025)
Cette étude vise à comprendre comment le code de conduite, qui est un instrument volontaire qui tire sa validité normative du droit international, peut venir s’imposer, au sens de contrainte juridique, à l’entreprise de droit privé. Il convient, pour ce faire, de s’interroger sur la fonction d’articulation que remplit le code de conduite entre les différents ordres juridiques. En assurant une telle médiation normative, cet instrument favorise une circulation des normes susceptible de conduire à la soumission des entreprises multinationales au droit international public. L’approche ascendante adoptée dans cette recherche permet de mettre en évidence que cette articulation s’opère en deux temps : d’une part, par une phase de réception des normes internationales, et d’autre part, par une phase d’exécution de celles-ci. C’est donc sur cette base que s’est construit le plan de l’étude. Il s’agit, dans un premier temps, d’analyser la phase de réception des normes internationales, lesquelles passent de l’ordre juridique international à l’ordre juridique interne de l’entreprise. Ce passage a pour effet de transformer les normes internationales : elles sont d’abord traduites par les intermédiaires, puis font l'objet d’une réinterprétation stratégique au bénéfice des entreprises multinationales. Dans cette perspective, les codes de conduite apparaissent comme des vecteurs de réception des normes internationales, activés essentiellement lorsque cela sert les intérêts de l’entreprise. Cependant, dans un second temps, les codes de conduite établis dans l’ordre juridique propre de l’entreprise sont progressivement repris par les États. Ces derniers qui cherchent à les exécuter et à en contrôler la mise en œuvre au sein de leurs propres ordres juridiques. Ce processus de circulation normative entre les différents ordres juridiques tend à mettre en évidence le durcissement des codes de conduite volontaires. Toutefois, cette contrainte nouvelle n’engendre pas de responsabilité de l’entreprise en cas de violation par cette dernière de son code de conduite. Si le code de conduite peut devenir un vecteur de contrainte, il constitue avant tout un instrument de responsabilisation de l’entreprise. This study seeks to understand how the code of conduct, a voluntary instrument deriving its normative validity from international law, can come to bind private companies in the sense of a legal constraint. To do so, it is necessary to examine the articulating function that the code of conduct performs between different legal orders. By ensuring such normative mediation, this instrument facilitates a circulation of norms that may lead to the submission of multinational enterprises to public international law. The bottom-up approach adopted in this research highlights that this articulation operates in two stages: first, through a phase of reception of international norms, and second, through a phase of their implementation. The structure of this study is therefore built upon this dual process.The first stage consists in analyzing the reception of international norms, which move from the international legal order into the internal legal order of the company. This transfer has the effect of transforming international norms: they are initially translated by intermediaries and subsequently subject to a strategic reinterpretation serving the interests of multinational enterprises. In this perspective, codes of conduct emerge as vectors of reception of international norms, activated primarily when they align with the company’s interests. However, in a second stage, the codes of conduct established within the company’s own legal framework are progressively taken up by States, which seek to implement and monitor their enforcement within their own legal systems. This process of normative circulation across legal orders tends to illustrate the gradual hardening of voluntary codes of conduct. Nevertheless, this new form of constraint does not create liability for the company in cases of breach of its own code of conduct. If the code of conduct can become a vector of constraint, it remains above all an instrument of corporate accountability.
Keywords: Autorégulation; Code de conduite; Code of conduct; Droit international; Droit international public; Entreprises multinationales; Multinationals; Public International Law

La politique monétaire de l’Eurosystème à l’épreuve du changement climatique : perspectives juridiques - Pozzo-Deschanel, Félix (Université Paris 2, 2025)
Dans la joute qui s’engage contre le réchauffement climatique, le secteur financier est appelé à jouer un rôle déterminant. En effet, les besoins de financement sont colossaux, tant pour permettre l’adaptation des sociétés à un climat désormais instable que pour contribuer à la limitation du réchauffement en cours. Dans ce contexte, au sein de l’écosystème financier, les banques centrales sont plus particulièrement amenées à être au cœur de ce changement de paradigme. La position unique qu’elles occupent, ainsi que les outils dont elles disposent, en font des acteurs clés de ce processus. Sous un angle juridique, la question du rôle que peut jouer l’Eurosystème dans la lutte contre le changement climatique invite, en premier lieu, à un examen attentif de son mandat. En d’autres termes, est-il possible, au regard de son mandat, pour l’Eurosystème d’intégrer la problématique climatique dans la conduite de sa politique monétaire ? Nous verrons qu’une réponse affirmative peut être apportée à cette question. Les traités européens pouvant même être lus comme imposant à l’Eurosystème de prendre en considération le changement climatique dans l’élaboration de sa politique monétaire. Au regard de cette assertion, une interrogation s’impose quant aux modalités concrètes de « verdissement » des instruments de politique monétaire par l’Eurosystème, ainsi qu’à la compatibilité de telles initiatives avec le cadre juridique applicable à ces outils. Il sera soutenu que la plupart des instruments de politique monétaire, qu’ils relèvent des outils dits conventionnels ou des dispositifs non conventionnels, peuvent être adaptés de sorte à contribuer à la lutte contre le changement climatique. In the ongoing battle against climate change, the financial sector is expected to assume a pivotal role in mobilizing the capital required to transform our economic system. The scale of the investment needed is considerable—both to adapt our societies to a destabilized climate and to mitigate ongoing global warming, thereby reducing its potentially devastating consequences. Within the financial ecosystem, central banks are particularly poised to be at the forefront of this paradigm shift. Their unique institutional position and the instruments at their disposal designate them as key actors in this transition. From a legal perspective, examining the potential role of the Eurosystem in addressing climate change first necessitates an inquiry into the scope of its mandate. In other words, does the Eurosystem, within the bounds of its mandate, have the capacity to integrate climate-related considerations into its monetary policy framework? It will be argued that such integration is indeed permissible. Moreover, the European Treaties, along with the Statutes of the ECB and the ESCB, can be interpreted as imposing a duty on the Eurosystem to factor climate change into the formulation of its monetary policy. On this basis, a further question arises: how can the Eurosystem ''green'' its monetary policy instruments, and what does the applicable legal framework permit in this regard? As will be demonstrated, a greening of most monetary policy tools – both conventional and unconventional – can be envisaged within the existing legal and institutional architecture.
Keywords: Banque centrale européenne; Banques centrales; Central Bank; Changement climatique; Climate change; Droit européen; ESBC; European Central Bank; European law; Eurosystem; Eurosystème; Monetary policy; Pays de l'Union européenne; Politique monétaire; Réchauffement de la Terre; SEBC; Traités

An evaluation of China’s securitization regulatory system - Cao, Lei (Université de Montréal, 2025)
Since its innovation as a modern financial product in the 1970s, securitization has swept the global financial market. In 2000s, in order to ease China’s concentrated debt risks in the banking system and to improve the country’s imbalanced financial system, the Chinese government started to promote a trial program of securitization. An associated regulatory system was then created to facilitate the development of the Chinese securitization markets. Unlike regulations drafted and applied in North America, where an ex-ante regulatory analysis procedure and an ex-post evaluation system are installed, the current Chinese securitization regulation system is built mainly upon a basis of trial and interim rules. In other words, Chinese regulations regarding securitization were not comprehensively assessed before their adoption and there has been no systemic ex-post evaluation of the current securitization regulatory system in the past 20 years. This raises the question of whether the Chinese securitization regulation system facilitates the achievement of its regulatory objectives. The author purports to answer this question using three tools: The theory of regulation, legal historical analysis of law, and comparative law. To begin the analysis, the author designs an analytical framework based on the theory of regulation to evaluate Chinese regulations on securitization. In this evaluative framework, perspectives and criteria are stipulated to guide and draw the boundary of the evaluation. While applying the analytical framework, the author reviews the development of the Chinese securitization regulatory system over the past 20 years. The author studies the historical context of regulations established and regulatory modifications adopted in order to assess whether the logic embedded in the current Chinese securitization regulatory system is still valid. To better evaluate the Chinese securitization regulatory system, the author also applies a micro comparison of certain Chinese securitization regulations with their counterparts in North America. The purpose of this comparison is also to understand whether the Chinese characteristics in Chinese securitization regulations facilitate the achievement of its regulatory objectives. At the end of this assessment, the author provides a report to find the merits and disadvantages of Chinese securitization regulatory system. Due to the evaluative nature of this research, no demonstrated solutions are proposed in this report. Depuis sa création dans les années 1970, la titrisation s’est répandue à travers le marché financier mondial. Dans les années 2000, le gouvernement chinois a commencé à promouvoir le programme de titrisation afin d'atténuer les risques liés à la concentration de la dette dans le système bancaire et d'améliorer un système financier déséquilibré. La règlementation associée a été mise en place pour faciliter le développement du marché chinois de la titrisation. Contrairement aux régles créées et appliquées en Amérique du Nord, qui suivent une analyse ex ante —c’est-à-dire avant leur adoption — et une évaluation ex post — soit après leur application pendant une certaine période, le système de réglementation de la titrisation actuellement en vigueur en Chine a été élaboré sur la base d’essais et de mesures provisoires. Autrement dit, la Chine ne s’est pas fondée sur une analyse ex ante approfondie, et n’a mené aucune évaluation systémique ex post de ses réglementations de la titrisation au cours des vingt dernières années. Ce système chinois de réglementation de la titrisation facilite-t-il ou non la réalisation de ses objectifs réglementaires ? L'auteur tente de répondre à cette question à partir de trois outils : la théorie de la réglementation, l’analyse historique du droit et le droit comparé. Pour commencer, l’auteur conçoit un cadre analytique basé sur la théorie de la réglementation pour évaluer les dispositions chinoises en matière de titrisation. Dans ce cadre d’évaluation, des perspectives et des critères sont proposés pour guider et délimiter l’évaluation. À la lumière de ce cadre analytique, l’auteur replace la réglementation chinoise de la titrisation dans son contexte historique et retrace les modifications apportées au cours de deux dernières décennies. Il s’agit ainsi d’évaluer si la logique qui a présidé à l’adoption de ces règles reste valide dans le contexte actuel. Mais pour mieux saisir les caractéristiques de la réglementation chinoise de la titrisation, l’auteur ajoute à cette analyse historique interne à la Chine des micro-comparaisons de la titrisation chinoise et de ses règles avec leurs homologues nord-américains dans différentes sections de cette thèse. C’est ainsi qu’il sera possible de voir si les caractéristiques chinoises de la réglementation en matière de titrisation facilitent ou non la réalisation de ses objectifs. Au terme de cette recherche évaluative, l’on proposera un rapport qui mettra en lumière les avantages et les inconvénients du système chinois. En raison de sa nature évaluative, cette thèse ne proposera aucune solution aux inconvénients repérés.
Keywords: China; Chine; Evaluation of Chinese; Financial Regulation; Marchés chinois; Réglementation financière; Securitization; Securitization Markets; Securitization Regulation; Titrisation; Titrisation (réglementation)

Validité des clauses de non-concurrence et de non-sollicitation dans la vente d’entreprises au Québec : enjeux juridiques et particularités du secteur technologique et du commerce électronique - Costache, Leon Gabriel (Université de Montréal, 2025)
La validité des clauses de non-concurrence et de non-sollicitation dans les contrats d’achat d’actions ou d’actifs d’entreprise repose sur des critères précis établis par la jurisprudence, à savoir que les clauses restrictives doivent être limitées quant à leur durée, territoire et activités visées à ce qui est nécessaire pour protéger les intérêts légitimes de l’acheteur au moment de la transaction. Depuis l'arrêt Payette c. Guay, la jurisprudence a évolué pour offrir une plus grande flexibilité dans l’interprétation de ces clauses dans les contrats de vente d'entreprises, favorisant ainsi la liberté commerciale. Le rôle des tribunaux, dans l’évaluation de la validité de ces clauses et dans l’interprétation de leur portée, devient donc crucial, surtout en raison des lacunes législatives en la matière. Dans un contexte où les parties exercent leurs activités commerciales dans ou à l’aide du domaine technologique ou numérique, l’analyse des clauses doit tenir compte des réalités du marché, où l’évolution rapide des technologies et l’absence de limites géographiques remettent en question les présupposés traditionnels. Cependant, malgré cette évolution dans l’analyse des clauses de non-concurrence et de non-sollicitation, le cadre juridique actuel tend à privilégier presque exclusivement les intérêts privés des parties contractantes, au détriment de la considération de l’intérêt public. Cela soulève la question de savoir si cette approche, qui favorise la liberté contractuelle, ne devrait pas être rééquilibrée par une meilleure prise en compte des intérêts publics, tout en tenant compte des nouvelles réalités technologiques. The validity of non-compete and non-solicitation provisions in purchase of shares or assets agreements is based on specific criteria established by case law. Indeed, such restrictive covenants must be limited in terms of duration, territory, and activities covered to what is necessary to protect the legitimate interests of the buyer at the time of the transaction. Since the Payette v. Guay decision, case law has evolved to offer greater flexibility in the interpretation of these clauses in sale of business contracts, promoting commercial freedom. Thus, the role of the courts in assessing the validity of these restrictive provisions and interpreting their scope has become crucial, particularly due to the lack of legislative guidance. In contexts where the parties to such business transaction conduct their commercial activities in or with the help of technology, the analysis of the validity of non-compete and non-solicitation clauses must also take into account such new realities, where rapid technological advancements and the absence of geographical limits challenge traditional assumptions. However, despite recent evolutions in the analysis of non-compete and non-solicitation clauses, the current legal framework tends to almost exclusively prioritize the analysis of private interests of the contracting parties, at the expense of considering the public interest. This raises the question of whether this approach, which favors contractual freedom, should be rebalanced by a better consideration of public interests, while reflecting recent technological impacts.
Keywords: Business; Clause; Commercial; Competition law; Concurrence; Contract; Contrat; Digital; Entreprise; Non-compete; Non-concurrence; Non-solicitation; Non-sollicitation; Numérique; Technologie; Technology; Transaction

Les pratiques déloyales dans les réseaux de distribution, mise à l'épreuve du droit de la concurrence - Ferré, Diane (Université Paris-Saclay, 2025)
A première vue, l'alliance des expressions "pratiques déloyales" et "réseaux de distribution" pourrait offusquer. Pourtant, le faible pouvoir de négociation du distributeur en réseau est à l'origine de pratiques déloyales occasionnées par le promoteur.Face à ce constat liminaire, la présente étude s'interroge : le droit de la concurrence, est-il suffisamment adapté pour se saisir de ce phénomène des pratiques déloyales dans les réseaux de distribution ? Ou au contraire, les règles générales ne seraient-elles pas devenues suffisamment obsolètes pour que l'on se décide à développer un régime sui generis ?Tout l'enjeu est alors de déterminer si, à l'instar des règles précédentes, le droit positif ne gagnerait pas à s'enrichir de mécanismes spécifiques pour lutter contre les pratiques déloyales au sein des réseaux de distribution.A cette dernière interrogation, nous avons répondu de façon nuancée. En premier lieu, nous évoquerons l'aménagement des règles substantielles du droit de la concurrence. De l'étude approfondie des règles du droit des pratiques anticoncurrentielles en passant par celles relatives aux pratiques restrictives de concurrence, le droit positif gagnerait à modifier ses règles pour s'adapter pleinement à la problématique des pratiques déloyales dans les réseaux de distribution.Cependant, parce que ces dernières règles resteraient ineffectives sans un cadre processuel adapté, notre étude nous a amené, en second lieu, à éprouver les règles processuelles. Si nous ne prônons pas une refonte intégrale des mécanismes, certains aménagements spécifiques s'imposent pour que ces règles soient adaptées à la problématique des pratiques déloyales dans les réseaux de distribution. At first glance, the combination of the terms ‘unfair practices' and ‘distribution networks' may seem offensive. However, the weak bargaining power of network distributors is at the root of unfair practices caused by the promoter.Given this preliminary observation, this study asks: is competition law sufficiently adapted to address the phenomenon of unfair practices in distribution networks? Or, on the contrary, have the general rules become sufficiently obsolete that we should decide to develop a sui generis regime?The challenge is therefore to determine whether, as with previous rules, positive law would benefit from being enriched with specific mechanisms to combat unfair practices within distribution networks.We have responded to this last question in a nuanced manner. Firstly, we will discuss the adjustment of the substantive rules of competition law. From an in-depth study of the rules of anti-competitive practices to those relating to restrictive practices, positive law would benefit from modifying its rules to fully adapt to the issue of unfair practices in distribution networks.However, because these rules would remain ineffective without an appropriate procedural framework, our study led us, secondly, to examine the procedural rules. While we do not advocate a complete overhaul of the mechanisms, certain specific adjustments are necessary to ensure that these rules are adapted to the issue of unfair practices in distribution networks.
Issue: 2025UPASH006
Keywords: Arbitres (droit); Circuits de distribution; Competition; Concurrence; Distribution networks; Pratiques déloyales; Procedure; Procédure; Recours collectifs (droit); Réseaux de distribution; Unfair practices

Predictive Artificial Intelligence Tools in the U.S. Criminal Trial : Reflections on Technology and Justice - Ilhan, Mina Ayşe (Université Côte d'Azur, 2025)
Under the aegis of efficiency and neutrality, algorithmic risk-assessment tools have been rapidly inserted into the realm of pretrial justice, promising scientific and objective prediction where presumption of innocence and scarce resources are pitted against each other. Their sprawl has been uneven and confined to looser pretrial rules than would govern similar proof at trial. These systems translate miscellaneous data into scores of “risk,” inviting courts to act on what might happen rather than on what has been proven, within a process already plagued by plea bargaining, racial disparity, and institutional asymmetry. This thesis argues that such tools do not merely constitute information about the defendant; they reorder what counts as usable knowledge and who is treated as a credible knower at the weakest stage of a criminal process. The thesis lays out how scores interact with judicial decision-making; how ostensibly neutral inputs (criminal history, prior contacts, residence, employment) can re-encode social disadvantage; and how opacity and trade-secret claims frustrate fundamental rights such as due process. The doctrinal analysis clarifies the boundary between regulation and punishment under United States v. Salerno, the demands of proportionality, and the significance of the presumption of innocence when decisions are predictive. A brief technical account explains why claims of “explainability” often exceed what such models can reliably demonstrate for legal purposes, but the core argument is juridical: claims of legitimacy must be substantiated by enforceable safeguards; falling short of that, systems described as ‘explainable' or ‘fair' remain as fancy adjectives. The thesis contends that the safeguards that govern the trial must be applied earlier in the criminal process, where liberty is already fragile. Accordingly, the thesis argues for invoking evidentiary rules early on: demonstrating reliability of the tools; reasoned judicial decisions that explain how any score was weighed against case-specific facts; meaningful opportunities for defence challenge; and, where appropriate, access to independent expertise to translate model outputs without displacing judicial authorship. The researcher is of the opinion that these emphases are necessary so that pretrial decisions remain individualised and proportionate and detention retains its status as an exceptional, non-punitive measure. Finally, it defends doubt as a juridical virtue, a disciplined moment of pause that reins in the allure of algorithmic certainty and reasserts judicial responsibility, so that the presumption of innocence and liberty remains the rule even in a predictive age. Sous l'égide de l'efficacité et de la neutralité, les outils algorithmiques d'évaluation du risque ont été rapidement introduits dans le domaine de la justice pré-procès, promettant une prédiction scientifique et objective là où la présomption d'innocence et la rareté des ressources se trouvent mises en tension. Leur déploiement a été inégal et s'est inscrit dans des règles pré-procès plus souples que celles qui régiraient des éléments de preuve similaires au stade du procès. Ces systèmes traduisent des données hétérogènes en scores de « risque », invitant les juridictions à agir en fonction de ce qui pourrait advenir plutôt que de ce qui a été prouvé, au sein d'un processus déjà marqué par le plaider-coupable, les disparités raciales et les asymétries institutionnelles. La présente thèse soutient que de tels outils ne constituent pas seulement une information relative au prévenu ; ils réorganisent ce qui compte comme connaissance mobilisable et déterminent qui est traité comme un sujet crédible de savoir au stade le plus fragile de la procédure pénale. Elle expose la manière dont les scores interagissent avec la prise de décision judiciaire ; comment des variables présentées comme neutres (antécédents judiciaires, contacts antérieurs avec la police, résidence, emploi) peuvent réencoder des désavantages sociaux ; et comment l'opacité ainsi que les revendications de secret commercial entravent des droits fondamentaux tels que le droit à une procédure régulière. L'analyse doctrinale précise la frontière entre régulation et punition au regard de l'arrêt United States v. Salerno, les exigences de proportionnalité et la portée de la présomption d'innocence lorsque les décisions sont de nature prédictive. Un bref exposé technique explique pourquoi les prétentions à « l'explicabilité » excèdent souvent ce que ces modèles peuvent démontrer de manière fiable à des fins juridiques, mais l'argument central demeure juridique : les revendications de légitimité doivent être étayées par des garanties effectives ; à défaut, les systèmes qualifiés d'« explicables » ou d'« équitables » ne demeurent que des adjectifs séduisants. La thèse soutient que les garanties gouvernant le procès doivent être appliquées plus en amont dans le processus pénal, là où la liberté est déjà fragile. En conséquence, elle plaide pour une mobilisation précoce des règles de preuve : démonstration de la fiabilité des outils ; décisions judiciaires motivées expliquant la manière dont tout score a été mis en balance avec les faits propres à l'affaire ; possibilités effectives de contestation par la défense ; et, le cas échéant, accès à une expertise indépendante permettant de traduire les résultats des modèles sans se substituer à l'autorité judiciaire. La chercheuse estime que ces exigences sont nécessaires afin que les décisions pré-procès demeurent individualisées et proportionnées, et que la détention conserve son caractère exceptionnel et non punitif. Enfin, la thèse défend le doute comme une vertu juridique, moment discipliné de suspension qui tempère l'attrait de la certitude algorithmique et réaffirme la responsabilité judiciaire, afin que la présomption d'innocence et la liberté demeurent la règle, y compris à l'ère prédictive.
Issue: 2025COAZ0023
Keywords: Algorithmes; Algorithmes predictifs; Algorithms; Criminal Justice; Intelligence artificielle en droit; Justice criminelle; Justice prédictive; Procès; Risk assessment tools; États-Unis

Les données personnelles : entre valeur patrimoniale et attribut de la personnalité - Kossou, Merveille (Université Jean Monnet, 2025)
La présente étude s'intéresse à la protection des données personnelles, en mettant en lumière leur ambivalence fondamentale : elles constituent à la fois un attribut de la personnalité, lié à la dignité et aux droits fondamentaux de l'individu, et une valeur patrimoniale, au cœur de l'économie numérique contemporaine. Partant du constat que les données sont devenues indispensables aux échanges économiques mondiaux tout en étant juridiquement conçues, en Europe, comme un droit fondamental de la personne, cette recherche interroge la manière dont le droit positif - en particulier le RGPD et la jurisprudence - appréhende cette dualité. Elle conclut que la conception européenne des données personnelles peine à intégrer pleinement leur dimension patrimoniale. Toutefois, l'Europe a récemment amorcé une évolution vers un système conciliant protection de la personne et exploitation économique des données personnelles. Cette dynamique d'unification des dimensions personnaliste et patrimoniale devrait aboutir à la reconnaissance d'une certaine patrimonialité des données personnelles, sans jamais remettre en cause les acquis en matière de protection des individus. This study focuses on the protection of personal data, highlighting their fundamental ambivalence: they are both an attribute of personality, linked to human dignity and fundamental rights, and a patrimonial value, at the heart of the contemporary digital economy. Starting from the observation that data have become indispensable to global economic exchanges while being legally conceived, in Europe, as a fundamental right of the individual, this research examines how positive law - in particular the GDPR and case law - addresses this duality. It concludes that the European conception of personal data struggles to fully integrate their patrimonial dimension. Nevertheless, Europe has recently initiated a shift towards a system that reconciles the protection of the individual with the economic exploitation of personal data. This dynamic of unifying the personalist and patrimonial dimensions should lead to the recognition of a certain patrimoniality of personal data, without in any way undermining the achievements made in terms of the protection of individuals.
Issue: 2025UJMO0046
Keywords: Attribut de la personnalité; Identité numérique; Patrimonial value; Personal data protection; Personality right; Protection de l'information (informatique); Protection de l'information (informatique) – Droit européen; Protection des données personnelles; Valeur patrimoniale

Le droit à l’avortement face à la rigueur du droit pénal congolais - Kyalenga Katsuva, Christelle (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
Le présent article considère que la législation congolaise en vigueur réprime strictement l’avortement. Toutefois, cette législation présente des lacunes devant les réalités pratiques, notamment en matière d’avortement thérapeutique, de tentative d’avortement et des qualifications juridiques complexes liées à la dualité des victimes. La RDC, à travers la ratification du Protocole de Maputo, reconnaît pour la première fois un droit à l’avortement dans des cas spécifiques, ce qui implique la nécessité d’une réforme du cadre pénal national pour assurer sa conformité. Cette intégration partielle du Protocole constitue une opportunité significative pour l’amélioration de la santé reproductive et la promotion des droits des femmes dans le pays. Cependant, la mise en œuvre effective de ce droit exige une volonté politique affirmée, une modernisation législative claire et une mobilisation concertée des institutions étatiques et de la société civile, afin de garantir que le droit à l’avortement soit appliqué de manière équitable, protégeant véritablement les femmes face aux grossesses non désirées tout en respectant leur dignité et leurs droits fondamentaux. The present article considers that the current Congolese legislation strictly prohibits abortion. However, this legislation exhibits gaps when confronted with practical realities, particularly in matters of therapeutic abortion, attempted abortion, and complex legal qualifications related to the duality of victims. The DRC, through the ratification of the Protocole de Maputo, recognizes for the first time a right to abortion in specific cases, which implies the need for reform of the national penal framework to ensure its compliance. This partial integration of the Protocol represents a significant opportunity for improving reproductive health and promoting women's rights in the country. However, the effective implementation of this right requires a strong political will, clear legislative modernization, and a concerted mobilization of state institutions and civil society to guarantee that the right to abortion is applied fairly, genuinely protecting women facing unwanted pregnancies while respecting their dignity and fundamental rights.
Keywords: Abortion; Avortement; Code pénal; Fetus; Fœtus; Penal Code; Protocole de Maputo

Droit du transport de passagers et responsabilité civile - Langer, Léhi (Université Jean Monnet, 2025)
À l'heure d'une mobilité toujours plus intense, le transport de passagers occupe une place essentielle dans nos sociétés. Son développement continu, porté par les progrès techniques, l'essor du tourisme et les politiques publiques, s'accompagne de nouveaux défis juridiques, en particulier en matière de responsabilité civile. Cette thèse interroge les transformations du droit de la responsabilité civile à la lumière des règles spécifiques au transport de passagers, dans un contexte marqué par une forte influence du droit européen et international.L'étude révèle un double mouvement : l'affirmation de droits autonomes pour les passagers d'une part, et la reconfiguration du rôle de la responsabilité civile d'autre part. Le contrat de transport, bien que central, cède partiellement sa place à des droits issus directement de normes européennes. Cette évolution complexifie la distinction entre responsabilité contractuelle et délictuelle, au profit de mécanismes hybrides de réparation et de garantie.Face à la diversité des sources et des régimes applicables selon les modes de transport, la cohérence du droit devient un enjeu majeur. La thèse propose une clarification des obligations du transporteur et une délimitation précise des notions clés telles que l'accident, le dommage corporel ou les circonstances extraordinaires. Elle appelle aussi à repenser certains fondements, notamment à l'aune des transports autonomes, des plateformes numériques et des défis posés par la multimodalité.En définitive, le droit du transport de passagers apparaît comme un champ d'expérimentation de la responsabilité civile contemporaine. Il invite à trouver un nouvel équilibre entre protection des passagers, efficacité du système et sécurité juridique des opérateurs. In an era of ever-increasing mobility, passenger transport plays a vital role in our societies. Its continuous development—driven by technological progress, the growth of tourism, and public policy—is accompanied by new legal challenges, particularly regarding civil liability. This thesis examines the evolution of civil liability in light of the specific rules governing passenger transport, within a context heavily influenced by European and international law.The study reveals a dual dynamic: on the one hand, the emergence of autonomous rights for passengers; on the other, a redefinition of the role of civil liability. While the transport contract remains central, it is increasingly complemented—if not partially replaced—by rights granted directly through European regulations. This shift complicates the traditional distinction between contractual and tortious liability, giving rise to hybrid mechanisms of reparation and protection.Given the diversity of sources and legal regimes across different transport modes, legal coherence becomes a major concern. The thesis proposes a clarification of the carrier's obligations and a precise delineation of key concepts such as "accident", "bodily harm", and "extraordinary circumstances". It also calls for a reconsideration of certain legal foundations, especially in the face of autonomous transport, digital platforms, and the challenges of multimodality.Ultimately, passenger transport law emerges as a testing ground for modern civil liability. It invites a new balance between passenger protection, system efficiency, and legal certainty for operators.
Issue: 2025UJMO0054
Keywords: Contract; Contrat; Droits; Liability; Passager; Passenger; Protection; Responsabilité; Rights; Transport; Transportation

Le micro-travail : Étude juridique d'une activité de production de données - Pak, Quentin (Université Lumière Lyon 2, 2025)
Le micro-travail est un néologisme tiré de la littérature sociologique. Il désigne un ensemble de prestations de courte durée, rémunérées ou non, consistant à produire des données numériques. Ces prestations sont appelées micro-tâches. Il en existe une multitude. Elles consistent, par exemple, à reconnaître des images, scanner des tickets de caisse, traduire des mots, etc. Certains utilisateurs de sites ou applications en réalisent ponctuellement. Toutefois, d’autres en effectuent régulièrement via des services dédiés à cette activité. Il s’agit des micro-travailleurs. Ces derniers n’ont aucun statut. Dans cette thèse, nous nous interrogeons donc sur la qualification du contrat de micro-travail conclu avec l’opérateur de micro-travail. Eu égard au principe d’indisponibilité du contrat de travail, l’analyse est effectuée à partir de cette catégorie juridique. En l’occurrence, nous tentons de répondre à deux questions. Premièrement, le micro-travail est-il une prestation de travail ? Deuxièmement, la relation de micro-travail est-elle une relation de travail subordonnée ? Micro-work is a neologism taken from sociological literature. It refers to a set of short-term services, paid or unpaid, consisting of producing digital data. These services are called micro-tasks. There are many different types. They consist, for example, of recognising images, scanning receipts, translating words, etc. Some users of websites or applications perform them on an ad hoc basis. However, others do them regularly via services dedicated to this activity. These are micro-workers. The latter have no status. In this thesis, we therefore examine the classification of the micro-work contract concluded with the micro-work operator. Given the principle that the classification of an employment contract does not depend on the will of the parties to the contract, the analysis is based on this legal category. In this case, we attempt to answer two questions. First, is micro-work a work ? Second, is the micro-work relationship a subordinate employment relationship?
Issue: 2025LYO20093
Keywords: Bases de données (gestion); Datas; Digital; Données; Droit des technologies de l'information et de la communication; Droit du travail; Information society services; Labour; Numérique; Plateforme; Platform; Service de la société de l'information; Société numérique; Subordination; Travail

La contribution de la technologie vers une modernisation efficace des modes alternatifs de règlement de conflits - Sangare, Abou Bakary (Université de Montréal, 2025)
Les modes alternatifs de règlement de conflits ont révolutionné le monde du règlement de litiges grâce à leurs nombreux avantages. Les coûts moins onéreux en dehors de l’arbitrage, la célérité des procédures, la confidentialité, le dialogue ouvert, l’émergence de solutions créatives profitant plus ou moins à chacune des parties, constituent entre autres les nombreux éléments qui les rendent plus efficaces par rapport à une procédure contentieuse devant une instance judiciaire ordinaire. Cependant, ces modes alternatifs de règlement de conflits font quand même face à bien d’écueils qui les rendent au fil du temps moins efficaces. L’imprévisibilité des situations conflictuelles apportées à la table des instances de résolution, entraîne une inadéquation des solutions envisagées. De plus, le capital humain fait aussi défaut quand on sait que le nombre de ces règlements amiables de litiges de ces dernières années accroît considérablement, acculant ainsi le personnel de gestion de ces conflits qui se retrouve à faire face aux mêmes défis que le personnel des instances judiciaires contentieuses. De plus, l’humain ne pouvant se détacher indéfiniment de ses émotions peut très rapidement tomber dans la partialité quand il s’agit de prendre des décisions. Il est dès lors capital de penser à une modernisation de ces modes alternatifs de règlement de conflits afin de les rendre plus efficaces par le biais de nouveaux moyens technologiques. Certes, la Résolution de litiges en ligne existe depuis quelques années maintenant. Cependant, il est temps d’y apporter de nouveaux ingrédients afin de rendre meilleure la recette. Alternative dispute resolution has revolutionized the world of dispute resolution thanks to its many advantages. Lower costs, faster procedures, confidentiality, open dialogue and the emergence of creative solutions that benefit both parties to a greater or lesser extent - these are just some of the factors that make alternative dispute resolution more effective than litigation in the ordinary courts. However, these alternative dispute resolution methods do face a number of pitfalls that make them less effective over time. The unpredictability of conflict situations brought to the resolution table leads to inadequate solutions. What's more, human capital is also in short supply, as the number of out-of-court settlements in recent years has risen sharply, leaving conflict management staff facing the same challenges as staff in contentious legal proceedings. What's more, since human beings are unable to detach themselves from their emotions indefinitely, they can quickly fall into the trap of bias when it comes to making decisions. It is therefore vital to consider modernizing these alternative dispute resolution methods, in order to make them more effective through new technological means. Online dispute resolution has been around for some years now. However, it's time to add new ingredients to make the recipe even better.
Keywords: ADR; Alternative dispute resolution; Arbitrage; Arbitration; Blockchain; Chatbots; Conciliation; ICT; Internet; Justice; Justice prédictive; MARD; Mediation; Modes alternatifs de règlement de conflits; Médiation; Négociation; ODR; Online dispute resolution; Predictive justice; Règlement de litiges en ligne; TIC; Technologie; Technology; Transaction

Problemi attuali dell'autonomia procedurale - Vaccarella, Manfredi Latini (Université Paris 2, 2025)
Les études de procédure civile et de droit de l’Union ont longtemps été tenues pour distinctes, les questions procédurales étant surtout envisagées à travers le droit international privé et le droit procédural transnational. Depuis le début des années 2000, l’intensification de l’harmonisation européenne a rendu inévitable la confrontation de certaines règles nationales avec les principes fondamentaux du droit de l’Union, dont la primauté. Si la Cour de justice rappelle l’importance de l’autonomie procédurale des États membres, celle-ci reste encadrée par l’équivalence et l’effectivité : lorsque des règles internes entravent la protection effective des droits issus du droit de l’Union, le juge national peut être tenu de les écarter. L’usage croissant de ces limites alimente une crise de l’autonomie procédurale, visible en Italie et en France, la jurisprudence de la CJUE – proche d’un ius superveniens – imposant des solutions parfois difficiles à concilier avec les traditions nationales. La thèse retrace d’abord l’histoire du procès civil et son lien avec l’État de droit, puis analyse le renvoi préjudiciel, mobilisé aussi pour des enjeux procéduraux et institutionnels. Les affaires Fininvest et SPV Project mettent en lumière la tension entre primauté et stabilité de la chose jugée, notamment en matière d’injonction de payer et de contrôle ex officio des clauses abusives ; l’arrêt Randstad illustre une fonction de coordination possible au sein de l’ordre interne. Le dernier chapitre examine le rôle des cours constitutionnelles, l’érosion des contre-limites et plaide pour une clarification législative des frontières de la compétence de l’Union en matière procédurale. Civil procedure and EU law were long treated as separate fields, with procedural questions framed mainly through private international and transnational procedural law. Since the early 2000s, however, EU harmonisation has made confrontation with core principles, above all the primacy of EU law, unavoidable. While the Court of Justice affirms Member States’ procedural autonomy, that autonomy is bounded by equivalence and effectiveness: where national rules hinder the practical effect of EU rights, national judges may be required to disapply them. Over the last two decades, these limits have been applied with growing intensity, putting Italian and French procedural traditions under strain. CJEU case law, operating almost as ius superveniens, increasingly drives solutions hard to reconcile with established categories. The thesis first reconstructs the historical link between civil procedure and the rule of law, highlighting the judiciary’s role in the balance of powers. It then analyses the preliminary ruling as the key vehicle of the Court’s authority, now used not only for substantive EU law but also for national procedural and judicial arrangements. Case studies include Fininvest and SPV Project, which expose the tension between primacy and the stability of res judicata (including injunction proceedings and ex officio control of unfair terms), and Randstad, showing how preliminary references may coordinate conflicts between domestic jurisdictions. The final chapter considers possible responses, focusing on constitutional courts and the limits of counter-limits, and argues for a clearer legislative definition of EU competence in procedural matters.
Keywords: CJEU (Court of Justice of the European Union); CJUE (Cour de justice de l’Union européenne); Civil procedural law; Constitutional courts; Counter-limits doctrine; Cour constitutionnelle; Crise de l’autonomie procédurale; Doctrine des contre-limites; Droit de l’Union européenne; Droit européen et droit interne; Droit processuel civil; Effectiveness and equivalence; Effectivité et équivalence; Efficacité du droit; European Union Law; France; Harmonisation procédurale; Hiérarchie des normes juridiques; Intégration européenne; Italie; Juridictions nationales; National courts; Preliminary ruling; Primacy of EU law; Primauté du droit de l’Union; Procédure (droit européen); Procédure civile; Renvoi préjudiciel; Res Judicata (authority of final judgments); Res iudicata (autorité de la chose jugée); Union européenne. Cour de justice

La fonction normative du droit de la famille contemporain à la lumière des obligations alimentaires - Colas, Clément (Université Paris 2, 2025)
Cette étude se propose d’interroger l’idée selon laquelle le droit de la famille, à l’heure du développement du pluralisme familial et de l’essor du rôle de l’autonomie de la volonté, aurait perdu, au moins pour partie, sa vocation à exercer une fonction normative. Chacun semblant, désormais, pouvoir faire ses propres choix en matière de vie privée et familiale, notamment en choisissant la forme et l’étendue de son union, il faudrait en conclure que le droit de la famille ne vient plus, aujourd’hui, défendre de modèles. Il deviendrait alors le simple support technique de l’exercice des libertés individuelles en matière familiale. Pour étudier ces phénomènes, nous étudierons plus spécifiquement le cas des obligations alimentaires, support juridique des solidarités intrafamiliales. Confronter les obligations alimentaires à l’évolution d’une part du droit de la famille, et d’autre part de l’appréhension sociale du groupe familial, permettra ainsi de révéler aussi bien les transformations de la fonction normative du droit de la famille contemporain que les besoins de réforme en matière de solidarité intrafamiliale. Cette analyse nous conduira à établir qu’en matière de fonction normative de droit de la famille, il faut davantage évoquer une transformation qu’un retrait. Réinvestie, la fonction normative du droit de la famille contemporain, si elle semble s’éloigner de sa vocation initiale à défendre un modèle familial unique, paraît toutefois défendre des modèles comportementaux en matière de vie familiale, articulés autour d’un certain nombre de principes fondamentaux tels que la protection de l’intérêt de l’enfant, la promotion de l’égalité entre les hommes et les femmes, ou encore la volonté de pacification des relations intrafamiliales. This study aims to examine the idea that family law, at a time of growing family pluralism, and of the rise of the role of autonomy of will, has lost, at least in part, its normative function. Now that everyone seems to be able to make their own choices in matters of private and family life, particularly in choosing the form and scope of their union, it must be concluded that family law no longer serves to defend models. It has thus become a mere technical support for the exercise of individual freedoms in family matters. To examine these phenomena, we will study more specifically the case of maintenance obligations, the legal basis for intra-family solidarity. Comparing maintenance obligations with developments in family law on the one hand and the social perception of the family group on the other will reveal both the changes in the normative function of contemporary family law and the need for reform in the area of intra-family solidarity. This analysis will lead us to realize that, when it comes to the normative function of family law, it is more accurate to speak of a transformation than a withdrawal. Reinvigorated, the normative function of contemporary family law, while seemingly moving away from its initial purpose of defending a single family model, nevertheless appears to defend behavioral models in family life, based on a number of fundamental principles such as protecting the interests of children, promoting equality between men and women, and seeking to pacify intra-family relations.
Keywords: Droit de la famille; Famille (droit); Normativité; Obligations alimentaires; Solidarité

A influência de terceiros sobre o controle societário interno: institutos, limites e regime de responsabilidade aplicável - uma análise necessária no âmbito da Lei n. 6.404/1976 - Silva, Ingrid Rodrigues da (Universidade de São Paulo, 2025)
Esta dissertação tem como objetivo analisar os limites jurídicos e o regime de responsabilidade aplicáveis à atuação de credores e demais terceiros alheios à estrutura societária que, direta ou indiretamente, influenciam o controle societário interno em deliberações societárias de sociedades por ações. Trata-se de uma temática ainda incipientemente explorada pela doutrina brasileira, o que impõe desafios teóricos relevantes e reforça a pertinência da investigação. A partir de uma abordagem fundamentada no ordenamento jurídico brasileiro, a pesquisa busca compreender de que modo agentes externos podem interferir no exercício do direito de voto e na condução das decisões estratégicas da companhia. A pesquisa desenvolveu-se inicialmente com a delimitação conceitual e histórica do direito de voto, examinando a dissociação entre a titularidade das ações e o efetivo exercício desse direito, a identificação do acionista controlador e as formas juridicamente reconhecidas de exercício do poder de controle. Na sequência, são analisados figuras ou institutos jurídicos que permitem a influência externa sobre o controle societário - como o penhor de ações, a alienação fiduciária em garantia, o usufruto, cláusulas de veto em geral e a figura do chamado "controle externo" - com ênfase nos efeitos decorrentes de consentimentos prévios ou autorizações concedidas por esses agentes em deliberações societárias. Diante da ausência de regulamentação específica sobre a atuação de credores ou terceiros no âmbito societário, bem como da não recepção, pelo ordenamento jurídico brasileiro, do controle externo como forma legítima de poder de controle, propõe-se uma construção doutrinária orientada à definição de limites objetivos para essa atuação. A proposta leva em consideração os riscos de conflito de interesses entre agentes externos, acionistas e a companhia e a análise da obrigatoriedade (ou não) de observância do interesse social por parte desses terceiros, no curso do processo de influência sobre os acionistas formalmente detentores do controle. Ao final, busca-se responder se o direito societário brasileiro oferece, ainda que de maneira indireta, mecanismos eficazes para coibir eventuais abusos na atuação de terceiros sobre o controle societário, e, em caso de violação, quais as consequências jurídicas e o regime de responsabilidade aplicável. This dissertation aims to analyze the legal boundaries and liability regime applicable to the conduct of creditors and other third parties external to the corporate structure who, directly or indirectly, influence internal corporate control in the decision-making processes of joint-stock companies. This topic remains incipiently addressed in Brazilian legal scholarship, which presents significant theoretical challenges and underscores the relevance of this investigation. Grounded in the Brazilian legal framework, the research seeks to understand how external agents may interfere with the exercise of voting rights and the formulation of strategic decisions within companies. The study begins with a conceptual and historical analysis of voting rights, examining the disassociation between share ownership and the actual exercise of voting power, the identification of the controlling shareholder, and the legally recognized forms of exercising corporate control. Subsequently, the dissertation examines legal mechanisms and arrangements that allow third-party influence over corporate control - such as share pledges, fiduciary transfers of shares in guarantee, usufruct rights, general veto clauses, and the so-called external control - with particular emphasis on the effects arising from prior consents or authorizations granted by these agents in corporate deliberations. Given the absence of specific regulation regarding the role of creditors or third parties in corporate governance, and considering that Brazilian law does not recognize external control as a legitimate form of exercising corporate power, this study proposes a doctrinal framework aimed at defining objective limits to such conduct. The proposal takes into account the risks of conflicts of interest among external agents, shareholders, and the company itself, as well as the analysis of whether these third parties must observe the corporate interest during the process of influencing shareholders who formally hold control. Finally, the dissertation seeks to determine whether Brazilian corporate law provides, even if indirectly, effective mechanisms to prevent abuses in third-party influence over corporate control and, in case of violations, what legal consequences and liability regimes are applicable.
Keywords: Controle societário; Corporate control; Creditors; Credores; Direito de voto; Influence over control; Influenciação sobre o controle; Legal limitations; Limites; Voting rights

La famille en droit constitutionnel africain - Amoussou, Vigny Landry (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2025)
Les Constitutions en Afrique ne sont pas étrangères au droit de la famille. On peut, certes, leur reprocher de régir avec parcimonie les types de comportements familiaux, mais elles ont le mérite de consolider la structure familiale comme le principal agent de socialisation, transmettant les valeurs, les normes et les coutumes. Dans le contexte africain en revanche, l’émergence d’une nouvelle forme familiale, la famille homoparentale ou, encore, homoparentalité sape lentement les normes traditionnelles et ouvrent des perspectives nouvelles sur la notion de famille. A la vérité, les bases constitutionnelles du droit de la famille en Afrique permettent de dégager les lignes fortes de « la famille africaine » comme entité et comme objectif de transmission des valeurs sociales et morales. African constitutions are not unrelated to family law. While they can certainly be criticized for reacting sparingly to types of family behavior, they have the merit of consolidating the family structure as the main agent of socialization, transmitting values, norms, and customs. In the African context, however, the emergence of a new family form, the same-sex family or, even, same-sex parenting, seems to challenge traditional norms and open new perspectives on the notion of family. In truth, the constitutional foundations of family law in Africa allow us to identify the strong lines of « the African family » as an entity and as an objective of transmitting social and moral values.
Keywords: African values; Constitutions; Droit de la famille; Family law; Homoparentalité; Homosexual parenting; Mariage; Marriage; Valeurs africaines

L'évolution du divorce en droit malien : étude comparée - Bah, Mamady (Université de Bordeaux, 2025)
Dans un souci d'évolution du droit du divorce, le législateur malien a, à travers la loi n° 2011-087 du 30 décembre 2011 portant Code des personnes et de la famille, procédé à sa libéralisation dans l'optique de donner plus de liberté aux époux voulant dissoudre leur union. À cet effet, la voie choisie par le législateur malien fut la diversité des cas de divorce, comme ce fut également le cas dans la législation française avec la loi n° 75-617 du 11 juillet 1975, maintenue et peaufinée par celle du 26 mai 2004, mais également dans certaines législations sous-régionales telles que les législations sénégalaise (loi n° 72-61 du 12 juin 1972) et béninoise (loi n° 2002-07 du 24 août 2004). Outre le divorce-sanction, le législateur malien a introduit deux nouveaux cas de divorce : le divorce par consentement mutuel et le divorce pour rupture de la vie commune. Parallèlement à sa politique de libéralisation du divorce, le législateur malien a également tenté de le dédramatiser. En ce sens, une place importante a été, pour la première fois, accordée à la volonté des époux dans le règlement des effets du divorce et à la constatation objective de l'échec du mariage. La déconnexion de certains effets du divorce de la notion de faute participe également à cette politique de dédramatisation du divorce. L'idée fondamentale d'une telle réforme du droit du divorce réside dans la volonté du législateur malien, à l'instar du législateur français de 1975, d'adapter le droit du divorce aux réalités conjugales, de responsabiliser les époux, de promouvoir la liberté individuelle au sein de la cellule conjugale et de dédramatiser le divorce. Mais ces objectifs ont-ils été atteints ? Quelques années après l'adoption du Code des personnes et de la famille, nous observons globalement un échec patent de la politique de libéralisation et une dédramatisation mitigée du divorce. Ce constat nous amène à procéder à un profond aménagement du droit du divorce, avec comme objectif de consacrer au profit des époux, un droit au divorce pacifique, respectueux des engagements internationaux et de l'ordre public familial en droit malien. In an effort to develop divorce law, the Malian legislator has, through Law no. 2011-087 of 30 December 2011 on the Code of Persons and the Family, proceeded with its liberalization with a view to giving more freedom to spouses wishing to dissolve their union. To this end, the path chosen by the Malian legislator was the diversity of divorce cases, as it was also the case in French legislation with Law no. 75-617 of July 11, 1975, maintained and refined by that of May 26, 2004, but also in certain sub-regional laws such as Senegalese (law no. 72-61 of June 12, 1972) and Beninese (law no. 2002-07 of August 24, 2004). In addition to divorce-sanction, the Malian legislator has introduced two new cases of divorce: divorce by mutual consent and divorce for breakdown of life together. In parallel with its policy of liberalization of divorce, the Malian legislator has also attempted to de-dramatize it. In this sense, an important place was given for the first time to the will of the spouses in the settlement of the effects of divorce and to the objective determination of the marriage breakdown. The disconnection of certain effects of divorce from the notion of fault also contributes to this policy of de-dramatizing divorce. The fundamental idea of such a reform of divorce law lies in the will of the Malian legislator, following the example of the French legislator of 1975, to adapt divorce law to conjugal realities, to empower the spouses, to promote individual freedom within the conjugal cell and to de-dramatize divorce. But have these objectives been achieved? A few years after the adoption of the Code of Persons and the Family, we generally observe an obvious failure of the liberalization policy and a mixed de-dramatization of divorce. This observation leads us to proceed with a profound adjustment of divorce law, with the aim of enshrining for the benefit of the spouses, a right to peaceful divorce, respectful of international commitments and family public order in Malian law.
Issue: 2025BORD0225
Keywords: Comparative law; De-Dramatization; Divorce; Droit au divorce; Droit comparé; Dédramatisation; Etude comparative; France; Legal pluralism; Liberalization; Libéralisation; Mali; Pluralisme juridique; Right to divorce

Le statut de la veuve en Côte d’ivoire - Damanan, Obikouho Jeanne-Josée (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
La veuve en Côte d’Ivoire et particulièrement celle des Dida de Téhiri est considérée comme un mineur qui bénéficie sous certaines conditions de droits en concurrence avec la belle famille. Par contre, si d’autres droits ne lui sont pas accordés, c’est parce que c’est un principe général appliqué à la femme. Cependant, on note une évolution partielle de son statut. Cette évolution lui donne le droit d’option matrimonial après le décès de son époux et lui permet de bénéficier du droit de propriété sur les biens mobiliers et du droit d’usage sur les biens immobiliers sous réserve des conditions de « dignité » successorale. L’analyse de ce sujet nous a conduit à soutenir que le statut de la veuve cadre avec la réalité sociale de cette société en dépit des changements que subit ladite société. The widow in Ivory Coast, and particularly that of the Dida of Tehiri, is considered a minor who, under certain conditions, benefits from rights in competition with the in-laws. On the other hand, if other rights are not granted to her, it is because this is a general principle applied to women. However, there has been a partial evolution of her status. This evolution gives her the right of matrimonial option after the death of her husband and allows her to benefit from the right of ownership over movable property and the right of use over immovable property subject to the conditions of inheritance "dignity". The analysis of this subject has led us to argue that the status of the widow fits in with the social reality of this society despite the changes that the said society is undergoing.
Keywords: Côte d’Ivoire; Dida (culture); Famille; Family; Mariage; Marriage; Veuve (statut); Widow(status)

La régularisation fiscale en France des avoirs étrangers non déclarés - Goudarzi, Laurent (Université Paris-Saclay, 2025)
La procédure de régularisation fiscale en France des avoir étrangers non déclarés témoigne du combat de l'administration fiscale contre l'omission des déclarations des comptes bancaires et autres actifs situés hors de l'État de résidence des contribuables.À grand renfort de moyens matériels et humains ainsi que d'un arsenal juridique efficaces assurant une synergie des autorités compétentes à déceler une telle fraude, la présente étude traite également des enjeux et autres failles gravitant autour de cette procédure de mise en conformité fiscale.Dans cette optique, il convient de s'intéresser aux causes de la fraude fiscale et la favorisant, de s'interroger sur la volonté persistante à vouloir dissimuler ses avoirs à l'administration fiscale et enfin, de démontrer en quoi les mécanismes instaurés de dissuasion contre une telle fraude tendent conformément aux valeurs démocratiques. The procedure for the tax regularization of undeclared foreign assets in France testifies to the tax authority its fight against the omission of declarations of bank accounts and other assets located outside the tax residence of taxpayers.With the help of material and human resources as well as an effective legal arsenal ensuring a synergy of the competent authorities to detect such fraud, the present study also deals with the issues and other loopholes revolving around this tax compliance procedure.With this in mind, it is necessary to look at the causes of tax fraud and encourage it, to question the persistent desire to hide one's assets from the tax authorities and finally, to demonstrate how the mechanisms put in place to deter such fraud tend in accordance with democratic values.
Issue: 2025UPASH005
Keywords: Avoirs étrangers; Bank canvassing; Bank secrecy; Compliance; Compliance (droit); Démarchage bancaire; Foreign assets; Fraude fiscale; Lanceur d'alerte; Secret bancaire; Tax fraud; Whistleblower

Le domaine public mobilier et immatériel en droit africain - Kouraogo, Abdoulaye (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2025)
L’étude du domaine public mobilier et immatériel en droit africain francophone révèle une évolution juridique contrastée. Historiquement ancrée dans la summa divisio romaine, la domanialité publique fut longtemps limitée aux seuls biens immobiliers, excluant les biens meubles et incorporels. Cette conception, influencée par la doctrine et la jurisprudence françaises du XIXe siècle, a progressivement cédé la place à une reconnaissance législative du domaine public mobilier, consacrée en France par l’ordonnance de 2006. Néanmoins, dans les États ouest-africains, cette reconnaissance reste timide et non systématique. Seul le Mali dispose d’une définition explicite du domaine public mobilier, tandis que les autres pays privilégient une protection sectorielle, notamment via les législations sur le patrimoine culturel. Les critères retenus, souvent calqués sur le modèle français du bien « insusceptible d’appropriation privée », peinent à saisir la spécificité des biens mobiliers et immatériels. S’agissant du patrimoine immatériel, son identification et sa valorisation soulèvent des défis conceptuels et pratiques. Malgré l’émergence d’une économie de la connaissance et la multiplication des textes encadrant les données publiques, les systèmes juridiques africains peinent à conceptualiser un véritable droit de l’immatériel public. Les enjeux de gouvernance numérique, de protection des données et de valorisation économique de ces actifs restent insuffisamment maîtrisés, dans un contexte marqué par la fracture numérique et les impératifs de sécurité nationale. En définitive, la consistance du domaine public africain demeure incertaine, tiraillée entre des héritages juridiques inadaptés et les nécessités d’une modernisation face aux mutations économiques contemporaines.
Keywords: Domaine public; Domanialité publique; Droit africain; Immatériel; Mobilier; Patrimoine culturel; Reconnaissance législative; Valorisation économique

Le contentieux des pactes d'associés - Lechêne, Jules (Université Paris Sciences et Lettres, 2025)
Cette thèse propose une analyse renouvelée du contentieux des pactes d’associés en l’appréhendant comme un risque juridique structurel, et non comme une simple contingence factuelle. L’étude met d’abord en lumière la fonction particulière des pactes, entendus comme instruments de couverture de l’aléa social qui traversent le contrat de société. Les engagements qu’ils contiennent – mécanismes de transfert de droits sociaux ou stipulations permettant d’exiger un comportement – révèlent toutefois des fragilités propres, susceptibles de nourrir des contestations au moment de leur mise en œuvre. L’analyse systématise alors les voies de remise en cause possibles et montre que le risque contentieux dépend autant des mécanismes juridiques en cause que de la compétence des parties à activer ou non ce contentieux. Face à ce constat, la recherche élabore un modèle contractuel de traitement du risque contentieux, fondé sur la notion autonome de contrainte, exercée à destination des parties ou du juge. Par des techniques telles quel a renonciation, les prérogatives d’interprétation, les accords de qualification ou de régime, ce modèle permet d’anticiper et d’encadrer les contestations. Appliqué aux différents types d’engagements rencontrés dans les pactes d’associés, ce modèle démontre sa pertinence tout en révélant les frontières de la contractualisation. Il ne supprime pas toute possibilité de litige, mais permet d’en saisir la logique et d’en proposer un traitement structuré dès l’origine du contrat. This thesis offers a renewed analysis of litigation arising from shareholders’ agreements by approaching it as a structural legal risk, and not as a mere factual contingency. The study first highlights the particular functionof such agreements, understood as instruments for covering the social uncertainty that runs through the company contract. The commitments they contain – mechanisms for the transfer of shares or stipulations requiring a certain behaviour – nevertheless reveal their own fragilities, likely to fuel disputes at the time of their implementation. The analysis then systematises the possible avenues for challenge and shows that litigation risk depends as much on the legal mechanisms involved as on the parties’ ability to activate or not activate such litigation.In response to this observation, the research develops a contractual model for the treatment of litigation risk,based on the autonomous notion of constraint, exercised either towards the parties or towards the judge.Through techniques such as waiver, interpretative prerogatives, and qualification or regime agreements, this model makes it possible to anticipate and frame potential disputes.Applied to the different types of commitments found in shareholders’ agreements, this model demonstrates its relevance while revealing the boundaries of contractualisation. It does not eliminate all possibilities of litigation, but enables one to grasp its logic and to propose a structured treatment from the very origin of the contract.
Issue: 2025UPSLD032
Keywords: Accord; Agreement; Behaviour; Comportement; Contentieux; Contract; Contractual constraint; Contrainte contractuelle; Contrat; Corporate law; Droit des sociétés; Droits sociaux; Interpretation; Interprétation; Litigation; Litigation risk; Pacte d'associés; Pacte d’actionnaires; Prerogative; Prérogative; Qualification; Regime; Risque contentieux; Régime; Shareholders' agreement; Shares; Transfer; Transfert

Le droit de la concurrence et la protection des données personnelles sur la question d’abus de position dominante : affaire C-252/21 (Meta c. Bundeskartellamt) - Tang Manga, Marcelle Viviane (Université de Montréal, 2025)
L’affaire C-252/21 (Meta c. Bundeskartellamt) traite de la conformité du RGPD avec les pratiques commerciales de Meta et explore la question du rôle de la protection des données dans l’équilibre du jeu de la concurrence, notamment en matière d’abus de position dominante. Elle met d’abord en avant l’hypothèse selon laquelle la collecte et le traitement illicite de données pourraient constituer un facteur de verrouillage du marché à l’endroit des potentiels concurrents tout en renforçant la position dominante de Meta. Ensuite, elle conforte l’idée selon laquelle créer de la concurrence loyale entre les exploitants des données personnelles pourrait constituer un levier capable de renforcer la protection des données personnelles. Bien plus encore, on pourrait déduire de cette affaire un dualisme patent entre l'ultralibéralisme des marchés voulu par le système capitaliste américain, qui prend fait et cause pour le comportement prédateur de Méta, et la volonté protectrice de l’UE à travers son dispositif RGPD et ses politiques anticoncurrentielles. Il s’agira alors pour nous d’analyser l’impact du modèle économique de Meta sur le droit de la concurrence tout en s’interrogeant sur la capacité des outils réglementaires à répondre à la problématique d’abus de position dominante.
Keywords: Abus de position dominante; Abuse of dominant position; Collecte de données; Competencia; Competition law; Concurrence (droit); Consent; Consentement; Data collection; Personal information; Privacy; Publicité ciblée; Renseignements personnels; Targeted advertising; Vie privée

Les infractions sexuelles numériques - Seye, Ass Soda (Université de Bordeaux, 2025)
La rencontre entre les infractions sexuelles et l’environnement numérique soulève une question fondamentale : comment concilier les éléments constitutifs de ces infractions, avec la distance inhérente au numérique ? En effet, certaines infractions sexuelles, par nature corporelle, semblent a priori incompatibles avec la dématérialisation. Cependant, cette opposition entre matérialité et numérique n’est pas insurmontable. En se fondant sur une méthode qui privilégie l’application des qualifications de droit commun, l’étude interroge la pertinence et la plasticité de ces qualifications face à l'émergence de plus en plus préoccupante de pratiques sexuelles numériques répréhensibles. C’est ainsi qu’une lecture contemporaine, dynamique et finaliste des incriminations existantes permettrait, dans de nombreux cas, d’intégrer sans bouleversement normatif les nouvelles manifestations liées au numérique des infractions sexuelles. Cette approche n’exclut pas, de manière subsidiaire, le recours àdes qualifications spéciales lorsque la spécificité des comportements ou des atteintes l’impose. L’objectif est ainsi de mesurer l’effectivité des instruments juridiques existants, tout en évaluant leur capacité à protéger les victimes et à prévenir les comportements illicites, dans un univers numérique où la matérialité des actes et des preuves est profondément bouleversée, à travers une analyse globale qui se déploie tant à l’égard des incriminations qu’à celui de la répression.
Keywords: Adaptation; Aggravation numérique; Compétence internationale; Cybercriminalité; Dématérialisation; Infractions avec contact; Infractions contre la personne; Infractions sans contact; Infractions sexuelles numérique; Internet; Investigations numériques; Qualifications de droit commun; Raids numériques; Règles d’imputation; Répression; Sanctions administratives; Techniques d’interprétation; Viol en live streaming; Violences sexuelles

Le foncier à l’aune du pluralisme juridique au Mali - Ag Oufene, Alhousseiny (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
A l’instar des autres de l’Afrique de l’Ouest, le droit d’accès à la terre est devenu une question récurrente avec des règles juridiques tant modernes que coutumières. Ainsi, le droit à la terre balbutie entre ces règles de droit qui garantissent ses modalités d’accès et de gestion. Ceci dit, les systèmes juridiques étatiques et non-étatiques se trouvent imbriqués de façon complexe et, de cette imbrication entre droits coutumiers, droits étatiques ou nés de la pratique ; naît une cohabitation ambiguë, sinon une confusion entre ‟droit formel et droit informel”, entre l’autorité reconnue aux chefs traditionnels et le pouvoir réservé exclusivement à l’Administration. Cet article vise à mettre en évidence les nombreuses frontières au sein desquelles ou par-delà desquelles s’organise la gouvernance de la sécurité foncière. Ainsi, dans la première partie, à savoir un pluralisme juridique à cohabitation fonctionnelle, s’articule autour du droit positif malien et des droits fonciers coutumiers. Quant à la seconde partie, un pluralisme juridique à cohabitation différenciée mettra en exergue le contentieux et la gestion du foncier. Like other West African countries, the right of access to land has become a recurring issue with both modern and customary legal rules. Thus, the right to land is faltering between these legal rules that guarantee its modalities of access and management. That said, state and non state legal systems are intertwined in a complex way and, from this intertwining between customary rights, state rights or rights born from practice; An ambiguous cohabitation, if not a confusion, arises between "formal law and informal law", between the authority granted to traditional leaders and the power reserved exclusively for the Administration. This article aims to highlight the many boundaries within or beyond which the governance of land security is organized. Thus, in the first part, namely a legal pluralism with functional cohabitation, is articulated around Malian positive law and customary land rights. As for the second part, a legal pluralism with differentiated cohabitation will highlight litigation and land management.
Keywords: Droits endogènes; Endogenous rights; Foncier; Land; Legal pluralism; Mali; Pluralisme juridique

L’admission de l’intervention du juge traditionnel dans le règlement des conflits fonciers ruraux en Côte d’Ivoire : quels apports au plan judiciaire ? - Atchori, Agbrou Roger (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
Le juge et le tribunal font partie intégrante d’une société humaine ; et, la terre est le plus grand bien qu’un être humain pourrait posséder. Toutefois, la possession entière et complète de la terre est hypothétique. Elle est la source de véritables conflits depuis des milliers de siècle. La colonisation de peuplement et d’exploitation en sont de véritables illustrations ; le cas de l’Afrique en général et celui de la Côte d’Ivoire en particulier, qui est une colonisation d’exploitation, explique au mieux le problème foncier, notamment le domaine rural qui opposait le juge judiciaire au juge traditionnel foncier qu’il faille légalement concilier pour le bien social. The judge and the court are an integral part of human society ; and, land is the greatest asset that a human being could possess. However, the complete and full possession of land is hypothétical. It has been the source of real conflicts for thousands of years. The colonization for settlement and exploitation are true illustrations of this ; the case of Africa in general and that of Côte d’Ivoire in particular, which is a colonization for exploitation, best explains the land issue, especially in the rural domain, which opposes the judical judge to the traditional land judge that must be legally reconciled for social good.
Keywords: Apport; Conflit foncier; Contribution; Judge; Juge; Land dispute; Regulation; Règlement; Tradition

Les partenariats entre fintechs et banques à l’ère de l’intelligence artificielle : enjeux stratégiques et défis juridiques en droit des affaires - Awanvoeke, Larios Borgia Dona (Université de Montréal, 2025)
Les partenariats entre fintechs et banques à l’ère de l’intelligence artificielle redéfinissent les modèles économiques et stratégiques du secteur financier. Face aux mutations technologiques, les banques traditionnelles s’associent aux fintechs pour innover, optimiser leurs services et répondre aux attentes des consommateurs. Toutefois, ces collaborations soulèvent des défis juridiques majeurs en matière de responsabilité, de protection des données et de conformité réglementaire. Ce mémoire analyse ces enjeux en adoptant une méthodologie combinant analyse doctrinale, droit comparé et étude des cadres réglementaires existants. L’approche doctrinale a permis d’explorer les concepts clés des fintechs, des banques et de l’IA, en mobilisant les théories économiques et juridiques pertinentes. L’étude comparative entre l’Union européenne, les États-Unis et le Canada a mis en lumière les différences réglementaires, notamment en matière de protection des données et de régulation de l’innovation. Enfin, l’examen des cadres législatifs actuels et des tendances émergentes, telles que les regulatory sandboxes et les innovation hubs, a permis d’anticiper les évolutions nécessaires pour encadrer ces transformations. Les résultats montrent que si l’IA favorise l’innovation et l’automatisation des services financiers, elle pose également des risques en matière de transparence des algorithmes, de cybersécurité et d’équilibre concurrentiel. L’étude met en évidence la nécessité d’une harmonisation réglementaire et de mécanismes de gouvernance adaptés pour garantir un développement équilibré du secteur. Ce mémoire propose plusieurs recommandations, notamment le renforcement des cadres juridiques sur la responsabilité algorithmique, la création de normes internationales harmonisées et la mise en place de collaborations entre banques, fintechs et régulateurs. Ces mesures visent à assurer un environnement financier sécurisé, innovant et conforme aux impératifs de transparence et de protection des utilisateurs. Ainsi, les partenariats fintechs-banques s’imposent comme un levier stratégique incontournable, nécessitant une régulation adaptée pour concilier innovation et stabilité du marché.
Keywords: Algorithm Transparency; Algorithmic Liability; Artificial Intelligence; Automation; Automatisation; Banks; Banques; Business law; Cadre réglementaire; Comparative Law; Competencia; Competition; Concurrence; Cybersecurity; Cybersécurité; Data Protection; Digital Transformation; Droit comparé; Droit des affaires; Financial Governance; Financial Innovation; Fintechs; Gestion des risques; Gouvernance financière; Innovation Hubs; Innovation financière; Innovation hubs; Inteligência artificial; Intelligence Artificielle; Intelligence artificielle; Partenariats stratégiques; Protection des données; Regulatory Framework; Regulatory Sandboxes; Responsabilité algorithmique; Risk Management; Régulation; Régulatory sandboxes; Strategic Partnerships; Transformation numérique; Transparence des algorithmes

Le sursis de paiement et la protection du contribuable en droit fiscal camerounais - Bidoung Dob, Pierre Landry N. (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
Keywords: Cameroun; Contribuable (protection); Droit fiscal; Sursis de paiement

Le travail des enfants au Mali - Coulibaly, Karamoko (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
Le Mali a mis en place un cadre juridique spécifique pour lutter contre le travail des enfants, en s’appuyant sur les conventions internationales telles que celles de l’OIT et la CDE. Malgré ces protections légales, la réalité socio-économique du pays complique l’application effective de ces lois. En raison de la pauvreté et de la nécessité pour de nombreuses familles de compléter leurs revenus, un grand nombre d’enfants travaillent dans l’agriculture, l’artisanat ou encore le commerce informel. Cette situation met en évidence la nécessité d’un renforcement des mesures d’application de la loi, notamment par le biais de contrôles plus rigoureux et de sanctions appropriées. En outre, des programmes de sensibilisation et d’appui aux familles vulnérables sont essentiels pour réduire la dépendance économique au travail des enfants. Le développement de l’accès à l’éducation et la mise en place de mécanismes de soutien financier aux familles apparaissent comme des solutions durables pour éradiquer progressivement le travail infantile au Mali.
Keywords: Droit du travail; Enfant; Malien

L'équilibre de la relation entre investisseur étranger et État hôte dans la jurisprudence arbitrale - Jorland, Maxime (Université Paris-Saclay, 2025)
Le droit des investissements internationaux s'est construit sous l'impulsion des tribunaux arbitraux qui, dans leur rôle d'interprétation du droit international coutumier et des traités d'investissement, ont contribué à enrichir le droit matériel des investissements. La multiplication des sentences rendues a constitué progressivement une véritable jurisprudence, visant à équilibrer la relation entre l'investisseur étranger et l'État hôte. Cependant, l'interprétation des traités par les tribunaux arbitraux s'est souvent faite dans un objectif de protection de l'investisseur face à la puissance publique de l'État, jusqu'à inverser parfois le rapport de force entre les deux opérateurs. De plus, l'absence de principe de précédent en arbitrage d'investissement a contribué à créer un flou notionnel, du fait des interprétations changeantes des dispositions des traités protégeant l'investisseur étranger. 2Cette étude vise donc à faire état du droit positif des investissements internationaux en déterminant un courant doctrinal commun aux sentences arbitrales. Une fois ce travail de compilation réalisé, l'objectif sera alors de déterminer l'état de l'équilibre des forces entre les deux opérateurs et proposer un rééquilibrage du droit des investissements. Ce rééquilibrage passe notamment par une redéfinition des critères jurisprudentiels imprécis ou changeants et une adaptation de la protection de l'investisseur étranger aux enjeux modernes du commerce international, tout en veillant à permettre à l'Etat hôte de conserver ses prérogatives de puissance publique. International investment law has largely been shaped by arbitral tribunals, whose interpretative function with regard to customary international law and investment treaties has contributed significantly to the development of substantive investment law. The proliferation of arbitral awards has progressively given rise to a de facto jurisprudence, aimed at striking a balance between the interests of foreign investors and the sovereign rights of host States. However, treaty interpretation by arbitral tribunals has often been guided by a protective logic in favour of the investor, at times to the extent of inverting the power dynamic between the two actors. Furthermore, the absence of a binding precedent doctrine in investment arbitration has fostered conceptual uncertainty, resulting from fluctuating interpretations of the treaty provisions safeguarding foreign investors.This study seeks to provide an overview of the current state of positive international investment law by identifying a coherent doctrinal trend emerging from arbitral case law. Based on this synthesis, the aim is to evaluate the prevailing balance of power between the investor and the host State, and to propose avenues for rebalancing investment law. Such rebalancing entails, in particular, a clarification of vague or inconsistent jurisprudential standards and an adaptation of investor protection to contemporary challenges of international trade, while ensuring that host States retain their sovereign regulatory authority.
Issue: 2025UPASH004
Keywords: Arbitrage; Arbitrage commercial international; Arbitration; CIRDI; Etat hôte; FDI; Host state; ICSID; International; Investissements; Investissements étrangers; Investisseur; Investments; Investor

Le travail des enfants en Afrique subsaharienne et la responsabilité internationale des entreprises multinationales - Kouassi, Danielle-Esther Niangoran (Université de Montréal, 2025)
Les droits de l’enfant occupent aujourd’hui une place centrale dans le domaine des droits de la personne. De nombreuses conventions ont été adoptées pour protéger les enfants et leur reconnaître des droits spécifiques à leur condition. C’est ainsi que l’idée de l’interdiction du travail des enfants a été introduite, ce travail nuit à leur développement physique et mental ainsi qu’à leur éducation. Plusieurs organismes internationaux, comme l’Organisation des Nations Unies (ONU) et l’Organisation Internationale du Travail (OIT), se sont engagés à lutter contre ce phénomène. Cependant, en Afrique subsaharienne, cette lutte rencontre de nombreux obstacles et le travail des enfants y est encore monnaie courante. Face à cette situation, la communauté internationale (États, organismes internationaux, organisations non gouvernementales, etc.) a entrepris de nombreuses actions. Malheureusement, celles-ci ont une efficacité limitée en raison de l’absence d’implication d’acteurs primordiaux : les entreprises multinationales. Elles occupent une place de plus en plus importante sur la scène internationale et une partie de ces entreprises profite de l’exploitation des enfants dans les pays d’Afrique subsaharienne sans pour autant reconnaître ce phénomène ou leur implication directe ou indirecte. Aussi, l’état actuel du droit, plus précisément du droit international, rend difficile, voire impossible d’engager leur responsabilité. Ce travail de recherche va donc s’intéresser de plus près aux insuffisances des normes internationales adoptées et à la nécessité d’engager la responsabilité de ces entreprises du point de vue du droit international.
Keywords: Child labor; Children's rights; Conventions de l’OIT; Corporate Social Responsibility; Droits des enfants; Economic exploitation; Entreprises multinationales; Exploitation économique; Human rights violations; ILO conventions; International responsibility; Litiges transnationaux; Multinational corporations; Multinationales; Organisation international du travail; Responsabilité internationale; Transnational litigation; Travail des enfants; Violations des droits humains; international labor organization

La société coopérative à l’épreuve de la formalisation de l’exploitation minière artisanale au Burkina Faso - Kouraogo, Abdoulaye; Ilboudo, Delwendé Christophe (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2025)
Le Code minier burkinabè de 2024 institue l’organisation en société coopérative (SCOOP) comme condition préalable d’obtention de l’Autorisation d’exploitation artisanale, marquant une évolution significative par rapport au cadre antérieur. Cette orientation vise à formaliser un secteur dominé par l’informel, à renforcer le contrôle étatique et à améliorer les conditions d’exploitation. Cependant, ce modèle obligatoire soulève des défis de fond. L’exigence légale entre en tension avec le principe fondamental d’adhésion volontaire, pouvant affecter la légitimité et la viabilité des SCOOP. Le risque d’une appropriation par des acteurs influents, détournant l’objectif coopératif, est réel. De plus, la supervision étatique intensive interroge sur l’autonomie des structures. Malgré ces limites, l’impératif de souveraineté et de sécurisation d’un secteur stratégique justifie l’intervention publique. Le défi consiste à concilier respect des principes coopératifs et nécessité de régulation. Pour réussir, une approche équilibrée est nécessaire : renforcer les capacités de gestion des coopératives, adapter le régime fiscal et veiller à ce que l’encadrement étatique favorise une véritable économie sociale et solidaire, et non une formalisation superficielle. The Burkinabe Mining Code of 2024 establishes the organization cooperative (SCOOP) as a prerequisite for obtaining an Artisanal Mining Authorization, marking a significant evolution from the previous framework. This orientation aims to formalize a sector dominated by the informal sector, strengthen state control, and improve operating conditions. However, this mandatory model raises fundamental challenges. The legal requirement conflicts with the fundamental principle of voluntary membership, potentially affecting the legitimacy and viability of SCOOPs. There is a real risk of appropriation by influential actors, distorting the cooperative objective. Moreover, intensive state supervision calls into question the autonomy of the structures. Despite these limitations, the imperative of sovereignty and securing a strategic sector justifies public intervention. The challenge is to reconcile respect for cooperative principles with the need for regulation. To succeed, a balanced approach is necessary : ​​strengthening the management capacities of cooperatives, adapting the tax regime and ensuring that state supervision promotes a genuine social and solidarity economy, and not superficial formalization.
Keywords: Artisanal mining sector; Cooperatives; Encadrement; Formalisation; Formalization; Regulation; Secteur minier artisanal; Sociétés coopératives; Souveraineté de l’Etat; State sovereignty

L'obligation d'information du banquier : essai d'une théorie générale - Koyangana Mawoyi, Gracia (Université Paris-Saclay, 2025)
L'obligation d'information du banquier peine à trouver un cadre juridique cohérent. L'objectif principal de cette étude est de proposer l'essai d'une théorie générale de l'obligation d'information du banquier en abordant les questions qui dominent cette notion notamment les interrogations sur son contenu, sa nature et son régime. En effet, l'étude de la notion d'obligation d'information permet d'appréhender son contenu et sa nature marqués par un courant pluraliste qui tend à la multiplication des diligences d'information du banquier et donc à la multiplication des obligations d'information du banquier. Le contenu de l'obligation d'information du banquier va de l'information documentaire au conseil en passant par la mise en garde et l'éclairage selon le type d'opération envisagée et la qualité du bénéficiaire.Par ailleurs, la nature de l'exigence d'information du banquier traduit d'une part, une confusion entre les notions de devoir et d'obligation en droit positif alors qu'une distinction existe entre les deux notions conduisant en principe au régime de responsabilité contractuelle pour une obligation et au régime de responsabilité extracontractuelle pour un devoir. D'autre part, une imprécision peut être relevée concernant la nature extracontractuelle ou contractuelle de l'obligation d'information. Aussi, la pluralité de contenus et de natures de l'obligation d'information du banquier emporte des interrogations sur la cohérence de la notion.Cependant, cette pluralité témoigne de la volonté affichée de protection de la clientèle du banquier au regard de la fonction décisionnelle attachée à l'obligation d'information du banquier qui sert avant tout à contraindre le banquier à apporter des informations aux bénéficiaires, clients ou cautions, afin qu'ils puissent décider au mieux pour leurs intérêts. La recherche d'une cohérence du droit positif est également attendue par rapport au régime de l'obligation d'information du banquier.La controverse pendante ici tient à l'application de la responsabilité contractuelle à l'inexécution de l'obligation d'information du banquier même lorsque celle-ci est intervenue avant la signature du contrat. Cet état du droit positif est l'enjeux central qui fonde le raisonnement prônant la nature contractuelle de l'obligation d'information du banquier. Toutes ces considérations tendent à démontrer que l'obligation d'information du banquier est véritablement une notion fonctionnelle puisque la compréhension de la physionomie de l'obligation d'information se trouve dans la volonté du droit positif, notamment par l'action du juge, qui tend à apporter une solution aux difficultés concrètes rencontrées par les créanciers de l'obligation d'information.
Issue: 2025UPASH002
Keywords: Bank; Banque (responsabilité); Divulgation d'informations; General theory; Information disclosure; Obligation d'information documentaire; Obligation d'éclairer; Obligation de conseil; Obligation de mise en garde; Obligation to advise; Obligation to enlight; Obligation to provide documentary information; Obligation to warn; Théorie générale

L’avis consultatif des cours de justice CEMAC et CAE : couleur et marqueur d’une construction silencieuse du droit communautaire - Nkili Mbida, Eugène Pascal Parfait (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2025)
La présente analyse est une forme d’endoscopie de la soft law communautaire. Parcourir ses profondeurs est révélateur de ce que l’avis consultatif émis par les Cours de justice CEMAC et CAE participe d’une silencieuse construction du Droit communautaire. Par sa subtile obligatoriété, il rappelle la mission d’application et d’interprétation des Traités et des textes subséquents, confiée aux Cours de justice par les « maîtres des Traités ». L’avis consultatif, démineur de contentieux, est un gage de sécurité juridique. Il évite l’émiettement du Droit communautaire tiraillé dans le conflit inhérent aux rapports de systèmes juridiques qu’il essaie de réguler au fil des saisines pertinentes des juges d’Arusha et de N’Djaména, dans son rôle le plus à tort marginalisé. This analysis is an endoscopy of Community soft law. Delving into its depths reveals that the advisory opinion issued by the CEMAC and East African Courts of justice is part of a silent construction of Community law. Through its subtle obligatory nature, it recalls the jurisdiction over the application and interpretation of Treaties and subsequent texts, entrusted to the Courts of Justice by the “masters of Treaties”. As minesweeper of disputes, the advisory opinion is a guarantee of legality. It avoids the fragmentation of Community law, torn in the conflict inherent in the relationships between legal systems that it attempts to regulate through the relevant petitions addressed to the judges of Arusha and N’Djamena, in its most wrongly marginalized role.
Keywords: Advisor opinion; Advisory function; Avis consultatif; Community law; Cours de justice; Court of justice; Droit communautaire; Fonction consultative

L'Incidence de la fraude fiscale et de la corruption sur le développement du Mali - Traore, Amadou Jean (Université du Littoral Côte d'Opale, 2025)
L'incidence de la fraude fiscale et de la corruption sur le développement cas du Mali n'a pas pour but de faire le procès de la corruption et de la fraude fiscale, mais plutôt de diagnostiquer leurs causes et leurs modes de fonctionnement. La perversité de la corruption et de la fraude fiscale n'est plus à être strictement démontrée mais à situer dans ses raisons et racines originelles, pour permettre d'endiguer son actualisation. Notre analyse s'évitera de plonger dans une étude descriptive mais énumérant tout arithmétiquement l'incidence de la corruption et de la fraude fiscale sur le développement du Mali. L'intérêt de cette étude fait référence aux différentes prérogatives de l'administration fiscale mises en oeuvre pour prévenir, détecter, sensibiliser et sanctionner l'évitement de l'impôt. Une bonne analyse du problème pourrait servir d'instrument efficace aux mains de l'État dans la lutte contre la corruption et la fraude fiscale, cette fin légitime en soi, qui préserve l'égalité fiscale, justifie la présence des moyens exorbitants du droit commun qui fragilise la sécurité juridique à laquelle le contribuable peut prétendre. The incidence of tax evasion and corruption on Mali's development case, is not intended to prosecute corruption and tax fraud, but rather to diagnose their causes and their modes of operation. The perversity of corruption and tax evasion is not to be strictly demonstrated but to be located in its original reasons and roots, to help stem its materialization. Our analysis will avoid to plunge into a descriptive study but arithmetically listing the incidence of corruption and tax evasion on the development of Mali. The interest of this study refers to the different prerogatives of the tax administration implemented to prevent, detect, raise awareness and sanction the avoidance of the tax. A good analysis of the problem could serve as an effective tool in the hands of the State in the fight again corruption and tax evasion. This legitimate purpose in itself which preserves fiscal equality, justifies the presence of the exhorbitant means of common law which weakens the legal certainty that the taxpayer can claim.
Issue: 2025DUNK0776
Keywords: Civisme; Corruption; Development impact; Fraude fiscale; Incidence sur le Développement; Mali; Sanctions fiscales; Tax evasion; Tax penalties

La revalorisation des mécanismes locaux de prévention et de gestion des conflits au Mali : une valeur ajoutée inestimable pour le système judiciaire moderne - Yalcouyé, Seydou; Dolo, Anidjou (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
La cohabitation entre les mécanismes modernes et traditionnels de prévention et de gestion des conflits au Mali (notamment dans en milieu rural) est une réalité. Entre les mécanismes modernes et les mécanismes traditionnels, le choix des communautés porte essentiellement sur les seconds ; quoique les premiers ne sont pas non plus en abandon. Comme raisons avancées pour justifier leur choix, elles considèrent de façon générale que le recours aux mécanismes modernes ne permet pas de vider totalement leur contentieux. Les communautés trouvent que ces mécanismes modernes rendent leurs conflits plus complexes et plus difficiles à gérer. D’où la méfiance du règlement administratif ou judiciaire des conflits car trop couteux et aux procédures trop complexes. Sur la base de ces constats, il reste permis de constater la nécessité de réaliser des compromis entre mécanismes modernes et mécanismes traditionnels de gestion des conflits en revalorisant davantage les seconds. Seul à ce prix que les défis de la décentralisation (gouvernance locale) et ceux de la démocratie seront relevés. The coexistence of modern and traditional conflict prevention and management mechanisms in Mali (particularly in rural areas) is a reality. Compared to modern and traditional mechanisms, communities primarily choose the latter; although they have not abandoned the former either. As reasons given to justify their choice, they generally consider that resorting to modern mechanisms does not completely resolve their disputes. Communities find that these modern mechanisms make their conflicts more complex and more difficult to manage. Hence their distrust of administrative or judicial conflict resolution, as they are too costly and require overly complex procedures. Based on these observations, it remains clear that compromises must be made between modern and traditional conflict management mechanisms by further revaluing the latter. Only in this way will the challenges of decentralization (local governance) and democracy be met.
Keywords: Autorité traditionnelle; Conflict management; Conflict prevention; Gestion des conflits; Gouvernance locale; Local governance; Légitimité traditionnelle; Prévention des conflits; Traditional authorities; Traditional legitimacy

Les inégalités entre les victimes d'un accident de spοrt en drοit de la respοnsabilité civile - Carlin, Ludwig (Normandie Université, 2025)
Le sport appelle au dépassement de soi et à la prise de risques. Qu’ils soient amateurs ou professionnels, mineurs ou majeurs, licenciés ou non, les sportifs sont exposés à la survenance d’un accident de sport, défini comme un évènement soudain et imprévu occasionnant un dommage à un sportif. La nature physique de l’activité pratiquée augmente les probabilités de survenance d’un tel accident. Lorsqu’il se produit, la victime aspire à obtenir une réparation intégrale de ses préjudices. Elle peut trouver le moyen d’y parvenir grâce aux règles composant le droit de la responsabilité civile. En la matière, le législateur n’a pas institué un régime unique de responsabilité applicable à tous les accidents de sport. Il a simplement inséré deux modestes régimes dans le Code du sport. La jurisprudence applique alors le droit commun et le droit spécial de la responsabilité civile pourtous aux victimes d’un accident de sport. Cette situation génère des inégalités de traitement entre elles à raison de l’existence ou non d’un contrat, de l’intervention d’une chose ou non dans l’accident, de l’âge de l’auteur du dommage, etc. Une correction de ces inégalités s’impose pour mettre fin à une injustice sociale. Plusieurs instruments peuvent alors être envisagés pour parvenir à l’égalisation, mais la plupart d’entre eux déçoivent. L’immortelle théorie de l’acceptation des risques est impuissante et les règles de concours de responsabilité sont insuffisamment correctrices. La multiplication des contrats en matière sportive et la modification de l’article L. 321-3-1 du Code du sport se révèlent lacunaires. La responsabilité sans faute et l’adoption du système néo-zélandais semblent irréalistes. Dans ce contexte, la seule solution correctrice et réaliste consiste à instituer un régime spécial de responsabilité pour faute en cas d’accident de sport. Il convient alors de bâtir ce régime. Sport encourages people to push themselves and take risks. Whether they are amateurs or professionals, minors or adults, licensed or unlicensed, athletes are exposed to the risk of a sports accident, defined as a sudden and unforeseen event causing injury to an athlete. The physical nature of the activity increases the likelihood of such an accident occurring. When an accident occurs, the victim seeks full compensation for their injuries. They can find a way to achieve this through the rules of civil liability law. In this area, the legislator has not established a single liability regime applicable to all sports accidents. It has simply inserted two modest regimes into the sports Code. Case law therefore applies common law and special civil liability law to all victims of sports accidents. This situation leads to unequal treatment between victims depending on whether or not there is a contract, whether or not an object was involved in the accident, the age of the person who caused the damage, etc. These inequalities must be corrected to end the social injustice. Several instruments can be considered to achieve equalisation, but most of them are disappointing. The immortal theory of risk acceptance is powerless and the rules of shared liability are insufficiently corrective. The proliferation of sports contracts and the amendment of Article L. 321-3-1 of the sports Code have proven to be inadequate. Strict liability and the adoption of the New Zealand system seem unrealistic. In this context, the only corrective and realistic solution is to establish a special system of fault-based liability in the event of a sports accident. This system must therefore be developed.
Keywords: Accidents; Inégalités; Responsabilité civile; Sportifs; Sports; Victimes

Les valeurs sociales pénales - Vauret, Julie (Université de Bordeaux, 2025)
Les valeurs sociales pénales se présentent classiquement comme l’objet de protection du droit pénal dont elles forment tout à la fois le fondement et les limites ; elles légitiment l’incrimination et la peine en même temps qu’elles en encadrent le champ d’application. Cette position singulière conduit les auteurs à envisager les valeurs à partir des fonctions qu’elles sont susceptibles d’assurer tant dans l’élaboration de la loi pénale par le législateur que dans son application par le juge. Une telle approche fait de la valeur une notion fonctionnelle dont le contenu subordonné à l’application qui en est faite ne peut que rester largement indéterminé. L’incertitude qui caractérise le contenu des valeurs est pourtant à l’origine de la plupart des obstacles qui s’opposent à ce qu’elles jouent pleinement le rôle qui leur est par ailleurs prêté. Or, si leur place au sein de la théorie de l’infraction a été analysée et critiquée, leur contenu doit lui aussi pouvoir être discuté au titre d’une théorie générale qui leur est spécifique. Envisagées pour elles-mêmes, les valeurs peuvent être abstraitement définies autour d’une structure et d’un contenu qui en déterminent les fonctions et la façon dont celles-ci sont susceptibles de s’exercer. Se dégage ainsi un système de valeurs articulées selon une logique et des principes précis leur permettant de devenir une clé de compréhension du droit pénal. Elles n’en forment plus seulement le fondement et les limites, elles participent à en garantir la cohérence et l’équilibre. Avec les valeurs, c’est finalement plus largement l’ordre public pénal qui apparaît, dans ce qui fait sa singularité et sa complexité. Penal social values are traditionally presented as the object of protection of criminal law, constituting both its foundation and its boundaries. They legitimate the offence and the punishment while simultaneously delineating their scope of application. This singular position has led scholars to approach values through the functions they are capable of fulfilling, both in the drafting of criminal legislation by the legislator and in its application by the judge. Such an approach turns value into a functional notion whose content—being subordinated to its use—necessarily remains largely indeterminate. Yet, the uncertainty that characterizes the content of values lies at the root of most of the obstacles preventing them from fully performing the role that is otherwise ascribed to them. While their place within the theory of the criminal offence has been analysed and criticised, their content must also be open to discussion within the framework of a general theory specific to them. Considered in themselves, values may be abstractly defined around a structure and a content that determine their functions and the manner in which these functions are likely to be exercised. From this emerges a system of values articulated according to a precise logic and principles, enabling them to become a key to understanding criminal law. They thus constitute not only its foundation and its limits, but also contribute to ensuring its coherence and balance. Through values, it is ultimately the broader concept of public penal order that comes into view, in all its singularity and complexity.
Keywords: Coherence; Cohérence; Criminalization; Dispositions pénales; Droit pénal; Fundamental values; Incrimination; Necessity; Nécessité; Ordre public; Ordre public pénal; Public penal order; Valeurs fondamentales

Etude comparative de la comptabilisation des stocks en PCGC et en SYSCOHADA - Kambale Kikono, Serge (International Journal of Innovation and Scientific Research, 2025)
Cet article a été consacré à une étude comparative de la comptabilisation des stocks en système comptable congolais et en Système comptable OHADA, avec comme finalité d’établir les points de convergence et de divergence entre ces deux systèmes comptables et dire si de ces deux systèmes comptables sont efficaces dans la comptabilisation des stocks. Ainsi, au terme de nos analyses, nous avons remarqué que les deux systèmes comptables comparés dégagent plus d’éléments de différence que de ressemblance en comptabilisation des stocks. Ces différences constituent, en effet des innovations majeures qu’apporte le Système comptable OHADA au Plan Comptable Général Congolais. D’autres avantages du Système Comptable OHADA sont également dus à des innovations intéressantes apportées par celui-ci en ce qui concerne certains aspects de la vie économique des entreprises. Parmi ces avantages, citons-en: la distinction des stocks, en particulier et la distinction les stocks en activités ordinaires et hors activités ordinaires, l’utilisation d’un compte de variation des stocks pour tout mouvement en rapport avec les stocks et la présence d’un compte pour enregistrer les services encours, etc. This article is devoted to a comparative study of stock accounting in the Congolese accounting system and in SYSCOHADA, with the aim of establishing the points of convergence and divergence between these two accounting systems and determining whether they are effective in stock accounting. At the end of our analysis, we have noted that the two accounting systems compared reveal more differences than similarities in inventory accounting. These differences are, in fact, innovations that SYSCOHADA brings to the PCGC. Other advantages of SYSCOHADA are also due to the major innovations it brings to certain aspects of the economic life of companies. Among these advantages are: the distinction between inventories, in particular, and liabilities and liabilities in general in ordinary and non-ordinary activities, the use of an inventory change account for any movement relating to inventories, the presence of an account to record services in progress, etc.
Keywords: Accounting; Comptabilité; Inventaire; Inventories

A framework for bank resolution in Namibia - Eiseb, Bryan Karl Gunther (University of Pretoria, 2025)
Banks are regarded as special financial institutions because, apart from the various critical intermediary and other functions they fulfil in a financial system, the hallmark of their business models is receiving deposits from the public and using such deposits for extending loans against interest from which they make profit. Unlike other companies, banks are however vulnerable to loss of public confidence and remain exposed to various risks and failure. Banks are thus critically important actors in domestic and global financial systems, - thus their safety is critical to the maintenance of financial stability. As a result, banks are subject to stringent regulation and supervision to ensure their safety. Despite prudential regulation, the failure of banks remains a reality. If the risk of bank failure is not adequately addressed through appropriate regulation and supervision, , it may result in a financial crisis like the 2008 Global Financial Crisis (2008 GFC). Because banks play a special role in an economy and their failure may have an adverse impact on financial stability and depositors, this thesis aligns with the view expressed by academics and international organisations that there is a need for a special regime (lex specialis) to deal with the failure of banks since normal insolvency procedures are not suitable for this purpose. f. This is because bank failures require swift, timely intervention by a supervisor to resolve failing banks in an orderly and optimal manner to ensure the maintenance of financial stability, depositor protection and relegating bailouts with taxpayers’ money as a last resort. A very notable lesson that emanated from the 2008 GFC is the criticality of special resolution frameworks for banks; the need to balance the interests of shareholders, creditors, and depositors, while promoting financial stability objectives. As a result, the need for special resolution frameworks for banks which empowers Resolution Authorities with adequate resolution tools and powers to resolve a failing bank timeous and orderly , has become a legislative imperative in contemporary financial systems. To deal with bank failures in Namibia, the Banking Institutions Act, 2 of 1998 (the BIA 1998) contained provisions that allowed for the assumption of control and liquidation of a failed bank. However, the newly enacted Banking Institution Act 13 of 2023 (the BIA 2023 which repealed the BIA 1998) has changed that position and introduced a single provision in section 70 that provides for bank resolution. Until now, prior to the introduction of this very new statutory provision, all bank failures in Namibia were dealt with under the limited supervisory tools of the BIA 1998. This study seeks to determine whether section 70 of the BIA 2023, is sufficiently aligned with international best practice as captured in the Financial Stability Board’s Key Attributes of Effective Resolution Regimes for Financial Institutions (FSB KAs), issued in 2011, as updated in 2014 and 2024. Alternatively, if the regime introduced by the BIA 2023 does not adequately align with the FSB KAs it is then considered whether the new Namibian bank resolution framework requires to be strengthened further to better align it with the FSB KAs. To consider possible further reforms to the new Namibian bank resolution regime, this thesis considers the resolution frameworks in Germany and Nigeria by way of comparative studies to observe best practices.
Keywords: Bank; Financial stability; Key Attributes; Namibia; Resolution

The Interpretation of UNCITRAL Law in Australian Courts: A Roadmap for Elevating the UN Sales Convention’s Status to That of Arbitration Law - Hayward, Benjamin (Sydney Law Review, 2025)
Despite being part of Australian law for more than 30 years, the United Nations Convention on Contracts for the International Sale of Goods (‘CISG’) has not secured the internationally minded interpretation that CISG art 7(1) requires. Australia’s international commercial arbitration (‘ICA’) laws, however, are routinely approached by Australian courts with an internationalist perspective, as their own interpretative rules require. It is tempting to conclude that Australia’s approach to interpreting its ICA laws is transferable to the CISG context. In this article I address a previously unexplored nuance affecting that conclusion. Australian courts routinely accept Singaporean, Hong Kong and New Zealand interpretative influence concerning ICA laws. In the CISG context, however, significantly less influence from those jurisdictions exists. That being so, I explore how Australia’s courts might better apply the CISG in an internationalist manner. First, I recommend that Australia’s courts emphasise to practitioners the need to consider the CISG’s application and its internationalist interpretation requirements. Second, I recommend that Australian courts use the amicus curiae procedure to solicit third party submissions addressing the CISG’s interpretation. Both techniques are applied by foreign courts in the ICA context and would assist Australian courts in discharging their CISG art 7(1) obligations.
Keywords: Asia-Pacific; Australia; CISG; Harmonisation; International commercial arbitration; Model Law; New York Convention; Sales law; Statutory interpretation

Responsabilité sociale en tant que vecteur de durabilité au sein des coopératives rurales au Bénin - Nakou, Zinsou Daniel; Simen Nana, Serge Francis (L'entreprise, 2025)
Cette recherche vise à élaborer un modèle pour encourager la durabilité chez les agriculteurs en intégrant la responsabilité sociale au sein des coopératives rurales au Bénin. Une méthodologie quantitative, exploratoire et confirmatoire, a été utilisée pour analyser des données recueillies auprès de 358 membres de sept coopératives. Les résultats montrent que la dépendance des coopératives envers le gouvernement est un facteur déterminant pour adopter un comportement socialement responsable. De plus, un manque de pression gouvernementale peut constituer un obstacle à leur engagement dans des programmes de responsabilité sociale. Cet article souligne l'importance de la confiance à long terme et de la coopération entre les coopératives rurales et les agriculteurs pour intégrer la responsabilité sociale dans ces structures. Pour que cette collaboration soit efficace, il est crucial que les besoins des agriculteurs soient au cœur des stratégies des coopératives rurales. Le modèle proposé met en avant la nécessité d'une co-création de valeur entre les acteurs clés, notamment le gouvernement, les coopératives rurales et les agriculteurs, qui doivent unir leurs ressources pour renforcer la responsabilité sociale et construire un avenir durable. This research aims to develop a model to encourage sustainability among farmers by integrating social responsibility within rural cooperatives in Benin. A quantitative, exploratory, and confirmatory methodology was used to analyze data collected from 358 members of seven cooperatives. The results show that the cooperatives' dependence on the government is a determining factor in adopting socially responsible behavior. Furthermore, a lack of government pressure can be an obstacle to their commitment to social responsibility programs. This article highlights the importance of long-term trust and cooperation between rural cooperatives and farmers to integrate social responsibility into these structures. For this collaboration to be effective, it is crucial that the needs of farmers are at the heart of the strategies of rural cooperatives. The proposed model emphasizes the necessity of co-creating value among key stakeholders, including the government, rural cooperatives, and farmers, who must unite their resources to strengthen social responsibility and build a sustainable future.
Keywords: Agriculteurs; Bénin; Coopératives rurales; Durabilité; Responsabilité sociale

Le sopravvenienze nei contratti di durata: tra risoluzione e adeguamento - Votta, Maria Luigia (LUISS Guido Carli, 2025)
La sopravvenienze nei contratti di durata. I contratti di durata–evoluzione della categoria. Le sopravvenienze contrattuali. La risoluzione come prodotto rimediale nei confronti delle sopravvenienze "tipiche". La risposta dell’ordinamento all’impossibilità sopravvenuta della prestazione–presupposti e disciplina. L’eccessiva onerosità sopravvenuta–ratio e presupposti applicativi. La rinegoziazione come strumento di adeguamento contrattuale. Il principio generale di adeguamento nei contratti di durata – il fenomeno dei relational contracts. La rinegoziazione come obbligo giuridico. Le clausole di adeguamento del contratto. La rinegoziazione di fonte pattizia. Le hardship clauses nel diritto internazionale. L’usura come sopravvenienza patologica–prospettive rimediali in un contesto interpretativo articolato. Recenti implicazioni dell'obbligo di rinegoziare. Il Covid-19 come sopravvenienza contrattuale–la normativa emergenziale. L’impatto del Covid-19 sulle locazioni commerciali. La rinegoziazione nel diritto della crisi d’impresa–luci e ombre nel nuovo impianto normativo. Il principio di rinegoziazione nel nuovo codice dei contratti pubblici.
Éventualités des contrats à long terme : entre résiliation et ajustement

The role of ADR and judicial agreements: legal analysis and behavioral economics insights - Solano Mantilla, Valeria (LUISS Guido Carli, 2025)
From rationality to reality. The evolution of law and economics through the behavioral lens. Understanding how we choose: foundations of behavioral economics. Rethinking law through the lens of behavioral economics. Why law needs behavioral economics. The challenge of integrating behavioral economics into private law: freedom vs regulation. The double-edged sword of behavioral economics: protecting consumers from psychological manipulation. Balancing innovation and consumer rights: a global view on consumer protection in the EU, Italy and Colombia. Alternative dispute resolution and the judicial agreements. The justice system seen though behavioral economics. Judicial agreements: procedural autonomy and enhancing judicial cooperation. Alternative dispute resolution (ADR) and mediation: legal frameworks, party autonomy and behavioral economic. A brief comparative analysis on mediation: EU, Italy and Colombia. Applying behavioral economics in the ADR (mediation).
Keywords: ADR; Alternative dispute resolution; Economic behaviour; Mediation; Médiation

Responsabilidad legal por contratos inteligentes: Una mirada desde el Derecho Civil y Comercial - Santacruz, Mario Francisco Cuvi; Erazo, Angie Gabriela Sánchez (Polo del Conocimiento, 2025)
El presente artículo analiza la responsabilidad legal derivada del uso de contratos inteligentes (smart contracts) desde la óptica del Derecho Civil y Comercial. Estos instrumentos digitales, basados en tecnología blockchain, están transformando la manera en que se celebran, ejecutan y supervisan los contratos. Sin embargo, su automatización y descentralización presentan nuevos retos jurídicos en relación con la voluntad contractual, la imputabilidad de las partes, la reparación de daños y la validez normativa. A partir del estudio doctrinal, normativo y comparado, se identifican las principales problemáticas relacionadas con su aplicación en jurisdicciones de tradición civilista, con especial énfasis en el caso ecuatoriano. Se proponen soluciones jurídicas que permitan armonizar la innovación tecnológica con los principios fundamentales del Derecho privado, asegurando la seguridad jurídica y la protección de los derechos de los contratantes. Se exploran experiencias internacionales, especialmente en sistemas híbridos como el estadounidense y el brasileño, para evidenciar cómo distintos marcos normativos han reaccionado ante esta revolución contractual. El artículo ofrece una base conceptual y práctica para futuras reformas legales y una mejor comprensión jurídica de estos nuevos mecanismos de contratación.
Keywords: Automatización contractual; Blockchain; Contrat intelligent; Contratos inteligentes; Derecho comercial; Droit commercial; Ecuador; Equateur; Responsabilidad civil; Responsabilité civile; Tecnología jurídica

Problématique d’estimation de valeur actuelle des actifs dans l’espace OHADA - Baya Muzela, Jean Claude; Nyengele Mutambila, Moise; Nkongolo Kaajila, Dieudonné (Revue du contrôle, de la comptabilité et de l’audit, 2025)
Dans un contexte d’absence de procédure claire concernant l’estimation de valeur actuelle des actifs, l’étude a gravité autour de ce questionnement : « Comment estimer la valeur actuelle des actifs dans l’espace OHADA ? Quelles seront les implications de cette estimation sur le résultat des entités ?». Pour répondre à cette question, l’étude a opté la démarche déductive comme méthode de recherche. Elle est contextualisée et illustrée par des données empiriques issues d’un cas pratique enfin de renforcer l’applicabilité. L’objectif assigné consiste à présenter une possibilité aux organisations économiques d’estimer leur patrimoine actif en temps réel en tenant compte de leur contrainte spécifique à l’environnement OHADA. Enfin de mieux agencer la réflexion, trois grandes parties ont constitué l’ossature de cette étude. La première a reposé sur le modèle d’analyse, la deuxième sur le résultat et la discussion de la recherche et la troisième sur les limites de la recherche. Tout compte fait, le résultat de la recherche a révélé qu’il existe une relation inverse entre estimation de valeur actuelle et le résultat des entités. L’estimation entraine une diminution sensible du résultat du fait de la comptabilisation de dépréciations et de ce fait, les hypothèses empiriques émises ont été confirmées. A titre de recommandation, la transposition de la démarche proposée dans cet article est de strict conseil pour toute organisation qui se veut pérenne car, au-delà de l’amincissement du résultat, le maintien de la capacité d’autofinancement demeure une force pour l’entité.
Keywords: Actifs (valeur); OHADA

ﻗواﻋد اﻷھﻠﯾﺔ ﻓﻲ اﻟﺗّﻘﻧﯾن اﻟﻣدﻧﻲ وﺗﻘﻧﯾن اﻷﺳرة، ﻣن ﻓرﺿﯾﺔ اﻟﺗﻛﺎﻣل ﺑﯾن اﻟﻧّﺻوص إﻟﻰ واﻗﻊ - Chihani, Samir; Gattal, Hamza (Revue des Sciences Humaines, 2025)
It is known that the civil codification is the general Shariah, reffering to it whenever there is no text on a specific issue in the rest of the relevant laws. Among these laws; the codification of the family. The civil codification included general provisions regarding capacity rules, some of them reffered to the texts of the family codification which had not yet been issued, and this embodies in the phenomenon of the principle of complementarity between the two laws. However, the issuance of the family codification nine years after the issuance of the civil codification showed the converse in many placements. Particularly in the rules governing the capacity of persons; therefore, the purpose of this study was to analyze the content of those rules, with shedding light the areas of incompatibility between them, and then providing solutions to get out of the state of incoherency between texts or even conflict between them.

La négociation collective dans l'économie informelle en droit congolais du travail - Batera Muhunjuka, Jacques; Kasereka Muyisa, Jean Chrysostome (International Multilingual Journal of Science and Technology, 2025)
[FR] L’étude sur la négociation collective dans l’économie informelle en République Démocratique du Congo (RDC), constitue une interrogation sur la possibilité offerte aux travailleurs de ce secteur employant une majorité écrasante de la population congolaise mais dans lequel les syndicats sont presque absents et inexistants. Elle est une occasion pour les auteurs de revenir sur l’importance de la convention collective pour les employés dans ce secteur, en insistant sur son rapport avec le travail décent et en présentant la syndicalisation comme une condition préalable à tout dialogue social entre employés dans ce secteur. De ce fait, quelques cas tirés d’expériences d’autres pays sont présentés pour illustrer ce rapport entre négociation collective et l’idéal du travail décent. Ainsi, les leçons tirées de ces derniers ont permis de conclure à l’urgence qu’il y a de promouvoir la syndicalisation des employés informels en RDC. [EN] The study on collective bargaining in the informal economy in the Democratic Republic of Congo raises questions about the possibility offered to workers in this sector, which employs an overwhelming majority of the Congolese population but where trade unions are nearly absent or non-existent. It provides the authors an opportunity to revisit the importance of collective agreements for employees in this sector, emphasizing their connection to decent work and presenting unionization as a prerequisite for any meaningful social dialogue among workers. Consequently, a number of cases drawn from experiences in other countries are presented to illustrate the relationship between collective bargaining and the ideal of decent work. The lessons learned from these examples led to the conclusion that there is an urgent need to promote the unionization of informal workers in the DRC.
Keywords: Collective bargaining; Congo (République démocratique); Economie informelle; Informal economy; Négociation collective; Syndicalisation; Unionization

Le renouveau sécuritaire de l’état du port - Midjresso, Roméo Houndosso (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2025)
La configuration actuelle du droit de la mer contemporain est essentiellement soucieuse de l’équilibre des pouvoirs juridiques entre trois figures d’États principaux ayant des compétences en matière de sécurité maritime. Il s’agit de l’État du pavillon, de l’État côtier et de l’État du port. Sous le renouveau, l’objet de cet article est d’analyser les compétences sécuritaires de l’État du port en droit international de la mer pour répondre à la question non encore débattue sur certains aspects ou trop peu débattue sur d’autres de la place de l’État du port dans l’architecture sécuritaire maritime. Il a été démontré, d’une part, qu’une catégorie de compétences nouvelles et exclusives lui est reconnue en matière de police des ouvrages portuaires. D’autre part, les compétences jadis reconnues en matière de navigation ont été accrues et élargies à d’autres domaines vitaux comme la pollution et la pêche. Ces nouvelles compétences rendent l’État du port incontournable dans la nouvelle partition sécuritaire. The current configuration of the contemporary maritime law is essentially concerned with the balance of legal powers between three main State figures with competences in maritime safety. These are the flag State, the coastal State and the port State. Under the revival, the purpose of this article is to analyse the security competences of the port State in international maritime law in order to answer the question of the place of the port State in the maritime security architecture, which is not yet debated in some respects or not sufficiently debated in others. It has been shown, on the one hand, that a category of new and exclusive competences has been recognised in the field of policing of port works. On the other hand, the previously recognised competences in the field of navigation have been increased and extended to other vital areas such as pollution and fishing. These new competences make the Port State an essential part of the new security partition.
Keywords: Competence; Compétence; Marine safety; Navigation; Ouvrage portuaire; Port State; Port facility; Sécurité marine; État du port

Le sort de biens des concubins à la rupture de leur union en droit congolais de la famille - Musubao Ushindi, Paul (International Multilingual Journal of Science and Technology, 2025)
Contrairement aux personnes mariées chez qui la liquidation de leurs intérêts patrimoniaux ne pose pas problème grâce aux règles sur les régimes matrimoniaux, il en est autrement pour les concubins pour qui le législateur congolais ne voue qu’indifférence par rapport à cette question, considérant que ceux-ci s’étant affranchis de la loi, ils ne sauraient retour recourir à cette loi pour les départager lors de la liquidation de leurs intérêts patrimoniaux. Il résulte de cette considération que le législateur ne prévoit aucune disposition spécifiquement dévolue aux concubins, ceux-ci ne peuvent invoquer que des règles de droit commun ou celles de la société créée de fait qui ne répondent pas convenablement à la question. Il est question dans cette étude de s’interroger si le législateur congolais ne serait pas mieux indiqué à accorder aux concubins un statut qui organise leur union ainsi que leur patrimoine.
Keywords: Concubinage; Congo (République démocratique); Droit congolais; Liquidation; Patrimoine

La répression des nuisances environnementales au Cameroun - Panzarin Angoula, Rita (Université Catholique d'Afrique Centrale, 2025)
Les progrès scientifiques, conjugués à la croissance démographique accélérée ainsi qu’au développement technologique et industriel, exercent une pression considérable sur l’environnement, rendant indispensables des mesures rigoureuses pour en assurer la préservation. Les Objectifs de Développement Durable (ODD) de l’ONU, ainsi que les Conférences des Parties à la Convention sur le climat, soutiennent activement les efforts de protection environnementale. Dans cette perspective, la Conférence de Stockholm de 1972 a inauguré le dialogue international sur les questions environnementales et posé les fondements du droit international de l’environnement. Le Cameroun, dans cette dynamique, a adopté des législations nationales visant à préserver l’environnement et à lutter contre les formes de pollution et de nuisances. À cet égard, la Loi-cadre de 1996 relative à la gestion de l’environnement établit les bases juridiques de la protection contre les nuisances et prévoit un dispositif répressif en cas d’infraction. Ce dispositif repose sur un ensemble d’incriminations et de sanctions, articulé autour d’un cadre institutionnel et procédural orienté vers la répression des atteintes à l’environnement. Toutefois, des lacunes dans sa mise en œuvre soulèvent des interrogations quant à son efficacité réelle. L’analyse de la répression des nuisances environnementales au Cameroun, qu’elles soient sonores, olfactives, esthétiques ou liées à la mauvaise gestion des déchets, met en évidence une volonté législative de sanctionner les infractions qui y sont rattachées. Toutefois, cette volonté demeure en décalage avec la gravité réelle des atteintes portées à l’environnement et à la santé humaine. Ce déséquilibre compromet le rendement du dispositif répressif, laissant ainsi de nombreuses nuisances impunies. Les principales causes de ce décalage résident dans la complexité des incriminations et la faiblesse des sanctions. Face à ces limites, il apparaît nécessaire de renforcer la mise en œuvre de la répression à travers une redéfinition rigoureuse des éléments constitutifs des infractions environnementales et un durcissement des sanctions applicables. De plus, un renforcement des capacités opérationnelles des acteurs concernés, ainsi qu’une meilleure coordination entre les institutions chargées de la répression sont nécessaires. Il convient également de réformer les mesures répressives en vigueur, tout en encadrant strictement les mécanismes alternatifs de règlement des litiges environnementaux, afin d’éviter qu’ils ne deviennent des échappatoires à la sanction. Scientific progress, combined with rapid population growth and technological and industrial development, exerts considerable pressure on the environment, making rigorous measures essential to ensure its preservation. The United Nations Sustainable Development Goals (SDGs), along with the Conferences of the Parties to the Climate Convention, actively support efforts to protect the environment. In this context, the 1972 Stockholm Conference inaugurated international dialogue on environmental issues and laid the foundations of international environmental law. Cameroon, in alignment with this global momentum, has adopted national legislation aimed at safeguarding the environment and combating various forms of pollution and nuisance. In this regard, the 1996 Framework Law on Environmental Management sets up the legal basis for protecting against nuisances and provides for a repressive mechanism in case of infringement. This mechanism is built upon a set of offences and sanctions, structured around an institutional and procedural framework geared towards the repression of environmental violations. However, shortcomings in its implementation raise questions about its actual effectiveness. An analysis of the repression of environmental nuisances whether auditory, olfactory, aesthetic, or linked to poor waste management reveals a legislative intent to penalize related offences. Nevertheless, this intent stays misaligned with the actual severity of harm caused to the environment and public health. Such imbalance undermines the effectiveness of the repressive framework, leaving nuisances unpunished. The main causes of this discrepancy lie in the complexity of the offences and the leniency of the sanctions. Considering these limitations, it is necessary to strengthen enforcement by rigorously redefining the constituent elements of environmental offences and tightening the applicable sanctions. Furthermore, enhancing the operational capacities of relevant actors and improving coordination among the institutions responsible for enforcement are essential. Existing repressive measures must also be reformed, while strictly regulating alternative mechanisms for resolving environmental disputes to prevent them from becoming loopholes that circumvent sanction. Wissenschaftlicher Fortschritt in Verbindung mit beschleunigtem Bevölkerungswachstum die technologische und industrielle Entwicklung erheblich unter Druck auf Umwelt, wobei strenge Maßnahmen unerlässlich sind, um sicherzustellen, dass die Umwelt Erhaltung der UN-Ziele für nachhaltige Entwicklung (SDGs) und der Konferenzen der Vertragsparteien des Klimaübereinkommens unterstützen aktiv die Bemühungen um Umweltschutz. In diesem Sinne wurde die Stockholmer Konferenz 1972 den internationalen Dialog über Umweltfragen aufzunehmen und die Grundlagen zu legen Das internationale Umweltrecht Kamerun hat in dieser Dynamik einzelstaatliche Rechtsvorschriften zur Erhaltung der Umwelt und zur Bekämpfung von Formen der Verschmutzung und Belästigungen. In diesem Zusammenhang das Rahmengesetz von 1996 über die Verwaltung von Die Umwelt schafft die rechtliche Grundlage für den Schutz vor Belästigungen und sieht eine repressive Maßnahmen im Falle von Verstößen. Dieses System basiert auf einer Reihe von Kriminalisierungen und Sanktionen, die sich um einen institutionellen und verfahrenstechnischen Rahmen für Repressionen drehen Umweltschäden. Allerdings führen Mängel bei der Umsetzung zu Lücken in der Fragen zu seiner tatsächlichen Wirksamkeit. die Analyse der Unterdrückung von Umweltbelästigungen in Kamerun, dass sie gesund, olfaktorisch, ästhetisch oder mit schlechter Abfallwirtschaft zusammenhängen, Es gibt Hinweise auf den Wunsch der Gesetzgebung, damit zusammenhängende Straftaten zu sanktionieren. Jedoch, Dieser Wunsch bleibt mit der wirklichen Schwere der Umweltschäden unvereinbar und der menschlichen Gesundheit. Dieses Ungleichgewicht beeinträchtigt die Leistung des repressiven Systems und lässt viele ungestrafte Belästigungen. Die Hauptursachen für diese Diskrepanz liegen in die Komplexität der Belastungen und die Schwäche der Sanktionen. die Notwendigkeit, die Umsetzung der Repression durch eine strikte Neudefinition zu verstärken die konstituierenden Elemente von Umweltverstößen und einer Verschärfung der Sanktionen darüber hinaus eine Stärkung der operativen Kapazitäten der betroffenen Akteure sowie eine Stärkung der operativen Kapazitäten der betroffenen Akteure sowie Es bedarf einer besseren Koordinierung zwischen den Strafverfolgungsbehörden. Die bestehenden repressiven Maßnahmen sollten ebenfalls reformiert werden, wobei gleichzeitig die alternative Mechanismen zur Beilegung von Umweltstreitigkeiten, um Sie werden nicht zu Fluchten vor der Bestrafung.
Keywords: ABFALL; Aesthetic Nuisances; Contaminación; Déchets; Environment; Environmental Nuisances; Environnement; Geruchsbelästigungen; Lärmbelästigungen; Medio ambiente; Molestias ambientales; Molestias de olores; Molestias de ruido; Molestias estéticas; Noise Nuisances; Nuisances Environnementales; Nuisances Esthétiques; Nuisances Olfactives; Nuisances Sonores; Odor Nuisances; PRINCIPALES ABRÉVIATIONS ET SIGLES UTILISÉS Affaire AJDA : Actualité Juridique Déchets; Pollution; Represión; Residuos.; Répression; Répression Environment; Répression.; Umwelt; Umweltbelästigungen; Unterdrückung; Verschmutzung; Waste; Waste.; Ästhetische Belästigungen

L’exigence d’évaluation d’impact pour responsabiliser les entreprises face aux risques engendrés par l’intelligence artificielle - Pierre-Gilles, Cédrik (Université de Montréal, 2025)
La grande majorité des lois encadrant le développement ou le déploiement de systèmes d’intelligence artificielle (« IA ») à l’échelle mondiale impose aux acteurs privés de réaliser une forme d’évaluation d’impact. Ce type d’exigence vise à opérationnaliser un principe de responsabilité et plus précisément à instaurer une responsabilité ex ante destinée à prévenir les préjudices liés à l’IA, dans un contexte où la complexité et l’opacité de ces technologies entravent l’efficacité des mécanismes de responsabilité ex post. Lorsqu’on s’interroge sur la façon dont les exigences d’évaluation d’impact cherchent concrètement à responsabiliser les entreprises en amont, on constate qu’elles relèvent d’une approche de métarégulation : en incorporant ces exigences aux textes de loi, l’État mobilise les structures de régulation internes des entreprises afin que celles-ci gèrent par elles-mêmes les risques engendrés par l’IA. Les entreprises sont ainsi appelées à recueillir des données, à élaborer des normes, à modifier leurs pratiques – en somme, à réguler leurs propres activités – afin d’atténuer les effets indésirables que leurs projets relatifs à l’IA pourraient avoir sur la société, même lorsque ces effets demeurent incertains. Ainsi comprise, la démarche d’évaluation d’impact obligatoire contribue non seulement à une conduite dite responsable des entreprises, mais aussi à la conception d’une responsabilité juridique aux dimensions sociale et prospective.
Keywords: Artificial Intelligence; Autorégulation; Corporations; Entreprises; Gestion du risque; Impact assessment; Inteligência artificial; Intelligence Artificielle; Intelligence artificielle; Meta-regulation; Métarégulation; Responsabilité; Responsibility; Risk management; Évaluation d’impact

Analyse critique du développement de la médiation en France : les résistances à l'essor de la médiation en droit privé - Prêté, Safya Bayoub (Université Bourgogne Franche-Comté, 2025)
La médiation est une technique de communication faisant intervenir un tiers impartial, neutre et indépendant, pour aider des individus à trouver une issue à leur crise conflictuelle. Par essence, la médiation est un outil de résolution des conflits pacifiant, fondé sur la responsabilisation des parties. Attrayante par sa souplesse, louée pour son coût présenté comme modéré, le législateur en a encouragé l’expansion. Alors que l’article 21 du code de procédure civile confie au juge la mission de concilier les parties, la médiation devient l’un des outils privilégiés par les pouvoirs publics pour permettre la réalisation de cette mission. Ainsi, la loi n°95-125 du 8 février 1995, relative à l’organisation des juridictions et à la procédure civile, pénale et administrative, institue la médiation judiciaire. Elle marque le début d’un ancrage législatif en faveur de ce processus. Ce premier mouvement en faveur de la médiation s’est accéléré en France, à l’initiative de l’Union européenne qui a fait adopter le 21 mai 2008 la Directive 2008/52/CE portant sur la médiation en matière civile et commerciale. Le postulat de départ de ce texte est qu’un « cadre juridique prévisible peut permettre aux citoyens de l’Union européenne (UE) de bénéficier pleinement des avantages de la médiation en tant que mécanisme de résolution des conflits, notamment sur le plan de la rentabilité et de la rapidité ». Puis, la médiation conventionnelle a été encadrée au sein du code de procédure civile. L’intégration de la Directive 2008/52/CE au sein du corpus de normes du droit interne positif a permis de créer une définition légale de la médiation en ces termes : « La médiation régie par le présent chapitre s'entend de tout processus structuré, quelle qu'en soit la dénomination, par lequel deux ou plusieurs parties tentent de parvenir à un accord en vue de la résolution amiable de leurs différends, avec l'aide d'un tiers, le médiateur, choisi par elles ou désigné, avec leur accord, par le juge saisi du litige ».Or, le mouvement d’expansion de la médiation semble freiné par un jeu de résistances. Certaines de ces résistances concernent le processus et sont prévisibles. D’autres tiennent à des variables exogènes, résultats de questionnements sur la médiation, le médiateur, l’office du juge, la déjudiciarisation, la déjuridictionnalisation, et l’ordre public. L’étude pose que l’essor de la médiation est contrarié par une méconnaissance de la médiation, ainsi qu’en raison d’une méconnaissance des acteurs de la médiation.Le mouvement d’encouragement des pouvoirs publics à la tentative de médiation, pour prévenir ou traiter des contentieux du droit privé, semble se muer en une politique globale de l’amiable, recentrée sur la mission du juge de concilier les parties. Cette politique de l’amiable persiste à produire des normes tendant, notamment, à encadrer la médiation, à créer un statut pour le médiateur, dans l’optique d’acculturer les justiciables à ce mode amiable.L’objet de la présente thèse est d’analyser les résistances à l’essor de la médiation en droit privé et leurs conséquences sur son développement en France. Il s’agit de saisir ces résistances et leurs enjeux ; et de redonner force au processus de médiation, en offrant à ses prescripteurs un faisceau d’arguments intelligibles. Mediation is a communication technique involving an impartial, neutral and independent third party to help individuals find a way out of their conflict crisis. By nature, mediation is a pacifying conflict resolution tool, based on the accountability of the parties. Attractive for its flexibility, praised for its moderate cost, the legislator encouraged its expansion. While Article 21 of the Code of Civil Procedure entrusts the judge with the task of reconciling the parties, mediation is becoming one of the tools favoured by the public authorities to enable this mission to be carried out. Thus, Law No. 95-125 of February 8, 1995, relating to the organization of the courts and civil, criminal and administrative procedure, establishes judicial mediation. It marks the beginning of a legislative anchoring in favour of this process. This initial movement in favour of mediation has accelerated in France, at the initiative of the European Union, which adopted Directive 2008/52/EC on mediation in civil and commercial matters on May 21, 2008. The premise of this text is that "a predictable legal framework can allow citizens of the European Union (EU) to fully benefit from the advantages of mediation as a dispute resolution mechanism, particularly in terms of cost-effectiveness and speed". Then, conventional mediation was framed in the Code of Civil Procedure. The incorporation of Directive 2008/52/EC into the body of norms of positive domestic law has made it possible to create a legal definition of mediation in the following terms: "Mediation governed by this chapter means any structured process, whatever its name, by which two or more parties attempt to reach an agreement with a view to the amicable resolution of their disputes, with the help of a third party, the mediator, chosen by them or appointed, with their agreement, by the judge hearing the dispute". However, the movement towards the expansion of mediation seems to be slowed down by a game of resistance. Some of these resistances are process-related and predictable. Others relate to exogenous variables, the result of questions about mediation, the mediator, the judge's office, diversion, dejurisdictionalization, and public order. The study posits that the development of mediation is thwarted by a lack of knowledge of mediation, as well as because of a lack of knowledge of the actors involved in mediation. The movement to encourage the public authorities to attempt mediation, to prevent or deal with private law disputes, seems to be turning into a global policy of amicable litigation, refocused on the judge's mission to reconcile the parties. This amicable policy persists in producing standards tending, in particular, to regulate mediation, to create a status for the mediator, with a view to acculturating litigants to this amicable method. The purpose of this thesis is to analyze the resistance to the rise of mediation in private law and their consequences on its development in France. It is a question of grasping these resistances and their stakes; and to give strength to the mediation process, by offering its prescribers a bundle of intelligible arguments.
Issue: 2025UBEUF002
Keywords: Amiable; Arbitrage (droit); Arbitration; Civil Law; Contract Law; Contrats; Droit civil; Droit des contrats; Droit privé; France; Mediation; Médiation; Private Law; Procedure Law; Procédure civile; Settlment

Le droit international à l’épreuve des catastrophes de pollutions résultant du transport maritime international des hydrocarbures - Tchassem Nzalé, Raymond (Université de Montréal, 2025)
La réalisation effective des objectifs de développement durable visés par la communauté internationale dépend en grande partie de la gestion efficace des catastrophes écologiques d’origine humaine. Dans le cadre des marées noires découlant du transport maritime international des hydrocarbures, le régime de responsabilité civile applicable se distingue du droit commun par certaines spécificités, gages prétendus de l’efficacité des mesures de réparation prévues, compte tenu de la particularité des dommages y afférents. Ces spécificités ont trait à l’objectivation de la responsabilité du propriétaire du navire et de la cargaison, la canalisation des charges réparatrices sur ces derniers et l’instauration d’un système de garantie obligatoire assortie d’un droit de limitation de responsabilité. De toute façon, l’indemnisation des victimes de marées noires reposent principalement sur le propriétaire du navire, et subsidiairement sur les propriétaires de cargaisons, qui agissent via des Fonds d’indemnisation en cas de défaillance du propriétaire du navire. Malgré toutes ces garanties de réparation, le régime international actuel de responsabilisation des marées noires présente des lacunes qui entravent souvent l'application effective du droit des victimes à une indemnisation rapide et intégrale. Au rang des facteurs qui favorisent ces lacunes, le conflit entre l'obligation légale d'appliquer rigoureusement ce droit et la nécessité de considérer les impératifs de développement social et économique des États et des investisseurs, inhérent à presque tout régime de responsabilité environnementale, occupe une place primordiale. Dans le cadre des marées noires, les manifestations de ce conflit sont perceptibles aussi bien au niveau juridique (coexistence de deux principes quasi antagonistes : le principe de limitation de responsabilité et celui de la réparation intégrale), qu’au niveau opérationnel. Pour remédier à ces problèmes et promouvoir la réalisation effective des objectifs de réparation escomptés par les rédacteurs des Conventions de l'OMI relatives aux marées noires, il est essentiel de prendre en compte les préoccupations de développement dans tout processus de responsabilisation de ces phénomènes. À ce titre, il est proposé d'inverser les étapes du processus en vigueur et à les réorganiser autour d'un Fonds d'indemnisation (FIIIPOL), collectivement financé par les acteurs majeurs impliqués dans le transport maritime international des hydrocarbures. Ce Fonds « illimitée » indemniserait automatiquement les victimes sur la base d’un principe de réparation VRAIMENT intégrale, avec un droit de recours contre le responsable réel. Soumis à une sorte de judiciarisation et de judicialisation du développement durable dûment conventionnée, ce recours serait assorti d’une tentative préalable et obligatoire de règlement amiable et la phase contentieuse y afférente serait centralisée au Tribunal international du droit de la mer (TIDM). The effective achievement of the international community's sustainable development objectives depends to a large extent on the effective management of man-made environmental disasters. In the context of oil spills resulting from the international maritime transport of hydrocarbons, the applicable civil liability regime differs from ordinary law in certain specific respects, which are claimed to guarantee the effectiveness of the compensation measures provided for, given the particular nature of the related damage. These specific features relate to the objectification of the liability of the shipowner and the cargo, the channelling of repair costs to the latter and the introduction of a compulsory guarantee system with a right to limit liability. In any case, compensation for victims of oil spills rests mainly with the shipowner, and secondarily with the cargo owners, who act via compensation funds in the event of the shipowner's default. Despite all these guarantees of compensation, the current international oil spill liability regime has shortcomings that often hinder the effective application of victims' right to prompt and full compensation. Among the factors contributing to these shortcomings, the conflict between the legal obligation to rigorously apply this right and the need to consider the social and economic development imperatives of States and investors, which is inherent in almost all environmental liability regimes, is of prime importance. In the case of oil spills, the manifestations of this conflict are perceptible both at the legal level (coexistence of two almost antagonistic principles: the principle of limitation of liability and the principle of full compensation) and at the operational level. To remedy these problems and promote the effective achievement of the reparation objectives expected by the drafters of the IMO Conventions relating to oil spills, it is essential to take account of development concerns in any process of accountability for these phenomena. To this end, it is proposed to reverse the stages of the current process and to reorganise them around an ‘unlimited’ Compensation Fund (FIIIPOL), collectively financed by the major players involved in the international maritime transport of hydrocarbons. This Fund would automatically compensate victims on the basis of an ‘unlimited’ principle of reparation, with a right of recourse against those actually responsible, subject, however, to a form of judicialisation of sustainable development duly agreed. With prior compulsory attempts at out-of-court settlements, the contentious phase of these appeals would be centralised at the International Tribunal for the Law of the Sea (ITLOS).
Keywords: Automation of procedures; Automatisation des procédures; Civil Liability; Compensation; Développement durable; Hydrocarbons; Hydrocarbures; Indemnisation; Judicialisation; Judiciarisation; Maritime transport; Marée noire; Oil spill; Responsabilité civil; Réparation illimitée; Sustainable development; Transport maritime; Unlimited compensation

Impact of Blockchain Adoption, Regulatory Environment, and Institutional Investor Participation on FinTech Innovation - Almestarehi, Ahmad Abdel Rahim; Al-Ababneh, Hassan Ali; Malkaw, Eyad Mohammad (Theoretical and Practical Research in Economic Fields, 2025)
This study investigates how blockchain integration, regulatory policies, and the participation of institutional investors impact fintech innovation in Jordanian fintech companies. A descriptive analytical approach was used to evaluate and summarize the effects of these factors on innovation in the sector. An electronic survey was conducted among 125 administrative personnel working in Jordan's fintech industry. The results indicate a strong presence of blockchain adoption, involvement of institutional investors, and overall fintech innovation in these companies. However, the regulatory landscape in Jordan's fintech sector was found to be moderate. Furthermore, the analysis reveals that both blockchain integration and the regulatory framework significantly influence fintech innovation, with a significance level of 0.05. In light of these findings, the study suggests the creation of strategies to promote blockchain adoption, aiming to enhance efficiency and innovation in the industry.
Number: 2

Révision du code minier et fiscalité miniere en République démocratique du Congo. Répenser la conciliation des intérêts de l’état et ceux des investisseurs du secteur minier - Mbazi, Grâce Beda; Mbasoni, Séraphin Christian; Iragi Ntwali, Valéry (Studia Universitatis Babeș-Bolyai Studia Europaea, 2025)
Revision of the Mining Code and Mining Taxation in the Democratic Republic of Congo. Rethinking the Reconciliation of the Interests of the State and Those of Investors in the Mining Sector. The new Mining Code of the Democratic Republic of Congo (DRC) introduced modified fiscal and customs regimes, impacting both the state and extractive companies. For the state, these regimes led to an increase in public revenues, contributing to the financing of essential services such as health, education, and infrastructure. For extractive companies, the new regimes resulted in higher fiscal burdens, with high tax rates and a multiplicity of taxes and royalties. This increased pressure on operating costs, making Congolese mining companies more competitive while discouraging foreign investments and leading to a decline in mining production. To reconcile the fiscal interests of the state with those of mining operators, it is recommended to strengthen the legislative and regulatory framework of the Congolese mining fiscal regime, promote dispute resolution methods such as arbitration or mediation, and consider renegotiating fiscal contracts.
Keywords: Activité minière; Fiscal measures; Mesures fiscales; Mining activities; Mining operators; Mining revenues; Mining tax regime; Opérateurs miniers; Renegotiation; Régime fiscal; State; Tax disputes

La planification maritime en Méditerranée : Étude sur la contribution d’un instrument de politique publique à la mise en œuvre du droit international de la mer - Seddik, Wissem (Aix-Marseille Université, 2025)
La notion de planification en mer se diffuse à partir des années 2000 avec un succès notable au sein des institutions de coopération internationale dans le domaine maritime. Cette « planification de l’espace maritime » est présentée comme un instrument de développement durable innovant et prometteur en ce qu’il permettrait de rationaliser la gestion des usages de l’espace marin. L’étude de son articulation au droit de la mer apparaît alors d’un intérêt évident. Cette thèse s’intéresse plus spécifiquement à la contribution, possible ou avérée, de l’instrument de planification à la mise en œuvre du droit international de la mer. Elle est menée dans un champ de recherche circonscrit à la mer Méditerranée. Du fait de son caractère semi-fermé et de la pluralité d’États riverains, issus de différents continents, qu’elle met en contact, la Méditerranée place la planification maritime face à des enjeux à la fois propres à la région et d’une portée universelle. Dans ce contexte, la présente étude montre que, derrière l’apparence séduisante du concept, la planification maritime est un objet protéiforme aux contours flous et aux finalités parfois équivoques. Elle porte l’analyse à la croisée de grandes questions du droit international de la mer telles que la territorialité en mer, le particularisme régional et l'articulation de ce corps de règles avec l'ordre juridique de l’Union européenne. Elle conduit plus largement à s’interroger sur les mutations de la normativité juridique induites par la promotion d’un nouveau genre d’instruments de politique publique en mer.
Keywords: Aire marine protégée; Conflits d’usage en mer; Convention de Barcelone; Droit international de la mer; Espace maritime; Politique maritime intégrée; Protection de l’environnement; Union européenne; Zonage maritime

Tax Reform and Investment Decision Effects in an Emerging Economy: Insights from Ghana - Yeboah, Michael; Danquah, Benjamin Adjei; Bawuah, Jonas; Nkwantabisa, Agyeiwaa Owusu (Theoretical and Practical Research in Economic Fields, 2025)
This study focuses on both domestic and foreign investment as indicators of economic growth in an emerging market context, examining the effects of tax reforms on investment decisions in Ghana from 1985 to 2020. The research employs a time-series analysis to integrate control variables like inflation, gross capital formation, and base rate, revealing their significant influence on investment activity in tandem with tax policy changes. Unlike previous research that mostly uses gross fixed capital formation as a proxy for investment, this study includes a wider range of investment types, giving a more complete picture of how the economy works. We did unit root and co-integration tests, which showed that the variables were first-order co-integrated. We performed the model estimate using a Vector Error Correction Model (VECM) and Granger causality tests. Results reveal that tax reforms have a measurable impact on investment patterns, underscoring the importance of adaptive tax policies in promoting sustainable economic development. The findings contribute to the broader literature on investment and fiscal policy in emerging economies, offering insights for policy-makers on optimizing tax strategies to encourage investment and drive economic growth.

El arbitraje como justicia alternativa y eficaz - Nieto, Gastón Fabricio Correa (Polo del Conocimiento, 2025)
El presente ensayo surge de la experiencia del ejercicio profesional de la abogacía en la que en el ámbito judicial, extrajudicial, donde se ha observado diferentes vicisitudes en el desarrollo y ejecución de procesos judiciales, generando de esta forma ineficiencia en la administración de justicia; para lo cual como alternativa viable surgen los métodos alternativos de solución de conflictos con la promulgación de la Ley de Arbitraje y Mediación surgen en septiembre de 1997 como una opción ante la deficiente administración de Justicia.Sin embargo, esta ineficiencia procesal representa a su vez un obstáculo real para su ejercicio efectivo de derechos, especialmente obtener “justicia” para los ciudadanos que enfrentan demoras prolongadas y procedimientos burocráticos que terminan por vulnerar sus derechos. Uno de los objetivos del artículo es la de establecer las medidas efectivas que se pueden adoptar en instancia extrajudicial y elementos necesarios alcanzar la tan preciada “Justicia” siendo esta “la constante y perpetua voluntad de dar a cada quien lo que le corresponde” (Ulpiano, 2015).
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Deficiencia judicial; Justicia; Negligencia; Retardo

Le consentement en droit de la propriété littéraire et artistique - Dramé, Mamadouba (Université de Lorraine, 2025)
Le processus d'autonomisation du droit de la propriété intellectuelle par rapport au droit commun en France a atteint son apogée à travers la loi n° 92-597 du 1re juillet 1992 qui créa un code en la matière. Depuis cette date, la matière n'a cessé de se développer. Et cette évolution n'est pas sans conséquence sur le consentement des différents acteurs du secteur. Il est question du consentement à tous les niveaux : que ce soit sur les opérations juridiques (cession, licence, contrat d'édition etc.) dont les œuvres font objet ou encore sur la volonté affichée par le législateur de protéger l'auteur ou le créateur de toute œuvre de l'esprit. L'objectif de cette thèse est donc de démontrer les manifestations du consentement de l'auteur ainsi sa particularité par rapport au droit commun. The process of making intellectual property law autonomous from common law in France reached its apogee with Law no. 92-597 of July 1, 1992, which created a code on the subject. Since then, the field has gone from strength to strength. And this evolution is not without consequences for the consent of the various players in the sector. Consent is an issue at every level, from the legal transactions (assignment, licensing, publishing contracts, etc.) to which works are subject, to the legislator's desire to protect the author or creator of any work of the mind. The aim of this thesis is therefore to demonstrate the manifestations of the author's consent, and how it differs from common law.
Keywords: Artificial Intelligence; Consent; Consentement (droit); Contract; Contrat; Contrefaçon; Copyright; Copyright infringement; Droit d'auteur; Exceptions aux droits d'auteur; Exceptions to Copyright; Intellectual property; Intelligence artificielle; Propriedade intelectual; Propriété intellectuelle

Le concept de transparence en droit : essai à la lumière du droit du travail - Zeimet, Marine (Université d'Orléans, 2025)
Inondant le discours juridique, la transparence fascine autant qu'elle intrigue. Jugée insaisissable, elle est utilisée par les juristes dans un sens courant. La transparence renvoie alors à l'accès à une information, à sa clarté, à un droit de savoir. Pourtant, cette approche de la transparence, presque par défaut, n'est pas pleinement satisfaisante. Elle ne permet pas de comprendre l'utilisation ou l'absence d'utilisation du terme dans le discours juridique. Le droit du travail français l'illustre particulièrement : dans le discours travailliste, l'information constitue un thème récurrent tandis que la transparence n'est pas un terme ancré, en tout cas pas autant que dans ses domaines de prédilection tels que le droit administratif ou le droit de la concurrence. Ambitionnant d'expliquer ce paradoxe, cette recherche propose un concept juridique de transparence. Selon ce concept, la transparence traduit l'idée selon laquelle l'exposition au regard d'autrui orienterait le comportement de la personne exposée. L'exposition au regard vise d'une part à informer les observateurs. Cette fonction informative, bien identifiée dans le discours juridique, constitue une fonction certes nécessaire mais mineure de la transparence. Elle est complétée par une fonction régulatrice : l'exposition au regard vise à orienter le comportement de la personne exposée. Il s'agit notamment de moraliser le comportement des responsables politiques ou de réguler le marché. Cette fonction régulatrice, peu identifiée dans le discours juridique, constitue pourtant la fonction majeure du concept de transparence. Dès lors, ce concept se définit comme une exposition au regard d'autrui exerçant une fonction informative et une fonction régulatrice, la seconde primant sur la première. En droit du travail, la fonction régulatrice associée à l'exposition au regard ne l'emporte que rarement sur la fonction informative, expliquant ainsi le faible ancrage de la transparence dans ce domaine. Certes, tout comme le terme de transparence, la fonction régulatrice n'est pas totalement absente du discours travailliste. Sa place y est cependant restreinte : tantôt écartée, tantôt concurrencée. L'identification et la hiérarchisation des fonctions de la transparence permettent donc de mieux comprendre l'utilisation du terme dans le discours juridique.
Keywords: Concept juridique; Divulgation d'informations; Droit; Droit du travail; Employeur et employé (droit); France; Information; Labour law; Protection de l'information (informatique) – Droit; Régulation (sciences sociales); Transparence (droit); Travailleurs

Comercio sostenible y arbitraje internacional: un enlace estratégico para la resolución de conflictos - León, Jorge Guillermo Cedeño; Erazo, Angie Gabriela Sánchez (Polo del Conocimiento, 2025)
El arbitraje internacional ha emergido como una herramienta clave para la resolución de controversias en el comercio sostenible, ofreciendo un marco eficiente y flexible. Este estudio analiza el uso del arbitraje en casos relacionados con comercio y sostenibilidad, evaluando su efectividad en la promoción de prácticas comerciales responsables.
Keywords: Arbitrage international; Arbitraje internacional; Comercio sostenible; Commerce durable; International commercial arbitration; Prácticas responsables; Resolución de controversias; Sostenibilidad

Le COC : entre maintien et inspiration à l’aune d’une lecture critique de la réforme française du droit des contrats - Chamaa, Claudia (Université de Montpellier; Université Saint-Joseph, 2025)
Le Code Napoléon a constitué l’une des sources d’inspiration majeure du COC libanais. Or, les dispositions du Code français concernant les obligations et les contrats ont fait l’objet d’une réforme par le biais de l’ordonnance du 10 février 2016 ratifiée par la loi de ratification du 20 avril 2018. Cela nous a conduits à nous interroger sur l’impact de la réforme du Code civil français sur le COC, notamment ses dispositions en matière contractuelle, et plus spécifiquement celles relatives au rapport des parties contractantes entre elles. Par le biais d’une étude critique des articles issus de la réforme ainsi qu’une comparaison entre ces articles et ceux du COC, nous sommes arrivés aux conclusions suivantes. Pour la phase précontractuelle, qui était déjà prévue et organisée par le COC, nous avons trouvé qu’il faudrait apporter de simples retouches aux institutions existantes. Toutefois, ces simples retouches ne suffisent pas à offrir un encadrement global de la phase précontractuelle. La promotion d’autres institutions consacrées par la réforme, à savoir la bonne foi précontractuelle et le pacte de préférence - auquel nous avons préféré la dénomination de contrat de préférence -, serait nécessaire. Quant aux éléments constitutifs du contrat, nous avons trouvé d’une part, qu’il faudra maintenir intactes les dispositions relatives à la cause, au consentement et aux sanctions de l’absence des éléments constitutifs dans le COC. En revanche, nous avons jugé primordial de moderniser celles relatives à l’objet. Une fois conclu, le contrat doit être exécuté. Une comparaison entre les divers outils prévus par le COC et ceux prévus par le Code civil issu de la réforme ainsi que leurs études critiques nous ont conduits à proposer de maintenir intact le principal outil permettant l’exécution du contrat, à savoir l’exécution forcée en nature. En revanche, nous avons proposé de consacrer textuellement d’autres outils prévus par le Code civil réformé : l’exception d’inexécution, les règles relatives à la durée du contrat, la règle apportant une solution en cas de disparition d’un indice nécessaire à la détermination d’un élément du contrat. De même, nous avons jugé essentiel d’apporter une précision à l’un des mécanismes équivalents à la cession de contrat dans le COC : il faudrait confirmer la libération du cédant par le biais d’un article que nous proposons d’introduire dans la partie relative à la reprise de dette. Cependant, parfois, l’exécution ne pourra être obtenue et le contractant devra se suffire dans ce cas des sanctions d’inexécution. Une étude critique des nouveautés introduites par la réforme dans ce domaine nous permet d’affirmer qu’il faudrait maintenir intactes les sanctions en cas d’inexécution. Si nous avons trouvé que les sanctions de l’inexécution doivent demeurer intactes dans le COC, en revanche nous avons jugé essentiel de moderniser et réviser certains aspects des sanctions d’inexécution du contrat en vue de prendre en considération le facteur du temps. Afin de remédier à cette lacune, nous avons jugé essentiel en premier lieu d’introduire une différenciation textuelle entre la force majeure définitive et temporaire. En second lieu, nous avons suggéré l’introduction d’un article permettant de trouver une solution en cas de changement imprévisible des circonstances rendant l’exécution excessivement onéreuse pour l’une des parties. En dernier lieu, nous avons estimé crucial que le COC abandonne le caractère systématique de l’effet rétroactif de la résolution. En somme, nous sommes arrivés à la conclusion suivante : si le COC gagne à s’inspirer de la réforme française du contrat dans certains aspects, il ne doit pas s’en inspirer dans d’autres.
Keywords: Contrat; Contrats; Droit; Droit comparé; Droit français; Droit libanais; Liban

L'unité des opérations sur obligations - Bottin, Jean Baptiste (Université Côte d'Azur, 2025)
Un nouveau chapitre dédié aux opérations sur obligations a été introduit dans le Code civil à l'occasion de la réforme du droit des obligations de 2016. Chacune de ces opérations est prévue au sein d'une section propre, sans qu'aucun article introductif ne souligne leurs éventuelles différences ou points communs. Cette unité formelle serait-elle le signe d'une unité substantielle ? Certainement pas si l'on s'en tient à la summa divisio doctrinale opposant les opérations translatives (cession de créance et cession de dette) aux opérations constitutives (novation et délégation). Cependant, on peut remarquer que les effets normalement reconnus aux opérations appartenant à l'une de ces catégories peuvent être produits par les opérations appartenant à l'autre ; le critère de l'effet est donc défaillant. C'est pourquoi il est proposé de suivre une méthode tenant compte de l'objet de ces opérations. Si l'on postule que l'obligation est composée d'éléments dissociables (conception élémentaire), chacun d'eux (debitum et obligatio) pourra se voir appliquer un effet différent. Ainsi, toute opération sur obligations nommée par le Code civil emporte nécessairement la modification du rapport de contrainte (obligatio) et possiblement la transmission du rapport de contribution (debitum). C'est la preuve de l'unité de ces opérations.
Keywords: Assignment of claim; Assumption of debt; Cession de créance; Cession de dette; Delegation; Dettes; Délégation; Novation; Obligations; Obligations (droit)

Análisis jurídico y funcional del crédito documentario en un entorno digitalizado - Jiménez Jiménez, María Mercedes (Universidad de Sevilla, 2025)
El crédito documentario. también denominado en la literatura jurídica como documentary letter of credit, es un medio de pago, un instrumento de financiación y una garantía. Es una operación bancaria cuyo origen se encuentra en el receptum argentarii del Derecho Romano Clásico. Su desarrollo ha sido paralelo a la evolución de la economía, el comercio y la banca. Desde el siglo XIX, el crédito documentario es una institución de gran importancia en el comercio internacional. Se define como todo acuerdo a través del cual, el ordenante (importador) se obliga frente al beneficiario (exportador) a solicitar la emisión de un crédito documentario a su entidad bancaria o financiera (banco emisor), la cual llevará a cabo el pago, aceptación o negociación del mismo a favor del beneficiario, siempre que éste presente al banco emisor (u otra entidad bancaria o financiera designada) una determinada documentación y dicha entidad bancaria o financiera preste su conformidad. Entre sus rasgos principales podemos resaltar la pluralidad de partes que intervienen en su operativa -inicialmente tripartita-, su naturaleza jurídica compleja o los principios rectores que lo rigen como son los principios de independencia y de estricto cumplimiento. Consecuencia de estas características, el crédito documentario es una figura que ha suscitado múltiples debates doctrinales y jurisprudenciales. La ausencia de Ley que lo regula en gran parte de los Ordenamientos Jurídicos del mundo también ha conllevado su difícil tratamiento. Sin embargo, gracias a la Cámara de Comercio Internacional de París, el crédito documentario es una figura regulada por las Reglas y Usos uniformes relativos a los créditos documentarios (actualmente RUU nº 600 de 2007). Además de ello, los trabajos de UNCITRAL y UNIDROIT han aportado grandes avances en lo que al comercio internacional se refiere y, con ello, a nuestra institución. La naturaleza jurídica de las RUU ha sido también discutida por la doctrina y jurisprudencia. Nueva Lex Mercatoria, usos y costumbres o cláusulas contractuales son algunas de las tesis vertidas. En lo referente a la naturaleza jurídica del crédito documentario, se puede afirmar que estamos ante una pluralidad negocial, lo que implica que el crédito documentario esté conformado por una diversidad de contratos independientes entre sí, pero con un objetivo común. Es necesario determinar la naturaleza jurídica de cada una de las relaciones que lo componen. Diferentes han sido las tesis vertidas sobre cada una de estas relaciones. Sin embargo, las posturas mayoritarias han podido calificar la relación entre importador y exportador (contrato subyacente que, en puridad, no forma parte de la operativa del crédito documentario), la relación entre ordenante y banco emisor (contrato de comisión), la relación entre el beneficiario y banco emisor (promesa unilateral) o la relación entre entidades bancarias o financieras con el banco emisor (contrato de comisión). No es posible, consecuentemente, determinar la naturaleza jurídica del crédito documentario como contrato unitario. Los documentos que ha de presentar el beneficiario para hacer efectivo su derecho de cobro, aceptación negociación del crédito documentario pueden ser los que expresa y voluntariamente dispongan las partes. Sin embargo, las RUU nº 600 establecen los más utilizados en el comercio internacional. Estos son la factura comercial, la póliza de seguro y los documentos de transporte, siendo el conocimiento de embarque el más habitual. El examen de los documentos se rige por los principios rectores dispuestos. En la actualidad, tanto la presentación como el examen de los documentos puede realizarse digitalmente. Aunque no pueda hablarse de un verdadero crédito documentario electrónico, los avances tecnológicos han ayudado a modernizar esta institución. Con ello, no solo se minimizan los altos costes, sino que lo dotan de una agilidad en su operativa muy necesaria en el comercio internacional.

Desglobalización y Derecho Internacional. Virdzhiniya Petrova Georgieva - Mora, Iván Escoto (Jurídica Ibero. Revista Semestral del Departamento de Derecho de la Universidad Iberoamericana, 2025)

Impacto de las tecnologías emergentes en la confidencialidad y transparencia del arbitraje internacional - Pérez-Pacheco, Yaritza; Lee, Díckar Bonyuet (Jurídica Ibero. Revista Semestral del Departamento de Derecho de la Universidad Iberoamericana, 2025)
El arbitraje comercial internacional enfrenta el desafío de integrar tecnologías emergentes como la inteligencia artificial, el Big Data y el blockchain, sin comprometer sus principios fundamentales de confidencialidad y transparencia. Este artículo analiza, a partir de una revisión documental y comparativa, cómo el uso de estas tecnologías im-pacta la gestión de casos, el análisis predictivo y la ejecución de laudos, al tiempo que mejora la eficiencia y accesibilidad del arbitraje, pero también genera riesgos en materia de privacidad, ciberseguridad y protección de datos sensibles. Asimismo, se analizan los enfoques regulatorios adoptados en distintas jurisdicciones, incluyendo el Reglamento de la Unión Europea, el modelo flexible de Estados Unidos y las iniciativas tecnológi-cas de países asiáticos como China y Hong Kong. La investigación concluye que, para equilibrar la innovación y la protección de la información, es indispensable implementar protocolos globales y estándares éticos que garanticen un arbitraje confiable y seguro en entornos digitales. International commercial arbitration faces the challenge of integrating technologies such as artificial intelligence, Big Data, and blockchain, without undermining confidentiality and transparency. This article examines how these tools impact case management, predictive analysis, and the enforcement of awards, improving efficiency while also raising concerns about privacy and cybersecurity. Regulatory approaches are explored, from the European Union’s framework to the more flexible model of the United States and technological initiatives in Asia. The research concludes that it is essential to establish global and ethical standards to ensure a secure and reliable arbitration process in the digital era.
Keywords: Arbitrage; Arbitragem; Arbitraje internacional; Arbitral award enforcement; Arbitration; Confidentiality; Confidentialité; Ejecución de laudos arbitrales; Emerging technologies; International arbitration; International dispute resolution; Resolución internacional de disputas; Tecnologías emergentes; Transparence; Transparency

Transparency in Investor-State Arbitration Under USMCA - Petrova Georgieva, Virdzhiniya (Jurídica Ibero. Revista Semestral del Departamento de Derecho de la Universidad Iberoamericana, 2025)
The provisions of USMCA and their interpretation and application in the developing case law of international arbitral tribunals constituted under its investment chapter show a progressive move towards a higher transparency standard in the resolution of inves-tor-State disputes. The incorporation of most of the UNCITRAL Rules on Transparen-cy in USMCA Annex 14-D expanded the scope of NAFTA’s transparency rules. The entry into force of USMCA and the recent end of NAFTA’s “legacy claims” is to bring normative uniformity across the case law of arbitral tribunals on issues of procedural transparency. In addition, better access to arbitral orders and awards under USMCA will promote the quality of the decisions, as tribunals and parties will be able to lean on the experience of their predecessors. Las disposiciones del T-MEC y su aplicación en la jurisprudencia arbitral internacional muestran un avance hacia mayores estándares de transparencia en disputas inversionista-Estado. Al incorporar la mayoría de las Reglas de Transparencia de la CNUDMI en su Anexo 14-D, el T-MEC amplió el marco del TLCAN. La entrada en vigor del T-MEC y el fin de las “reclamaciones heredadas” del TLCAN promueven una mayor uniformidad normativa en torno a la transparencia procesal. Esta coherencia fortalecerá la aceptación del capítulo de inversión del T-MEC y aumentará la legitimidad del arbitraje de inversiones a nivel global.
Keywords: Arbitraje internacional de inversiones; Arbitrajes entre Inversionistas y Estados; CNUDMI; International Investment Arbitration; NAFTA; Procedural transparency; T-MEC; TLCAN; Transparencia procedimental; UNCITRAL Rules on Transparency; USMCA

La transparencia en el arbitraje internacional: avances y nuevos retos - Pollero, Marianela Bruno (Jurídica Ibero: Revista Semestral del Departamento de Derecho de la Universidad Iberoamericana, 2025)
Este artículo responde a la propuesta académica del Departamento de Derecho de la Uni-versidad Iberoamericana en conmemoración del 10.° aniversario de las normas de trans-parencia de la Comisión de las Naciones Unidas para el Derecho Mercantil (CNUDMI) y complementa la actividad académica realizada por la Universidad Iberoamericana, la Secretaría de Relaciones Exteriores de México y el Centro de Mediación y Arbitraje de la Cámara de Comercio de la Ciudad de México (CANACO), con el apoyo de la Secre-taría de la CNUDMI, en el marco del UNCITRAL LAC DAYS- México 2024. Durante esta actividad se organizaron tres mesas de debate integradas por desta-cados miembros de la comunidad arbitral, de la sociedad civil y del sector privado. La temática de estudio brindó desde México una visión sobre la confidencialidad vs. la transparencia, así como los avances y los retos de la transparencia en el arbitraje inter-nacional.
Keywords: Arbitrage international; Arbitragem Internacional; Arbitraje internacional; Arbitration; Transparence (droit); Transparencia

Reflexiones sobre el régimen de transparencia en el arbitraje comercial internacional - Rendón, Martha Angélica Alvarez (Jurídica Ibero. Revista Semestral del Departamento de Derecho de la Universidad Iberoamericana, 2025)
From an approach to the concepts of transparency, confidentiality, and privacy, this article examines the tension that may arise between these principles in international commercial arbitration. It also analyzes how arbitration rules address confidentiality and transparency, questioning whether a balance between the two has been achieved. Additionally, it reflects on the impact of public interest in promoting transparency in arbitral proceedings, considering whether the measures adopted are compatible with this type of arbitration. Desde un acercamiento a las nociones de transparencia, confidencialidad y privacidad, en este artículo se valora la tensión que puede existir entre dichos conceptos en el arbi-traje comercial internacional. Asimismo, se alude a algunos reglamentos de arbitraje que abordan la confidencialidad y la transparencia, parar mostrar si se alcanza un equilibrio entre los principios analizados. Además, se llama a reflexionar sobre el impacto del inte-rés público en la búsqueda de la transparencia en los procesos arbitrales, con la finalidad de abrir el debate sobre la compatibilidad de las medidas que se han adoptado en este rubro en el arbitraje comercial.
Keywords: Arbitrage; Arbitragem; Arbitraje comercial internacional; Arbitraje de inversión; Arbitration; Confidencialidad; Confidentiality; International commercial arbitration; Interés público; Investment arbitration; Privacidad; Privacy; Public interest; Transparence; Transparencia; Transparency

Le produit sportif durable : d'un droit des déchets à un droit de l'économie circulaire - Bermann, Clara (Université de Lille, 2025)
Cette thèse propose une lecture renouvelée du produit sportif durable, en croisant les exigences de circularité et de performance. En partant du droit des déchets, elle analyse les mécanismes de requalification permettant d’intégrer les produits usagés dans une économie circulaire, conciliant soutenabilité, innovation et responsabilités juridiques. L’étude s’organise autour du cycle de vie du produit, depuis l’écoconception jusqu’à sa fin d’usage. Elle met en lumière les leviers juridiques activables pour accompagner cette transformation : la responsabilité élargie du producteur, la traçabilité, le réemploi, la réparation, la valorisation matière, et l’intégration de matériaux recyclés. Elle interroge également l’adéquation du cadre normatif aux nouveaux modes d’usage, comme la location, la mutualisation ou la seconde main, caractéristiques de modèles plus sobres et partagés. En s’appuyant sur une méthodologie juridique rigoureuse et une expérience de terrain, la recherche propose les fondements d’un droit de l’économie circulaire appliqué au sport, à même d’encadrer la transition vers des systèmes durables. À travers l’analyse du produit sportif comme vecteur juridique, elle invite à repenser les catégories classiques du droit face aux défis environnementaux contemporains.
Annexes, 64 p. : https://pepite-depot.univ-lille.fr/LIBRE/EDSJPG/2025/2025ULILD007_annexes.pdf
Keywords: Articles de sport; Design durable; Droit des déchets; Déchets (élimination); Environnement (droit); Produit sportif durable; Responsabilité élargie du producteur; Écoconception; Économie circulaire; Économie de fonctionnalité

Organizational Identity for Cross-border Digital Trade: Achieving Technical and Legal Interoperability Within the Model Law on the Use and Cross-border Recognition of Identity Management and Trust Services (MLIT) Using the vLEI - Marin, Ivan; Castellani, Luca G. (United Nations Commission on International Trade, 2025)
Identity management is a cornerstone of digital trade and a core component of trust services, starting with electronic signatures. However, there is limited awareness of its legal and technical implications. The United Nations Commission on International Trade Law (UNCITRAL) has prepared a Model Law on the Use and Cross-border Recognition of Identity Management and Trust Services to provide uniform guidance on how to establish an enabling legal environment for identity management and trust services. The Global Legal Entity Identifier Foundation (GLEIF) has developed the Legal Entity Identifier (LEI) and its digital counterpart the verifiable LEI (vLEI) as universal solutions for a secure and cost-effective persistent business identifier. This paper illustrates how the MLIT and the vLEI may interact to provide legal and operational certainty to identification needs, thus fostering global economic growth.
Keywords: Digital cross-border trade; Digital trade; GLEIF; LEI; Legal entity digital identity; MLTR compliance; Trade facilitation; vLEI verifiable credential

Le Pouvoir de licencier : Étude sur les transformations du pouvoir de l’employeur - Rascle, Marie (Université Lumière Lyon 2, 2025)
Bien que le pouvoir de l’employeur soit une référence majeure du droit du travail, il en va autrement du pouvoir de licencier. Lorsque celui-ci est étudié, c’est principalement sous l’angle d’un pouvoir de représentation, les auteurs s’attachant alors à déterminer l’identité de celui qui, dans l’entreprise, est habilité à exercer un tel pouvoir. Il apparaît pourtant qu’une lecture plus ambitieuse du pouvoir de licencier est nécessaire. Les transformations du droit du licenciement observées depuis une quinzaine d’années imposent une telle réflexion. Ainsi a-t-il été choisi de ne pas réduire le pouvoir de licencier à une simple question de représentation, mais de l’envisager comme « un pouvoir en action », c’est-à-dire de s’intéresser à la manière dont les règles du droit du travail le saisissent, le façonnent, l’encadrent ou le limitent. À l’heure où le législateur semble plus enclin à sécuriser les conditions de la rupture contractuelle ou à promouvoir les ruptures négociées du contrat de travail, qu’à regarder l’acte de rupture de ce contrat pour ce qu’il est, c’est-à-dire un acte de pouvoir, l’on ne peut manquer de s’interroger sur une question aussi redoutable que nécessaire : que reste-t-il du pouvoir de licencier ?
Keywords: Contrat; Employeur; Employé; Licenciement; Pouvoir

Les ADR comme mécanismes de gestion des différends sociaux et environnementaux dans les grands projets miniers au Cameroun - Abane Engolo, Patrick Edgard; Abomo Efoua, Christiane (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
Les grands projets miniers sont porteurs d’enjeux économiques, sociaux, et environnementaux au Cameroun. L’exploitation minière est dans ce sens juridiquement encadrée par le Code minier. Elle implique autant d’opportunités que de risques susceptibles d’engendrer des différends sociaux et environnementaux. La gestion de ces différends implique la convocation des Alternative Dispute Resolution (ADR), qui constituent une voie d’accès à la résolution des litiges aussi importante que la saisine du juge. Cependant, l’apparente libéralité de ces ADR suscite des inquiétudes quant à l’efficacité de leur mise en œuvre et leur force juridique. Il en ressort que, bien que ces mécanismes soient consacrés, leur encadrement juridique nécessite d’être renforcé. Major mining projects pose economic, social and environmental challenges in Cameroon. Mining operations are therefore legally regulated by the Mining Code. They present both opportunities and risks that can lead to social and environmental disputes. Managing these disputes therefore requires the convening of Alternative Dispute Resolution (ADR) mechanisms, which constitute a means of accessing justice as important as going to court. However, the apparent liberality of these ADR mechanisms raises concerns about the effectiveness of their implementation and their legal force. It appears that although these mechanisms are established, their legal framework needs to be strengthened.
Keywords: Arbitrage; Arbitration; Conciliation; Mediation; Médiation; Parties prenantes; Stakeholders

Perspectives internes des entreprises minières en lien avec les obligations de consultation des peuples autochtones : un enjeu de gouvernance - Boirin, Zoé (Université Paris 1 ; Université d'Ottawa, 2025)
Le cadre politico-juridique canadien qui régit la consultation des peuples autochtones engendre une situation de « régulation négociée » entre les entreprises minières et ces peuples. Autrement dit, les pratiques de consultation sont élaborées à travers un processus de négociation entre les entreprises et les communautés autochtones. En raison, notamment, de l'encadrement juridique des activités minières, encore fondé sur le principe du free entry, les entreprises minières occupent une place prépondérante dans la manière dont les perspectives et les intérêts des peuples autochtones sont intégrés dans le développement minier. Le principal enjeu de cette régulation négociée réside dans l’asymétrie des rapports de force entre les différents acteurs, souvent défavorable aux peuples autochtones. Dans ce contexte, cette thèse s'inscrit dans le constat qu'il existe peu de recherches sur les pratiques internes des entreprises minières en matière de consultation des peuples autochtones. Adoptant une approche sociojuridique, nous avons mené une recherche empirique fondée sur deux études de cas : la première auprès d’une entreprise opérant à l’échelle provinciale/territoriale, et la seconde au sein de la filiale d’une multinationale. Les résultats issus de ces études de cas nous ont permis d’identifier des points de convergence et de divergence entre les deux entreprises, confirmant ainsi la diversité des acteurs au sein de l’industrie et des influences qui les façonnent. Ces résultats nourrissent également la réflexion sur la régulation des pratiques de consultation, notamment en ce qui concerne l’enjeu de l’asymétrie des rapports de force. The Canadian politico-legal framework governing the consultation of Indigenous peoples creates a situation of "negotiated regulation" between mining companies and these peoples. In other words, consultation practices are developed through a negotiation process between companies and Indigenous communities. This situation is largely influenced by the legal framework surrounding mining activities, which still relies on the principle of free entry, giving mining companies a dominant role in determining how the perspectives and interests of Indigenous peoples are integrated into mining development. The primary issue of this negotiated regulation lies in the asymmetry of power dynamics between the various actors, often to the detriment of Indigenous peoples. In this context, this thesis arises from the observation that there is limited research on how mining companies internally develop their consultation practices with Indigenous peoples. Adopting a socio-legal approach, we conducted empirical research based on two case studies: the first with a company operating at the provincial/territorial level, and the second within the subsidiary of a multinational corporation. The findings from these case studies allowed us to identify points of convergence and divergence between the two companies, thus confirming the diversity of actors within the industry and the various influences shaping them. These results also contribute to the
Issue: 2025PA01D025
Keywords: Consultation; Corporations; Entreprises; Indigenous peoples; Mining projects; Peuples autochtones; Projets miniers; Sociologie du droit; Sociology of law

La douane malienne : enjeux de la régionalisation - Coulibaly, Youssouf Z; Coulibaly, Alou (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
La douane est une administration chargée d’établir et de percevoir les droits imposés sur les marchandises à la sortie ou à l’entrée du territoire du pays. Au Mali, le libéralisme économique de la deuxième république a engendré des reformes tant sur le plan organisationnel des douanes. L’assouplissement des procédures douanières et les facilités particulières dans l’octroi des régimes économiques matérialisent ce changement. Force est de constate sur le plan légal et réglementaire, on assista d’une part à la relecture du Code des Douanes et d’autre part à la reforme tarifaire. Ainsi dans cet article nous article, nous faisons une analyse critique des textes réglementaires en vigueur afin de proposer des pistes de solution pour une douane plus efficace et plus performante.
Keywords: Douane; Harmonisation; Régionalisation; Tarif; Taxe

An Assessment of Concurrent Jurisdiction and Claim of Ownership of Trademarks under OAPI Legislation - Dashaco Akuriah, Nelson (International Multilingual Journal of Science and Technology, 2025)
Trademarks are economic tools that aid businesses to communicate with their customers and capture a vast section of the population. Trademarks are only useful when used efficiently in the course of trade, meaning the higher the reputation of the mark, the more consumers want to associate themselves to the products or services the mark is affixed upon. This study examines the criteria to own a trademark and how ownership claims are handled between the African Organisation of Intellectual property as known by its French acronym OAPI and the competent domestic courts found at the level of Member States which has become a breathing ground for confusion in the resolution of disputes. Due to both bodies having concurrent jurisdiction in dispute resolution, the cost has become unbearable on trademark owners or beneficiaries of an exclusive license of exploitation, coupled with inconsistency in judgements from the two structures. The article highlights some key improvements expanding trademark subject matter and provides information on how the two institutions cited above handle matters of jurisdiction based on case law. The article also brings to the limelight how the OAPI administrative litigation bodies can collaborate with the competent domestic courts to arrive at clear and concise decisions. In conclusion the paper provides some recommendations on bridging the gap between both jurisdictions in order to attain the objectives of all parties involved.
Keywords: Concurrent Jurisdiction; Intellectual property; Litigation; Ownership; Registration; Trademarks; Use

L’impact de l’importation sur l’économie malienne - Dolo, Yamadou; Dolo, Anidjou; Coulibaly, Alou (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
Le Mali importe de nombreux produits en raison du manque de production locale et de la faible compétitivité de certaines industries maliennes. Cette dépendance excessive aux importations affaiblit l'économie nationale et limite les opportunités pour les secteurs agricoles, industriels et commerciaux du pays. Pour remédier à ces problèmes, l’étude recommande de stimuler la production locale, de soutenir les industries et les agriculteurs maliens, et de mettre en place des politiques commerciales et industrielles favorables à la compétitivité des produits nationaux sur le marché international. Ces mesures permettraient de limiter la dépendance aux importations étrangères et de renforcer ainsi l'économie malienne. Ainsi l'objectif que vise cette étude est d'analyser les conséquences économiques et sociales enfin de proposer des solutions idoines. Mali imports many products due to a lack of local production and the low competitiveness of some Malian industries. This excessive dependence on imports weakens the national economy and limits opportunities for the country's agricultural, industrial, and commercial sectors. To address these problems, the study recommends stimulating local production, supporting Malian industries and farmers, and implementing trade and industrial policies that promote the competitiveness of domestic products on the international market. These measures would help limit dependence on foreign imports and thus strengthen the Malian economy. The objective of this study is to analyze the economic and social consequences and propose appropriate solutions.
Keywords: Dependence; Dépendance; Economie; Economy; Import; Import-export; Importation; Taxation

L’apport du juge à l’autorité de la chose jugée de la sentence arbitrale en contentieux du sport au Cameroun - Mandeng, Naomie Audrey (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
Par le truchement de la résolution des litiges nés du mouvement et des acteurs sportifs, le juge statuant dans le contentieux sportif se préoccupe également de l’applicabilité de ses décisions juridictionnelles. Sauf que l’on ne devrait pas généraliser le poids de celle-ci sur tous les cas rendus par le juge sportif. Se voulant intelligible ce dernier l’acuité de l’autorité de chose jugée face à certains incidents de procédure. Cette négation est davantage entretenue par des modalités spécifiques. Par ailleurs, dans son énoncé, le juge sportif prescrit de se référer au dispositif pour dériver prosaïquement les termes de l’autorité de chose jugée et la force exécutoire de la sentence arbitrale.
Keywords: Autorité de la chose jugée; Cameroun; Juge; Sentence arbitrale; Sport

Le potentiel de la propriété intellectuelle pour le développement en Afrique : le cas du droit des marques dans les pays membres de l'OAPI - Massala, Kélicia (Université de Montréal, 2025)
Ce mémoire explore le potentiel du droit des marques comme levier stratégique de développement socio-économique dans les États membres de l’OAPI. En s’appuyant sur une analyse rigoureuse du système juridique harmonisé issu de l’Accord de Bangui, il met en lumière les forces et les limites du cadre actuel, à l’aune des défis structurels, institutionnels et économiques qui caractérisent la région. À travers une approche multidisciplinaire, combinant analyse doctrinale, données empiriques et entretiens de terrain, ce travail examine les mécanismes concrets de valorisation des marques locales, les disparités entre titulaires nationaux et étrangers, ainsi que les stratégies d’accompagnement en matière de sensibilisation, de formation et d’accès au système. Il propose également des pistes de réforme et des recommandations pour renforcer l’écosystème de la propriété intellectuelle au service de l’innovation, de la compétitivité des PME et de la protection des savoirs locaux. En filigrane, ce mémoire interroge la capacité des droits de propriété intellectuelle à contribuer de manière durable à l’émergence économique du continent africain.
Keywords: Développement économique; Economic Development; Innovation; Intellectual property; Legal Reforms; Marques; OAPI; PME; Propriedade intelectual; Propriété intellectuelle; Réformes juridiques; SMEs; Trademarks; Valorisation des savoirs locaux; Valorization of Local Knowledge

Le droit douanier camerounais à l’ère du terrorisme - Onana, Wafai (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
Le droit douanier camerounais est traditionnellement tourné vers les missions de perception des recettes et de la protection du tissu économique local. Avec la récente apparition du terrorisme, ce droit doit désormais conjuguer avec la menace sécuritaire ; ce qui suppose une certaine mutation. Ainsi, le changement subi par le droit douanier du fait de sa rencontre avec le phénomène terroriste est tout d’abord théorique ; puisqu’il faut aménager le cadre théorique d’accueil au plan douanier de la dimension sécuritaire. Ce changement est aussi opérationnel en ce sens qu’il induit l’appropriation et l’exercice de la compétence sécuritaire, indicateur du passage d’une prérogative subsidiaire d’aide à la lutte contre l’insécurité à une véritable mission sécuritaire douanière. Cameroonian customs law is traditionally focused on the missions of revenue collection and protection of the local economy. With the recent appearance of terrorism, it must now take into account the security threat, which implies a certain mutation. Thus, the change that customs law must undergo due to the terrorist phenomenon is first of all theoretical, given that it’s necessary to adapt the theoretical framework of reception of the security dimension. This change is also operational in the sense that it induces the appropriation and the effective exercise of security competence, as indicator of the transition from a subsidiary prerogative of aid in the fight against insecurity to a true security mission.
Keywords: Custom law; Droit douanier; Mandat sécuritaire; Protection; Security mandate; Terrorism; Terrorisme

A comparative statutory analysis of the causes of bank failures in Zimbabwe - Tsaura, Oscar (North-West University, 2025)
Zimbabwean financial sector has experienced significant periods of financial distress as depicted by numerous bank failures since 1980. Bank failure occurs when a financial institution experiences significant financial distress, rendering it incapable of fulfilling its obligations to depositors, shareholders and other stakeholders. In other words, bank failure is when a financial institution undergoes substantial financial distress rendering it unable to meet its obligations as they become due. In this thesis, the researcher adopted the definition of bank failure which refers to a situation where a bank is in financial distress and is recapitalised either by the central bank or a strategic investor, acquired by another institution, surrenders its license or the license is suspended, or it closes its operations altogether. This thesis reveals that in Zimbabwe bank failures can be attributed to various factors including the failure of regulatory and supervisory systems to detect irregularities in the operations of banking institutions. In addition, poor corporate governance practices such as inadequate oversight, inexperienced management, undue influence by dominant shareholders, nonperforming loans, excessive risk-taking, abusive related party transactions and noncompliance with laws are commonly cited as causes of bank failures in Zimbabwe. Bank failures often pose negative implications to the banking sector and banking stakeholders such as depositors and investors. This owes to the fact that banks serve as intermediaries that facilitate the avenues for deposits and extend credit services to individuals and the production sector of the economy. It is submitted that the proper functioning of banks requires effective and adequate regulatory supervision. Failure to provide robust and effective regulation of banks could lead to bank failures. This thesis presents a comparative analysis of the banking statutory framework of Zimbabwe and those of the UK and South Africa to determine if the banking laws in Zimbabwe are robust enough to prevent bank failures. The thesis reveals that the banking statutory framework in Zimbabwe is not robust enough to curb bank failures in times of stress because it lacks effective regulatory oversight. This thesis further reveals that poor banking regulation, inconsistent enforcement, weak regulatory insolvency procedures, and inadequate supervision framework are some of the weaknesses in the current banking statutory framework which needs to be rectified in order to combat bank failures effectively in Zimbabwe. The Banking Act does not fully incorporate the international best standards on bank supervision to prevent bank failures. Consequently, the banking statutory framework in Zimbabwe does not comprehensively and effectively provide for the prevention of bank failures like those of the UK and South Africa. The robustness of the banking statutory framework is in providing adequate and effective regulatory provisions and enforcement mechanisms that curb bank failures in Zimbabwe. The researcher proposes the adoption of a new model, the Zimbabwean twin peaks model, comprising the Zimbabwean Prudential Regulatory Authority and the Zimbabwean Financial Sector Conduct Authority. It is argued that if the adoption of the twin peaks model is considered and robustly implemented, it can prevent the causes of bank failures in Zimbabwe.
Keywords: Bank failure; Banking legislation; Banking statutory framework; Banks; Curatorship; Financial regulations; Financial stability; Fraud; Money laundering; Political instability; Zimbabwe

Libres propos sur la volonté des parties dans l’arbitrage OHADA - Waham Mayegle, Joseph Laurent (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2025)
L’arbitrage est une réalité en Afrique depuis longtemps déjà. C’est avec l’avènement de l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires que ce domaine a pu avoir un dispositif bien structuré. Etant un mode alternatif de règlement des différends, l’arbitrage a pour fondement prépondérant la volonté des parties qui y font recours. Il s’est donc posé en filigrane la question de la portée de la volonté des parties à l’arbitrage OHADA. Le constat est que tout comme en matière contractuelle, elle est un élément indispensable à l’efficacité de ce mode de résolution des litiges. C’est la raison pour laquelle sa portée est traduite par une prégnance avérée, et un recul tout de même constaté.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Volonté des parties

La seguridad jurídica como garantía del debido proceso en el cumplimiento de las resoluciones judiciales en los procedimientos voluntario, sumario y ordinario - Muñoz, Nohely Alejandra Zambrano; Pacheco, Marco Antonio Acosta; Reyes, Eloísa Carolina Solís; Parra, José Antonio Velez (Polo del Conocimiento, 2025)
El estudio de la seguridad jurídica como garantía del debido proceso en el cumplimiento de las resoluciones judiciales en los procedimientos voluntario, sumario y ordinario tuvo como objetivo analizar la incidencia de la seguridad jurídica en el cumplimiento de las resoluciones judiciales en los procedimientos voluntario, sumario y ordinario como garantía de los procesos judiciales. Para lo cual, se utilizó una investigación de tipo desriptiva y de campo, con un enfoque mixto y el método hermenéutico; para la recopilación de información primaria se aplicó una encuesta y entrevista a los juristas en libre ejercicio de su profesión. Se obtuvo que que todas las personas tienen derecho al debido proceso, el cual está ligado estrechamente al derecho a la seguridad jurídica ya que, este segundo implica el conocimiento y certeza del derecho positivo, la confianza de la sociedad en las instituciones del Estado y en el orden jurídico y la existencia de mecanismos jurídicos frente a las afectaciones que pudieren existir. Se concluyó que la seguridad jurídica como garantía del debido proceso en el cumplimiento de las resoluciones judiciales es esencial para mantener la confianza en el sistema legal y para proteger los derechos fundamentales de las personas involucradas en cualquier procedimiento legal, ya sea voluntario, sumario u ordinario.
Keywords: Debido proceso; Due process; Judicial decisions; Legal certainty; Ordinary procedure; Procedimiento ordinario; Procedimiento sumario; Procedimiento voluntario; Resoluciones judiciales; Seguridad jurídica; Summary procedure; Voluntary procedure

Les compétences juridiques des États face à la criminalité en mer - Abalo, Abla Mathilde (Université de Strasbourg, 2025)
Dans la recherche d’un équilibre entre la liberté de navigation et la souveraineté territoriale, le droit de la mer a réparti les compétences entre les États - État côtier, État du port, État du pavillon et État tiers - suivant le zonage des espaces maritimes. Cette délimitation constitue le socle juridique sur lequel reposent les actions de l’État en mer contre la criminalité. L’étude interroge donc la capacité des règles établies à offrir aux États des réponses suffisantes et adaptées pour faire face à ce fléau. Elle montre que leurs compétences normatives et d’exécution sont globalement limitées. Le cadre juridique existant n’a au demeurant d’efficacité qu’en étant renforcé par une action globale. Et pour la consolider, la thèse explore la juridictionnalisation de la lutte contre la criminalité en mer. Cette approche est prometteuse, car la pratique du TIDM se développe et sa capacité à traiter la diversité des situations en mer se confirme progressivement. In seeking a balance between freedom of navigation and territorial sovereignty, maritime law has divided jurisdiction among States – coastal States, port States, flag States and third States – according to the zoning of maritime areas. This delimitation forms the legal basis for State action at sea against crime. The study therefore questions the ability of the established rules to provide states with sufficient and appropriate responses to this scourge. It shows that their normative and enforcement powers are generally limited. The existing legal framework can only be effective if it is reinforced by comprehensive action. To consolidate it, the thesis explores the judicialization of the fight against crime at sea. This approach is promising, as the practice of the ITLOS is developing and its ability to deal with the diversity of situations at sea is gradually being confirmed.
Keywords: Action de l'État en mer; Activités illicites; Compétence; Criminalité en mer; Criminalité maritime; Droit maritime; Police en mer; Sécurité maritime; État côtier; État du pavillon; État du port

From trustworthy AI to technical standards : The distinctive European approach to artificial intelligence regulation - Gornet, Mélanie (Institut polytechnique de Paris, 2025)
L'Europe a été à l'avant-garde de l'éthique de l'intelligence artificielle (IA), en élaborant des chartes et des principes non contraignants sur l'IA « digne de confiance ». Le terme « digne de confiance » est utilisé par l'Europe pour désigner les systèmes d'IA qui sont « éthiques », « légaux » et « techniquement robustes ». L'Europe a complété ces principes non contraignants par un texte de loi sur l'IA, connu sous le nom de règlement sur l'IA, ou AI Act. Le règlement sur l'IA est l'un des premiers cadres légaux au monde à réglementer les systèmes d'IA dans différents secteurs et cas d'utilisation, en mettant l'accent sur la sécurité et la protection des droits fondamentaux. Pour les questions opérationnelles, le règlement sur l'IA s'appuie principalement sur des normes techniques en cours d'élaboration. L'approche européenne combine donc trois niveaux d'instruments réglementaires : les chartes éthiques de l'IA, le règlement sur l'IA et les normes techniques.L'approche par la normalisation est traditionnelle dans le domaine de la sécurité des produits, mais dans le règlement sur l'IA, les normes sont également censées répondre aux préoccupations en matière de droits fondamentaux. Pour éviter de faire des choix normatifs difficiles, les organismes de normalisation jouent la carte de la sécurité en élaborant des normes qui restent à un niveau élevé. De plus, dans le cadre du règlement sur l'IA, la responsabilité de l'élaboration des normes techniques est déléguée à des organismes de normalisation privés, où les grandes entreprises multinationales sont surreprésentées et exercent une influence considérable. Ces normes sont également généralement payantes, bien que la situation puisse évoluer dans les années à venir après une récente jurisprudence de la Cour de justice de l'Union européenne. Les experts en normalisation sont donc sous pression pour fournir des normes à temps et de bonne qualité. Europe has been at the forefront of Artificial Intelligence (AI) ethics, developing non-binding charters and principles on "trustworthy'' AI. The term "trustworthiness'' is used by Europe to designate AI systems that are "ethical'', "legal'' and "technically robust''. Europe has supplemented these non-binding principles with a binding regulation on AI, known as the AI Act. The AI Act is one of the world's first comprehensive frameworks for regulating AI systems across different industries and use cases, focusing on safety and protection of fundamental rights. The AI Act relies, for operational questions, mostly on technical standards that are in the course of development. The European approach thus combines three layers of regulatory instruments: AI ethics charters, the AI Act and technical standards.The standardisation approach is traditional in product safety, but under the AI Act, standards are also expected to address fundamental rights concerns. To avoid making hard normative choices, standardisation organisations are playing it safe, developing standards which remain at a high-level. Moreover, under the AI Act, the responsibility for developing technical standards is delegated to private standardisation bodies, where large multinational companies are over-represented and hold significant influence. These standards are also often locked behind paywalls, although the situation may evolve in the coming years after a recent case law from the Court of Justice of the European Union. Standardisation experts therefore face pressures to deliver standards on time and of good quality.
Keywords: AI Act; Apprentissage machine; Artificial Intelligence; Ethics; Inteligência artificial; Intelligence Artificielle; Intelligence artificielle; Machine learning; Normes techniques; Regulation; Règlement IA; Régulation; Technical standards; Éthique

Les connaissements électroniques - Stevens, Frank (Droit Maritime Français, 2025)
Bien que le connaissement électronique semble offrir des avantages, l’industrie hésite toujours à l’utiliser. L’absence de cadre légal expliquerait cette prudence des praticiens. Aussi, cette contribution vise à analyser précisément la fonction de titre négociable du connaissement pour déterminer ce que cela implique pour le législateur désireux de réglementer l’utilisation des connaissements électroniques. Le r ôle que peut jouer la technique de la « blockchain » est également analysé.

L’œuvre libre : essai d'analyse contractuelle - Chevallier, Adélaïde (Université de Bordeaux, 2025)
L’oeuvre libre, aussi connue sous le nom d’open source, est une création protégée par le droit d’auteur, mais dont l’exploitation est ouverte à tous. Si l’expression reste à ce jour peu connue du grand public, les oeuvres libres sont désormais un incontournable des pratiques quotidiennes, en attestent le succès de l’encyclopédie en ligne Wikipédia et l’attrait croissant pour les logiciels libres tels Linux, OpenOffice ou la plateforme Moodle. Malgré son essor, le phénomène du libre demeure juridiquement peu, voire mal, appréhendé. De surcroît, sa licéité fait régulièrement l’objet de contestations doctrinales, l’oeuvre libre s’inscrivant à rebours des règles traditionnelles du droit français, selon lesquelles les biens sont intangibles, non numériques et réservés à l’usage exclusif de leur titulaire. La finalité de l’étude consiste dès lors à démontrer qu’en dépit de son caractère disruptif, l’oeuvre libre peut en l’état intégrer l’ordre juridique français au moyen d’une analyse contractuelle. The concept of the “free cultural work,” also referred to as open source, designates a creation protected by copyright yet made available for use by all. While the expression remains relatively unfamiliar to the general public, free cultural works have become indispensable in contemporary practice, as illustrated by the success of the online encyclopedia Wikipedia and the growing appeal of free software such as Linux, OpenOffice, and the Moodle platform. Notwithstanding this expansion, the legal phenomenon of free cultural works continues to be only partially, if not inadequately, addressed. Furthermore, its legitimacy is the subject of recurrent doctrinal debate, insofar as the free cultural work stands in contrast to the traditional principles of French law, according to which property is tangible, non-digital, and reserved for the exclusive use of its owner. The purpose of this study is therefore to demonstrate that, despite its disruptive character, the free cultural work may, in its current form, be accommodated within the French legal order through contractual analysis.
Keywords: Contract law; Contrat; Copyright; Droit d'auteur; Free cultural works; Free license; Free software; Intellectual property; Licence libre; Logiciel libre; Oeuvre libre; Open source; Propriété intellectuelle

Promoting Treaties in Nigeria and Operationalising the Singapore Convention on Mediation - Okoli, Pontian (African Journal of Legal Studies, 2025)
In Nigeria, the United Nations Convention on International Settlement Agreements Resulting from Mediation (2018) has entered into force. This Convention was incorporated or domesticated by referring to it in the Arbitration and Mediation Act (2023), but statutes are often dedicated to the domestication of treaties. There is no consensus on the most pragmatic way(s) to facilitate Nigerian treaty engagement. This article examines the Nigerian legal regime on treaties and explores the extent to which the regime can be maximised considering the Vienna Convention on the Law of Treaties (1969). A case is made for a principled basis to underpin the domestication of treaties that facilitate international business, including dispute resolution treaties. This analytical basis should enable legislative flexibility already woven into the overarching legal regime. The article articulates how such flexibility can be used to promote the operationalisation of relevant treaties using the Arbitration and Mediation Act as a paradigm.
Keywords: Good faith; International commercial mediation; Legislative flexibility; Singapore Convention; Treaties; Vienna Convention

International Arbitration: Impact on Global Economy - Jahan, Bushrat (International Journal of Innovation and Applied Studies, 2025)
The significant increase in the development of world economy over the last few decades have been experienced a considerable increase in the number of commercial disputes. When there is any business and dealings with contracts the question of dispute must be happened. But all of the parties actually want to run their business well and smoothly. In recent world a massive part of global economy depends on the trans-border business. But disputes in such business dealings sometimes can be the reasons to become risk the inter-relation of those parties. Which can affect the global economy as a whole. Comparing to the disputes inside domestic entities the trans-border or international business disputes can arise as bigger problem because of different jurisdictions, diverse legal systems and tradition. International Court of Justice (ICJ) already has the jurisdiction to try all the international civil suits but Alternative Dispute Resolution (ADR) mechanism also considered as a viable alternative to resolve the dispute over the court. The international arbitration arises as a way of alternative dispute resolution mechanism which upraise benefits both of the parties and maintain the confidentiality. In this paper details of international arbitration and the broader impact of this mechanism in the global business economy will be focused. The legal status and the implementation process of international arbitration also be the discussing point of this paper.
Keywords: Business economy; Enforcement of awards; Globalization; International Arbitration

L'amélioration de l'accès à la justice au Bénin dans le domaine commercial et foncier : comment les modes alternatifs de règlement des conflits et la technologie peuvent être mis à contribution ? - Agoïnon, Fifamè Danielle Esperancia (Université de Montréal, 2025)
En dépit de l'importance cruciale de la justice au sein de notre société, il est manifeste que le système judiciaire béninois présente d'importants défis en matière d'accessibilité, d'efficacité et de confiance publique. Les coûts de la justice, la perte de contrôle des problèmes, les délais d’attente avant procès, la structure labyrinthique des tribunaux, l'impossibilité de se représenter seul, ainsi que le caractère inhospitalier des tribunaux constituent des indicateurs d'un système judiciaire défaillant. En effet, des limitations dans l'accès à la justice alimentent la méfiance des citoyens à l'égard du système judiciaire étatique. Dans un souci de célérité et d'efficacité de la justice, un vent de généralisation des modes alternatifs de règlement des conflits et de recours des technologies souffle sur les procédures judiciaires en général et sur les procédures civiles et commerciales en particulier. S’inscrivant dans cette logique, la loi n° 2020-08 du 23 Avril 2020 portant modernisation de la justice en République du Bénin n’a pas manqué de faire faire une place aux modes alternatifs de règlement des conflits. Elle met également un accent sur la dématérialisation progressive des procédures judiciaires concernant la saisine des juridictions, le suivi des procédures et le paiement électronique des frais afférents. Cependant, malgré ces mesures à encourager, les juridictions, au risque de rompre, ploient toujours devant les litiges fonciers et commerciaux. La présente étude a pour objet d'analyser les forces et les faiblesses du système judicaire béninois et vérifier si la modernisation des modes alternatifs de règlement des différends et l’intégration de la technologie dans les processus de résolution des différends peuvent être un vecteur de l’accès à la justice au Bénin. Despite the crucial importance of justice in our society, it is clear that the Beninese justice system presents significant challenges in terms of accessibility, efficiency and public trust. The costs of justice, the loss of control of problems, pre-trial waiting times, the labyrinthine structure of the courts, the inability to represent the costs of justice, the loss of control of problems, pre-trial waiting times, the labyrinthine structure of the courts, the inability to represent oneself, as well as the inhospitable nature of the courts are indicators of a broken justice system. Indeed, limitations in access to justice fuel citizens' mistrust of the state justice system. In the interests of speed and efficiency of justice, a wind of generalization of alternative methods of dispute resolution and recourse of technologies is blowing through judicial procedures in general and civil and commercial procedures in particular. In line with this logic, Law No. 2020-08 of 23 April 2020 on the modernization of justice in the Republic of Benin did not fail to make room for alternative methods of conflict resolution. It also emphasizes the gradual dematerialization of judicial procedures concerning the referral of cases to the courts, the monitoring of procedures and the electronic payment of related costs. However, despite these measures to be encouraged, the courts, at the risk of breaking down, are still bending before land and commercial disputes. The purpose of this study is to analyze the strengths and weaknesses of the Beninese judicial system and to verify whether the modernization of alternative dispute resolution methods and the integration of technology into dispute resolution processes can be a vector of access to justice in Benin.
Keywords: ACCESS TO JUSTICE; ADR; Accès à la justice; Business; Bénin; Commercial; Différend; Dispute; Foncier; Information; Land; MARD; Technologie; Technology

Le droit à l’alimentation : un droit fondamental au cœur des inégalités sociales et économiques en Afrique de l'Ouest - Berthe, Baba (Afrilex : Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2025)
Le droit à l’alimentation est un droit fondamental inscrit dans le cadre juridique international, notamment à travers le Pacte international relatif aux droits économiques, sociaux et culturels. Cet article explore la manière dont ce droit est souvent contourné par des inégalités socio-économiques, des conflits armés et les effets du changement climatique, laissant des millions de personnes dans l’insécurité alimentaire. En analysant les politiques publiques, l’article met en évidence les lacunes et les réussites des efforts déployés par différents pays pour garantir à leur citoyens l’accès à une alimentation suffisante et de qualité. Des initiatives menées par des ONG et des projets communautaires démontrent qu’il est possible de lutter contre la faim et de promouvoir la sécurité alimentaire, mais elles nécessitent un soutien politique et financier soutenu. En conclusion, cet article souligne l’urgence de renforcer les mécanismes de protection du droit à l’alimentation face aux crises alimentaires croissantes et plaide pour une action concertée afin de surmonter ces défis futurs. Garantir le droit à l’alimentation n’est pas seulement une démarche juridique, mais aussi un impératif moral et économique pour le développement durable. The right to food is a fundamental right enshrined in the international legal framework, notably through the International Covenant on Economic, Social and Cultural Rights. This article explores how this right is often circumvented by socio-economic inequalities, armed conflicts and the effects of climate change, leaving millions of people food insecure. By analysing public policies, the article highlights the gaps and successes of efforts made by different countries to ensure access to sufficient and nutritious food. Initiatives led by NGOs and community projects demonstrate that it is possible to combat hunger and promote food security, but they require sustained political and financial support. In conclusion, this article highlights the urgency of strengthening the protection mechanisms of the right to food in the face of growing food crises and calls for concerted action to overcome future challenges. Ensuring the right to food is not only a matter of social justice, but also a moral and economic imperative for sustainable development.
Keywords: Droit fondamental; Food security; Fundamental right; Inequalities; Inégalités; Nutrition; Politiques publiques; Public policies; Sécurité alimentaire

Le secret professionnel à l’ère de l’externalisation des services en droit ivoirien - Coulibaly, Dogodana (Afrilex : Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2025)
Le secret professionnel, qui est un moyen de protection de la vie privée, ne parvient pas à assurer complètement sa fonction dans les opérations d’externalisation des services. Premièrement, la pratique d’externalisation révèle au prestataire de services d’externalisation les données à caractère personnel des personnes qui sont en relation d’affaires avec le professionnel qui y a recours. Aussi, dans l’exécution de sa mission, le prestataire découvre une infinité de données sensibles des partenaires et clients de son cocontractant. L’externalisation consacre donc la divulgation des informations couvertes par le secret professionnel sans l’accord préalable de leurs titulaires. Deuxièmement, en dépit de cette immixtion dans la sphère privée de leur vie, les victimes de cette pratique ne sont pas sûres d’engager avec succès ni la responsabilité civile ni la responsabilité pénale des auteurs de cette divulgation. Cela dit, l’externalisation qui est une exigence de l’économie moderne n’est pas à proscrire ; car elle peut se faire dans le respect du droit à la protection de la vie privée de tous. À cette fin, tous ceux qui sont intéressés par cette pratique, à l’instar des clients et partenaires du professionnel qui externalise son activité, doivent préalablement et valablement consentir à l’opération d’externalisation. Professional secrecy, which is a means of protecting privacy, fails to fully perform its function in outsourcing operations. First of all, the outsourcing practice discloses to the outsourcing service provider the personal data of all persons who have a business relationship with the trader using it. Also, in the execution of its mission, the service provider discovers a host of sensitive data of the partners and customers of its co-contractor. Outsourcing therefore enshrines the disclosure of information covered by professional secrecy without the prior consent of the holders of that information. Secondly, despite this interference in the private sphere of their lives, the victims of this practice are not sure whether to successfully engage either civil or criminal liability of the perpetrators of this violation. That said, outsourcing, which is a requirement of the modern economy, is not to be avoided; because it can be done while respecting the right to privacy of all. To this end, all those who are interested in this practice, like the customers and partners of the professional who outsources his activity, must first and validly consent to the outsourcing operation.
Keywords: Consent; Consentement; Disclosure; Divulgation; Liability; Outsourcing of services; Privacy; Professional secrecy; Responsabilité; Secret professionnel; Services (externalisation); Vie privée

Regards sur le retard dans l'exécution du contrat - Dabo, Aïssata (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2025)
Le retard dans l’exécution du contrat recouvre les situations dans lesquelles le débiteur d’une obligation n’y satisfait pas dans le délai qui lui est imparti. Cet incident est de nature à remettre en cause le temps contractuel. Davantage, le retard bouleverse l’économie du contrat, étant donné que celui qui s’exécute en retard s’acquitte en deçà de son dû. Néanmoins, il émerge une sorte de tolérance envers le retard, en articulation avec la survie du contrat. La question se pose, après, de savoir si le redéploiement du retard dans l’exécution du contrat ne tend pas à le différencier des autres formes d’inexécution, alors même qu’il reste encadré par le droit commun de l’inexécution. Pour le moins, le retard dans l’exécution se voit actualisé dans ses tenants et aboutissants. Bien plus, l’approche renouvelée se tourne vers le dépassement d’une difficulté, par hypothèse remédiable, et semble poser les bases d’un régime dérogatoire.
Keywords: Effets; Exécution en retard; Obligations contractuelles; Établissement

The Protection of E-Banking Services Against Cybercrimes in Cameroon: Prospects and Challenges - Ghaseh, Nkambeh Allen (International Multilingual Journal of Science and Technology, 2025)
This article seeks to examine the extent to which users of e-banking services are protected in Cameroon. Over the past decades financial transactions have gradually emerged from traditional methods to modern forms of banking. The Information and Communication Technology (ICT) has transformed the banking system into a digital arena. With e-banking, customers can access their bank accounts, transfer funds, pay bills, and check their accounts balances. Banks serve as the backbone of every modern economy and should be protected. The development of e-banking in the 1980s with the aid of ICT has rendered banks and their customers vulnerable to cybercrimes. As an effort to combat cybercrimes and ensure cyber security in Cameroon, the 2010 Cyber Law provides both substantive and procedural rules. It is rather unfortunate that, the measures put in place to ensure cyber security and protect bank customers against cybercrimes are to a greater extent ineffective. The main objective of this article is to determine the protection accorded to banks and their customers against cybercrimes. The method adopted in the course of this work is doctrinal wherein, both primary and secondary sources of data were collected. The findings reveal among others that, the measures put in place to combat cybercrimes within the banking sphere in Cameroon are not effective. There is lack of explicit definitions for cyber offences. Most of the offences provided by the 2010 Cyber Law are vague and ambiguous. We therefore recommend that, the 2010 Cyber Law should be amended to address the current issues of ICT. This amendment should include explicit definitions for the different forms of cybercrimes with severe sanctions. Banks are advised to put in place effective monitoring machineries to mitigate cybercrimes.

La consécration inachevée de l'égalité entre héritiers réservataires en droit congolais de la famille - Kaluta Lubuli, Isaac (International Multilingual Journal of Science and Technology, 2025)
La présente étude tente à démontrer combien les règles relatives à la réserve héréditaire et à la détermination des héritiers réservataires sont de nature à les mettre à conflit avec eux-mêmes et avec les autres héritiers cités au niveau de l’article 758 du Code congolais de la famille. De ce fait, les auteurs démontrent qu’elles entretiennent une inégalité permanente, cela devant ne pas coller au contexte africain. C’est ainsi que la réflexion se propose de proposer des réformes en vue de restaurer cette égalité, gage de la paix et de la cohésion dans les familles.
Keywords: Congo; Egalité; Famille (droit); Héritier réservataire

La dénonciation des traités en droit international africain - Kassabo, Léon Dié (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2025)
La dénonciation des traités en droit international africain soulève des enjeux juridiques importants. Elle s’inscrit dans le cadre de la Convention de Vienne sur le droit des traités de 1969, qui régit les conditions de retrait d’un traité, notamment à travers ses articles 54 et 56. Ceux-ci prévoient que la dénonciation est possible soit conformément aux dispositions du traité, soit avec le consentement de toutes les parties, ou encore si la nature du traité le permet, moyennant un préavis raisonnable. En Afrique, plusieurs États ont récemment exercé leur droit de retrait, notamment vis-à-vis d’engagements relatifs aux droits de l’homme. Un exemple marquant est la dénonciation du traité de la CEDEAO par les Etats de l’AES sur le fondement juridique de l’article 91 dudit traité. Ces pratiques suscitent des débats sur leur conformité au droit international, en particulier quant à la protection des droits acquis et à la sécurité juridique. Elles traduisent une tension entre le respect de la souveraineté étatique et les obligations internationales, soulevant des inquiétudes quant à la fragilisation des mécanismes africains de protection des droits humains. Dès lors, la question de la dénonciation des traités interpelle sur la nécessité de garantir un équilibre entre les intérêts étatiques et la pérennité des institutions juridiques régionales.
Keywords: Dénonciation; Engagements internationaux; Souveraineté; Sécurité juridique; Traités

The regulation of crypto-assets in South Africa with particular regard to crypto-asset market manipulation - Mgijima, Lwandiso (University of Pretoria, 2025)
Market manipulation is one of the dishonest means used by unscrupulous investors to make unjustified profits. It is conduct which unlawfully interferes with the normal operations of the markets in order to create false appearances with respect to the trading activity or the price of a financial asset. Market abuse is one of the various challenges plaguing the crypto-assets market, and is one of the financial regulators’ priority concerns. This study examines and discusses the problem of market manipulation in crypto-assets, and the need for the enactment of an effective regulatory framework in order to combat this problem and to promote investor protection and safeguard the integrity of the markets. The study finds that South Africa and other countries need to introduce rules in crypto-assets market which aim at regulating the activities of crypto-asset service providers. Currently South Africa has not enacted a comprehensive regulatory framework to address the various illegal uses of crypto-assets. The general approach adopted by South Africa to regulate crypto-assets activities involves subjecting crypto-asset service providers and their activities under the various financial sector laws established to regulate the traditional financial markets. This approach has been criticised as being inefficient in light of the unique risks presented by crypto-assets. The study discusses some of these arguments in detail and concludes by highlighting the need for the adoption of innovative regulations, in the long term, which comprehensively and effectively addressed the various risks presented by crypto-assets which also include market manipulation.
Keywords: Crypto-asset; Crypto-assets; Framework; Manipulation; Markets; Misconduct; Regulation; Service provider

La sanction des personnes privées morales par les organisations internationales - Ouedraogo, Ahmed Sidwaouga (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2025)
Le conflit armé opposant la Russie à l’Ukraine a relancé au plan international la question des sanctions ciblées contre les personnes privées morales par les Organisations Internationales. Jadis focalisée sur les individus les sanctions internationales soulèvent la question de leur légalité lorsqu’elles concernent des tiers à l’Organisation. Ainsi les multinationales ou les Organisations Non Gouvernementales (ONG) qui interviennent dans le Blanchiment International de Capitaux, dans le financement international du terrorisme, dans la violation des droits de l’homme ou à qui l’on est reproche des faits de corruption courent le risque d’être sanctionnées par des Organisations internationales universelles comme l’ONU. Mais de plus en plus au plan régional, des Organisations comme l’UEMOA ainsi que la CEDEAO vont intervenir également en matière de sanction des personnes privées morales au plan africain. The armed conflict between Russia and Ukraine has revived the issue of targeted sanctions against private legal entities by international organizations at the international level. Previously focused on individuals, international sanctions raise the question of their legality when they concern third parties to the organization. Thus, multinationals or non-governmental organizations (NGOs) involved in international money laundering, international terrorist financing, human rights violations, or those accused of corruption run the risk of being sanctioned by universal international organizations such as the UN. But increasingly at the regional level, organizations such as UEMOA and ECOWAS will also intervene in matters of sanctioning private legal entities at the African level.
Keywords: CEDEAO; ECOWAS; International organizations; Organisations Internationales; Personnes privées morales; Private legal entities; Sanctions; UEMOA; WAEMU

Cadre juridique du partenariat sino-camerounais : colonialité, investissement chinois et développement - Passi Soh, Babette Laurence (Université du Québec à Montréal, 2025)
Le travail de recherche aborde le cadre juridique du partenariat entre la Chine et le Cameroun, en se concentrant sur les impacts de la colonialité, des investissements chinois et du développement national. Le travail présente un sommaire structuré en plusieurs sections, chacune explorant divers aspects des relations sino-camerounaises.Dans la première section, le cadre juridique et politique de développement au Cameroun est examiné, mettant en lumière les influences historiques, notamment coloniales, sur le droit des affaires. Il est souligné que le Cameroun allie des systèmes juridiques de droit civil et de common law, hérités des périodes coloniales françaises et britanniques. Cette dualité rend difficile l’application uniforme des lois, ce qui se traduit par des inégalités dans les investissements étrangers, particulièrement ceux de la Chine, avec un cadre juridique isolé et sans harmonisation efficace présentant des défi s pour le développement économique. La politique de développement camerounaise, illustrée par la Stratégie Nationale de Développement (SND30) et la Vision 2035, vise à transformer l'économie. Les instruments juridiques entourant les partenariats publics-privés (PPP), comme les contrats de type Build-Operate-Transfer (BOT), sont analysés, mettant en avant les défi s d'une dépendance accrue vis-à-vis des financements chinois et des lacunes juridiques. La deuxième section traite du partenariat commercial avec la Chine, en se concentrant sur le Traité bilatéral d'investissement (TBI) et la présence croissante d'entreprises chinoises au Cameroun. Bien que ces investissements apportent des avantages, tels que la modernisation des infrastructures, ils soulèvent des préoccupations quant à la souveraineté économique et à un nouveau colonialisme économique. Le rapport souligne la nécessité d'un cadre normatif cohérent pour gérer les investissements afin d'entraîner une transformation économique durable. Les obstacles à l'atteinte des objectifs de la Vision 2035 sont également discutés, notamment l'incohérence du cadre normatif, la corruption et l'influence des élites. Le document préconise l'intégration de l'Afrikapitalisme, une idéologie économique axée sur le développement durable et inclusif, et suggère des réformes anti-corruption et l'adaptation des lois pour répondre aux besoins spécifiques du Cameroun. Enfin, la conclusion réaffirme l'importance de reconstruire un cadre juridique qui favorise une véritable coopération gagnant-gagnant avec les investisseurs étrangers, en tenant compte des réalités socio-économiques du pays. Le texte conclut en insistant sur la nécessité d'un équilibre entre les intérêts nationaux et l'attraction d'investissements, pour un développement durable et équitable.
Keywords: Afrique; Cameroun; Chine; Droit des affaires; Développement économique; Relations économiques extérieures

La paternité juridique : une protection précaire des droits de l'enfant en droit congolais de la famille - Safi Ngalya, Pierrette; Amani Miruho, Landry; Kasereka Muyisa, Jean Chrysostome (International Multilingual Journal of Science and Technology, 2025)
Le droit congolais de la famille prévoit que tout enfant congolais doit avoir un père et une mère. Ainsi, le Code de la famille consacre les mécanismes d’établissement et de contestation de la filiation tant maternelle que paternelle. Parlant plus précisément de cette exigence pour ce qui est de la filiation paternelle, le législateur s’est employé à consacrer la paternité juridique comme alternative, toutes les fois que l’action en recherche de paternité se soldera en un échec. Cependant, l’enfant à père juridique est exclu de la succession de ce soi-disant père. De ce point de vue, la présente étude s’emploie à démontrer combien la protection de l’enfant né hors mariage semble s’être arrêté à mi-chemin, ce qui pose un problème de sécurité juridique.
Keywords: Congo (République démocratique); Enfant (protection); Paternité juridique

The UNCITRAL Model Law: "Follow you follow me" or "I do it my way" - Wilske, Stephan (Contemporary Asia arbitration Journal, 2025)
Keywords: Arbitral Awards; Arbitral procedure; Arbitration agreements; Arbitration friendliness; Domestic arbitration law; Germany; Harmonization; Harmonization of law; International Commercial Arbitration; International standards; Modernization; Recognition and enforcement; Statutory frameworks; Taiwan; UNCITRAL Model Law

A cláusula de não concorrência : análise funcional e estrutural - Bedendi, Luís Felipe Ferrari (Universidade de São Paulo, 2025)
A dissertação propõe analisar a cláusula de não concorrência sob perspectivas funcional e estrutural, explorando suas origens históricas, fundamentos jurídicos e aplicações práticas, especialmente no contexto brasileiro. O estudo busca identificar os elementos essenciais dessa cláusula e avaliar sua compatibilidade com os princípios constitucionais da livre iniciativa e da concorrência, fundamentais à ordem econômica, além de posicioná-la perante o fenômeno da concorrência e o direito concorrencial. A pesquisa utiliza métodos históricos e dogmáticos, abrangendo análises legislativas, doutrinárias e jurisprudenciais. Também incorpora referências ao direito estrangeiro para examinar como a cláusula de não concorrência é tratada em diferentes sistemas jurídicos. A coleta de dados da jurisdição estatal e da atividade do Conselho Administrativo de Defesa Econômica permite compreender as interpretações dos órgãos decisórios brasileiros sobre a matéria. O estudo conclui que a cláusula de não concorrência desempenha um papel vital na proteção de investimentos e elementos imateriais, como clientela e segredos empresariais. Contudo, sua regulamentação no Brasil ainda é fragmentada, com previsões específicas no Código Civil, na Consolidação das Leis do Trabalho e na Lei de Franquias, sem que qualquer deles trate verdadeiramente do aspecto contratual da cláusula. Não obstante, conclui-se ser possível o encontro de elementos funcionais e estruturais comuns à cláusula, independentemente da relação jurídica base, a partir de que se propõe a categorizá-la como um instituto jurídico. Além disso, oferece subsídios para futuras discussões legislativas e jurisprudenciais, destacando a importância de conciliar a proteção de interesses econômicos com a promoção da livre concorrência. This dissertation analyzes the non-compete clause from functional and structural perspectives, exploring its historical origins, legal foundations, and practical applications, particularly in the Brazilian context. The study aims to identify the essential elements of this clause and evaluate its compatibility with the constitutional principles of free enterprise and competition, which are fundamental to the economic order, while positioning it in relation to the phenomenon of competition and antitrust law. The research employs historical and dogmatic methods, encompassing legislative, doctrinal, and jurisprudential analyses. References to foreign law are incorporated to examine how the non-compete clause is addressed in different legal systems. Data collected from state jurisdiction and the activities of the Administrative Council for Economic Defense provide insights into how Brazilian decision-making bodies interpret the matter. The study concludes that the non-compete clause plays a vital role in protecting investments and intangible elements such as clientele and trade secrets. However, its regulation in Brazil remains fragmented, with specific provisions in the Civil Code, the Consolidation of Labor Laws, and the Franchise Law, none of which adequately address the contractual aspect of the clause. Nevertheless, it is concluded that functional and structural elements common to the clause can be identified, regardless of the underlying legal relationship, leading to its proposed categorization as a legal institute. Furthermore, the dissertation offers resources for future legislative and jurisprudential discussions, emphasizing the importance of balancing the protection of economic interests with the promotion of free competition.
Keywords: Antitrust law; Cláusula de não concorrência; Direito concorrencial; Elementos estruturais; Funcionalidade; Functionality; Non-compete clause; Structural elements

Essays on banking and society - Heyert, Axelle (Université de Strasbourg, 2025)
This dissertation examines the relationship between banking and society. It contributes to a better understanding of how banking affects society and, in turn on how society shapes banking practices. The first chapter studies the impact of inflation on trust in banks. Chapter two deals with the effect of trust in banks on financial inclusion. The third chapter investigates whether financial inclusion influences life satisfaction. Chapter four delves into how female bank leadership affects firm credit. The final chapter focuses on the influence of bank leaders’ age on sustainable lending. Overall, this dissertation highlights the important role of banks in societal development and the major influence of society in shaping banking practices.
Keywords: ACCESS TO CREDIT; Accès au crédit; Banking; Banks; Banques; Bonheur; Confiance; Financial inclusion; Gender; Genre; Inclusion financière; Inflation; Life satisfaction; Prêts durables; Sustainable lending; Trust in banks

L’évolution du régime juridique de l’immunité d’exécution en droit OHADA Postulats comparatifs de l’Acte Uniforme portant procédures simplifiées de recouvrement et voies d’exécution - Tshibuabua Tshiboba, Charles Daniel (Revue de l'UKA, 2025)
La question de l’immunité d’exécution en droit OHADA était devenue, au regard de l’évolution doctrinale et jurisprudentielle, très controversée tant le flou qu’entretenait l’article 30 de l’AUPSRVE sur ses bénéficiaires, Entreprises Publiques, était incontournable et semait l’insécurité juridique dans le processus de recouvrement des créances. La révision de cette disposition s’est imposée avec acuité et la présente étude tend à en expliciter la nouvelle compréhension.
Keywords: AUPSRVE; Immunité d’exécution; Jurisprudence; OHADA; Personne morale de droit public; Procédure simplifiée; Recouvrement de créances; Révision; Voies d'exécution

Le droit à un procès équitable au Mali - Koïta, Aly Kola (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
Le droit à un procès équitable est tributaire du respect des droits fondamentaux. Ce constat suffisamment éloquent rappelle une évidence : plus un Etat sera enclin à protéger les droits et libertés fondamentaux de l'individu, plus il va se montrer soucieux d'organiser une procédure pénale conforme à ces aspirations. Ces propos se fondent aisément dans les lignes directrices du procès pénal malien où, depuis le « reflux de l'orientation autoritariste » amorcée en 1991, le législateur se montre plus regardant sur les droits des personnes poursuivies. La dernière illustration en date peut être tirée de l'extension en amont des droits de la défense, consécutive de l’équité libéralisation du procès pénal et de la volonté persistante d'accorder une audience de plus en plus soutenue à procédurale dans notre ancien système inquisitorial, dont les imperfections et anachronismes n'avaient cessé d'émouvoir. C'est dans cette optique qu’analyse cet article la problématique de la diffusion du modèle du respect des garanties procédurales en matière pénale au Mal. he right to a fair trial depends on respect for fundamental rights. This sufficiently eloquent observation reminds us of the obvious: the more inclined a State is to protect the fundamental rights and freedoms of the individual, the more it will be concerned to organize a criminal procedure in accordance with these aspirations. These remarks easily fit into the guidelines of the Malian criminal trial where, since the "ebb of authoritarian orientation" that began in 1991, the legislator has been more attentive to the rights of those prosecuted. The latest illustration to date can be drawn from the upstream extension of the rights of the defence, as a result of the fair liberalization of the criminal trial and the persistent desire to grant an increasingly sustained hearing to procedural in our old inquisitorial system, whose imperfections and anachronisms had never ceased to move. It is in this perspective that this article analyzes the problem of the diffusion of the model of respect for procedural guarantees in criminal matters to Evil.
Keywords: Accusatoire; Adversarial; Equité; Fairness; Inquisitoire; Inquisitorial; Justice; Procès; Trial

L'environnement dans le traité révisé de la CEEAC : une prise en compte mitigée - Meli Fotie, Anthony (International Multilingual Journal of Science and Technology, 2025)
Née à une époque où la protection de l’environnement constituait un leitmotiv sur la scène internationale, il a fallu plus de trois décennies à la CEEAC pour inscrire expressément cette protection dans son texte fondamental notamment son Traité révisé. Nonobstant cet exploit, des manquements sont observables. D’une part, le Traité considère la protection de l’environnement comme un moyen de l’intégration économique et non comme un objectif à part entière de la communauté. D’autre part, l’environnement est appréhendé de manière sectorielle dans le Traité pourtant, la tendance doit être la globalisation de l’environnement par l’inclusion de celui-ci dans tous les politiques sociaux économiques de la communauté tel que se revendique aujourd’hui le développement durable. A l’épreuve, la CEEAC se doit dans son Traité de rendre à l’environnement toute l’attention et l’importance qui lui sont reconnues aujourd’hui. Born at a time when environmental protection was a leitmotif on the international scene, it took more than three decades dor ECCAS to expressly include this protection in its fundamental text, particularly its Revised Treaty. Notwithstanding this feat, shortcomings are observable. On the one hand, the Treaty considers environment protection as a means of economic integration and not as a separate objective of the community. On the other hand, the environment is understood in a sectoral manner in the Treaty, however, the trend most most be the globalization of the environment through the inclusion of it in all, the social and economic policies of the community such as sustainable development is now being promoted. Under the test, the ECCAS must in its Treaty give to the environment all the attention and importance that is recognized for it today.
Keywords: CEEAC; ECCAS; Environment (protection); Environnement (protection); Revised Treaty; Traité révisé

The Middle Eastern and African Arbitration Review 2025 : Telecoms disputes in the Middle East and Africa - Mouzoula, Natalia; Kamau, Alice (Anjarwalla Collins & Haidermota, 2025)

Financial regulation and risk management: addressing risk challenges in a changing financial environment - Ojo, Marianne (Munich Personal RePEc Archive, 2025)
Will the April 2nd Announcement generate its intended objectives? It’s still early days – however, it appears increasingly likely that negotiation outcomes – particularly between those significantly impacted by the Announcement, will be a major determinant in deciding whether the tariff hikes resulting from the April 2nd Announcement, will be short or long term. As of the 11th April, 2025, President Trump’s universal tariffs on China had amounted to 145% whilst China announced tariffs of 125% on U.S imports. Amongst other things, this paper aims to address complexities and challenges faced by regulators in identifying and assessing risk, problems arising from different perceptions of risk, and solutions aimed at countering problems of risk regulation. It will approach these issues through an assessment of explanations put forward to justify the growing importance of risks, well known risk theories such as cultural theory, risk society theory and governmentality theory. In addressing the problems posed as a result of the difficulty in quantifying risks, it will consider a means whereby risks can be quantified reasonably without the consequential effects which result from the dual nature of risk that is, risks emanating from the management of institutional risks.
Keywords: Financial Forecasting and Simulation; General Financial Markets; International Financial Markets; Regulation and Business Law

How the Liberation Day Announcement is Shaping the Global Trade Order: From Free Trade to Fair Trade Agreements - Ojo, Marianne (Journal of Finance Research Letters, 2025)
It may be assumed that all of the United States’ trading partners were impacted by the recent “Liberation Day” announcement – an announcement which constitutes “two distinct tariff actions” – as will be highlighted in this paper. However, despite previous concerns of being targeted by their free trade agreement (FTA) partner, Canada and Mexico – as would have been or should be expected, have been exempted from the tariff imposition. As well as addressing factors which have contributed to the shift from free trade to increasingly and predominantly protectionist stances and most likely, fair trade practices, this paper is aimed at highlighting and explaining the rationales behind the recent historical developments – as well as highlighting those factors that have triggered the build up to the Liberation Day Announcement of the 2nd April 2025. It is remarked that “Trump’s reciprocal tariff doctrine, holds foreign countries accountable”. Against this backdrop of discontent with World Trade Organisation’s dispute resolution mechanisms, which will be further elaborated on, in the paper, the immediate and possible long term impacts of the Announcement, will be considered. As well as exploring the reasons for recent developments – by way of reference to historical developments and data, the paper also considers the underlying frameworks governing the calculations of recent tariff rates and hikes. Whilst there are arguments regarding the validity of such calculations, or whether the current scenario justifies the basis for implementing “national emergency measures”, what can be regarded as an emergency response can be determined through a consideration of underlying and contributory factors. If negotiations, and more specifically, bilateral negotiations, take place as hoped, between those countries impacted by the Liberation Day Announcement, financial stability across global markets is expected to be restored. However, if retaliatory measures follow – with an escalation of trade wars, possible repercussions should be cause for concern. The global trading system is still recovering from the recent crisis which was largely uncontrollable – hence, it is more likely (and hoped) that the recent market turbulence and volatilities will be short term.
Keywords: Deregulation; Dispute resolution mechanisms; Financial stability; Free trade agreements; Manufacturing; Monetary policy; Protectionism; World Trade Organisation

Le débiteur assisté en droit OHADA des procédures collectives - Rabalta Djiraibe, Clarisse (International Multilingual Journal of Science and Technology, 2025)
En droit OHADA des procédures collectives de sauvegarde, le débiteur fait l’objet d’une assistance. Elle concerne tant les actes d’administration que de disposition. Vu l’importance de ces actes de gestion sur lesquels elle porte afin d’atteindre les finalités de redressement de l’entreprise débitrice et le paiement de ses créanciers, la présente étude fait une analyse approfondie de cet aspect salvateur. Under OHADA law on collective safeguard procedures, the debtor is provided with assistance. This concerns both acts of administration and acts of disposal. In view of the importance of these acts of management in achieving the goals of reorganizing the debtor company and paying its creditors, the present study provides an in-depth analysis of this life-saving aspect.
Keywords: Assistance; Collective procedures; Debtor; Débiteur; Procédures collectives

Legal remedies for breach of E-commerce contracts and related offences in Cameroon: a critical analysis - Saidou, Dan Lamy Nouhou (International Multilingual Journal of Science and Technology, 2025)
Avec de plus en plus de transactions commerciales effectuées par voie électronique, les litiges résultant d'intérêts conflictuels ou de malveillance deviennent inévitables, car Internet est devenu un terreau fertile pour divers abus. Ces abus vont de la rupture de contrat et des actes délictuels aux actes criminels. Il en résulte que l'utilisation d'Internet a donné une dimension différente à ces litiges. Cependant, comme le dit la célèbre maxime Ubi Jus Ubi Remedium, là où il y a un droit, il y a un remède. Le Cameroun, suivant cette tendance, a adopté un cadre juridique qui offre une panoplie de recours disponibles pour les victimes de violations du commerce électronique et d'infractions connexes, dans l'intention de rapprocher la partie lésée le plus possible de la position qu'elle aurait occupée s'il n'y avait pas eu d'abus. Le but de cet article est d'évaluer l'efficacité du cadre actuel pour remédier aux victimes de violations du commerce électronique et d'infractions connexes. L'article examine donc les bases des responsabilités en commerce électronique et les recours disponibles pour les victimes, mettant en évidence les difficultés qui rendent ces recours moins efficaces à cet égard. Plusieurs recommandations ont été proposées par cet article pour améliorer le statu quo. With more and more business being conducted through electronic means, disputes stemming from conflicting interests or malice become inevitable, as the internet has become a breeding ground for diverse abuses. These abuses range from contractual breaches and tortious acts to criminal acts. It follows that the use of the internet has given a different dimension to these disputes. However, as the famous maxim Ubi Jus, Ubi Remedium states, where there is a right, there is a remedy. Cameroon, following this trend, adopted a legal framework that provided a panoply of remedies available to victims of breaches of e-commerce contracts and related offenses to bring the aggrieved party as close as possible to the position he would have been in if there had been no abuse. The purpose of this article is to assess the efficiency of the present framework for remedying victims of e-commerce breaches and related offenses. The article thus examines the basis for liabilities in e-commerce and the remedies available to victims, bringing out the difficulties which render these remedies less efficient for the purpose. Several recommendations have been proffer by this article to improve the status quo.
Keywords: Commerce électronique; E-commerce; Electronic transactions; Recours; Remedies; Transactions électroniques

La théorie de l'apparence dans le régime général des obligations du Mali - Sangaré, Sékou (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
L'apparence désigne tout à la fois ce qui est visible, directement accessible aux sens, et ce qui est trompeur. Articuler et unifier les deux sens du mot permet de construire une théorie générale de l'apparence, qui manifeste le rapport du droit à la réalité. Le droit, parce qu'il est artificiel, définit en effet lui-même la réalité en distribuant les pertinences et en consacrant des réalités autonomes. L'apparence est au cœur, des règles juridiques de fond, comme le droit des contrats, Elle est également une source autonome de droits et d'obligations. Les tiers peuvent lui accorder crédit puisqu'il importe peu qu'elle soit exceptionnellement dissociée d'une ''réalité'' qui serait demeurée occulte. Cette nouvelle approche bouleverse la place de l'apparence en droit positif. Elle n'est plus un dysfonctionnement ponctuel du rapport qui doit s'établir entre le fait et le droit. De simple correctif d'équite, l'apparence est devenue un principe général du droit. Elle est une règle pleine et entière, articulée avec la notion de confiance : foi est due à l'apparence.

Fiscalité dérisoire ou les origines de l’économie informelle dans les pays en voie de développement : éléments de réflexion à partir du cas du Mali - Sissoko, M’Baha Moussa (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
Cet article est le fruit des recherches empiriques menées à Bamako, auprès des acteurs publics/institutionnels (notamment l’institut national de statistique) mais aussi de l’exploitation et de l’analyse de la littérature académique sur l’économie informelle. Il n’a pas pour objet de faire une présentation des règles et principes de recouvrement des impôts au Mali, encore moins leur contentieux. Dans un cadre institutionnel normal, nous savons que les finances publiques proviennent de la mobilisation des recettes publiques par les agents assermentés de l’Etat et des collectivités territoriales. Mais, globalement, on constate au Mali que l’Etat central rencontre d’énormes difficultés dans l’application concrète de cette mobilisation des ressources propres alors qu’un tel exercice, relève, rappelons-le, de ses fonctions régaliennes. Cette situation résulte d’une part de la difficulté de recouvrement de certains impôts et taxes et de la rareté de certaines matières imposables d’autre part. Dans ce contexte particulier, [de faible mobilisation des recettes publiques], cet article aide à comprendre les difficultés rencontrées par le l’Etat central en raison notamment de la prédominance de cette économie informelle. This article is the fruit of empirical research carried out in Bamako, with public/institutional players (notably the national statistics institute), as well as the exploitation and analysis of academic literature on the informal economy. It is not intended as a presentation of the rules and principles of tax collection in Mali, still less their litigation. In a normal institutional framework, we know that public finances come from the mobilization of public revenues by sworn agents of the State and local authorities. But, on the whole, we can see that the central government in Mali is encountering enormous difficulties in the practical application of this mobilization of its own resources, even though such an exercise, it should be remembered, falls within its regalian functions. This situation is partly due to the difficulty of collecting certain taxes, and partly to the scarcity of certain taxable materials. In this particular context [of low mobilization of public revenues], this article helps to understand the difficulties encountered by the central government, due in particular to the predominance of the informal economy.
Keywords: Citizen; Citoyen; Economie informelle; Finances publiques; Fiscalité; Impôt; Informal economy; Mali; Public finance; Tax; Taxation

La responsabilité sociétale dans l’ancrage territorial des entreprises du secteur agro-industriel : quel enjeu pour le développement durable au Cameroun ? - Tongue, Thomas Yves (International Multilingual Journal of Science and Technology, 2025)
L’État Camerounais désireux d’attirer des investissements agro-industriels directs se montre parfois complaisant au détriment de la maitrise des impacts locaux de ces entreprises sur l’environnement. Situation qui est permanemment source de conflit avec les communautés locales qui aspirent à protéger leur espace ressource. Dans un contexte de contestations sociales, les entreprises sont de plus en plus interpellées sur leur engagement à la responsabilité sociétale et leur redevabilité environnementale envers leur territoire d’action. Paradoxalement, alors que le Cameroun a adhéré aux idéaux de développement durable, un foisonnement d’initiatives et d’expérimentations faites sur le terrain mettent en exergues plusieurs insuffisances d’une responsabilité sociétale hybride, intuitive qui ne permet pas véritablement à ces entreprises de contribuer au développement durable de leur localité d’implantation et de satisfaire aux attentes des populations locales. Cette réflexion prendra appui sur l’approche des parties prenantes de la responsabilité sociétale des entreprises afin d’en proposer un modèle co-construit adapté à la préservation des intérêts écologiques dans l’ancrage local des entreprises du secteur agro-industriel au Cameroun.
Keywords: CSR; Développement durable; Parties prenantes; RSE; Responsabilité sociétale des entreprises; Social responsibility; Stakeholder; Sustainable development

L'obligation d'exploiter un bien - Vaillant, Roxane (Université de Montpellier, 2025)
Le droit de propriété est présenté comme un droit absolu. Tout propriétaire ne peut être privé de sa propriété sans son consentement ou hors des cas prévus par la loi. Or c’est justement au titre d’une obligation légale que certains propriétaires sont tenus d’exploiter leur bien. C’est en cela que cet objet d’étude porte sur l’obligation d’exploiter un bien. Il consiste à retracer les manifestations d’une telle obligation en droit privé et d’en analyser les conséquences, particulièrement sur le droit de propriété. Il s’agira, préalablement, de s’attacher à la notion même d’exploitation. Bien qu’il existe plusieurs acceptions de cette notion, seule l’exploitation comme activité sera retenue dans le cadre de cette étude. Ainsi, exploiter renvoie à l’action de tirer profit ou bon parti de quelque chose considéré comme objet d’exploitation. Cette étude s’articule autour d’un double constat. D’une part, l’obligation d’exploiter a pour particularité de concerner une diversité de bien (brevet d’invention, marque, fonds de commerce, fonds rural) et par la même une pluralité de matières (droit des biens, de la propriété intellectuelle ou droit rural). L’obligation d’exploiter est ponctuellement intégrée par le législateur en droit positif. On la retrouve ainsi en droit rural notamment lors de l'exercice du droit de reprise ou du droit de préemption, en droit des baux commerciaux lors de l'exercice du droit au renouvèlement, mais encore en droit de la propriété intellectuelle. Mais parfois, cette même exigence d’exploitation est expressément formulée lorsque le législateur sanctionne un défaut d’exploitation, il en est ainsi en droit des brevets lorsqu’une licence obligatoire s’impose au titulaire du brevet en cas de non-exploitation ou d’abandon d’exploitation depuis plus de trois ans. Outre une obligation légale, l'obligation d'exploiter un bien, peut être d'origine contractuelle et être stipulée dans un contrat sous forme de clause d'exploitation. Une telle obligation d'exploiter peut également être prévue dans le cadre d'une stipulation contractuelle prévoyant la rémunération due par le cessionnaire au cédant sous la forme d'une redevance proportionnelle à l'exploitation. D’autre part, les biens concernés par cette obligation, présentent une caractéristique commune, ils sont tous créateurs de richesse dès lors qu’ils sont exploités. Or, la nature de ces biens justifie la présence d’une telle obligation afin de préserver et maintenir leur valeur et par la même leur propre existence. L’étude de l’obligation d’exploiter un bien, permet de mettre en exergue la nécessaire articulation entre les impératifs juridiques et les considérations d’ordre économique, tel que la préservation du potentiel économique de ces biens conditionnée à leur exploitation. L’intérêt de l’étude menée est d’apporter des éléments de réflexion sur les incidences juridiques de la mise en œuvre de cette obligation sur le droit de propriété, en ce que les prérogatives inhérentes à ce droit peuvent être menacées par cette obligation qui influence sur le droit d’user de la chose à la fois pour le propriétaire mais également pour le simple détenteur. Le titre de propriété lui-même peut être mis en péril. De telles atteintes au droit de propriété se justifient soit par des considérations d’intérêt général, soit par des considérations d’intérêt privé. Des éléments communs caractérisent ces différents biens concernés par cette obligation d'exploiter, notamment celui d'avoir un pouvoir de création de richesse indépendamment des modalités d'exploitation choisies par le propriétaire ou locataire, il conviendra dès lors d’analyser la nature et le régime d’une telle obligation.
Issue: 2025UMOND010
Keywords: Asset; Droit des biens; Exploitation; Property; Propriété; To exploit

A trans-border African crypto asset licence to promote economic growth and deepen financial inclusion - Van der Lith, Johann Daniel (University of Pretoria, 2025)
Financial technology (Fintech) is a rapidly growing industry, both locally and globally. In various ways, Fintech is undeniably transforming financial services and products in every possible part of the financial sector by changing how people access and use financial services. By using innovative technologies, such as distributed ledger technology and cloud technology, and combining large data sets, including alternative data sets, better products can be provided that can be hyper-personalised for market segments and improve access and participation in respect of financial services. Fintech is solving issues that touch the consumer, through a bottom-up approach, considering the retail consumer as a starting point, in contrast to the common traditional finance evolution from the institutional investors to the retail consumer in a top-to-bottom approach. What is exciting about what Fintech can do for Africa, is that it can move inefficiencies in services and product life cycles to become efficiencies and move the frontiers for already efficient products and services. Fintech, therefore, provides an opportunity to improve the archaic and pave the way for the future. This study focuses mainly on crypto assets to limit its scope. It first examines the Fintech landscape in Africa, more specifically, the activity level in each selected comparative country, namely Mauritius, Kenya, Zambia, Namibia and South Africa, and how the activity benefits or can potentially benefit the economy in the host country and lead to the deepening of financial inclusion. It further examines the regulatory frameworks in those countries. The study examines the regulatory approach taken and the local activity, exploring some of the risks identified in each country, and considers the requirements that regulators chose to implement to mitigate these risks, as well as the current state of regulatory frameworks. Consideration is given as to whether similarities in both the risks and the mitigation requirements exist and how this can be aligned across jurisdictions. Recently, international standard-setting bodies have increased their focus on ensuring the alignment and cooperation of regulatory approaches globally. In light of the call for alignment and increased collaboration through policy recommendations and guidance, and or regulators to provide comprehensive and effective regulatory approaches without stifling innovation, this study considers the theoretical possibility of allowing certain Fintech companies, specifically crypto asset service providers (subject to specified conditions) to operate across jurisdictions with a trans-border licence. This study examines Europe’s Markets in Crypto Assets Regulation, as it was the first of its kind continental-wide framework for crypto assets, offering numerous lessons to be learned from this framework. The Commonwealth Model Law on Virtual Assets is also considered, as it is intended to assist member countries in implementing Virtual Asset and Virtual Asset Service Provider regimes in their respective jurisdictions, as they deem appropriate. Lastly, the study will explore what a theoretical trans-border regulatory framework containing prudential and market conduct requirements could look like and what embedded supervision tools, for instance, through forensic nodes or zero-knowledge proofs, could be utilised to ensure that all the regulators participating as part of a licencing panel receive real-time data and have a full view of the level of compliance with the requirements imposed by the joint framework and can proactively and intrusively act, when needed. The proposed trans-border regulatory framework aims to support crypto asset service providers with multi-jurisdictional strategies in Africa in scaling their operations, with a focus on building Africa as a global Fintech hub. The proposed framework aims to achieve this through a harmonised regulatory framework that simplifies compliance, increases efficiencies, enhances innovation, allows for scalability, and better risk management. In addition to the goal of positioning Africa as a globally recognised Fintech hub, the harmonised framework aims to realise the purported benefits of the technologies utilised by crypto asset service providers, thereby deepening financial inclusion and promoting inclusive economic growth through increased access and participation, as well as lower costs.
Keywords: Crypto assets; Embedded supervision; Financial inclusion; Financial technology; Regulatory frameworks

An Organizational Theory of Corporate Law - Aguirre, Emilie; Yen, Julie; Battilana, Julie (The Journal of Corporation Law, 2025)
Corporate law is in a moment of vibrant and contentious discussions about potential reforms. As firms exit Delaware, passive investment predominates, private equity expands, and public markets decline, corporate law faces a growing set of challenges that threaten its stability and efficacy. At the same time, the world faces pressing crises, including climate change, social and economic inequalities, and threats to democracy, though corporate law scholars typically consider these crises to be outside corporate law’s remit. In this Article, we argue that to understand and address the multidimensional crises that face both corporate law and society, we must address shortcomings in corporate law doctrine. We show how modern corporate law, shaped by neoclassical economic theories, provides an incomplete picture of the firm, and we propose an expanded theoretical perspective that draws from organization theory, a field long dedicated to understanding the complexities of the firm. This updated perspective demonstrates how firms actually consist of multiple constituents, including workers, the environment, and shareholders, who invest different forms of capital in the firm: labor capital, natural capital, and financial capital. It further shows that modern corporate law entrenches problematic power imbalances, privileging boards and insider shareholders over workers, the environment, and minority shareholders. Moreover, building on organization theory, we explain how corporate law fundamentally shapes and constrains firm behavior, leading these entrenched power imbalances to generate far-reaching negative consequences. To address these shortcomings, we propose redesigning board representation, fiduciary duties, and executive compensation to empower workers, the environment, and minority shareholders in relation to boards and insider shareholders. Integrating the organizational and economic perspectives can help address problematic power imbalances and ultimately provide a more effective corporate law framework to govern firms and serve society.

Arbitration Fees, Expenses and Determination Controls - Al-Taani, Muhanned; Al-Majali, Tawfiq; Mosabeh, Rageh; Mayah, Yousef (Jordan Journal of Applied Science-Humanities Series, 2025)

Artificial Intelligence in Accounting: Revolutionizing Financial Management in the Digital Landscape - Alnaimat, Mohammad Ahmad; Korsun, Inna; Lutsenko, Kostiantyn; Khodorkovskyi, Oleksandr; Artemchuk, Mykyta (Theoretical and Practical Research in Economic Fields, 2025)
The use of artificial intelligence (AI) builds up the accounting system efficiency, increases data entry accuracy and simplifying the accounting process. The aim of the study is to prove the effectiveness of modern AI-based information technologies (IT) in accounting and the possibilities of AI application for process optimization. The effectiveness and efficiency were proven using comparison methods, statistical analysis, graphical cause-and-effect analysis, modelling using the linear regression method. The assessment was carried out using quantitative and qualitative indicators of labour productivity and process optimization. The results of the study showed that 18 accounting department employees on average are needed to perform standard transactions in the companies studied without AI. With AI, 1 person can handle such a volume of work. Accordingly, with the implementation of AI, the average reduction in Transaction Processing Time per Week is 696.26 hours. Regression analysis confirmed that the implementation of AI increases the companies’ productivity in terms of Transaction Processing Time. Reducing the Data Processing Complexity by one unit leads to a reduction in transaction processing time by 592.69 seconds. Each percent increase in Data Entry Accuracy contributes to a reduction in processing time by 5135.51 seconds. The prospects for implementing AI in accounting include further improving algorithms to increase the accuracy and speed of transaction processing, optimizing material and time consumed.
Keywords: Accounting; Artificial Intelligence; Automation; Data analytics; Digital environment; Financial management; Inteligência artificial; Intelligence Artificielle; Machine learning

Fairness, Digital Markets and Competition Law – Reconciling Fairness Norms in Digital Markets Act, Data Act and AI Act with Competition Law - Kianzad, Behrang (Journal of Law, Market & Innovation, 2025)
The present article explores the implication of fairness as a regulatory and competition law concept applied to digital and Artificial Intelligence markets, in light of recent law and policy developments targeting the interaction between data, market power and competition law. Much of the policy discussions, legislative proposals as well some emerging case law elevate the matter of “fairness” in the context of digital markets and AI, creating both a novel regulatory framework as well as encouraging competition law to curb “unfairness” of said markets and related “unfair practices”. The interface between intellectual property rights and competition law is of utmost importance in this context, where we might find similar analogous insights as we can find regarding the matter of fairness within traditional EU competition law. Further, the question remains whether the “fairness norm” expressed in regulatory acts such Digital Markets Act, EU AI Act and the EU Data Act are akin to the “fairness” norms found in Union competition law, mainly under Article 102 Treaty on the Functioning of the European Union (TFEU).

La place de la femme dans la mise en œuvre du droit des affaires - SPO - OHADA (2025)

Les holdings en droit africain des affaires - ERSUMA - OHADA (2025)

Contribution à l’étude de la réservation des utilités des données numériques - Grave-Renaud, Gonzague (Université de Lille, 2025)
La dématérialisation et la numérisation croissantes de notre économie ont élevé les données au rang de matière première indispensable. La valeur des données réside dans leurs exploitations potentielles. C’est pourquoi leurs détenteurs cherchent à maximiser leurs revenus en limitant l’accès. Ce constat souligne les enjeux de gouvernance des données. La problématique de la réservation des données a alors émergé. Le constat est que la propriété intellectuelle ne parvient pas à appréhender pleinement la donnée. Néanmoins, l’analyse du droit positif révèle l’existence de mécanismes du droit commun permettant une réservation des utilités des données, tels que le contrat, la concurrence déloyale et parasitaire et le secret des affaires. Bien que ces mécanismes offrent une réservation, ils ne sont pas exempts de lacunes. Aussi, la question de la propriété des données a émergé et a suscité un vif débat. Cette interrogation a engendré un renouvellement des approches théoriques et pratiques du droit de propriété. Dans une approche prospective, un droit exclusif d’exploitation sur les données a été esquissé sous la forme d’un droit sui generis. Cet exercice de conceptualisation a mis en exergue les difficultés que pourrait entraîner une telle reconnaissance. Par ailleurs, il est impératif de trouver un juste équilibre entre la volonté d’appropriation des données et le droit d’accès des tiers à celles-ci afin d’instaurer un régime de protection à la fois efficace et équitable.
Keywords: Biens incorporels; Brevets d'invention; Contrats; Data; Données; Droit d'auteur; Droit des affaires; Droit d’accès; Intellectual property; Investissements; Investments; Propriedade intelectual; Propriété; Propriété intellectuelle; Protection de l'information (informatique) – Droit; Reservation; Responsabilité (droit); Right of access; Réservation; Secret; Systèmes d'information; Valeur; Value

Les frontières du salariat - Caron-Thérage, Maéva (Université de Lille, 2025)
Ouvrier à l’usine, candidat à l’Emission Koh Lanta, livreur de la plateforme numérique de travail TakeEatEasy, mannequin ou encore cadre en télétravail… sont autant de salariés, rassemblés sous l’empire du Code du travail, qui ne se ressemblent pas. Le salariat d’hier n’est sans doute plus celui d’aujourd’hui. Il s’accorde désormais avec les technologies de l’information et de la communication qui contribuent à une certaine autonomie des salariés mais aussi à la création de nouvelles formes d’emploi. Il ne faut pourtant pas en conclure à l’obsolescence de la subordination. Ce critère du contrat de travail mérite certes d’être modifié – pour prendre en compte un pouvoir de direction de l’employeur qui s’invisibilise de plus en plus – mais il a tout de même su faire preuve d’une adaptabilité garantissant sa pérennité. Cette étude propose donc de sécuriser les frontières du salariat par l’étude et l’amendement de son critère de subordination afin de le réconcilier pleinement avec la notion d’autonomie. Ce faisant, il convient de déterminer qui est salarié et qui doit et ne doit pas l’être. Des stratégies sont mises en place pour éviter le salariat, il faut alors permettre au critère de subordination d’être sollicité de façon efficiente pour assurer une exacte requalification. Lorsque des stratégies sont, au contraire, mises en place pour détourner le salariat, cela amène à penser la nécessité d’un socle minimum des droits des travailleurs, s’ajoutant aux statuts existants, sous la forme d’un code général de l’activité professionnelle. A factory worker, a contestant on the television programme Koh Lanta, a delivery driver for the digital labour platform TakeEatEasy, a model, or a remote-working executive — all are employees, gathered within the scope of the Labour Code, yet they bear little resemblance to one another. The salaried employment of yesterday is, without doubt, no longer that of today. It now evolves in conjunction with information and communication technologies, which foster a degree of autonomy among employees while also giving rise to new forms of work. Nevertheless, this evolution should not be taken as signalling the obsolescence of subordination. While this defining criterion of the employment contract certainly merits re-examination — so as to take account of an employer’s managerial authority that increasingly operates in less visible ways — it has nonetheless demonstrated an adaptability ensuring its continued relevance. This study thus seeks to consolidate the boundaries of salaried employment through an analysis and amendment of its subordination criterion, with the aim of fully reconciling it with the notion of autonomy. In doing so, it becomes necessary to determine who qualifies as an employee, and who should — or should not — be regarded as such. As strategies are increasingly devised to circumvent salaried status, the criterion of subordination must be applied effectively to ensure proper reclassification. Conversely, when strategies are used to distort or exploit salaried employment, this calls for the establishment of a minimum foundation of workers’ rights, supplementing existing legal statuses, in the form of a General Code of Professional Activity.
Keywords: Autonomie des salariés; Droit commun du travail; Droit du travail; Effets des innovations technologiques; Employeur et employé (droit); Nudge; Organisation du travail; Qualification (droit); Qualification du contrat de travail; Salariat; Subordination; Ubérisation

Réflexions sur la réforme de l'immunité d'exécution des personnes morales de droit public en droit OHADA - Awoki, Ariel Kougnontèma (Revue africaine de droit des affaires, 2025)
L’article dissèque les apports de la réforme récente de l’Acte uniforme portant organisation des procédures simplifiées de recouvrement et des voies d’exécution, dans son aspect relatif à l’immunité d’exécution des personnes morales de droit public dans l’OHADA. Le nouveau texte a-t-il permis d’obtenir des avancées décisives sur cette question ? Le doute est permis. Ainsi, cette étude démontre que, malgré quelques avancées notables, surtout en termes de clarification concernant l’identité des personnes morales publiques bénéficiaires de l’immunité d’exécution, l’on ne saurait parler d’une « révolution copernicienne ». La réforme pêche par son manque d’ambition et d’audace. Alors que le contexte était favorable au changement consacrant l’immunité d’exécution relative, le législateur de l’OHADA a plutôt fait preuve de minimalisme, en maintenant le caractère absolu et exorbitant de ce privilège et en introduisant de nouveaux tempéraments à l’immunité dont le caractère véritablement novateur mérite d’être relativisé. Il n’a pas su non plus, dans une perspective de modernisation de son droit de l’exécution, renforcer davantage la protection des créanciers, en mettant entre leurs mains des moyens de pression extrajudiciaires et juridictionnels, complémentaires aux voies d’exécution ordinaires, qui permettent l’exacte exécution des créances publiques. Le législateur a ainsi manqué une véritable opportunité de s’aligner sur les évolutions contemporaines observées en droit international et dans certains droits étrangers, favorables à l’immunité restreinte ou fonctionnelle. Finalement, seule l’intervention décisive de la CCJA qui, au moyen d’une sage et courageuse application du nouveau dispositif, pourra contribuer à un plus grand assouplissement de l’immunité absolue d’exécution.

South Africa judicial review of trade remedies in South Africa - Brink, Gustav Francois (Global Trade and Customs Journal, 2025)
No abstract available.
Keywords: Judicial review; South Africa; Trade remedies

Le régime fiscal de la TVA à l’épreuve des activités numériques au Mali - Daou, Yacouba; Camara, Oumar Sinè; Toe, Souleymane (Revue africaine de droit des affaires, 2025)
Le commerce électronique au Mali connaît une forte croissance, mais l’inadaptation du régime fiscal, notamment en matière de TVA, engendre d’importantes difficultés. La nature immatérielle et extraterritoriale des transactions numériques complique leur contrôle, favorisant ainsi l’évasion fiscale et la fraude. De plus, l’identification des acteurs du commerce numérique reste un défi majeur, rendant l’application de la législation fiscale inefficace. Pour y remédier, une réforme s’impose particulièrement par la mise en place d’un mécanisme de collecte de la TVA par les plateformes en ligne, comme l’ont fait le Kenya et le Nigeria. Cette mesure permettrait de mieux encadrer la fiscalité du commerce électronique, d’assurer une concurrence équitable et d’optimiser la mobilisation des recettes fiscales.

La confrontation du droit processuel au processus de légitimation des décisions de justice en Afrique : l’exemple du Mali - Dougoune, Moussa (Revue africaine de droit des affaires, 2025)
Cet article est une étude analytique des solutions de compromis élaborées afin de satisfaire les promesses faites par les États et les institutions communautaires relativement à la bonne administration de la justice. Tout le processus de production et d’exécution des décisions de justice s’y trouve mis à l’épreuve dans l’analyse empirique. Cette étude présente un intérêt particulier dans la mesure où certains États ont procédé à une relecture de leurs Codes de procédure susceptibles d’avoir des incidences sur le processus de légitimation des décisions de justice. L’analyse démontre que l’ambition affichée demeure toujours la recherche d’une légitimité des décisions de justice eu égard à l’évolution des contextes socioculturels et socio-économiques. Cela entraîne nécessairement, en raison de la prolifération des espaces d’intégration (juridique et économique), des difficultés de trouver un équilibre entre le respect du droit processuel positif et les règles coutumières en certaines matières. Enfin, trente ans après l’adoption des espaces d’intégration, l’heure est au bilan, car le droit national ne peut être appliqué de façon systématique et isolée en toutes circonstances.

Who can become a Member of a Company under OHADA Law: A Critical Appraisal - Eposi, Gladys Nku Tiku (International Journal of Science and Research, 2025)
OHADA Law plays a crucial role in fostering economic growth and regional integration by harmonizing business regulations in the era of globalization and trade liberalization. This study examines the legal framework surrounding company membership under OHADA Law. While certain individuals such as legally incapacitated persons or those facing legal prohibitions cannot become company members, the law provides alternative solutions. The study explores the distinction between members and shareholders and clarifies the eligibility criteria for company membership. Using an analytical approach, this research finds that any natural or corporate entity, unless restricted by legal incapacity, prohibition, or incompatibility, can be a company member under OHADA Uniform Act. Furthermore, the law offers flexibility for incapacitated individuals by allowing legal representatives to act on their behalf.
Keywords: Business law; Company membership; Corporate governance; OHADA Law; Shareholder rights

La transaction douanière dans les Etats de la sous-région CEMAC - Fonchap Kungang, Clauvis (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
Il existe certains litiges en droit douanier où l’on ne peut accéder au juge sans avoir écarté la possibilité d’un recours à la transaction. La transaction a non seulement l’avantage de réduire les délais, mais aussi d’alléger les procédures de résolution des litiges en matière douanière. La question se pose de savoir en quoi consiste la transaction douanière dans la sous-région CEMAC ? En réalité, le problème qui se pose est celui de rechercher l’appréhension de cette procédure qui est également largement appliquée en droit fiscal. Face à cette interrogation, des recherches ont été menées sur le sujet à l’aide de la méthode juridique axée sur l’exégèse des textes de droit douanier de la sous-région, principalement le Code des douanes CEMAC. De ces recherches, il apparait que la transaction est un privilège de l’administration des douanes qui marque l’extinction des poursuites à la fois fréquente et vigoureuse. Il s’agit donc d’une procédure particulière. A ce propos, il est apparu loisible de présenter l’encadrement juridique de la transaction douanière d’une part, avant de faire l’état de sa mise en œuvre d’autre part. L’avènement de la transaction a réduit d’une certaine manière les pouvoirs du juge en contentieux douanier, ce dernier ne pouvant se saisir de manière automatique de certains litiges. Certain disputes in customs law cannot be brought to court without first exploring the possibility of a transaction. Transaction offers the advantage of reducing delays and streamlining the resolution of customs disputes. This raises the question: what constitutes a customs transaction in the CEMAC sub-region? The challenge lies in understanding this procedure, which is also common in tax law. Research into this question employed a legal method, focusing on the interpretation of customs law texts in the sub-region, primarily the CEMAC Customs Code. This research reveals that transactions are a privilege to the customs administration, resulting in the cessation of frequent and vigorous prosecutions. As such, they represent a special procedure. Accordingly, this paper seeks to outline the legal framework for customs transactions and describe their implementation. The advent of transactions has, to some extent, curtailed the powers of judges in customs litigation, as certain disputes can no longer be automatically brought before them.
Keywords: Administration douanière; Customs administration; Customs disputes; Customs users; Financial interests; Intérêts financiers; Litiges Douaniers; Transaction; Usagers douaniers

Prestation caractéristique en droit international privé des contrats en Afrique francophone - Goudjo, Traouré Durve Mathieu Red (Revue africaine de droit des affaires, 2025)
Le principe en DIP selon lequel les contrats sont soumis à la loi choisie par les parties, dite loi d’autonomie, est largement remis en cause. La théorie objective conteste les fondements de la thèse subjective et les conséquences de son application. Il est admis partout que la volonté n’est qu’un indice de localisation du contrat et que cette volonté ne peut s’émanciper ni errer à la recherche d’un pays avantageux sans lien objectif avec le contrat. Mais la thèse du rattachement fonctionnel qui consiste à lier le contrat à l'ordre juridique dans lequel il déploie sa fonction économique ou sociale en identifiant cet ordre au lieu où le débiteur de la prestation caractéristique à sa résidence est discutable à nos yeux. Dans les États d’Afrique, il est nécessaire d’accorder une place beaucoup plus importante à la prestation caractéristique comme facteur de rattachement, mais ceci, par le biais de son lieu d’exécution. Cette démarche de surclassement de la prestation caractéristique dans la détermination de la loi applicable se justifie par l’essence même du contrat qui est d’être exécuté, et par la nécessité de préservation des intérêts du DIP qui dans le droit constitue la science de la tolérance et de l’acceptation des peuples dans leur diversité.

The future of a prohibition on indirect unfair discrimination as part of South African anti-discrimination employment law : a comparative reflection - Huysamen, Elsabe (Stellenbosch University, 2025)
ENGLISH ABSTRACT: The Constitution of the Republic of South Africa, 1996 (“Constitution”) enshrines the right to equality, emphasising “the full and equal enjoyment of all rights and freedoms”. This commitment embodies the principle of substantive equality, which extends beyond mere formal equality by addressing systemic inequities and striving for transformative change. The pursuit of transformative equality is underpinned by two constitutionally mandated mechanisms: affirmative action and the prohibition of unfair discrimination, both direct and indirect. Within this framework, the prohibition of unfair discrimination serves a dual purpose: It establishes a foundation for defending formal equality while simultaneously acting as a transformative tool, particularly in safeguarding against indirect discrimination. In a transformative context, the concept of protection against indirect discrimination specifically is significant as it acknowledges that equal treatment can still perpetuate inequality. The concept has the unique ability to identify hidden barriers and protect against more subtle forms of unfair discrimination, rendering it instrumental in advancing substantive equality and promoting long-term, systemic change. Yet, despite its transformative potential, the application of protection against indirect unfair discrimination in South African employment jurisprudence remains underdeveloped. And even in jurisdictions where the concept has received greater attention (for purposes of this study, the United States of America, Canada and the United Kingdom), it has not significantly advanced substantive workplace transformation. The reasons for this limited success are partly shared across these jurisdictions and partly unique to South Africa. Given the above, the primary objectives of this study are threefold: (i) to explore the protection against indirect discrimination in advancing transformative equality within the South African constitutional framework; (ii) to investigate the reasons for the limited development and application of this concept in South African employment law; and (iii) to assess whether the prohibition of indirect discrimination should be upheld as a distinct legal concept in employment law. These objectives were anchored by the fundamental question guiding the study: what role does the concept stand to play in employment law in SA in future and, if any, to what extent and in what form? The study begins by examining the broader concept of equality – a notion that is both complex and continually evolving. Key questions that are addressed include: What does equality mean? What are the objectives inherent to equality? What values underpin the concept? Following this exploration, the focus shifts to the role of equality within the South African Constitution, specifically the content of the right to equality as provided for in section 9 of the Constitution. This includes an overview of the constitutionally mandated mechanisms for enforcing equality, namely affirmative action and the prohibition of unfair discrimination, with particular attention to protection against indirect forms of unfair discrimination. The study thereafter narrows its focus to the application of the latter concept within South African employment law. It highlights the challenges that have hindered the effective development of the concept, which can be broadly categorised as conceptual and practical obstacles. The South African experience is compared to the development and application of the concept in the United States, Canada, and the United Kingdom, offering a comparative perspective on the concept’s evolution in the aforesaid jurisdictions. The study concludes by presenting suggestions and recommendations on the future role of indirect discrimination within South African anti-discrimination employment law. It also recommends strategies for more effective implementation of the concept.
Keywords: Affirmative action programs; Discrimination in employment; Employment; Labor laws and legislation; Law reform; South Africa; Unfair labor practices

Money Laundering: New Technologies and Control Challenges (Cryptocurrencies, Blockchain) - Kontogeorgis, Georgios (International Multilingual Journal of Science and Technology, 2025)
Tackling corruption is a global issue and tackling it effectively requires determination, cooperation and specialised technological knowledge. A significant proportion of global GDP is the sum of the money associated with corruption and fraud. The main objective of this article is to assess how new technologies such as cryptocurrencies and blockchain can combat corruption. The methodology of this article is a literature review. Specifically, scientific articles from databases and international organizations with expertise in new technologies are studied. This article deals with the new ways of corruption and money laundering. New technologies and the knowledge of them are a very important element in order to deal effectively with corruption. Perpetrators of financial crimes are usually ahead of the auditing authorities in terms of techniques and therefore knowledge of the new technology and the possibilities it offers is essential to effectively combat corruption and fraud globally. Cryptocurrencies and blockchain can combat corruption primarily due to their key characteristics of transparency, security, and decentralization. A key prerequisite for the transparency of cryptocurrencies is the application of supervision rules by the responsible authorities and the implementation of blockchain technology. In practice this is often not the case and cryptocurrencies are used as a money laundering tool.
Keywords: Corruption; Cryptocurrencies; Fraud; Money laundering; New technologies

Social justice at the Commission for Conciliation Mediation and Arbitration (CCMA) and the critical role of the commissioner - Letlonkane, Katlego (Stellenbosch University, 2025)
ENGLISH ABSTRACT: This study provides exploratory insight into the social justice mandate of the Commission for Conciliation Mediation and Arbitration (“CCMA”) in the context of labour relations in South Africa. As a vehicle for the advancement of social justice through the efficient resolution of labour disputes, the CCMA is a compelling actor in the pursuit of social justice in South Africa’s labour environment. Social justice as a legislative and policy imperative requires an investment in understanding its conceptual ideals and demands in order to empower those acting in its pursuit with the knowledge they need to fulfil its demands. The CCMA’s most critical functionary, its commissioner, holds the key to unlocking labour justice for many members of the public. One wonders, given the criticality of advancing social justice in labour relations, whether social justice is appropriately understood in order to enable the kind of decision-making that efficiently and consistently addresses the workings of power and inequality as they manifest in employment relationships. This study’s main provocation is to transform the pursuit of social justice (in the South African labour context, at least) from an elusive endeavour to a more tangible, realistic one. It attempts to offer a way of thinking about and applying social justice in the practice of labour dispute resolution in South Africa and the CCMA context. It critically explores the interwoven mechanisms of power, prejudice, and injustice and how these mechanisms work to sustain unequal labour relations. The commissioner’s role is thus a critical one, that involves a deliberate pursuit to recognise, understand and interrupt these movements of power and mitigate the effect of inequality. Any movement towards social justice that does not pay close attention to this matrix of power and prejudice threatens to dilute the transformative potency of social justice. This study identifies and discusses the decisions of commissioners that fall short of the kind of conscientious decision-making required by a mandate of social justice. Discussions in this study also point out significant achievements in centralising social justice principles in decision-making processes at the CCMA, where arbitrators, in reducing injustice and advancing justice in labour relations, show a conscientious consideration and appreciation of historical contexts, power, privilege and disadvantage. Living up to the constitutional imperative to transform society in the way of equality, commissioners ought to develop their agency and be empowered by the Constitution of the Republic of South Africa, 1996, to disrupt inequality. This study contributes to the understanding and clarification of social justice and its implications for the South African labour environment. It also posits ubuntu as an important consideration in the balancing exercise required to achieve justice.
Keywords: Arbitration; CCMA; Commission for Conciliation; Mediation; and Arbitration; Dispute resolution (Law); Mediation; Mediation and conciliation; Industrial; Officials and employees; Social justice

De quoi l'article 22 de l’Acte uniforme sur les sûretés est-il le nom ? - Mfini, Mon-espoir (Revue africaine de droit des affaires, 2025)

Eppur si muobe ! Et pourtant, on peut bien supprimer le dessaisissement - Mfini, Symphorin Angy Mon-espoir (Revue africaine de droit des affaires, 2025)
Keywords: Action paulienne; Créancier; Dessaisissement; Débiteur; Procédures collectives

L’office du juge en matière de divorce par consentement mutuel - Ndiaye, Ndeye Amy (Afrilex : Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2025)
Au Sénégal, depuis l’entrée en vigueur du Code de la Famille, le législateur a définitivement opté pour la judiciarisation de la rupture du lien matrimonial. La version faite à l’amiable, plus connue sous le nom de divorce par consentement mutuel, est souvent qualifiée de souple, d’équitable, de commode et d’un peu plus conforme à la culture sénégalaise. Par ailleurs, une lecture beaucoup plus fine des textes combinée à une analyse plus poussée de la réalité, démontre que ce type de divorce n’est pas ou ne devrait pas être aussi simpliste que certains le pensent. A l’épreuve de la pratique, il soulève des difficultés qui n’ont pas été complétement abordées ni réglées expressément par le législateur sénégalais encore moins par la doctrine . Le présent article souligne l’importance de l’office du juge en la matière, en dépit de l’apparente passiveté de son rôle.
Keywords: Consentement; Convention; Divorce; Homologation; Office du juge

Les arcanes du recours de l’assureur facultés en droits positifs français et africains (CEMAC et CIMA) - Ngamkan, Gaston (Revue africaine de droit des affaires, 2025)
L’assureur qui indemnise des marchandises sinistrées par suite d’un transport entend nécessairement se retourner contre l’auteur du dommage (transporteur maritime ou routier, entrepreneur de manutention, commissionnaire de transport). Pour autant, ce recours n’est jamais simple, dès lors que le responsable lui oppose quasi-systématiquement une fin de non-recevoir, le plus souvent tiré du défaut de qualité ou d’intérêt, notamment lorsqu’il fonde son recours sur la subrogation légale prévue par des textes spéciaux du droit de transport maritime ou terrestre. D’après ces textes, l’assureur n’est autorisé à recourir contre le responsable du sinistre que pour autant qu’il a réglé l’indemnité d’assurance. Il doit donc rapporter deux preuves : le paiement effectif de l’indemnité d’assurance et la légitimité de ce paiement, lequel doit être un paiement imposé par la police d’assurance. De façon générale, les tribunaux font preuve d’une appréciation rigoriste de ces conditions, précisément en déclarant irrecevables pour défaut de qualité de nombreux recours des assureurs, faisant peser sur ces derniers une suspicion qui est loin d’être légitime et donnant parfois l’impression de faire le procès des assureurs qui ne font pourtant qu’exercer les actions leurs assurés-victimes. Devant cette escalade de rigueur des tribunaux dans la mise en œuvre des textes du droit spécial, par la médiation de leurs conseils avisés et futés, les assureurs ont fait preuve de perspicacité et ont imaginé des voies d’évitement destinées à tempérer l’extrême sévérité de la jurisprudence. C’est ainsi qu’ils ont recours avec bonheur, outre la subrogation légale du droit des transports, à la subrogation légale de droit commun de l’article 1251 alinéa 3 du Code civil (art. 1346 du Code civil français) et à la subrogation conventionnelle de l’article 1250-1 du Code civil (art. 1346-1 du Code civil français). Et, lorsque les conditions de ces subrogations du Code civil ne sont pas réunies, l’assureur faculté a beau jeu de recourir à des succédanés de la subrogation, lesquels sont : la cession de droits dans les conditions prévues par l’article 1690 du Code civil et la théorie de l’enrichissement injuste, ce grand principe général du droit qui prescrit que nul ne peut s’enrichir injustement aux dépens d’autrui. En l’état actuel de la jurisprudence, l’assureur qui exerce un recours contre le transporteur ou tout autre maillon de la chaine de transport dispose de plusieurs flèches dans son carquois dont il a le libre choix. Il y a donc, à l’évidence, un apaisement du contentieux dans la jurisprudence judiciaire, laquelle rejoint, sur ce point, la jurisprudence arbitrale, assurant de la sorte une certaine péréquation entre les deux ordres judiciaires, toute chose qui mérite un satisfecit sans réserve.

La responsabilité civile des experts-comptables dans le droit de l’OHADA - Ngue, Elise Rolline (Revue africaine de droit des affaires, 2025)
Dans le cadre de l'OHADA, la responsabilité civile des experts-comptables vise à protéger les parties prenantes tout en assurant la sécurité juridique de la profession. Le cadre juridique repose principalement sur l'Acte uniforme portant sur le droit comptable et à l'information financière (AUDCIF), sur l'Acte uniforme relatif au droit commercial général (AUDCG) et sur l'Acte uniforme relatif au droit des sociétés commerciales et du groupement d'intérêt économique (AUSCGIE). Ces textes établissent les fondements de la responsabilité des experts-comptables vis-à-vis des clients et des tiers. La responsabilité civile de l'expert-comptable dans l’espace OHADA est régie par une obligation de moyens. Cela signifie que, bien que l'expert-comptable soit tenu d'utiliser toutes ses compétences pour fournir un service conforme aux règles comptables et juridiques, il n'est pas tenu à une obligation de résultat, sauf dans des cas spécifiques. De plus, il peut être tenu responsable vis-à-vis des tiers lorsqu'une faute commise dans l'exercice de ses fonctions leur cause un préjudice direct. Cependant, des limites existent dans la régulation actuelle, notamment en ce qui concerne la protection des tiers et la question des délais de prescription. En parallèle, des mécanismes de protection sont mis en place pour sécuriser la pratique professionnelle de l'expert-comptable. Ces protections incluent les clauses limitatives de responsabilité, les causes d’exonération (comme la force majeure ou la faute du client), ainsi que des assurances professionnelles couvrant les risques liés à la responsabilité civile. Les ordres professionnels jouent également un rôle clé en encadrant la déontologie et la discipline des experts-comptables, apportant une garantie supplémentaire aux clients et une certaine immunité disciplinaire aux experts-comptables en cas de faute mineure. Enfin, des perspectives d'amélioration du cadre juridique sont nécessaires pour renforcer l’équilibre entre la protection des parties prenantes et la sécurité juridique des professionnels. Cela inclut une réforme visant à clarifier certaines dispositions légales et à encourager une répartition plus juste des risques entre experts-comptables, clients et tiers.

La mise en œuvre de la médiation institutionnelle en droit OHADA - Oueina, Florent; Oussale, Aladji Aberridjoua Aubin Hugues (Revue africaine de droit des affaires, 2025)
Il ne suffit pas d’adopter un nouvel Acte uniforme pour satisfaire à la demande ou garantir une sécurité juridique apparente du droit africain des affaires ou encore enrichir le régime uniforme du règlement des différends dans l’espace OHADA ; ou même pallier le vide législatif qui existait encore au sein de l’OHADA sur la médiation. Il ne s’agit pas d’un Acte uniforme de plus, mais d’un réel instrument juridique qui pourrait favoriser le retour des investisseurs et améliorer les conditions des affaires dans l’espace OHADA. Il faut chercher à savoir si cette nouvelle approche de la justice sera une réussite dans ledit espace.

L'indépendance du commissaire aux comptes en droit OHADA des sociétés commerciales - Oulando, Massongo Kodjo (Revue africaine de droit des affaires, 2025)
Les pouvoirs et missions du commissaire aux comptes se sont accrus, allant de la mission principale de certification des comptes sociaux à des missions annexes d’information, de garantie d’égalité entre associés et de pérennité de l’entreprise. Au regard de l’importance de ce contrôleur légal, le législateur OHADA a, sous certaines conditions, généralisé sa présence dans les sociétés commerciales. Dans son office, il doit revêtir les vertus d’un contrôleur indépendant. Condition sine qua non de l’efficacité de sa mission, cette indépendance est consacrée par le législateur OHADA à travers notamment la prévention des situations possibles de dépendance et l’érection de certaines garanties préventives et curatives d’indépendance. Toutefois, un certain nombre de facteurs, résultant tant de la législation que de la pratique, sont potentiellement sources d’affaiblissement de cette indépendance recherchée, rendant nécessaire un meilleur renforcement afin de permettre à cet « organe supra social » de remplir pleinement sa mission de contrôle.

L’infraction douanière en droit camerounais - Sassie Dob, Thomas (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
L’infraction douanière en droit camerounais est une infraction particulière. De quoi tient-t-elle cette particularité ? Voici l’interrogation autour de laquelle la présente étude s’est construite. Il s’est alors révélé que la particularité de l’infraction douanière en droit camerounais a une origine double c’est-à-dire qu’elle le tient aussi bien de ses critères d’identification que de sa qualification légale. Ainsi, contrairement à l’infraction pénale ou de droit commun qui exige la réunion des critères légal, matériel et moral pour sa détermination, l’infraction douanière ne conditionne son identification qu’à la réunion des critères d’ordre légal et matériel qualifiés de critères décisifs. Leur seule mise en évidence suffit pour identifier une infraction douanière. Le critère moral lui n’est qu’adventice ou accessoire. Aussi, dans sa qualification légale, l’infraction douanière répond à une classification bipartite. Ceci sous-entend que le droit douanier ne reconnait que les délits et les contraventions comme infractions. Il n’existe donc pas de crimes en matière douanière comme en matière pénale. Customs offences under Cameroonian public law are special. What makes it so special? This is the question on which this study is based. It has emerged that the special nature of customs offences in Cameroonian public law has a dual origin, i.e., it derives from both the criteria by which they are identified and their legal classification. Thus, unlike a criminal offence or an offence under ordinary law, which requires legal, material and moral criteria to be met in order to be identified, a customs offence can only be identified if the legal and material criteria, described as decisive criteria, are met. Their mere presence is sufficient to identify a customs offence. The moral criterion is only incidental or accessory. In its legal classification, customs offences are classified in two categories. This means that customs law recognizes only misdemeanor ours and contraventions as offences. There are therefore no crimes in customs law as there are in criminal law.
Keywords: Cameroon; Cameroonian law; Cameroun; Customs offence; Droit camerounais; Infraction douanière

La responsabilité civile sur les marchés financiers : les limites de la réglementation des valeurs mobilières quant à la protection des investisseurs en cas de pratiques abusives - Shab Afrouz, Shahrzad (Université de Montréal, 2025)
Ce mémoire étudie les limites de la réglementation des marchés financiers quant à la protection des investisseurs en cas de pratiques abusives et la responsabilité civile des défendeurs quant aux pertes économiques. Il compare les recours disponibles à l’investisseur prévu par le régime de responsabilité civile de la Loi sur les valeurs mobilières du Québec et le droit commun. Il établit l’importance de revoir les mécanismes de protection des investisseurs sur une base régulière pour assurer la stabilité des marchés financiers, tout en reconnaissant que la mise en œuvre de la réglementation des valeurs mobilières joue un rôle important dans la confiance du public sur les marchés financiers. Ce mémoire discute du défi auquel l’investisseur fait face quant au recouvrement des pertes attribuées à une faute commise sur les marchés financiers, particulièrement le défi de l’obtention de l’autorisation préalable du tribunal et de la preuve de causalité. Il faut reconnaitre que, pour établir un équilibre entre la protection des investisseurs et l’efficience des marchés, la coexistence du recours privé et public est nécessaire. Ces mesures ont pour objectif de décourager les pratiques déloyales sur les marchés financiers. De plus, l’étendue des dommages de l’investisseur doit être revue périodiquement et considérée à la lumière du contexte économique en cours pour assurer la cohérence du régime de responsabilité civile. En effet, il est important d’adopter une limite de responsabilité civile qui tient compte de l’aversion au risque de chacune des parties et qui ne désavantage pas l’une d’elles de manière excessive. Ceci permet d’atteindre un meilleur équilibre entre l’intérêt des investisseurs et les acteurs des marchés financiers, et de limiter le risque de poursuites opportunistes.
Keywords: Aversion au risques; Civil liability; Investissements; Investisseur (protection); Investments; Investor protection; Limites de responsabilité; Limits of liability; Marché financier; Protection des investisseurs; Responsabilité civile; Risk aversion; Valeurs mobilières

La protection juridique des majeurs : étude comparative entre les droits français, égyptien et koweïtien - Althafiri, Meshal (Université de Bordeaux, 2025)
Le droit des personnes protégées se présente, aujourd’hui, en France, comme un sujet d’actualité de premier rang en occupant un espace considérable dans les tables rondes des conférenciers, chercheurs et juristes français. Le sujet du droit des personnes protégées a toujours été un sujet d’actualité au Koweït. La particularité du système législatif de ce pays, se déclarant dans sa constitution comme étant un pays musulman dont la loi islamique est une des sources principales de sa législation, provient de la combinaison, souvent problématique, entre cette dernière et les deux autres sources majeures que sont la « Common Law » et le droit civil/roman germanique. L’évolution des législations koweïtiennes en vigueur est une nécessité omniprésente qui s’impose à chaque fois que le législateur fait face à l’évolution de la société. Parmi les pays du Golfe, le Koweït a été un des premiers a toujours manifesté sa volonté de suivre l’évolution sociale et économique à l’échelle internationale en s’inspirant de l’exemple occidental dont la France constitue une des figures les plus intéressantes, surtout au niveau législatif. L’intitulé d’un tel travail pourrait être « La protection juridique des majeurs ». Cette thèse vise à comparer les droits français, égyptien et koweïtien. Surtout que les trois droits ne prévoient pas les mêmes garanties, malgré leur affirmation de garantir cette protection. En ce qui concerne le droit français, avec ses multiples sources : droit interne, communautaire et international, il a instauré un système solide et riche, doté de vrais moyens et d’une série d’institutions publiques et privées veillant à garantir la protection juridique des majeurs. Cependant, le système est loin d’être parfait. Des efforts sont toujours déployés à tous les niveaux afin de combler les lacunes persistantes. Le droit koweïtien et le droit égyptien, quant à eux, disposent des systèmes assez récents, dont les sources proviennent majoritairement du droit musulman, du code civil et des conventions internationales.Il sera intéressant de comparer comment les systèmes koweïtien, égyptien et français assurent et garantissent la protection juridique des majeurs. Quelles sont les garanties prévues par les trois législateurs ? Quelles sont les problématiques que vivent les trois sociétés malgré la particularité de chacune, notamment la koweïtienne dont les deux tiers de la population sont des étrangers ?
Keywords: Comparative law; Droit comparative; Egyptian; Egyptien; France; Incapacité (droit); Koweït; Koweïtien; Kuwaiti; Legal protection; Majeurs protégés; Personnes (droit); Personnes protégées; Protected adults; Protected persons; Protection juridique; Égypte; Études comparatives

Mediación y Arbitraje en Línea: Ventajas y Desafíos - Salguero, Katherine Coraima Guano; López, Vilma Patricia Salguero; Cáceres, Alez Remigio Escobar; Chávez, Luis Alberto Morales (Polo del Conocimiento, 2025)
La mediación y el arbitraje en línea han surgido como soluciones eficaces para la resolución de conflictos en un mundo digitalizado, ofreciendo ventajas como reducción de costos, accesibilidad y flexibilidad horaria. Sin embargo, enfrentan desafíos como la brecha digital y la seguridad de la información. Un estudio basado en encuestas a profesionales y usuarios confirma la utilidad de estas herramientas, pero subraya la necesidad de mejorar la infraestructura tecnológica y establecer marcos regulatorios claros. A pesar de los obstáculos, estos métodos representan una evolución significativa en la gestión de disputas legales.
Keywords: Arbitrage; Arbitragem; Arbitraje en línea; Arbitration; Brecha digital; Mediación; Mediation; ODR; Online dispute resolution

Party autonomy and the applicable law to the merits in intellectual property arbitration - Rivoire, Maxence (Arbitration International, 2025)
The freedom of the parties to choose the applicable law to the merits is often presented as an important benefit of arbitrating disputes involving intellectual property (IP). Yet, the reality is more uncertain and controversial than is commonly assumed. Is party autonomy really permitted in IP arbitration? Should it be? This article answers these questions with regard to patents, trademarks, and copyrights, using recent examples drawn from arbitral practice. It first examines the situation where the parties only made a choice of contract law, and considers in this regard whether that law can and/or should be extended to infringement claims and/or the remedies to infringement, either directly or through the technique of characterization. After discussing the impact of overriding mandatory rules in contractual IP cases, the article then examines the situation where the parties chose a law to govern IP questions, including by way of a broad choice-of-law agreement covering non-contractual problems. It seeks to provide as much guidance as possible to arbitral tribunals, using mainly the distinction among infringement, ownership, and validity issues, and by distinguishing among different scenarios in which party autonomy is more or less acceptable.
Keywords: Arbitrage; Arbitragem; Arbitration; Intellectual property; Party autonomy

Examining the Impact of Remote Work on Employees, Employers, and the State in Nigeria - Adeyinka, Mutiu Abiodun; Gbajumo-sherrif, Mariam A.; Elegbede, S. Tunde (African Journal of Economic and Business Research, 2025)
Abstract The rise of remote work, accelerated by the COVID-19 pandemic, has created significant challenges for employees, employers, and the government, complicating the management of remote teams while striving to maintain productivity and organizational cohesion. The central problem addressed in this study is the deteriorating state of employment relations marked by downsizing and layoffs, particularly in the private sector in Nigeria. This study aims to analyze the impact of remote work on these stakeholders through a systematic and thematic review based on PRISMA guidelines. Twenty four publications from 2013 to 2023 were reviewed, sourced from Google Scholar, DOAJ, Scopus, and Web of Science. The findings indicate that while organizations are beginning to adopt tools for remote work and virtual communication, these resources are primarily accessible to larger companies due to associated costs. Additionally, the study highlights the pressing need for enhanced infrastructure and structural improvements to support remote work at a societal and economic level. In conclusion, the study recommends that the government enhance infrastructural development and that organizations implement better strategies for remote work. Furthermore, individuals should pursue advancements in technology to adapt to the changing landscape. These recommendations aim to promote sustainable employment relations and economic development in Nigeria in light of the evolving digital economy.
Keywords: Employees; Employment Relations; Government; Remote Work

Libérer le potentiel commercial de l'Afrique : Stimuler les marchés régionaux et réduire les risques - Conférence des Nations Unies sur le Commerce et le Développement (CNUCED) (Nations Unies, 2025)
Rapport sur le développement économique en Afrique 2024

Effects of Dynamic Capabilities and Multichannel Integration Quality on Bank Performance; A Moderated Role of Environmental Dynamism : A Moderated Mediation Model Analysis - Geleta, Negash; Amentie, Chalchissa; Getahun, Misganu (African Journal of Economic and Business Research, 2025)
This study investigates the effects of dynamic capabilities (DCs) and multichannel integration quality (MCIQ) on the performance of banks (BP). It also explores the moderating role of environmental dynamism in the banking industry, using a moderated mediation model. Quantitative analyses were employed to examine data collected from multiple banks. Structural equation modeling (SEM) was used to test the relationships between variables, while moderation and mediation effects were analyzed using SEM-AMOS. The findings reveal that dynamic capabilities and MCIQ significantly enhance bank performance. Furthermore, environmental dynamism (ED) moderates the relationship between these variables, intensifying their effects on performance under high levels of dynamism. The mediation analysis shows that MCIQ partially mediates the impact of dynamic capabilities on bank performance. The study is limited by its cross-sectional design, which restricts causal inferences. Additionally, the findings may not be generalizable to non-banking industries or regions with distinct regulatory frameworks. The results provide actionable insights for bank managers, emphasizing the importance of fostering DCs and enhancing MCIQ to sustain performance in rapidly changing environments. The findings highlight significant social benefits, as improved dynamic capabilities (DCs) and critical information quality (MCIQ) enhance bank performance, fostering economic stability, financial inclusion, and customer trust. By enabling resilience and innovation in dynamic environments, banks contribute to broader societal goals, including sustainable development and socio-economic growth. This research contributes to the literature by integrating DCs and MCIQ in a moderated mediation framework, offering a novel perspective on their interplay with environmental dynamism in the banking sector.
Keywords: Dynamic Capabilities; Environmental Dynamism; Moderated Mediation Model; Multichannel integration quality

La contravention et le droit administratif. : contribution à l'étude du droit pénal de police - Paget-Blanc, Natacha (Université Paris 1, 2025)
La thèse propose d’étudier la spécificité des contraventions en s’interrogeant sur les liens qu’elles entretiennent avec les catégories du droit administratif. Ces infractions présentent un contenu et un régime qui les distingue des crimes et délits pour les rapprocher des sanctions administratives et mesures de police administrative. Elles sont notamment définies par voie réglementaire, faiblement soumises aux garanties pénales et dénuées d’exigence d’élément moral. Peu appréhendée par la doctrine en raison de la division disciplinaire entre droit pénal et droit administratif, cette ambivalence pose la question de la nature réelle des contraventions et de leur place au sein de l’ordonnancement juridique. La thèse soutient que les contraventions constituent une catégorie hybride située aux frontières du droit pénal et du droit administratif. Pour rendre compte de leur nature, elle propose de les concevoir comme des infractions relevant du droit pénal de police, soit la portion du droit pénal mise au service de l’efficacité de la police administrative. Ce droit prend appui sur des contraventions, délits et sanctions administratives présentant une certaine unité par leur fonction d’exécution des règlements de police. This thesis examines the specific nature of contraventions, looking at how they relate to the categories of administrative law. The content and regime of these offences distinguish them from crimes and misdemeanors, and bring them closer to administrative sanctions and administrative policing measures. In particular, they are defined by regulation, are not subject to penal guarantees and do not require a moral element. This ambivalence, which is little understood by academic writers because of the disciplinary division between criminal law and administrative law, raises the question of the real nature of contraventions and their place within the legal system. This thesis argues that contraventions constitute a hybrid category situated at the frontiers of criminal law and administrative law. To account for their nature, it proposes to conceive of contraventions as offences under police criminal law, i.e. the portion of criminal law that serves the effectiveness of the administrative police. It is based on contraventions, délits and administrative sanctions that have a certain unity in their function of enforcing police regulations.

Blanchiment des capitaux, financement du terrorisme et climat des affaires en Afrique - ERSUMA - OHADA (Ecole régionale supérieure de la Magistrature, 2025)

Conformity of Goods to the Contract of Sale under the OHADA Uniform Act on General Commercial Law: A Critical Analysis and Appraisal - Djieufack, Roland (Journal of Law and Public Policy, 2025)

La systématisation de l'appel en matière pénale au Mali - Bah, Oumar; Sissoko, Amadou (Revue Africaine des Sciences Juridiques, Administratives et Politiques, 2025)
L’appel est une voie de recours de droit commun contre un jugement rendu en première instance. Il permet, par la critique du jugement rendu par une juridiction de premier degré, de reformer ou vise à l’annuler. Seules les parties peuvent interjeter appel d’une décision rendue en matière pénale si elles ne sont pas d’accord avec le verdict du juge. Il s’agit de l’accusé et de la partie civilement responsable, mais le procureur général peut également faire appel. La victime, appelée partie civile, peut également interjeter appel. Toutefois, la partie civile ne peut interjeter appel que sur l’action civile et non sur la peine prononcée. Il y a cependant quelques complications liées à l’appel d’où la nécessité de le circonscrire dans la plus grande satisfaction des justiciables.
Keywords: Appel; Code de procédure pénale; Code pénal; Droit pénal; Mali; Systématisation

L’efficacité dans la mise en œuvre de la clause de hardship en droit burkinabè - Congo, Ibrahim Patrick (Afrilex : Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2025)
La clause de hardship permet aux parties de renégocier un contrat lorsque des circonstances bouleversent son environnement et rendent l’exécution d’une obligation excessivement onéreuse. Elle est d’importance dans un monde sujet à des crises politiques, économiques et financières. Toutefois, le droit burkinabè y consacre très peu de dispositions, voire quasiment pas. L’absence de critères et règles clairs est potentiellement source de litiges et de décisions divergentes. Afin d’éviter l’insécurité juridique et d’assurer une survie du contrat face à un imprévu substantiel, les parties doivent rédiger une clause de hardship encadrant avec précision les conditions de sa mise en œuvre. Pour ce faire, les parties peuvent recourir aux principes fondamentaux du droit des contrats, s’inspirer du droit comparé ainsi que des solutions développées par la pratique et éprouvées par la jurisprudence. The hardship clause allows the parties to renegotiate a contract when unforeseen change of circumstances disrupt its environment and render the performance of an obligation excessively burdensome. This clause is particularly significant in a world exposed to political, economic, and financial crises. However, Burkinabe law provides very few, if any, specific provisions on this matter. The absence of clear criteria and rules creates a potential risk of disputes and inconsistent judicial decisions. To prevent legal uncertainty and ensure the survival of the contract in the face of substantial unforeseen events, the parties must draft a hardship clause that precisely defines the conditions for its implementation. To achieve that, the parties may rely on fundamental principles of contract law, draw inspiration from comparative law, and refer to solutions developed through practice and validated by case law.
Keywords: Bonne foi; Contractual balance; Equilibre contractuel; Hardship; Imbalance; Imprévision; Renegotiation; Renégociation; Unforeseen change of circumstances

La protection des parties au contrat d'affacturage en droit burkinabé à la lumière de la loi n° 006-2022/alt, relative à l'activité d’affacturage au Burkina Faso - Congo, Ibrahim Patrick; Sawadogo, Félicité (Revue africaine de droit des affaires, 2025)
L’adoption de la loi n° 006-2022/ALT, du 13 juin 2022, relative à l’activité d’affacturage au Burkina Faso, marque une avancée significative dans l’encadrement juridique de cette pratique. Ce texte vise à régir une technique de financement particulière aux avantages reconnus. Cependant, il révèle une dynamique particulière dans la protection des droits de chaque partie. Reconnu comme la partie faible du contrat, l’adhérent est soumis à un régime relativement peu protecteur qui restreint sa liberté contractuelle et lui impose une obligation de garantie. Toutefois, au regard des risques encourus par l’affactureur, acteur central du mécanisme d’affacturage, la loi lui accorde une protection accrue. Cela inclut des droits renforcés en matière de garantie et de gestion des créances cédées. Bien que cette protection puisse apparaître déséquilibrée, elle se légitime par les risques financiers qu’assume l’affactureur et la nécessité d’assurer la viabilité du système d’affacturage et de sécuriser les flux économiques. La loi burkinabè instaure un cadre visant à concilier les intérêts divergents des parties, en tenant compte de leurs rôles respectifs dans le contrat. Ce qui peut dans une application pratique soulever des enjeux d’interprétation et d’équilibre.

La nouveauté contractuelle : entre liberté et intangibilité - Correa, Joseph Jean-Louis (Afrilex : Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2025)
Les défis posés par la nouveauté contractuelle, notamment face à l’idée d’une complétude du code des obligations civiles, sont réels. Bien que séduisante, cette complétude est mise à l’épreuve par des situations contractuelles inédites, exigeant une vigilance constante de l’interprète pour éviter le déni de justice. L’innovation dans les pratiques contractuelles révèle des limites des cadres juridiques traditionnels. Ces nouveaux contrats, souvent en dehors des catégories codifiées, remettent en question la rigidité du droit positif sénégalais. L’étude propose d’adapter les règles existantes aux évolutions du phénomène contractuel pour une meilleure réception des pratiques modernes. Elle plaide pour une ouverture du droit des contrats, dans le respect des principes fondamentaux. Cela nécessite une réflexion sur la gouvernance contractuelle et le rôle du juge face à des situations non prévues par la loi. The challenges posed by contractual innovation, particularly regarding the idea of the completeness of the Civil Obligations Code, are significant. While appealing, this completeness is tested by unprecedented contractual situations, requiring constant vigilance from interpreters to avoid denial of justice. Innovation in contractual practices exposes the limitations of traditional legal frameworks. These new contracts, often outside codified categories, challenge the rigidity of Senegalese positive law. The study suggests adapting existing rules to the evolution of contractual phenomena for better integration of modern practices. It advocates for opening up contract law while respecting fundamental principles. This requires a reflection on contractual governance and the role of judges in addressing situations not foreseen by the law.
Keywords: Contractual governance; Contractual innovation; Contrats innommés; Droit positif; Flexibilisation; Flexibility; Gouvernance contractuelle; Nouveauté contractuelle; Positive law; Unnamed contracts

L'équité dans l'arbitrage - Djeudjo Tankeu, Ghislain (Revue Africaine des Sciences Juridiques, Administratives et Politiques, 2025)
Le tribunal arbitral tranche le litige conformément aux règles de droit, mais cette garantie est fragile car le législateur OHADA ajoute à moins que les parties lui aient conféré mission de statuer en amiable composition. Ces amiables compositeurs sont donc des arbitres qui peuvent ne pas appliquer la loi, qui peuvent statuer en équité, ce qui implique la reconnaissance, aux arbitres, d’un pouvoir modérateur sur les obligations contractuelles litigieuses. Mais cette autorisation de statuer en amiable composition ne leur interdit pas de statuer en droit, simplement, le tribunal arbitral amiable compositeur qui appliquerait exclusivement les règles de droit, doit s’expliquer sur la conformité de celles-ci à l’équité. L’arbitrage tend aussi à la satisfaction de l’idéal du procès équitable. C’est ainsi que l’équité est une exigence dans la constitution et lors des suites du tribunal arbitral. The arbitral tribunal shall decide the dispute in accordance with the rules of law; but this guarantee is fragile because the OHADA legislator adds unless the parties have given him the mission to rule in amicable composition. These amicable composers are therefore arbiters who may not apply the law, who can rule in equity; which implies the recognition, to the arbitrators, of a moderating power over the disputed contractual obligations. But this authorization to rule in amicable composition does not prevent them from ruling in law. Clearly, the amicable arbitral tribunal which would exclusively apply the rules of law, must explain their compliance with fairness. Arbitration also tends to satisfy the ideal of a fair trial. This is how fairness becomes a requirement in the constitution and during the proceedings of the arbitral tribunal.

L’exécution forcée sur les propriétés des personnes publiques : Le cas du Cameroun, du Sénégal et de la France - Eyanga Mewolo, Anicet (Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2025)
La survivance des prérogatives de puissance publique de l’administration publique sous l’effet de l’intégration communautaire et de la diversification des revenus des personnes publiques préoccupe aujourd’hui. Traditionnellement, les personnes publiques jouissent de l’immunité d’exécution, prérogative de protection de la puissance publique contre les aliénations forcées de leurs biens. Pourtant l’étude de l’aménagement de l’exécution forcée sur les propriétés publiques au Cameroun, au Sénégal et en France permet d’affirmer la restriction de cette exécution. L’interdiction de procéder à l’exécution forcée des biens des personnes publiques, bien qu’étant limitée, est justifiée par la continuité du service public et le refus de fragmentation de la puissance publique. Cependant, cette exécution peut connaître une extension due à la métamorphose structurelle et fonctionnelle des personnes publiques. The survival of the prerogatives of public power of public administration under the effect of community integration and the diversification of the revenue of public persons is a concern today. Tradtionally, public persons get immunity from execution, a prerogative of protection of the public authorities against forced alienations of their property. But, the study of the arrangement of forced execution on public properties in Cameroon, Senegal and France allows us to affirm the restriction of this execution. The prohibition on carrying out the forced execution of the property of public entities, although limited, is justified by the continuity of public service and the refusal of fragmentation of public power. However, this execution may expand due to the structural and functional metamorphosis of public entitis.
Keywords: Cameroun; Etude comparative; Exécution forcée; Forced execution; France; Immunity; Immunité; Insaisissabilité; Personnes publiques; Property; Propriété; Public person; Sénégal; Unseizability

La vente internationale des marchandises en droit camerounais : étude à la lumière des méthodes du droit international privé - Fansi, Marcellin (Revue Africaine des Sciences Juridiques, Administratives et Politiques, 2025)
L’adhésion du Cameroun à la Convention de Vienne sur le contrat de vente internationale des marchandises n’est pas un simple effet de mode, elle recèle d’importants enjeux. Sous l’angle des méthodes du droit international privé, cette adhésion suggère la substitution d’un droit matériel contenu dans la Convention, à la méthode conflictuelle traditionnelle jugée complexe et empreinte d’incertitudes. L’ambition est alors d’offrir aux opérateurs un corps de règles claires et précises, conférant la sécurité juridique indispensable à l’essor du commerce international. Mais ces bonnes intentions législatives ne suffisent pas à elles seules pour garantir l’objectif visé. Les réalités de l’ordre juridique international caractérisé par la diversité et la complexité constituent encore de réels obstacles sur la voie du législateur. En attendant, l’efficacité du droit matériel proposé sera largement tributaire de l’attitude des parties et surtout du juge qui doivent maintenant jouer leur partition.
Keywords: Conflits de lois; Conventions internationales; Règles matérielles; Vente internationale

L’appréciation du préjudice doit-elle rester entre les mains des juges du fait ? - Faye, Fodé David (Revue africaine de droit des affaires, 2025)
La responsabilité civile offre une tribune exceptionnelle à l’expression de l’office du juge. Elle est d’ailleurs connue et reconnue comme une discipline prétorienne, c’est-à-dire formée et moulue au gré de la jurisprudence. C’est à partir de quelques dispositions y relatives dans le Code civil de 1804 que le juge français a construit l’une des disciplines les plus transversales et les plus denses en termes de spécificités et d’applications variées. Au Sénégal, l’appréciation du préjudice relevant du juge est une prérogative reconnue au juge des faits et qu’il doit effectuer au jour du jugement. Cependant, cette appréciation souveraine consacrée donne en pratique une difficulté pour le justiciable. La responsabilité civile dans les systèmes juridiques romano-germaniques se présente comme le lit de l’activité jurisprudentielle la plus fertile, à côté du droit des contrats avec lequel ils forment le droit des obligations. Sur la qualification de la faute, sur l’appréciation du lien causal, sur les caractères du dommage indemnisable et entre autres questions telles que l’appréciation du préjudice, le juge du fait dispose d’une latitude qui rend son intervention à la fois inéluctable et décisive. L’objectif de cette étude est de présenter l’état de la question et permet de mieux analyser l’office du juge dans le cadre du procès civil et plus particulièrement sur la question de l’appréciation. « Dans cette immensité d’objets divers, qui composent les matières civiles, et dont le jugement, dans le plus grand nombre des cas, est moins l’application d’un texte précis, que la combinaison de plusieurs textes qui conduisent à la décision bien plus qu’ils ne la renferment, on ne peut pas plus se passer de jurisprudence que de lois » J.-M. PORTALIS, « Discours préliminaire sur le projet de Code civil présenté le 1er pluviôse an IX », in Le discours et le Code. Portalis, deux siècles après le Code Napoléon, Litec, 2004.

Pacta sunt servanda dans le droit des obligations OHADA de lege ferenda - Goudjo, Traouré Durve Mathieu Red (Revue africaine de droit des affaires, 2025)
Dans le système juridique civiliste, le droit OHADA se déploie avec ses marques propres caractérisées par des sources hétéroclites pour un même système. C’est dans ce système juridique que la présente étude, portant sur la question cruciale, essentielle, voire unique du pacta sunt servanda se déploie. Cette étude envisage d’explorer l’un des remèdes aux difficultés du respect de la parole donnée dans le dernier projet en date d’harmonisation du droit des obligations OHADA. Ce remède semble être plus proche des spécificités africaines et s’en inspire. La solidarité[1] propre au peuple africain, la fraternité et la camaraderie d’affaire nous orientent vers la renégociation en cas de difficulté d’exécution du contrat, pour que celui-ci, conservant son caractère sacré, soit respecté. Ce recours à la renégociation pour permettre le respect des engagements est justifié par une admission largement partagée de la sacralité du principe. Seulement, l’analyse purement économique de son admission parait critiquable. La renégociation envisagée comme remède aux difficultés d’exécution du contrat devra donc se départir de sa connotation économique pour se mettre en conformité avec les réalités de l’Afrique.

La summa divisio droit public-droit privé à l’épreuve de l’évolution du droit : la pertinence controversée d’un édifice juridique résistant - Guissé, Abdoulaye (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
Cette réflexion s’inscrit dans le contexte des débats relatifs à l’actualité de la distinction classique entre droit public et droit privé au regard du développement contemporain des branches du droit. Certes, l’univers du droit est caractérisé par une distinction bien connue entre le droit public et le droit privé appelé summa divisio. Cette expression latine signifiant la « division la plus élevée » ou « division suprême » consiste à opérer une distinction entre deux catégories juridiques, notamment droit public et droit privé, considérée comme étant la division la plus fondamentale. Toutefois, l’existence des disciplines, de plus en plus difficile, à classer (empruntant, à la fois, au droit public et au droit privé), renforcée par la porosité des frontières entre droit public et droit privé, révèle que cette distinction n’est pas absolue. Ce qui permet de s’interroger sur la pertinence cette summa divisio. This reflection takes place in the context of debates relating to the topicality of the classic distinction between public law and private law with regard to the contemporary development of branches of law. Certainly, the world of law is characterized by a well-known distinction between public law and private law called summa divisio. This Latin expression meaning the “highest division” or “supreme division” consists of making a distinction between two legal categories, notably public law and private law, considered to be the most fundamental division. However, the existence of disciplines, which are increasingly difficult to classify (borrowing from both public law and private law), reinforced by the porosity of the boundaries between public law and private law, reveals that this distinction is not absolute. Which allows us to question the relevance of this summa divisio.
Keywords: Droit privé; Droit public; Private law; Public law; Summa divisio

La citoyenneté fiscale et le numérique en droit camerounais - Gwos, Joachim Ivan (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
Le Cameroun a entrepris depuis une quinzaine d’années de réglementer et de réguler le secteur du numérique afin de protéger, mais surtout de conserver sa souveraineté dans ce nouvel espace offrant des possibilités quasi infinies et qui n’ont de limites que la force de l’imagination humaine. Cet encadrement juridique vise davantage à sécuriser et à garantir le pouvoir financier de l’Etat qui repose à titre principal sur les prélèvements obligatoires des citoyens. Ainsi, les matières imposables reconnues par le droit camerounais doivent, dans le physique comme dans le numérique, pouvoir être recouvrées par l’Administration fiscale grâce au civisme des citoyens. Le numérique permet ainsi aux citoyens d’accomplir leurs droits et obligations fiscaux avec plus de facilité. Cette modernisation de la citoyenneté fiscale empreinte de facilités, accentue cependant les risques d’incivisme. Ainsi, au-delà de toute volonté d’éviter l’impôt, le droit camerounais est, en l’état actuel, permissible à l’incivisme fiscal. Over the past fifteen years, Cameroon has undertaken to regulate the digital sector in order to protect and, above all, preserve its sovereignty in this new space offering almost infinite possibilities, limited only by the power of the human imagination. The aim of this legal framework is to secure and guarantee the financial power of the State, which is based primarily on compulsory levies on citizens. Thus, the taxable matters recognised by Cameroonian law must, in both physical and digital form, be recoverable by the tax authorities thanks to the civic-mindedness of citizens. Digital technology therefore makes it easier for citizens to fulfil their tax rights and obligations. However, this modernisation of tax citizenship, marked by ease of use, also accentuates the risks of incivility. Thus, beyond any desire to avoid tax, Cameroonian law is, in its current state, open to tax incivility.
Keywords: Cameroonian law; Citoyen fiscal; Citoyenneté fiscale; Civisme fiscal; Droit camerounais; Information fiscale; Tax citizen; Tax citizenship; Tax information

Whistleblowers and their role in the fight against corruption. Problems in protecting whistleblowers and suggestions for improvement - Kontogeorgis, Georgios (International Multilingual Journal of Science and Technology, 2025)
Whistleblower protection is necessary to reduce mismanagement in private and public organisations worldwide. The protection of whistleblowers is a complex and particularly challenging task that it is up to national authorities. The research methodology is the literature review. In this context, reputable scientific journals, reports from international organisations and websites dealing with the research field of whistleblowers are studied. The main conclusions are that there is an institutional framework for the functioning and protection of whistleblowers, but best practices are not fully implemented. Furthermore, the effectiveness of the use of whistleblowers is extremely high in detecting fraud and high public risks compared to other audit techniques. For this reason, the protection and framework of the whistleblower process is increasingly being legislated for by more and more countries as their importance is recognised. Finally, monitoring the use of whistleblowers and applying best practices and criteria for their effectiveness will make their use more effective.
Keywords: Corruption; Criminal activities; Financial Crime; Fraud; Whistleblower

Le recouvrement forcé de l’impôt contre les personnes publiques en droit fiscal camerounais - Maoh Maoh, Maurice (Afrilex : Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2025)
Au Cameroun, les personnes publiques contribuable sont souvent contraintes au paiement de leurs dettes d’impôt par la mise en œuvre du recouvrement forcé. Si une telle pratique peut a priori paraître légitime dans son fondement, elle devient sujet à caution une fois dirigée contre un sujet de droit en situation d’exorbitance. Le recours à l’exécution forcée contre elles apparait aux yeux du chercheur comme un acte insolite digne d’être questionné. A travers la mobilisation de la méthode juridique avec une emphase sur la dogmatique, le régime applicable aux personnes publiques en matière de recouvrement forcé de l’impôt a été scruté pour parvenir aux résultats de la présente recherche. En effet, le recouvrement forcé est en principe neutralisé par les privilèges particuliers de la personne publique. Toutefois, le recouvrement forcé des impôts dont elles sont redevables est rendu possible par le recours aux succédané de voies d’exécution malgré leur précarité. In Cameroon, public entities often face forced tax collection measures. Such a practice may gives a great deal of trouble to public authorities according to their missions of satisfying the general interest. The usage of forced execution against public entities has been questioned. An anlysis of the question from a legal perspective reveals that we are in the presence of a regim that reconciles the specificity of public entities and the optimisation of tax revenue. Therefore, forced tax collection measures are neutralized by the special privileges of those entities. Exceptionnaly, by mobilizing substitutes measures, public entities can be forced to pay their taxes.
Keywords: Cameroon; Cameroun; Exécution forcée; Forced recovery; Immunité d’exécution; Impôt; Personne morale de droit public; Public entities; Recouvrement forcé; Tax collection

An analysis of the challenges in combatting money laundering within Bureaux de Change establishments in Botswana - Mokone, Philadelphia Pontsho (Journal of Money Laundering Control, 2025)
PURPOSE : Financial institutions such as Bureaux de Change are susceptible to money laundering, posing a significant risk to a nation’s financial stability and security if not properly regulated and supervised. Botswana is a member of the Financial Action Task Force (FATF), a global organisation that sets standards, promotes policies to prevent money laundering, terrorist financing and arms proliferation, all to safeguard the global financial system. Efforts have been made to incorporate FATF recommendations on money laundering into the fiscal laws of Botswana. However, some deficiencies still remain. Although there are no recorded cases of money laundering in Botswana, Bureaux de Change entities are susceptible to it as their business involves cash transactions and rapid money transactions. This paper aims to analyse the challenges faced by Bureaux de Change entities in combating money laundering in Botswana. This will be done by assessing the effectiveness of the current regulatory framework and role of the regulatory authorities in combating money laundering within Bureaux de Change entities. DESIGN/METHODOLOGY/APPROACH : This paper provides a comprehensive examination of the obstacles faced by Bureaux de Change entities in Botswana when it comes to combating money laundering. A qualitative research method and doctrinal research method are both used in this context. FINDINGS : It is hoped that policymakers and other relevant persons will adopt the recommendations provided in the paper to enhance the curbing of money laundering in Botswana. RESEARCH LIMITATIONS/IMPLICATIONS : This paper is only limited to the regulation of money laundering within the Bureaux de Change entities in Botswana and does not provide empirical research. PRACTICAL IMPLICATIONS : This paper is useful to policymakers, lawyers, law students and regulatory bodies especially in Botswana. SOCIAL IMPLICATIONS : This paper suggests changes to the Bank of Botswana (Bureaux de Change) Regulations of 2004 to improve their effectiveness, robustness and competitiveness in combating money laundering. ORIGINALITY/VALUE : This paper is original research on the challenges of combating money laundering within Bureaux de Change entities in Botswana.
Emerald Publishing Limited
Keywords: Botswana; Bureaux de Change; Cash transactions; Financial security; Financial stability; Money laundering; Risk; Supervision

La responsabilité du dirigeant social pour insuffisance d’actif en droit de OHADA - Njonga Moukala, Simon de Gaulle (Revue africaine de droit des affaires, 2025)
Le chef d’entreprise qui, par sa faute, occasionne la défaillance économique de son entreprise, engage sa responsabilité. Sur quel fondement une telle responsabilité peut-elle être recherchée ? L’action en comblement du passif prévue à l’article 183 de l’acte uniforme relatif aux procédures collectives d’apurement du passif vise à engager la responsabilité pour insuffisance d’actif des dirigeants sociaux. Calque de la responsabilité civile de droit commun, la responsabilité pour insuffisance d’actif est engagée par la réunion du tryptique : faute de gestion, préjudice et lien de causalité. En cas de faute de gestion ayant contribué à l’insuffisance d’actif, les dettes de la personne morale seront supportées en tout ou partie, avec ou sans solidarité, par tous les dirigeants ou certains d’entre eux. Le tribunal dispose d’un pouvoir d’appréciation considérable lui permettant de décider de celui ou de ceux des dirigeants qui supporteront le passif ainsi que du montant supporté. Toutefois, celui-ci ne peut être supérieur au montant de l’insuffisance d’actif. La procédure collective peut même être étendue au dirigeant qui n’a pas acquitté le passif créé par sa faute. Il s’agit donc d’une responsabilité spéciale, dérogatoire de la responsabilité civile de droit commun.

La séparation entre la propriété et le pouvoir dans les sociétés commerciales régies par le droit de l'OHADA - Njonga Moukala, Simon de Gaulle (Revue Africaine des Sciences Juridiques, Administratives et Politiques, 2025)
La propriété et le pouvoir entretiennent un lien très étroit dans la mesure où les détenteurs du capital social, en leur qualité de propriétaires, s’illustrent généralement par leur propension à vouloir exercer le pouvoir au sein de la société commerciale dont la majorité des titres sociaux sont détenus, à vouloir diriger, administrer, contrôler la société. Le législateur OHADA permet de rompre un tel lien en offrant la possibilité de désigner des dirigeants qui n’ont pas la qualité d’associé ou même des tiers en qualité d’administrateurs. Il y a donc une volonté manifeste de dépatrimonialisation du pouvoir : les associés, propriétaires, ne sont plus nécessairement détenteurs du pouvoir décisionnel au sein de la société. Les associés minoritaires ou commanditaires sont quasiment insignifiants dans le fonctionnement de la société dont les grandes orientations sont décidées par les associés majoritaires ou les associés commandités, alors qu’ils ont tous sans exception, participer à la constitution du capital social.
Keywords: Capital social; Contrôlaire; Contrôle; Dépatrimonialisation; Pouvoir; Propriété

Implementation of safeguard measures in digital trade to protect African domestic industries and platforms - Rotich, Nelly Chepngetich (University of Pretoria, 2025)
As technology continues to advance, more trade is moving online. The increase in digital trade brings with it both opportunities and challenges in the international trade field. The increase in digital trade could for instance result in a spike in digital trade imports which may subsequently cause or threaten to cause serious injury to domestic industries and platforms dealing in like or directly substitutable digital data/content and services. This would necessitate the application of safeguard measures to avert any such serious injury or threat to serious injury caused to the domestic industries and platforms. The procedure for applying safeguard measures to digital trade currently is unclear. The current legal framework on safeguard measures does not apply to digital trade despite increased digital trade over the years. Thus, this study explores the prospects and practical challenges relating to safeguard measures’ application to digital trade with a specific focus on African domestic industries and platforms. While domestic industries and platforms in any part of the world could be affected by surges in digital trade imports, Africa is in a precarious position. Intra-Africa digital trade volumes could be increased and disadvantages of African domestic industries and platforms by surges in digital trade imports could be prevented through regulation and judicious use of safeguard measures. This study established the need to regulate to tap into the potential of digital trade and prevent African industries and platforms from falling behind and from the disadvantage of market dominance by big techs from outside Africa. In conclusion, the study noted legal and institutional gaps in the application of safeguard measures to digital trade. The study has recommended that specific institutions at the global, continental and national levels take necessary actions to build a clear and robust framework for safeguard measures in digital trade.
Keywords: Digital trade; International Trade

Sous-traitance de la prestation de sécurité privée civile en droit burkinabé - Somda, Laurent Saâtieme (Revue africaine de droit des affaires, 2025)
Des conditions irrégulières de recrutement aux violences physiques et morales en passant par l’absence ou violation du droit du travail et de la Sécurité sociale, le retard, voire le non-versement des salaires, des conditions inhumaines de travail, de la réduction des agents en domestiques par certains bénéficiaires de service, absence d’agrément de certaines SPS, les licenciements abusifs, les SPS fictives, la précarité des engagements, des salaires abusivement bas, le non-respect du SMIG, les traitements arbitraires et discriminatoires, sont autant de difficultés auxquelles sont confrontés nombres d’agents des Services Privé de Sécurité (SPS) au Burkina Faso. Derrière la création d’emplois dont se prévalent ces SPS, sommeille « une funeste arnaque sur fond d’esclavage des temps modernes ». Et depuis quelques décennies, cette situation délétère ne fait que se détériorer, car le secteur de la sécurité privée, jadis assuré par chaque entreprise, s’externalise de plus en plus par le recours à la sous-traitance. Si cette pratique très en vogue dans le monde des affaires et très favorable au PME s’adapte à beaucoup de secteurs d’activité, il n’est pas sans intérêt de nous interroger sur son application dans le secteur des SPS au Burkina Faso. En d’autres termes, dans un contexte d’insécurité larvée, la réflexion sur l’encadrement juridique et institutionnel de la sous-traitance dans le secteur sensible des activités des SPS n’est pas inopportune et appelle à une vigilance plus accrue de la puissance publique.

La summa divisio des droits patrimoniaux et des droits extrapatrimoniaux : étude critique - Sounon Tamou, Abdou Soumaïla (Revue africaine de droit des affaires, 2025)
Pendant longtemps, la summa divisio des droits patrimoniaux et des droits extrapatrimoniaux a paru très simple et loin de susciter de débats. C’était sans compter avec le fait que le monde change très vite et que ce qui était patrimonial pouvait, d’un moment à un autre, basculer dans le domaine de l’extrapatrimonial et vice-versa. Effectivement, le doute sur l’exactitude de la distinction est né, de sorte que l’on trouve qu’une étude critique sur la summa divisio des droits patrimoniaux et des droits extra-patrimoniaux est devenue nécessaire. En effet, les deux critères qui sous-tendaient cette distinction, à savoir, la pécuniarité et la cessibilité, ont tous été jugés insuffisants, notamment par une grande partie de la doctrine. Certains n’hésitent même plus à souhaiter que les frontières entre droits patrimoniaux et droits extrapatrimoniaux soient redéfinies. C’est pourquoi, cette la réflexion qui se veut bien critique, pose la question fondamentale de savoir si la summa divisio des droits patrimoniaux et des droits extrapatrimoniaux peut encore être considérée comme la summa divisio des droits subjectifs. L’opinion dominante relève un recul de cette grande division des droits subjectifs. Ce n’est cependant pas pour autant qu’il faille l’abandonner. Ce qu’il sera utile de faire, c’est de procéder à une redéfinition des critères de la distinction. L’on préconise le maintien de la distinction classique avec le constat qui appelle nécessairement des réglages, tantôt de la patrimonialisation des droits extrapatrimoniaux, tantôt de l’extrapatrimonialisation des droits patrimoniaux.

Reflections on legal complexities in the liquidation of microfinance institutions in CEMAC - Tamboli, Nda Aubin (Revue Africaine des Sciences Juridiques, Administratives et Politiques, 2025)
The CEMAC legislator sets out via Regulation No 02/14/CEMAC/UMAC/COBAC of 25th April 2014 on the management of credit institutions in difficulty to ensure harmonisation of liquidation operations for credit institutions and microfinance institutions. However, the co-existence of a dual regime for liquidation operations makes the procedure cumbersome and complex. The latter is glaring in the distinction of the assets of a MFI into different compartments. Adopting the doctrinal research method, the paper sets out to critically examine the complexities in liquidation operations inherent in the 2014 regulation. It reveals that the co-existence of the banking and non-banking compartments render liquidation operations cumbersome, and recommends the adoption of a regulation that is specifically adapted to the management of liquidation operations in MFIs.

Les principes comptables de l’OHADA à l’ère de la comptabilité informatisée - Tankoano, Gnoari (Revue africaine de droit des affaires, 2025)
Dans un environnement des affaires marqué par l’omniprésence des technologies de l’information et de communication, le législateur OHADA a fait l’option de renforcer et de moderniser son arsenal juridique face aux défis posés par l’usage des outils numériques dans la pratique comptable. En effet, certes, les principes classiques régissant l’élaboration, la tenue et la sécurité des comptes ainsi que les comportements des comptables restent d’application. Du reste, l’étude a dédié à ces principes des analyses appréciables. Cependant, les nouvelles règles permettent de hisser ces principes classiques à la hauteur des défis de la digitalisation de l’activité comptable. Elles concourent à l’impératif de fiabilité, de sécurité, d’authenticité et d’intégrité de l’information comptable, face aux risques d’altération aisée, de fugacité, de surpression et de modification d’une information automatisée. Toutefois, la couverture du droit OHADA à cette nouvelle réalité n’est que partielle et ne parait pas approfondie. Pour une matière qui fait rarement l’objet d’études approfondies par les juristes, notre article, tout en révélant les innovations et les défis, jette les bases de réflexions. Cet exercice est essentiel au regard de la double technicité du sujet abordé, tenant, d’une part, à son objet, à savoir la comptabilité, et d’autre part, à la prise en compte des technologies de l’information et de la communication. En effet, non seulement, l’étude permet aux entités et praticiens d’avoir une meilleure compréhension des principes comptables modernes, mais aussi, elle offre aux contrôleurs des outils d’analyse de la conformité, et aux juges une compréhension et interprétation plus éclairées de cette discipline singulière. Les propositions qui en ressortent permettront au législateur de combler les incohérences et insuffisances juridiques afin de répondre plus efficacement aux défis de la digitalisation de la comptabilité.

Les institutions de régulation au Cameroun - Tchoumen Ngongang, Mérimé Aimé (Revue Africaine des Sciences Juridiques, Administratives et Politiques, 2025)
L’examen des institutions de régulation a pour objectif de mettre en équilibre le principe de concurrence. Cet objectif se situe au cœur des missions essentielles de l’État dans l’optique d’une vie sociale harmonieuse qui prenne en compte les intérêts de toutes les entités ; individuelles ou collectives, publiques ou privées. Il s’agit en effet à la fois de la normalisation de la société, des activités économiques, et de manière plus significative, la mission de contrôle du fonctionnement du marché par l’Etat. Dans une économie libérale, l’Etat a en effet, pour mission, de s’assurer que les opérateurs économiques agissent vis-à-vis des consommateurs et de leurs concurrents dans des conditions conformes aux règles du droit économique et en respect de la règlementation, ceci conformément aux règles du marché et au droit de la concurrence. La protection des consommateurs et la préservation d’une saine concurrence entre différents actes restent donc la priorité des pouvoirs publics. C’est ainsi que l’Etat qui est garant de cet équilibre, va mettre sur pied des mécanismes et institutions de régulation. Normalization is at the heart of the essential missions of the State for a harmonious social life that takes into account the interests of all entities. It is in fact the normalization of the society, normalization of the economic activities, more significats, the mission of control of the operation of the market by the State. In liberal economy, the State has the mission of ensuring that economic operators are acting vis-à-vis consumers and their competitors under conditions that comply to the rules of economic law and in compliance with regulations, in accordance with the compliance with market rules and competition law. The protection of consumers and preservation of healthy competition between differents players. This is how the State, which is the guarant of this balance, will set up mechanisms, institutions and instruments of regulation.
Keywords: Competencia; Competition law; Concurrence; Consommation

The Limits of Shareholder Ratification - Anabtawi, Iman (The Journal of Corporation Law, 2025)
In this Article, I analyze the expanding common law doctrine of shareholder ratification, whereby shareholder approval can, for all practical purposes, absolve directors of fiduciary liability for their conflicted business decisions. Delaware law now allows a shareholder vote to perform substantially more work than ever before. Under prevailing doctrine, in transactions between a company and any party other than a controlling shareholder, shareholder ratification reinstates the business judgment rule and makes it irrebuttable, other than for waste. Substantive judicial review is effectively avoided for such transactions. Despite its extraordinary importance in corporate governance, the shareholder ratification doctrine’s foundations are feeble and its limits uncertain. Theoretically, there is no well-established basis for equating shareholder approval with either the informed, disinterested, and good-faith decision of a board or judicial review. Doctrinally, shareholder ratification’s expansion beyond its traditional context of self-dealing has been a judicial innovation, rather than an elaboration of precedent. And historically, the shareholder ratification doctrine, which originated in early 20th-century state interesteddirector statutes, was motivated by fairness principles that were lost in translation into the common law. This Article recovers the fairness genealogy of the shareholder ratification doctrine and, in doing so, provides useful guidance for the doctrine’s development, limits, and future application.

Le lieu de travail - Djampa, Patrick Juvet (Revue Africaine des Sciences Juridiques, Administratives et Politiques, 2025)
Les possibilités de lieux de travail différents ou d’une pluralité de lieux, impliquent des contraintes ou des opportunités de travail dont la prise en compte dans le rapport entre un l’employeur et son salarié, appelle une normalisation qui pour l’instant n’existe au mieux que dans un contrat qui spécifie une situation particulière de conditions de travail. Les outils numériques et des possibilités de travail à distance à partir de la plupart des lieux qui se développent en parallèle de l’allongement des trajets domicile travail et des dysfonctionnements des réseaux de transports, produisent de nouvelles situations de travail. De plus en plus, ces changements notables sont à atteindre a minima dans deux axes : d’une part, le renforcement de la présence des technologies de l’information dans les lieux de travail, avec la multiplication des objets connectés interagissant entre eux ou avec les êtres humains ; d’autre part, l’évolution significative des métiers, qui sont de plus en plus imbriquées aux systèmes d’information, ce qui, en retour aura un impact significatif sur l’évolution des lieux de travail.

La crise du mariage : étude sociojuridique des causes de la récurrence des divorces dans les Etats d’Afrique noire francophone - Edimo, François (Revue Africaine des Sciences Juridiques, Administratives et Politiques, 2025)
Le mariage est considéré dans les sociétés traditionnelles d’Afrique Noire Francophone comme une volonté divine, un engagement pour la vie. Le divorce est inconnu ici. Cependant, les chiffres et les statistiques relatifs aux divorces interpellent sur la recherche des causes de la récurrence de ce phénomène. L’analyse de la question a permis d’aboutir à un double constat. D’une part, l’accommodation des Hommes aux règles conflictogènes, adoptées pour régir une institution qu’ils n’ont pas créée, est à l’origine de la multiplication des divorces. Il s’agit notamment des obligations du choix de la forme du mariage et du régime de gestion des biens. Ces causes sont complétées d’autre part, par la prise en compte incongrue des traditions culturelles africaines et l’affranchissement de la femme, qui dans le contrat de mariage, sont des réalités allogènes avec lesquelles les couples dans les Etats d’Afrique Noire Francophone peinent à faire corps.
Keywords: Autorité parentale; Communauté des biens; Divorce; Dot; Liberté conjugale; Mariage; Monogamie; Polygamie; Puissance maritale; Régime matrimonial; Système matrimonial; Séparation des biens

Le règlement des différends en matière d’environnement au Cameroun - Gueukam Tchako, Yannick (Revue Africaine des Sciences Juridiques, Administratives et Politiques, 2025)
La présente contribution intitulée « Le règlement des différends en matière d’environnement au Cameroun » ; vise la mise en œuvre des règles de protection de l’environnement de par l’impact des actes mis en cause ou du préjudice causé, selon l’origine des acteurs ou selon les règles invocables. Ce faisant, elle s’intéresse aux solutions qu’apportent certaines dispositions relatives à la matière environnementale au cameroun. A l’analyse, on observe dans la première hypothèse, que les modes alternatifs de règlement non contentieux des différends se veulent plus rapide et accessibles tout en favorisant le respect des lois environnementales. Dans la seconde hypothèse, il s’agit de faire appel au juge judiciaire pour trancher les différends. De par son impact, la position du juge apparaît comme l’outil essentiel d’identification des dommages susceptibles d’être causés à l’environnement et constituant le socle sur lequel est construit le plan de gestion de l’environnement. The present contribution entiled « The settlement of environmental disputes in Cameroon » ; aims at the implementation of environmental protection rules according to the impact of the acts in question or of the damage caused, depending on the origin of the impact or according to the invocable rules. In doing so, it looks at the solutions provited by certain provisions relating to environmental matters in Cameroun. On analysis, it can be observed in the first hypothesis, the alternative methods of non-contentious settlement of disputes that are intented to be faster and more accessible while promoting compliance with environmental laws. In the second hyperthesis, it is a question of appealing to the judicial judge to settle disputes. Because of its impact, the position of the judge appears to be the essentiel tool for identifying the damage likely to be caused to the environment and constituting the basis on which the environmental management plan is built.
Keywords: Différends; Disputes; Environment; Environnement; Jurisdictional settlement; MARD; Non-jurisdictional settlement; Règlement juridctionnel; Règlement non juridictionnel

Le consentement et les rapports sexuels en droit nigérien et français - Harouna Zakari, Ibrahim (Revue Africaine des Sciences Juridiques, Administratives et Politiques, 2025)
La question du consentement et des relations sexuelles suscite rarement des débats compte tenu du caractère tabou attribué au sexe. Et pourtant, il est important de savoir quelles en sont ses implications quand les rapports sexuels sont entretenus aussi bien en dehors du cadre matrimonial, qu’en son sein, surtout dans un contexte marqué du sceau de forte dose d’islam. En c’est l’exemple du Niger, où l’on conçoit mal le refus de rapports sexuels opposé par l’un des conjoints à l’autre, que le mariage soit forcé ou pas. Tout cela, contrairement au droit français où, ostensiblement, le consentement de l’autre partenaire (homme comme femme) aux rapports sexuels devient de plus en plus très protégé. Enfin, il faut examiner si l’on peut parler de consentement des parents de la prostituée aux rapports sexuels entrepris par celle-ci. The question of consent and sexual relations rarely gives rise to debate as it is due to the taboo nature that we recognize in sex. And yet, it is important to know what its implications are when relationships are maintained both within the marital context and beyond. The question seems important in more than one way, especially analyzed in a country with a high percentage of people of the Muslim faith like Niger, where the connection between the refusal of sexual relations opposed by one of the spouses to the other and marital duty is not obvious, unlike French law where the consent of the other (spouse or simple partner) is very protected. Finally, we must question consent to sexual relations, when these could only be granted following a forced marriage, for example.
Keywords: Consent; Consentement; Devoir conjugal; Divorce; Fornication; Mariage forcé; Marital duty; Parents; Prostitution; Proxénète; Proxénétisme; Rape; Relations sexuelles; Repudiation; Répudiation; Sexual relations; Viol

The effects of Basel III on the intermediation and market activities of WAEMU banks - Kouakou, Thiédjé Gaudens-Omer (University Library of Munich, Germany, 2025)
This paper analyzes the effect of Basel III adapted to WAEMU on the behavior of banks in the zone (intermediation and market activities). After having developed a model for optimizing the return on bank equity, under various constraints (balance sheet constraints, Basel III regulatory constraints), we resort to linear programming via the Danzig simplex algorithm and to a structure of reasonable rates to obtain the optimal values of the various bank balance sheet items. The results, obtained by comparing these theoretical values with the values observed before Basel III (before January 1, 2018), show an increase in the supply of loans, obtained not only from deposits and bank refinancing but also via resources from the financial markets. We can also observe the intuitive result of an increase of bank reserves in line with the constraint that Basel III imposes on banks to increase their liquidity. In short, Basel III tends to strengthen bank financing in the zone, while improving the soundness of banks through the constitution of larger reserves.
Keywords: Calibration; Credit supply; Linear programming; Prudential regulation

L’enrichissement sans cause des établissements de crédit dans le droit de la Communauté Economique et Monétaire de l’Afrique Centrale (CEMAC) - Nfoutcha, Georges (Revue Africaine des Sciences Juridiques, Administratives et Politiques, 2025)
Il ne devrait guère résister de contradiction entre l’enrichissement sans cause et l’enrichissement illicite des établissements de crédit. Le premier relève du Droit civil alors que le second relève indubitablement du Droit pénal. Cette distinction devrait s’estomper en pénalisant l’enrichissement sans cause des établissements bancaires. En ce sens, l’infraction d’enrichissement sans cause des établissements permettrait de renforcer la politique pénale ou criminelle. L’enrichissement sans cause des établissements de crédit, ou l’enrichissement injustifié en Droit français, pose également la difficulté de la justice sociale. La question de la répétition de l’indu semble déjà réglée sous l’emprise de la législation en la matière. Mais, le souci de l’indemnisation mériterait d’être réglementé avec beaucoup d’acuité. Pris à ce titre, la mise en cause de l’enrichissement sans cause, fut-il un établissement de crédit, nécessiterait autant de restituer ce qui est dû, mais également indemniser la victime. Cette mesure devrait s’opérer de la manière la plus juste dans la mesure du possible. Les exigences d’équité y primeraient. Le droit de la Communauté Economique et Monétaire de l’Afrique Centrale gagnerait à se doter d’un véritable fond des dépôts de risques de l’enrichissement sans cause. Cette institution viserait à recevoir ces deniers en toutes fins utiles. Aussi, l’article 1303 du Code civil français résultant de l’ordonnance du 10 février 2016 devrait nourrir notre arsenal juridique sur la mise en œuvre d’une notion d’origine jurisprudentielle en quête de consistance digeste.
Keywords: Civil right; Credit institutions; Criminal law; Criminal policy; Droit civil; Droit pénal; Enrichissement illicite; Enrichissement sans cause; Etablissement de crédit; Illicit enrichment; Institution; Penal policy; Politique criminelle; Politique pénale; Unjust enrichment

Un délit de mise en danger élargi en droit burkinabè - Palgo, Diane Horélie (Revue Africaine des Sciences Juridiques, Administratives et Politiques, 2025)
Le droit pénal burkinabè prévoit de nouvelles dispositions consacrant une infraction de mise en danger de la personne d’autrui dans le code pénal de 2018. Ces dispositions juridiques sont originales, car elles prévoient à la fois une infraction générale de la mise en danger et une infraction plus spécifique. L’infraction de mise en danger délibérée d’autrui de type élargi est contenue dans l’alinéa 1 de l’article 521-5. Elle est formulée de façon générale, car l’analyse de l’incrimination permet de constater que l’infraction prend en compte tous les domaines et tous les comportements susceptibles d’exposer autrui à un risque de mort ou de blessures. Toutefois, cette formulation générale parait excessive dans la recherche de la prévention ; une excessivité conduisant à une difficulté d’adaptabilité de la norme pénale à la société burkinabè.
Keywords: Droit pénal; Délit; Excessivité; Formulation générale; Formulation trop générale; Mise en danger d’autrui; Mort ou blessures; Prévention

La limitation de l’excès de l’autonomie de la volonté par le solidarisme contractuel - Sangaré, Sékou; Sissoko, Diomansy I. (Revue Africaine des Sciences Juridiques, Administratives et Politiques, 2025)
Le solidarisme contractuel pourrait ainsi être décrit comme la doctrine qui érige en principe du droit des contrats les exigences de loyauté, de solidarité ou de bonne foi et qui impose aux contractants l’obligation de collaborer. Depuis quelques années, le solidarise contractuel né au début du 20e siècle connaît un regain d’actualité en droit des contrats. Le solidarisme contractuel prétend constituer un nouveau fondement de cette théorie générale. Matériellement, deux éléments l’identifient. Le premier est le lien de solidarité entres contractants. Il résulte de la prise en charge réciproque par ces derniers de l’intérêt au contrat de l’autre. Le second élément, la conciliation des intérêts, se définit comme une juste répétition des charges et des profils contractuels. Juridiquement, le solidarisme contractuel s’identifie à un principe descriptif, distinct de la bonne foi dont le domaine d’application est moindre. Pendant la phase d’exécution du contrat, ses effets justifient largement les devoirs comportementaux imposés par le droit positif aux contractants. Toutefois, cette conception du lien contractuel est fortement discutée. Dans cette étude, il est question de démontrer que l’approche autonomiste du solidarisme contractuel existe à travers le dépassement de la conception individualiste et antagoniste du contrat et la mise en avant de nouvelles obligations contractuelles. Ainsi, il faut tempérer cette analyse avec l’activation d’une autonomie inachevée qui s’inscrit dans le cadre de l’utopie représentative du solidarisme contractuel et la relativité de l’influence du solidariste contractuel.
Keywords: Contrats; Droit des contrats; Excès de l’autonomie de la volonté; RGO; Solidarisme contractuel

Les fiançailles à la lumière du code des personnes et de la famille du Mali - Touré, Omorou Zackaria; Maïga, Assalia Tiébory; Harouna, Mohamed Albachar (Revue Africaine des Sciences Juridiques, Administratives et Politiques, 2025)
En Afrique, et plus particulièrement au Mali, la plupart des familles et/ou communautés ont toujours exercé dans une certaine mesure un contrôle sur le processus de formation des unions. Tout comme la vie sociale, les fiançailles sont régies par un certain nombre de règles et pratiques. C’est pourquoi, l’analyse de la nature juridique des fiançailles s’impose avec acuité. Les fiançailles, à l’instar de toute convention, engendrent forcément des effets non seulement entre les parties mais également à l’égard de leurs familles respectives. Certes, la convention des fiançailles n’oblige pas les fiancés à contracter le mariage. Mais la possibilité de rupture unilatérale offerte à chaque fiancé doit être justifiée par des motifs légitimes faute de quoi la responsabilité de l’auteur pourra être engagée. C’est l’abus de ce droit qui est sanctionné sur le fondement de la responsabilité civile ouvrant droit à des dommages et intérêts. Le juge dispose d’un pouvoir souverain d’appréciation. Il appartient à la victime qui cherche réparation de prouver l’existence d’un préjudice réparable. In Africa, and particularly in Mali, most families and/or communities have always exercised some degree of control over the union formation process. Just like social life, engagements are governed by a certain number of rules and practices. This is why the analysis of the legal nature of engagement is urgently needed. Engagement, like any agreement, necessarily generates effects not only between the parties but also with regard to their respective families. Certainly, the engagement agreement does not oblige the engaged couple to enter into marriage. But the possibility of unilateral termination offered to each fiancé must be justified by legitimate reasons, failing which the perpetrator may be held liable. It is the abuse of this right which is punished on the basis of civil liability giving right to damages and interest. The judge has a sovereign power of appreciation. It is up to the victim seeking compensation to prove the existence of reparable injury.
Keywords: Famille; Fiançailles; Mali; Personnes

La protection du débiteur dans la constitution des sûretés judiciaires OHADA - Teguia, Jean Nestor Legrand (Espace Géographique et Société Marocaine, 2025)
Les sûretés judiciaires OHADA constituent une arme redoutable entre les mains du créancier. La constitution desdites sûretés par la voie d’une procédure d’urgence, permet au créancier desurprendre le débiteur afin d’avoirune main mise sur ses biens à son insu. Le juge qui facilite cette tâche au créancier à titre conservatoire ne s’appuieque sur de simples apparences de l’existence réelle de la créance et d’une éventuelle menace de son recouvrement. Face à cette situation qui peut être illégitime et doncpréjudiciable à l’égard du débiteur, ce dernier bénéficie d’une protection remarquable, à travers son droit à l’information et son droit à l’action. Par son droit à l’information, le débiteur oblige le créancier à porter à sa connaissance l’inscription provisoire faiteà son insu sur ses biens. Malgré le déphasage entre les dispositions des articles 213 et 217 de L’AUS, le débiteur,informé de la mesureprise contre lui, peut faire valoir son droit d’agirqui consiste à réclamerla radiation de l’inscription provisoire dans l’hypothèse où le créancier n’a pas réuni toutes les conditions exigées. Il peut également réagir en demandant le cantonnement de l’assiettede la sûreté judiciaire ou en procédant à une substitution de garantie dans le but de sauvegarder au mieux ses intérêts.
Number: 95
Keywords: Débiteur; Délais; Information; Intérêts; Protection judiciaires; Réaction; Sûretés

Essai sur l'optimisation fiscale : exploration des mécanismes d'optimisation fiscale à travers l'étude des groupes de sociétés - Bakhtous, Siham (Université de Perpignan Via Domitia, 2025)
Cette étude explore les contours et les tensions de l'optimisation fiscale dans un monde globalisé et numérisé, à travers le prisme des groupes de sociétés. En retraçant l'histoire de l'impôt, elle met en lumière les transformations profondes du système fiscal mondial, où les stratégies fiscales transfrontalières se sont progressivement développées, en dehors des prévisions des législations nationales. Bien qu'enraciné dans le principe fondamental de la liberté de choisir la voie fiscale la moins imposée, l'optimisation fiscale a évolué en réponse aux mutations économiques, juridiques et technologiques, donnant lieu à des pratiques parfois controversées qui se situent aux frontières de la légalité et de l'éthique. À l'intersection du droit, de l'économie et de la politique fiscale, l'optimisation fiscale dépasse le simple objectif de réduction de la charge fiscale : elle reflète un processus global où la mobilité des capitaux et des actifs immatériels perturbe les règles fiscales classiques. Bien que souvent conformes à la législation, ces pratiques d'optimisation fiscale dites « agressives » perturbent l'équilibre des systèmes fiscaux mondiaux, contribuant à un phénomène préoccupant : l'érosion de la base d'imposition et le transfert de bénéfices vers des juridictions à faible fiscalité. Cette dérive a mis en évidence les défaillances des systèmes fiscaux nationaux, incapables de suivre le rythme des mutations économiques et de réguler efficacement les pratiques des multinationales. En déconstruisant les mécanismes sous-jacents de l'optimisation fiscale agressive, cette recherche invite à une critique constructive de l'arsenal législatif actuel. Elle souligne l'urgence de repenser les instruments fiscaux dans un contexte où la mobilité du capital et des actifs immatériels redéfinit les règles du jeu économique et de restaurer un équilibre entre les exigences d'efficacité économique des multinationales et la nécessité de garantir une justice fiscale à la hauteur des enjeux mondiaux
Keywords: Base erosion; Digital; Droit fiscal (droit international); Déductions fiscales; Groupes de sociétés; Impôts; Numérique; Optimisation; Optimization; Profit shifting; Restructuration; Restructuring; Réductions fiscales; Tax; Transfert des bénéfices; Érosion de la base d'imposition; Évasion fiscale

Directive portant harmonisation de l'imposition des revenus et des bénéfices dans les Etats membres de la CEMAC - Communauté Economique et Monétaire de l'Afrique Centrale (2025)

L'associé salarié - Brenn, Chloé Le (CY Cergy Paris Université, 2025)
L'associé salarié est aujourd'hui une figure répandue dans le paysage juridique, en dépit d'une contradiction évidente : il est à la fois propriétaire du capital et subordonné à la société qui l'emploie. Cette antinomie apparente et les interrogations qui en découlent apparaissent, pourtant, majoritairement passées sous silence. Le cumul des qualités d'associé et de salarié est ainsi admis par principe, notamment depuis l'avènement des dispositifs légaux d'actionnariat salarié.Ce silence nourrit l'opportunité d'une étude approfondie de la figure de l'associé salarié. Une analyse miroir du droit des sociétés et du droit du travail est à même de vérifier la réelle compatibilité de ces qualités, tant au niveau de la licéité du cumul que des règles qui lui sont applicables. La proposition est la suivante : se plonger dans l'analyse chronologique du cumul des qualités d'associé et de salarié, de sa naissance à sa disparition, par une étude combinée du droit du travail et du droit des sociétés.En ressort une compatibilité relative des qualités tenant davantage à l'influence du droit du travail que du droit des sociétés. Ce constat ne doit cependant pas minimiser les influences réciproques des deux branches du droit. Contrairement au postulat qui semble suivi par une majorité d'auteurs, l'associé salarié n'est pas juste un salarié particulier : il est également un associé singulier. The employee shareholder is now a commonplace figure, despite a major contradiction: he is both owner of the capital and subordinate to the company that employs him. This apparent conflict and the questions it raises are largely ignored. The dual status of shareholder and employee is accepted as a matter of principle, particularly since the advent of legal employee share ownership schemes.This silence provides an opportunity for a study of the situation of the employee shareholder. A mirror analysis of company law and labour law is able to study the real compatibility of these qualities, simultaneously of the lawfulness of the combination and the rules applicable to it. The proposal is: to analyse in chronological order the dual status of shareholder and employee, from its inception to its demise, by a combined study of labour law and company law.A relative compatibility of these roles emerges. It is due more to the influence of labour law than company law. However, this observation should not minimise the reciprocal influences of the two branches. Contrary to the assumption that seems to be followed by some authors, the employee shareholder is not just a particular employee: he is also a singular shareholder.
Keywords: Actionnariat salarié; Associé; Associé salarié; Corporate law; Droit des sociétés; Droit du travail; Employee; Employee shareholder; Labor law; Salarié; Shareholder

Responsabilité délictuelle et contrat : étude d’une dynamique juridique à la lumière des fonctions des dommages-intérêts - Perrouin-Verbe, Dorothée (Université Paris-Panthéon-Assas, 2025)
Cette thèse s'intéresse à l'histoire de la clause générale de responsabilité en droit français et à son impact sur les rapports entre les régimes de responsabilité délictuelle et contractuelle. La généralité de la clause entraîne sa nécessaire subsidiarité par rapport aux règles de la responsabilité contractuelle, dans un rapport qui rappelle celui entre le droit commun et le droit spécial. Il s'ensuit que la responsabilité délictuelle doit être exclue du contrat, et que cette exclusion est d'autant plus forte et définitive que l'on se rapproche du cœur du contrat et de la fonction propre de la responsabilité contractuelle, à savoir la satisfaction par équivalent du créancier lésé. Cette subsidiarité est également à l'origine de la présence de la clause générale de responsabilité tout autour du contrat, pour régir les marges du contrat, les situations para-contractuelles. Si la nature de la responsabilité dans ces marges ne sera plus débattue, ses effets devront être tempérés pour s'adapter à la présence du contrat.
Keywords: Clause générale; Contract; Contractual liability; Contrats; Culpa in contrahendo; France; General clause; Inexécution du contrat; Non-cumulation principle; Non-performance of contract; Precontractual liability; Principe de l’effet relatif des contrats; Principe de non-cumul; Privity; Responsabilité contractuelle; Responsabilité délictuelle; Responsabilité précontractuelle; Third-parties; Tiers; Tiers (droit); Tortious liability

RSE au Congo: Sortie de l’impasse des réformes imposées en temps de guerres? Vers une politique de responsabilité sociétale de l’entreprise - Ntamwenge, Corneille (International Journal of Innovation and Applied Studies, 2025)
L’étude ne porte ni sur les actes et pratiques de dépossession totale, ni sur les pernicieuses dégradations sociétales identifiées. Elle se penche plutôt sur la problématique de la RSE au Congo, examinant l’évolution de la mise en œuvre des notions de responsabilité sociétale et de codes d’éthique dans les entreprises opérant sur le territoire congolais. La finalité de l’étude comporte trois visées solidaires. La première concerne la conception et la définition de la RSE au Congo, alors que la deuxième, l’existence potentielle d’une politique de RSE pour toutes les entreprises du Congo. Les résultats recueillis à ce niveau impliquent directement la question suivante, troisième visée de l’étude. Comment procéder pour concevoir et instituer une politique pertinente de responsabilité sociétale de l’entreprise au Congo ? Le traitement de cette question a fait ressortir le rôle majeur de la législation et de l’éthique des affaires (EA) dans la politique de RSE au XXIe siècle. L’étude se présente ainsi comme un appel pressant à la conception d’une politique de RSE pour toutes les entreprises actives sur le territoire congolais. Les réflexions et analyses de cette étude sont réparties en six sections: (1) introduction, (2) cadre juridique de la RSE au Congo, (3) expérience congolaise de la RSE, (4) définition de la RSE, (5) histoire de l’EA et de la RSE et (6) remarques conclusives. L’apport de l’éthique des affaires a éclairé l’étude sur trois thèmes, à savoir la RSE, l’institutionnalisation de l’éthique et la mise en œuvre des politiques de RSE. The study does not concern the acts and practices of full dispossession, nor pernicious societal degradations identified. It rather focusses on the issue of CSR in the Congo, examining evolution of implementating notions of societal responsibility and codes of ethics in the enterprises that operate on Congolese territory. Its purpose has three interlinked aims. The first one concerns the conception and definition of CSR in the Congo, while the second, the potential existence of a CSR policy for all Congolese companies. Results collected at this level straightly imply following question, the third aim of the study. How to proceed in designing and establishing relevant corporate societal responsibility policy in the Congo ? The treatment of this issue has highlighted the major function of legislation and business ethics (BE) in CSR policy in the 21st Century. The study thus presents itself as a pressing call for designing a CSR policy for all active enterprises on the Congolese territory. The reflections and analyses of this study are divided into six sections: (1) introduction, (2) legal framework for CSR in the Congo, (3) Congolese experience of CSR, (4) CSR definition, (5) history of BE and CSR, and (6) conclusive remarks. The contribution of business ethics has shed light on the study upon three themes: CSR, institutionalization of ethics, and implementation of CSR policies.
Keywords: CSR; Développement durable; Industrie extractive; Intégrité morale; RSE; Responsabilité sociale de l'entreprise; Régulation non-obligatoire; Éthique des affaires

La dimension sociale du droit traditionnel africain : réflexion à l’aune des droits fonciers - Birba, Mamoudou (Afrilex : Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2025)
Les droits fonciers structurent la vie quotidienne des populations dans la société traditionnelle africaine en ce qu’ils se rapportent au domaine de la terre. Cette dernière qui constitue la base productive de l’alimentation et des pratiques culturelles est un facteur de reproduction sociale, revêtant ainsi un caractère essentiel pour le monde rural. La formation et la circulation des droits fonciers traditionnels sont alors sous-tendues par des considérations idéologiques et idéelles qui leur confèrent une dimension sociale. Dès lors, en considérant les contextes sociaux de pauvreté, de précarité et de vulnérabilité, on s’interroge sur les déterminants et les manifestations de la dimension sociale des droits fonciers traditionnels. A l’analyse, leurs fondements et leurs fonctions s’avèrent être des garanties à l’inclusion sociale, faisant ainsi écho aux droits économiques, sociaux et culturels contenus dans les droits de l’homme. Land rights structure people’s daily lives in traditional African society insofar as they relate to the land domain. Land is the productive basis of food production and cultural practices, and is a factor in social reproduction, making it essential to the rural world. The formation and circulation of traditional land rights are therefore underpinned by ideological and idealistic considerations that give them a social dimension. Taking into account the social contexts of poverty, precariousness and vulnerability, we therefore examine the determinants and manifestations of the social dimension of traditional land rights. On analysis, their foundations and functions turn out to be guarantees of social inclusion, echoing the economic, social and cultural rights contained in human rights.
Keywords: Droit de l’homme; Droit des biens; Droits fonciers; Human rights; Ideology; Idéologie; Land rights; Société traditionnelle; Traditional society

L’Emergence du concept de la responsabilité sociétale des entreprises en Afrique - Djerma, Ousmane Bazoumana; Sangaré, Sékou (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
La responsabilité sociétale des entreprises également appelée responsabilité sociale des entreprises est définie comme la responsabilité des entreprises vis-à-vis des effets qu’elles exercent sur la société. Toutes les entreprises peuvent mettre en œuvre une démarche RSE, et ce qu’elle que soit leur taille, leur forme juridique ou leur secteur d’activité. La responsabilité sociétale permet de conjuguer performance économique, performance sociale et performance environnementale. C’est une démarche accessible à toutes les entreprises. L’entreprise qui déploie une démarche de RSE va donc chercher à développer des pratiques plus éthiques et plus durables dans son mode de fonctionnement de façon à contribuer aux enjeux de développement durable. La RSE est source de nombreux bénéfices pour l’entreprise. Elle permet d’abord de mettre en place une vision stratégique partagée et constitue un vecteur d’engagement et de fidélisation des collaborateurs. Elle a également un outil pour se différencier commercialement, améliorer son image et sa réputation réaliser des gains de productivité et gagner en compétitivité.
Keywords: Afrique; Concept; Emergence; Entreprise; RSE; Responsabilité sociale de l'entreprise

La protection du consommateur d’assurance dans la rupture du lien contractuel en droit CIMA : l’incidence du critère de l’utilité contractuelle - Kamdem Meuyo, Paulin (Revue africaine de droit des affaires, 2025)
Le contrat d’assurance appartient à la catégorie des contrats de consommation et se caractérise par l’opposition entre les professionnels de l’assurance et les consommateurs des services d’assurance. La souscription d’un contrat d’assurance par un consommateur s’expliquerait en grande partie par la recherche du profit, de l’utilité que pourrait lui apporter ledit contrat. A ce titre, sur le fondement de l’utilité, le contrat d’assurance devrait pouvoir assurer au consommateur une certaine sécurité juridique même au stade de l’extinction du contrat. En principe, dans la rupture du lien contractuel, la bonne foi doit nécessairement guider le comportement des parties dans l’usage des facultés de résiliation. Aussi, dans l’intérêt du consommateur, l’utilité contractuelle peut être présentée comme critère de la résiliation du contrat de telle sorte que l’inutilité du contrat d’assurance serait considérée comme la cause et la condition de la résiliation. Ce critère d’utilité constituerait ainsi une donnée fondamentale d’appréciation de la résiliation du contrat d’assurance, laquelle serait abusive s’il est établi que dans l’exercice de son droit, le professionnel d’assurance avait pour objectif de se détourner de ses engagements contractuels ou de priver le consommateur du bénéfice qu’il pouvait tirer du contrat.

The Effectiveness of the Legal Frameworks in the establishment of Liability of Land Transport Operators in cases of Accidents in Cameroon: A Critical Appraisal - Kombo, Kutiefe Umaro (International Multilingual Journal of Science and Technology, 2025)
The liability of land transport operators in Cameroon is guaranteed by a good number of laws including; the constitution of Cameroon, the penal code, the 2001 law governing the Profession of Road Transport Operators, the 2023 law governing the rail sector in Cameroon and more. Such liability can be under the Tort of negligence, vicarious liability, or strict liability as provided for under section 289(1) of the Cameroonian penal code on Unintentional killing. However, the laxity of the courts in handling accident-related disputes, the contradictory and vague nature of the laws on the liability regime and even the lenient nature of the sanctions provided for by these laws do not meet up with the rate of accidents today in Cameroon. This article therefore has as its objective to examine the effectiveness of the legal frameworks in the establishment of liability of land transport operators in cases of accidents in Cameroon. Arguably, the author holds that the legal frameworks establishing the liability of land transport operators in cases of an accident in Cameroon are ineffective. A doctrinal research method has been adopted where both primary and secondary sources of information have been consulted. Our finding reveals that; the ineffectiveness of legal frameworks in the establishment of the liability of land transport operators in cases of accidents is a result of the laxity of the courts in implementing the laws and, the vague and contradictor nature of the law. We, therefore, recommend that; separate court hearings should be set for accident-related disputes and judges trained only on that, the laws should be revised, the sanctions in cases of accidents should be increased and all mitigating circumstances in cases of accidents should not be taken into consideration like a first-time offender, the plea of guilt etc.
Keywords: Accidents; Cameroun; Land Transport Operators; Liability; Opérateurs de transport terrestre; Responsabilité; Transport terrestre

The Artificial Intelligence (AI) framework and the benefits of its use in internal audit - Kontogeorgis, Georgios (International Multilingual Journal of Science and Technology, 2025)
AI is well known today as a valuable tool that can improve our daily lives. In addition, it can improve the efficiency and productivity of many professions, such as the internal auditor. The research methodology is literature review. The primary objectives of the article are twofold: Firstly, to provide a comprehensive description of the institutional framework for the operation of AI internationally, and secondly, to examine the benefits that arise from the use of AI in internal audit units and organisations in general. The significance of the research lies in its examination of artificial intelligence (AI) as a valuable instrument in the arsenal of internal auditors. The findings suggest that AI has the potential to enhance the efficacy of internal audits, reduce the time required for their execution, reduce the frequency of internal audits, and, in general, optimise the operations of companies and organisations.
Keywords: AI; Artificial Intelligence; Corruption; Fraud; Inteligência artificial; Intelligence Artificielle; Internal audit; Management

L’abolition de la peine de mort infligée à la société à l’ouverture de la liquidation des biens en droit de l’OHADA - Mfini, Mon-espoir (Revue africaine de droit des affaires, 2025)

La protection des entreprises numériques au Cameroun - Njandeu, Monique Aimé (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
Les transformations que subissent les entreprises à l’ère du numérique font d’elles des moteurs de l’économie. La mutation ainsi observée constitue le leitmotiv des politiques nationales contemporaines. Toutefois, les avantages qu’on tire de la numérisation des entreprises sont relativement biaisés par la recrudescence des frasques altérant la sécurité des personnes et des biens. La protection de celles-ci devient dès lors un enjeu de politique juridique. C’est ainsi que répondant à la question de savoir comment s’organise la protection des entreprises numériques en droit camerounais, la présente réflexion constate que celle-ci ne fait pas l’objet de dispositions spécifiques. En effet, en l’état actuel du droit positif, l’encadrement juridique des entreprises numériques tire son essence du droit commun et de certaines dispositions éparses contenues dans le corpus législatif et réglementaire applicable en la matière. En procédant à un examen minutieux de celui-ci, il est désormais devenu impérieux que soit remodelé l’existant en tenant compte de la spécificité de l’entreprise numérique et du contexte ambiant.
Keywords: Entreprise numérique; Identité numérique; Protection; Sécurité des biens; Sécurité des personnes

La transaction dans le règlement des litiges fiscaux au Bénin, au Cameroun et au Gabon - Nzamboung, Eugène (Afrilex : Revue d’étude et de recherche sur le droit et l’administration dans les pays d’Afrique, 2025)
Transaction et droit fiscal : un oxymore ? A priori tout porte à le croire. Dans son ipséité, l’impôt est commandement, marqueur de la puissance publique. La transaction par contre implique des négociations entre cotransigeants. Comment donc expliquer son introduction dans le droit fiscal des Etats sous étude ? En réalité, il s’agit d’une réponse aux nombreux défis que pose le droit fiscal moderne. Entre difficultés de recouvrement et contestations constantes de l’impôt, la transaction fiscale se hisse en remède. Elle cristallise la contractualisation progressive de l’obligation fiscale. Mais l’usage de ce contrat pour régler les litiges fiscaux dans ces Etats interroge sur sa portée dans la protection des intérêts du contribuable et de l’administration fiscale. Dès lors, on peut légitimement se demander quel est l’apport de la transaction dans le règlement des litiges fiscaux au Bénin, au Cameroun et au Gabon ? A travers l’analyse des textes et des pratiques fiscales dans ces Etats, l’hypothèse d’un apport mitigé de la transaction fiscale est retenue. Si elle est par essence un outil de négociation de la justice fiscale, elle relativise néanmoins de ce fait même la sécurité fiscale. Il est donc nécessaire de rationaliser la mise en œuvre de cette institution libérale du droit fiscal. Transaction and tax law: an oxymoron? A priori everything leads us to believe it. In its selfhood, the tax is a command, a marker of public power. The transaction, on the other hand, involves negotiations between co-transigents. How can we explain its introduction into the tax law of the States under study? In reality, it is a response to the many challenges posed by modern tax law. Between collection difficulties and constant tax disputes, the tax transaction is emerging as a remedy. It thus crystallizes the progressive contractualization of the tax obligation. But the use of this contract to settle tax disputes in these States calls into question its scope in protecting the interests of the taxpayer and the tax administration. Therefore, we can legitimately ask what contribution does the transaction make to the settlement of tax disputes in Benin, Cameroon and Gabon ? Through the analysis of tax texts and practices in these States, the hypothesis of a mixed contribution of the tax transaction is retained. If it is in essence a tool for negotiating tax justice, it nevertheless formalizes tax insecurity. It is therefore necessary to rationalize the implementation of this liberal institution of tax law.
Keywords: Bénin; Cameroun; Gabon; Justice fiscale; Legal certainty; Performance fiscale; Sécurité juridique; Tax justice; Tax performance; Tax transaction; Transaction fiscale

L’adhésion du Burundi à l’OHADA : un impératif ou un choix ? - Nzohabonayo, Anaclet (Revue africaine de droit des affaires, 2025)
Le Burundi vit un moment crucial dont la gestion est déterminante pour l’instauration d’un climat des affaires favorable aux investissements et aux opérations économiques. Il s’est doté du Plan national de développement 2018-2027 dont l’objectif fondamental est la réalisation des objectifs de développement durable conçus pour mettre en œuvre l’Agenda 2030 des Nations unies. Sa vision 2040-2060 a été imaginée pour concrétiser ses engagements au titre de l’Agenda 2063 de l’Union africaine et de la vision 2050 de la Communauté d’Afrique de l’Est dont il est respectivement membre. Il est membre de plusieurs organisations d’intégration économique régionale au rendement mitigé. Pour tirer profit de cette appartenance et réaliser les objectifs prônés dans ces outils de planification, le pays doit faire peau neuve en adhérant au traité de l’OHADA. Dans le passé récent, des réformes partielles ou isolées de certains segments du droit des affaires n’ont pas permis de rompre avec les critiques d’insécurité juridique et judiciaire qui compromettent l’attractivité de la destination burundaise pour les investisseurs étrangers. Dès lors, l’étude estime que l’adhésion du Burundi à l’OHADA n’est pas une question de choix, mais plutôt un impératif pour se doter d’un droit des affaires fédérateur, rassurant pour les investisseurs et d’autres opérateurs économiques. La dynamique est en cours et, espérons, que la voie de la raison prendra toujours le dessus sur les émotions et les peurs pour prendre des décisions rationnelles inspirées des conclusions des études de faisabilité.

L'Exécution, condition du procès juste et équitable : actes du séminaire des 15 et 16 mai 2023 - République du Sénégal (Médiateur de la République, 2025)

La personnalisation des biens - Sangaré, Sékou; Traoré, Almamy Amadou (Revue des Réflexions Constitutionnelles : Revue mensuelle de publication en droit constitutionnelle, 2025)
La perturbation des catégories des biens en droit civil n’a jamais été entreprise jusqu’alors, c’est tout simplement parce qu’elles avaient su bien vieillir et passer le temps sans changement. Il est vrai que le droit des biens a toujours eu des scrupules à saisir certaines entités juridiques, et qui plus est, le vivant. Tout converge vers le maintien de la summa divisio des personnes et des biens grâce à un remaniement des catégories de biens. L’heure est donc venue de transformer l’architecture générale des biens afin que chacun y trouve sa place.

Le gage de stocks : un gage de trop ? - Tsafack Djoumessi, Cédric Carol (Revue africaine de droit des affaires, 2025)
Avait-on besoin de consacrer des dispositions spécifiques au gage de stocks ? Si du point de vue formel, la précision paraît être justifiée, tel ne semble pas le cas du point de vue substantiel. L’article 120 de l’AUS dispose de façon péremptoire que, sans préjudice des dispositions de la présente sous-section, le gage de stocks est soumis aux règles générales du gage des biens meubles corporels. Mais les dispositions singulières applicables à cette sûreté qui avait pour finalité de compléter ou de neutraliser les règles de droit commun, paraissent, d’une part, noyées dans ces dernières. D’autre part, l’exigence du bordereau de gage de stocks est non seulement facultative et tend en plus à complexifier la constitution de ladite sûreté, contrairement au régime de droit commun qui se veut plus souple. Il s’ensuit que l’érection des dispositions spécifiques au gage de stocks serait une emphase inutile et inopportune.

International investment regime reform : integrating sustainable development into Uganda’s bilateral investment treaty system – a new model bit - Asiimwe, Esther Muchwa (University of Pretoria, 2025)
This thesis critically analyses Uganda’s bilateral investment treaty (BIT) system to determine its compatibility with sustainable development imperatives and proposes a new model BIT that aligns with Uganda’s evolving development priorities. Recognising the country’s reliance on foreign direct investment (FDI) for economic growth, this study interrogates the extent to which Uganda’s current BITs—many of which were concluded during earlier policymaking eras—expose the country to legal, economic, and regulatory risks. These include susceptibility to investor–state dispute settlement (ISDS) claims, constraints on the host state’s right to regulate, and a lack of provisions promoting environmental, social, and developmental objectives. Through doctrinal and comparative legal analysis, the study traces the historical evolution of international investment law (IIL), critiques the limitations of Uganda’s domestic and treaty-based FDI frameworks, and identifies substantive and structural weaknesses in Uganda’s in-force and model BITs. The analysis also considers international reform efforts and best practices from new-generation investment agreements, including the AfCFTA Protocol on Investment, the Investment Facilitation for Development (IFD) Agreement, and the SADC and EAC Model BITs. Particular attention is paid to the South African BIT reform experience as a comparator for Uganda’s reform journey. The study finds that Uganda’s BIT system is outdated, overly protective of investors, and poorly aligned with its sustainable development goals (SDGs). It recommends terminating unratified and problematic BITs, renegotiating existing ones, and adopting a new model BIT that balances investor protection with Uganda’s regulatory autonomy and sustainable development objectives. To this end, a draft model BIT is proposed as an annex to guide future treaty negotiations and reform Uganda’s investment regime in line with contemporary global standards and regional aspirations.
Keywords: Bilateral Investment Treaties (BITs); ISDS; Investissements; Investment law reform; Investments; Investor-State Dispute Settlement; Uganda

La armonización del derecho contractual internacional por medio de los restatements internacionales. - Carreño Bernal, Emmanuel Guillermo (Revista Boliviana de Derecho, 2025)
El artículo analiza cómo el crecimiento del comercio internacional ha resaltado la necesidad de marcos jurídicos armonizados para regular relaciones contractuales de carácter internacional. Los Restatements Internacionales han surgido como una herramienta clave para consolidar principios jurídicos comunes. Además, el estudio revisa los esfuerzos de organismos globales y regionales como UNIDROIT y OHADAC, así como iniciativas académicas como los Principios LANDO y los Principios de Derecho Contractual Asiático. The article analyzes how the growth of international trade has highlighted the need for harmonized legal frameworks to regulate international contractual relations. International Restatements have emerged as a key tool for consolidating common legal principles. Additionally, the study reviews the efforts of global and regional organizations such as UNIDROIT and OHADAC, as well as academic initiatives like the LANDO Principles and the Asian Contract Law Principles.
Keywords: Armonización jurídica; Contratación transfronteriza; Cross-border contracting; International principles; International restatements; Legal harmonization; Principios internacionales; Restatements internacionales

Climate justice and litigation in the context of South Africa - Chihombe, Denmark (North-West University, 2025)
This study interrogates the intersection of climate justice and litigation in the South African context. It addresses the urgent need for legal methods to address the disproportionate impact of climate change on marginalised communities. As climate change has become one of the greatest global challenges, marginalised communities most keenly feel its impacts, particularly those historically disadvantaged by socioeconomic inequalities rooted in apartheid. What follows is a critical examination of the most important international climate frameworks, in particular the United Nations Framework Convention on Climate Change (hereinafter UNFCCC) and the Paris Agreement, which have shaped the global discourse on climate change. The increasing recognition of the rights of historically marginalised and vulnerable communities underscores the potential role of climate litigation in achieving climate justice for all by holding both government and corporations accountable for their actions and lack thereof in mitigating climate change. The study examines the South African legal framework and recognises its progressive constitution that guarantees environmental rights. On the other hand, the study highlights significant barriers to effective climate action, particularly for the country’s most vulnerable, poor and marginalised populations, who often lack access to legal resources and skills needed for climate action. Using decided climate cases such as Earthlife Africa v. Minister of Environment, the study highlights the problems that plaintiffs often face when it comes to proving causation and the need for expert evidence in such litigation. Finally, the study concludes that while climate litigation offer opportunities for climate justice, the challenges identified need to be addressed to ensure the effectiveness of climate processes in achieving climate justice. The study therefore makes recommendations for strengthening legal aid, promoting public climate litigation and improving community capacity. By implementing these recommendations, climate justice will be achieved so that South Africa can effectively utilise climate litigation to demand climate justice for both current and future generations.
Keywords: Climate change; Global challenges; Justice; Litigation; Marginalised communities

A path to paperless trade: analysing the legal gaps and economic benefit of adopting or maintaining a legal framework that takes into account the UNCITRAL Model Law on Electronic Transferable Records (MLETR) - Committee on Trade and Investment (CTI) (Asia-Pacific Economic Cooperation, 2025)
Keywords: Asia and the Pacific; DIGITAL TECHNOLOGY; ELECTRONIC COMMERCE; UN Convention on the Use of Electronic Communications in International Contracts (2005); UNCITRAL Model Law on Electronic Commerce (1996); UNCITRAL Model Law on Electronic Transferable Records (2017)

Les grands arrêts de la Cour suprême du Bénin : Chambre judiciaire. Tome 1 - Cour suprême (Editions du CREDIJ, 2025)
Fidèle à sa vocation de juridiction suprême, la plus vieille de la République, la Cour suprême se veut résolument gardienne du raisonnement juridique au Bénin. Parce qu'elle entend assumer pleinement cette vocation, elle se par conséquent ouverte dans sa mission fondamentale d'interprétation uniforme des lois de la République sur tout le territoire national et d'uniformisation de la jurisprudence.

Les grands arrêts de la Cour Suprême du Bénin : Chambre administrative. Tome 1 - Cour suprême; ASCAP Bénin (Editions du CREDIJ, 2025)
Fidèle à sa vocation de juridiction suprême, la plus vieille de la République, la Cour suprême se veut résolument gardienne du raisonnement juridique au Bénin. Parce qu'elle entend assumer pleinement cette vocation, elle se par conséquent ouverte dans sa mission fondamentale d'interprétation uniforme des lois de la République sur tout le territoire national et d'uniformisation de la jurisprudence.

L'état de l'application de la compétence pénale dans l'espace OHADA - Hadidjatou, Ousmanou (Revue Africaine des Réflexions Juridiques et Politiques, 2025)
La signature du traité instituant l’Organisation pour l’Harmonisation en Afrique du Droit des Affaires (OHADA) a donné place à une nouvelle pensée de l’intégration communautaire par le droit. Par cet instrument juridique, les États signataires ont manifesté leur volonté de contribuer en Afrique à l’instauration d’un espace économique unifié et apte à répondre aux aspirations des investisseurs. Pour atteindre cet objectif, les États membres de l’OHADA ont entendu remédier à un certain nombre de non-conformités liées à la présence massive de lois nationales contradictoires, au contenu souvent obsolète. Mais en matière pénale, matière charnière du droit, l’on constate que cette uniformisation n’est pas effective. Même si c’est le législateur OHADA qui organise la norme de comportement, la norme de sanction est laissée à la charge de chaque Etats parties. Cette disparité peut alors s’avérer être un frein à la volonté des Etats membres. De ce fait, il est impératif qu’une unification soit faite pour la matière pénale dans le but d’atteindre l’objectif souhaité qui est celui de la sécurité juridique mais surtout l’exigence d’efficacité et d’effectivité du droit OHADA. The signing of the treaty establishing the Organization for the Harmonization of Business Law in Africa (OHADA) gave way to a new way of thinking about community integration through law. Through this legal instrument, the signatory States have demonstrated their desire to contribute in Africa to the establishment of a unified economic space capable of meeting the aspirations of investors. To achieve this objective, OHADA member states intended to remedy a certain number of non-compliances linked to the massive presence of contradictory national laws, often with obsolete content. But in criminal matters, a pivotal area of law, we see that this standardization is not effective. Even if it is the OHADA legislator who organizes the standard of behavior, the standard of sanction is left to the responsibility of each State party. This disparity can then prove to be a brake on the will of Member States. Therefore, it is imperative that a unification be made for criminal matters in order to achieve the desired objective which is that of legal security but above all the requirement for efficiency and effectiveness of OHADA law.
Keywords: Compétence; Criminal matters; Jurisdiction; Matière pénale

Code civil - Institut français d'information juridique (Droit.org, 2025)

Code de commerce - Institut français d'information juridique (Droit.org, 2025)

Code de la consommation - Institut français d'information juridique (Droit.org, 2025)

Code de la propriété intellectuelle - Institut français d'information juridique (Droit.org, 2025)

Code de la sécurité sociale - Institut français d'information juridique (Droit.org, 2025)

Code de procédure civile - Institut français d'information juridique (Droit.org, 2025)

Code de procédure pénale - Institut français d'information juridique (Droit.org, 2025)

Code des assurances - Institut français d'information juridique (Droit.org, 2025)

Code des douanes - Institut français d'information juridique (Droit.org, 2025)

Code des juridictions financières - Institut français d'information juridique (Droit.org, 2025)

Code des ports maritimes - Institut français d'information juridique (Droit.org, 2025)

Code des procédures civiles d'exécution - Institut français d'information juridique (Droit.org, 2025)

Code des transports - Institut français d'information juridique (Droit.org, 2025)

Code du travail - Institut français d'information juridique (Droit.org, 2025)

Code minier (nouveau) - Institut français d'information juridique (Droit.org, 2025)

Code monétaire et financier - Institut français d'information juridique (Droit.org, 2025)

Code pénal - Institut français d'information juridique (Droit.org, 2025)

Livre des procédures fiscales - Institut français d'information juridique (Droit.org, 2025)

L’ordre public et la faveur dans la phase précontractuelle en droit camerounais du travail - Kemta Pewo, Carole (Revue Africaine des Réflexions Juridiques et Politiques, 2025)
La flexibilité de la nouvelle législation camerounaise du travail a des limites. En effet, l’employeur, au moment de l’embauche, est tenu de respecter les dispositions d’ordre public absolu prévues par le législateur social. Certaines contraintes spécifiques au droit du travail seront imposées au chef d'entreprise en vue de sauvegarder les intérêts fondamentaux du salarié. D’autres dispositions viseront les intérêts économiques de toute entreprise. Toutefois, il est permis aux partenaires sociaux, avec l’ordre public relatif, d’aménager certaines prescriptions législatives dans un sens plus favorable au salarié. Ils sont libres de le faire à tout stade de leur contrat, sur la base soit de l’article 1134 du Code civil, soit des conventions collectives du travail, des accords d’établissements ou des usages. C’est dire que la formation d’un contrat de travail peut être fortement influencée par des clauses plus favorables.
Keywords: Clause plus favorable; Contrat de travail; Flexibilité; Ordre public

Internationality overreach in the interpretation of uniform private law conventions: the Contra Proferentem rule and the CISG - Kryla-Cudna, Katarzyna (International and comparative law quarterly, 2025)
This article argues that the rule of contra proferentem is not applicable to international sales contracts governed by the United Nations Convention on Contracts for the International Sale of Goods (CISG). It further argues that the common recognition of the rule of contra proferentem under the CISG is an instance of a broader phenomenon which it calls ‘internationality overreach’. ‘Internationality overreach’ is the tendency to project onto the provisions of a uniform private law instrument doctrines and concepts which are inaccurately presumed to constitute universally recognised principles of private law or the ‘common core’ of various legal systems. This article demonstrates that internationality overreach disrupts the goals underpinning the harmonisation of commercial law in two ways: first, it undermines uniformity in the application of international conventions; and, second, it leads to outcomes that fall short of the agreement reached by the Contracting States during the drafting process. While this article focuses on the CISG, the argument developed in this article is of equal relevance to other uniform private law conventions which follow the principle of autonomous interpretation.
Keywords: INTERNATIONAL SALE OF GOODS; INTERNATIONAL TRADE LAW; UN Convention on Contracts for the International Sale of Goods (1980)

La place des époux dans la pratique des affaires en droit OHADA - Mainibe Tchiombe, Calice Cléopâtre (Revue Africaine des Réflexions Juridiques et Politiques, 2025)
Le mariage est une institution fondamentale dans de nombreuses sociétés africaines, et le droit OHADA (Organisation pour l’Harmonisation en Afrique du Droit des Affaires) joue un rôle clé dans la régulation des relations entre époux. Depuis son adoption en 1993, le droit OHADA a visé à harmoniser les législations nationales en matière de droit des affaires et de la famille, le législateur s’est également intéressé aux époux. Dans ce contexte il est essentiel de comprendre la place des époux en droit OHADA, notamment en ce qui concerne les droits et devoirs des époux, la gestion des biens communs et personnels dans leurs activités économiques en mettant en lumière les principaux aspects de ce sujet fascinant. Mariage is a fondamental institution in many African societies,and OHADA law plays a key role in regulating relations between spouses.Since its Adoption in 1993.The aim of ohada law has been to harmonise national legislation on business and family law,and the legislator has also taken an interest in spouses .In this context,it is essential to understang the place of spouses in OHADA law particulary as regards the rights and duties of joint and personal property in their economic activities,by higblighting the main aspects of the subject.
Keywords: Affaires; Business; Droit OHADA; Epoux; Mariage; Marriage; OHADA Law; Spouses

La transaction en droit pénal camerounais : contribution à une étude fonctionnelle - Mbarga, Daniel Armel Owona (Revue Africaine des Réflexions Juridiques et Politiques, 2025)
Mode alternatif de règlement des conflits, la transaction s’est introduite dans le droit pénal camerounais. Or, cette discipline est le lieu où s’exerce la violence légitime de l’Etat. La présence de la transaction en son sein suscite des interrogations, qu’il nous est apparu pertinent d’apprécier ce rapprochement. A l’analyse, il s’avère que face à l’engorgement des juridictions et le souci de lutter contre le détournement des deniers publics, la transaction se présente comme un moyen efficace. Aussi, dans une démarche processuelle où la décision imposée est de plus en plus mal ressentie par les justiciables, la transaction se pare de la tunique de la légitimité en aménageant un cadre dans lequel la décision trouve sa source entre une offre et une acceptation. Seulement, le consentement est problématique en cette matière. Pour s’assurer qu’il a été donné de manière libre et éclairé, la présence d’un avocat aux côtés du mis en cause doit être impérative. C’est en cela, qu’à travers la transaction, le droit pénal camerounais peut offrir une justice de qualité.
Keywords: Consentement; Droit pénal; Justice de qualité; Légitimité; Transaction

Corporate purpose and governance in Africa: French-influenced OHADA law, local norms, and heterodox pluralism - Minzoto, Bonheur (Journal of Corporate Law Studies, 2025)
This article examines corporate governance in Africa and its significance for corporate repurposing. It relies on the framework of the Organisation for the Harmonisation of Business Law in Africa (OHADA), which unites seventeen African states under one corporate law jurisdiction while exploring how the interpretation and practice of this legal system can be integrated with or influenced by national sectoral laws and cultural norms. The workings of these different legal sources denote the case for heterodox pluralism of corporate purpose, whereby corporate membership is not tethered to shareholding only, but the workforce and neighbouring too and corporate legitimacy is not merely a function of legal arrangements but equally derives from broader society. The governance of corporations in Africa must correspond to such imperatives to ensure that the prevailing shareholder primacy norm does not continue its unencumbered de facto reign and reduce African stakeholderism to comparative impotence and mere scholarly exercise.
Keywords: CSR; Corporate governance; Corporate purpose; DRC mining legislation; Directors’ liability; Directors’ sustainability duties; Local cultures

A legal analysis of the application of the FATF grey-listing standards on South Africa - Mthembu, Zanele (North-West University, 2025)
The Financial Action Task Force (FATF) is a watchdog established to counter the abuse of the financial system by criminals for money laundering, the financing acts of terrorists and proliferation financing. For the FATF to achieve its mandate, it came up with a set of global standards in the form of Recommendations. The Recommendations seek to mitigate the risks of money laundering and terrorist financing and to assess whether FATF member countries are taking effective action to combat money laundering and terrorist financing. South Africa is a member of the FATF and therefore, is obliged to comply with the standards set to combat money laundering and terrorist financing and proliferation. The FATF uses assessments done through peer mutual evaluations. In other words, FATF members assess one another’s anti-money laundering and counter-terrorism financing (AML/CTF) regulatory frameworks for compliance with FATF’s standards. Following the FATF's assessment in the years 2003, 2009 and 2018, South Africa’s AML/CTF regulatory framework was found to be weak leading to greylisting in 2023. The greylisting of South Africa follows the findings of strategic deficiencies in the country’s implementation of the FATF AML/CFT standards. Greylisting by the FATF carries various economic and reputational implications for South Africa such as increased scrutiny from international partners resulting in increased compliance costs for financial institutions, an estimated reduction in South Africa’s gross domestic product (GDP) and a decrease in foreign direct investment (FDI). Since the greylisting, South Africa has embarked on a legislative and regulatory journey to address the shortcomings with a view to be taken off the greylist. This dissertation provides a detailed analysis of the FATF standards, evaluates South Africa's legislative and institutional responses in the form of the Prevention of Organised Crime Act 121 of 1998, Financial Intelligence Centre Act 38 of 2001 and the Protection of Constitutional Democracy Against Terrorist and Related Activities Act 33 of 2004, and assess their effectiveness in addressing the identified deficiencies. Recommendations are suggested to assist in fortifying South Africa’s AML/CTF regulatory framework.
Keywords: Accountable institutions; GAFI; Greylist; Money laundering; Mutual evaluation; Recommendations; Terrorism financing

The interpretation of social relations in the environmental, social and governance framework - Nxumalo, Nyiko (North-West University, 2025)
Environmental, social and governance (ESG) issues have gained prominence in recent years. Companies have come to understand their role in the global economy and that their decisions cannot be based solely on profits. They are now required to have regard for the environment in which they operate, to be mindful of the social factors that affect their employees, customers and the community at large, and to ensure that their corporate governance complies with the standards set out in the Companies Act 71 of 2008 and the various King Reports. While ESG has become a buzz word in the corporate world, there is still much uncertainty among stakeholders about what they are required to do and what the reporting requirements, if any, are. Its implementation in South Africa is still in its infancy and there is much uncertainty about what ESG monitoring and compliance truly entail. A perfect illustration of this is the fact that the Johannesburg Stock Exchange (JSE) only published ESG disclosure guidelines for the first time in 2022. This means that until the guidelines were published, hundreds of companies in South Africa had been wondering aimlessly in the dark when it comes to ESG issues. To make matters worse, while environmental issues and corporate governance issues have received significant attention from scholars and legislators in South Africa alike, the "S" in ESG has received little attention. It is often treated as the undesirable stepchild that everyone conveniently forgets is part of the ESG family. The purpose of this study is to highlight the gaps in the existing ESG regulatory framework, which leads to gaps in the understanding and monitoring of the implementation of the social indicators of ESG. The study aims to firstly determine whether companies in South Africa have a proper understanding of the social framework of ESG and whether the current legal and/or regulatory framework in South Africa offers sufficient guidance to n organisations to ensure that they comply with and fully implement the social guidelines of the ESG framework.
Keywords: ESG; ESG Framework; Governance factors; King IV report; Section 29 of Companies Act; Social factors; Social indicators

Responsabilité pénale et intelligence artificielle : quel régime pour les infractions causées par des véhicules à délégation de conduite ? - Panzarin Angoula, Rita (Revue Africaine des Réflexions Juridiques et Politiques, 2025)
L'Intelligence Artificielle transforme profondément la société, notamment à travers la mise en place progressive des véhicules autonomes. Cependant, cette évolution technologique introduit de nouveaux défis juridiques, en particulier en matière de responsabilité pénale. En cas d'infraction impliquant un véhicule à délégation de conduite, la responsabilité incombe-t-elle au conducteur, au constructeur, au programmeur ou au système lui-même ? Cette problématique invite à repenser les concepts de responsabilité et d'imputabilité en droit pénal. Il s'agit d'examiner comment adapter le droit pénal actuel aux technologies autonomes, notamment en élaborant une théorie de la responsabilité et en analysant l'attribution des fautes humaines dans des situations de négligence ou d'imprudence. Enfin, l'essor de l'Intelligence Artificielle soulève la question de la reconnaissance d'une personnalité juridique pour ces technologies, rendant nécessaire une réforme légale afin de mieux encadrer les responsabilités des véhicules autonomes et de leurs concepteurs. Artificial Intelligence is profoundly transforming society, in particular through the gradual implementation of autonomous vehicles. However, this technological evolution introduces new legal challenges, particularly in the area of criminal liability. In the event of an offence involving a delegated driving vehicle, does the responsibility lie with the driver, the manufacturer, the programmer, or the system itself? This issue invites us to rethink the concepts of responsibility and imputability in criminal law. The aim is to examine how current criminal law can be adapted to autonomous technologies, in particular by developing a theory of liability and analysing the attribution of human fault in situations of negligence or recklessness. Finally, the rise of Artificial Intelligence raises the question of the recognition of a legal personality for these technologies, making a legal reform necessary in order to better regulate the responsibilities of autonomous vehicles and their designers.
Keywords: AI; Artificial Intelligence; Autonomous vehicles; Criminal liability; Inteligência artificial; Intelligence Artificielle; Responsabilité pénale; Vehicle with delegated driving; Véhicule à délégation de conduite; Véhicules autonomes

Transforming arbitration: exploring the impact of AI, blockchain, metaverse and Web3 - Piers, Maud; McCarthy, Sean (Radboud University Press, 2025)
In an era where technology is rapidly transforming the legal landscape, Transforming Arbitration explores how innovations like AI, blockchain, the Metaverse, and Web3 are reshaping arbitration as a key form of dispute resolution. The book features insights from leading academics, practitioners, and policymakers, offering a comprehensive look at how these advancements are influencing our conceptual, substantive and procedural understandings of many parts of this field. Each chapter examines the challenges and opportunities presented by these technologies, raising important questions about the compatibility of traditional arbitration processes with digital innovations. As the legal field adapts to developments like cryptocurrencies, NFTs, and 'virtual' disputes, this book provides valuable guidance on the future implications for arbitration. By questioning established norms and advocating for fresh approaches, Transforming Arbitration is a vital resource for legal professionals and scholars committed to evolving with the times. Combining theoretical exploration with practical recommendations, this collaborative volume equips the legal community with the tools to navigate the complexities of our digital age with confidence and foresight.
Keywords: AI; Arbitrage; Arbitragem; Arbitration; Artificial Intelligence; Blockchain; Convention on the Recognition and Enforcement of Foreign Arbitral Awards (1958); Electronic Commerce; Inteligência artificial; Intelligence Artificielle; International commercial arbitration; MARD; Mediación; Mediation; Mediação; Médiation; UNCITRAL Arbitration Rules; UNCITRAL Model Law on International Commercial Arbitration (1985)

Impact of the basel accords on small indigenous banks in developing countries : the case of Zambia - Rolls II, Douglas Walter (University of Pretoria, 2025)
The purpose of this thesis is to evaluate the impact of the Basel Accords on small indigenous banks in developing countries, with particular concentration on small Zambian banks. The problem statement intends to investigate whether implementing the three Basel Accords is conducive to the growth of small banks in Zambia. The study further aims to determine whether the present approach to legal regulation of small banks in Zambia is appropriate. The methodology is based on desk-bound research and examination of both primary sources and secondary sources of material such as books, journals, and relevant articles. The study is impacted by the dearth of secondary research work and the difficulty of getting information from sources like the Zambian central bank and other information centres. While Basel I and II seem to have stabilised the Zambian financial sector, the Basel III Accord appears to have impacted negatively on many small banks to the extent that they have been forced into merger and acquisition arrangements with larger foreign banks to fund their undercapitalised positions to survive. It also emerges that the Zambian financial system is strongly linked to the international global economy; regionalisation with organisations like SADC and COMESA being the first stages in the process. This situation is likely to introduce increased instability in the Zambian financial sector by making banks more vulnerable to the vagaries of the international financial markets. It is thus recommended that the Zambian central bank should be more proactive in lobbying for better conditions for small banks from the Basel Committee for Banking Supervision and other international financial regulatory bodies; it should also avoid “cutting and pasting” rules from other jurisdictions to avoid possible distortions in the banking sector. It should also encourage further development of primary and secondary markets in low-cost paper and provide small banks with long-term, low-interest loans to support their growth. The Bank of Zambia, the Zambian central bank, should consider establishing a separate Act financial services Act for small banks to better regulate them. The central bank should also seek out non-Basel Accord solutions for small banks including re-examining the positive aspects of the infant-industry argument. Lastly, it should introduce a formal system for classifying banks in Zambia. At the international level, it is suggested that the global standard-setting bodies should undergo radical reforms to ensure that they are in tandem with the problems that banks in developing countries face as well as allow them to have a say in global standard setting. It is recommended that global standard-setting bodies apply simpler rules for smaller banks. The impact of the Basel Accords on small indigenous banks in developing countries and Zambia, in particular, is important because of the role that small banks play in developing economies in growing small and medium-sized businesses that are often ignored by large foreign banks. It is also important that small banks are allowed to grow into large and medium-sized banks to effectively compete against foreign multinational banks. Institutions based on neoliberal ideals appear to only serve Western businesses’ interests despite their call for all countries to create a level playing field. Due to the dearth of empirical research, there are several gaps in the work that may provide opportunities for further research in this important area of the law.
Keywords: Banking supervision; Basel accords; Basel committee; Developing countries; Financial regulatory framework; Small banks

Expedited procedures in the Multilateral Investment Court: efficiency and consistency - Shouzab, Ali (Uppsala universitet, 2025)
The ongoing ISDS reform, under UNCITRAL Working Group III with a substantial input from the EU, has recently proposed for the establishment of a Multilateral Investment Court (MIC) with an appellate mechanism. Simultaneously, expedited arbitration procedures have gathered significant academic interest in the recent decades. While extensive literature exists on both the MIC development and expedited procedures, their intersection remains relatively unexplored. This dissertation bridges this research gap by analyzing how the best practices from different expedited procedures and EU treaties could be used to establish expedited MIC procedures. Adopting a doctrinal methodology, the research identifies the prominent models and trends in different expedited procedures, accesses their compatibility with the objectives of MIC, and finally proposes a suitable model to attain (cost and time) efficiency and consistency both for the first-tier and appellate proceedings in MIC. By doing so, the study contributes some recommendations for the development of expedited MIC procedures.
Keywords: Appellate Proceedings; Consistency; Efficiency; Expedited MIC Procedures; Expedited Procedures; First-Tier Proceedings; ISDS Reform; Multilateral Investment Court (MIC); UNCITRAL Working Group III

Římskoprávní kořeny nabytí vlastnického práva přírůstkem v návrhu tereziánské kodifikace soukromého práva a v navazujících revizních osnovách - Šmídová Malárová, Lenka (Masarykova Univerzita, 2025)
Monografie představuje výsledky právněhistorické a romanistické analýzy právní úpravy nabývání vlastnického práva přírůstkem (akcesí) v návrhu tereziánské kodifikace soukromého práva z roku 1766 a v navazujících osnovách Hortenově (1776), Martiniho (1796) i finální Zeillerovy, na jejímž základě byl v roce 1811 vydán Všeobecný zákoník občanský (ABGB).
Keywords: Codification du droit; Droit des biens; Droit romain; E-knihy; Elektronické knihy; Knihy; Property law; Propriété; Právní dějiny; Soukromé právo; Vlastnické právo; Čítárna; římské právo

Anonim şirketin haklı sebeple feshinde haklı sebep teşkil edebilecek durumlar - Sunay Ece, Defne (Dokuz Eylül Üniversitesi, 2025)
6102 sayılı Türk Ticaret Kanunu m. 531'de anonim şirketin özel sona erme hallerinden biri olarak haklı sebeplerle fesih düzenlenmiştir. Bu düzenleme ile 6762 sayılı Türk Ticaret Kanunu döneminde anonim şirketin haklı sebeple feshinin mümkün olup olmadığı yönündeki tartışmalar sona ermiş ve anonim şirketin haklı sebeple feshi kurumu hukukumuza kazandırılmıştır. Anonim şirketin haklı sebeple feshi, haklı sebeplerin varlığı durumunda, sermayenin en az onda birini ve halka açık şirketlerde yirmide birini temsil eden pay sahipleri tarafından istenebilir. Anonim şirketin haklı sebeple feshi davası şirket merkezinin bulunduğu yer asliye ticaret mahkemesinde açılır. Kanunda anonim şirketin haklı sebeple feshinde haklı sebep kavramı tanımlanmamış ve haklı sebep teşkil edebilecek durumlara örnek gösterilmemiştir. Kanun gerekçesinde bu kavramın niteliklerinin gösterilmesinin ve tanımlanmasının yargı kararları ve doktrine bırakıldığı belirtilmiştir. İleri sürülen sebeplerin haklı sebep olarak kabul edilip edilmemesi mahkemenin takdirindedir. Yargılama sonucunda mahkemenin şirketin feshine, davacı pay sahiplerinin paylarının değerinin ödenerek şirketten çıkarılmasına veya uygun düşen ve kabul edilebilir diğer bir çözüme karar verme yetkisi bulunmaktadır. Çalışmamız kapsamında anonim şirketin haklı sebeple feshinde haklı sebep teşkil edebilecek durumlar incelenmiştir. Bu inceleme yapılırken kanun metni ve gerekçesi, doktrinde ileri sürülen görüşler ve yargı kararları ile çalışmamız desteklenmiştir. Article 531 of the Turkish Commercial Code No. 6102 regulates the dissolution of a joint stock company for just cause as one of its special grounds for termination. With the introduction of this provision, the debates regarding whether the dissolution of a joint stock company for just cause was possible under the period of the Turkish Commercial Code No. 6762 have been resolved, and the institution of dissolution of a joint stock company for just cause has been incorporated into our legal system. The dissolution of a joint stock company for just cause may be requested by shareholders representing at least one-tenth of the capital, or one-twentieth in publicly traded companies, in the presence of just causes. The lawsuit for the dissolution of a joint stock company for just cause is filed in the commercial court where the company's head office is located. The law does not define the concept of "just cause" in the context of the dissolution of a joint stock company, nor does it provide examples of situations that might constitute just cause. According to the legislative intent, the determination and definition of the characteristics of this concept are left to judicial decisions and legal doctrine. Whether the reasons presented are accepted as just cause is at the discretion of the court. Following the trial, the court has the authority to decide on the dissolution of the company, the payment of the value of the shares to the plaintiff shareholders in exchange for their exit from the company, or another suitable and acceptable solution. This study examines situations that may constitute just cause for the dissolution of a joint stock company for just cause. In this analysis, the text and rationale of the law, views expressed in legal doctrine and judicial decisions have been taken into account.
914518
Keywords: Commercial Law; Corporate law; Dissolution; Joint Stock Company; Just Cause

Sürdürülebilir tedarik zinciri uygulamaları ve ev dışında teslimatın e-memnuniyet, e-sadakat ve ödeme isteği üzerine etkisi: Tüketicilere yönelik karma yöntem uygulaması - Teki̇n, Makber (Akdeniz Üniversitesi, 2025)
Dijitalleşmenin hız kazandığı ve tüketici davranışlarının dönüşüme uğradığı günümüz e-ticaret ortamında, özellikle Covid-19 pandemisi sonrası çevrimiçi alışverişin yaygınlaşması sürdürülebilir lojistik uygulamalarının önemini artırmıştır. Artan sipariş hacmi, çevresel etkiler, karbon salımı ve teslimat sürelerine ilişkin beklentiler; daha verimli, esnek ve çevre dostu teslimat çözümlerine olan ihtiyacı gündeme getirmiştir. Bu bağlamda ev dışında teslimat gibi alternatif lojistik hizmetler ile sosyal, çevresel ve ekonomik sürdürülebilirlik yaklaşımları, tüketici davranışlarını etkileme potansiyeli taşıyan önemli değişkenler olarak öne çıkmaktadır. Bu doğrultuda tezin amacı, sürdürülebilir tedarik zinciri uygulamaları ile ev dışında teslimat modellerinin, e-memnuniyet, e-sadakat ve ödeme isteği üzerindeki etkilerini tüketiciler üzerinden incelemektir. Araştırma, açıklayıcı sıralı karma yöntem stratejisi ile yürütülmüştür. İlk aşamada 300'ü aşkın tüketiciden anket yoluyla nicel veriler toplanmış, ardından ikinci aşamada 27 katılımcı ile yapılan yarı yapılandırılmış görüşmeler aracılığıyla nitel veriler elde edilmiştir. Nicel veriler yapısal eşitlik modellemesiyle, nitel veriler ise tematik analiz yöntemiyle değerlendirilmiştir. Bulgular, özellikle sosyal ve çevresel sürdürülebilirlik boyutlarının e-memnuniyet üzerinde ve ekonomik ve çevresel sürdürülebilirlik boyutlarının ise e-sadakat üzerinde anlamlı etkiler yarattığı yönündedir. Sürdürülebilirliğin üç boyutu da ödeme istekliliği üzerinde anlamlı ve pozitif bir etki yaratmamıştır. Ekonomik sürdürülebilirlik boyutu ise tüketiciler tarafından doğrudan algılanamadığı için memnuniyet üzerinde anlamlı bir etki göstermemiştir. Ev dışında teslimat uygulamalarının esneklik, zaman tasarrufu ve erişilebilirlik gibi avantajlar sunarak e-memnuniyeti ve ödeme isteğini artırdığını göstermektedir. Son olarak e-memnuniyetin, e-sadakati ve e-sadakatin, ödeme isteğini pozitif yönde anlamlı etkilediği sonucuna ulaşılmıştır. Bu tez, sürdürülebilir tedarik zinciri yönetimi, ev dışında teslimat ve e-ticarette tüketici memnuniyeti, tüketici sadakati ve ödeme isteğini bütüncül biçimde ele alan özgün bir model sunmaktadır. Sürdürülebilir tedarik zinciri uygulamaları ve ev dışında teslimat hizmetlerinin tüketici davranışları üzerindeki etkilerini açıklamak amacıyla Sosyal Kimlik Teorisi (SIT), Yeşil Tüketici Davranışı Yaklaşımı ve destekleyici olarak Yeniliğin Yayılımı Teorisi (YYT) çerçevesinde şekillenen kuramsal yapı, sürdürülebilir uygulamaların tüketicilerdeki karşılığını açıklamaya yardımcı olmuştur. Ayrıca bu çalışma, Türkiye örneğinde sürdürülebilir teslimat hizmetlerine yönelik farkındalık düzeyini ve bu hizmetlerin e-memnuniyet, e-sadakat ve ödeme davranışları üzerindeki etkilerini analiz ederek hem akademik literatüre hem de pratik lojistik ve pazarlama stratejilerine katkı sunması beklenmektedir. In today's rapidly evolving e-commerce landscape, shaped by accelerated digitalization and shifting consumer behaviors, the widespread adoption of online shopping - particularly in the aftermath of the Covid-19 pandemic - has amplified the significance of sustainable logistics practices. Increasing order volumes, environmental impacts, carbon emissions, and heightened expectations regarding delivery times have underscored the need for more efficient, flexible, and eco-friendly delivery solutions. In this context, out-of-home delivery services and the dimensions of social, environmental, and economic sustainability have emerged as key variables with the potential to influence consumer behavior. Accordingly, the purpose of this dissertation is to examine the effects of sustainable supply chain practices and out-of-home delivery models on e-satisfaction, e-loyalty, and willingness to pay, through the lens of consumer perceptions. The research adopts an explanatory sequential mixed-methods design. In the first phase, quantitative data were collected via a survey administered to over 300 consumers; in the second phase, qualitative data were obtained through semi-structured interviews conducted with 27 participants. The quantitative data were analyzed using structural equation modeling, while the qualitative data were evaluated through thematic analysis. The findings indicate that the social and environmental dimensions of sustainability have a significant impact on e-satisfaction, while the economic and environmental dimensions significantly influence e-loyalty. None of the three dimensions of sustainability were found to have a significant and positive effect on willingness to pay. The economic dimension of sustainability did not show a significant effect on satisfaction, likely because it is not directly perceived by consumers. Out-of-home delivery practices were found to enhance e-satisfaction and willingness to pay by offering advantages such as flexibility, time savings, and accessibility. Finally, the results revealed that e-satisfaction has a positive and significant effect on e-loyalty, and e-loyalty, in turn, significantly and positively affects willingness to pay. This study aims to develop an original and integrative model that examines sustainable supply chain management, out-of-home delivery, and key consumer outcomes in e-commerce, namely e-satisfaction, e-loyalty, and willingness to pay. Grounded in the Social Identity Theory (SIT), the Green Consumer Behavior Approach, and supported by the Diffusion of Innovations Theory (DOI), the proposed theoretical framework explains how sustainable supply chain practices and out-of-home delivery services shape consumer behavior. Moreover, by investigating the level of awareness of sustainable delivery services in the Turkish context and analyzing their effects on e-satisfaction, e-loyalty, and payment behavior, this research is expected to provide significant contributions to both academic literature and practical implications for logistics and marketing strategies.
Keywords: E-commerce; E-ticaret; Ev Dışı Teslimat; Green Consumer Behavior; Karma Yöntem; Mixed Methods; Out-of-Home Delivery; Sustainable Supply Chain Practices; Sürdürülebilir Tedarik Zinciri Uygulamaları; Yeşil Tüketici Davranışı

La spécificité des contrats de transaction des moyens de paiement dématérialisés - Touaïba Tirmou, Alice (Revue Africaine des Réflexions Juridiques et Politiques, 2025)
Les contrats de transaction des moyens de paiement dématérialisés se caractérisent par une certaine spécificité. Spécificité empreinte d’imprévisibilité juridique. Cette spécificité se voit liée à l’objet du contrat qu’est « la transaction des moyens de paiement dématérialisés ». En effet, il est avéré que les moyens de paiement dématérialisés recèlent une grande complexité, une grande ambigüité qui rend difficile la compréhension et le mécanisme de son fonctionnement. Cette spécificité ambigüité contenue dans les moyens de paiement dématérialisés, est ancrée dans les relations contractuelles relatives à la transaction des moyens de paiement dématérialisés par le fait de la complexité liée à la formation du contrat et par le fait de l’entremêlement des responsabilités des deux parties au contrat. Transaction contracts for dematerialized means of payment are characterized by a certain specificity. Specificity marked by legal unpredictability. This specificity is linked to the purpose of the contract which is “the transaction of dematerialized means of payment”. Indeed, it is proven that dematerialized means of payment contain great complexity, great ambiguity which makes it difficult to understand and the mechanism of its operation. This specific ambiguity contained in dematerialized means of payment is anchored in the contractual relationships relating to the transaction of dematerialized means of payment due to the complexity linked to the formation of the contract and due to the intermingling of the responsibilities of the two parties to the contract.
Keywords: Contract; Contrat; Dematerialized means of payment; Imprévisibilité juridique; Legal unpredictability; Moyens de paiement dématérialisés; Responsabilité; Responsibility; Transaction

Anonim şirketlerde imtiyazlı paylar ve imtiyazlı pay sahipleri özel kurulu - Tuğçe Altintaş, Fatma (Ufuk Üniversitesi, 2025)
Serbest piyasada önemli bir işleve sahip anonim şirketlerde, şirkete yeni sermaye sağlamak veya şirketteki mevcut pay sahiplerinin kontrolü elinde tutmak amacıyla imtiyazlı paylar oluşturulur. İmtiyazlı paylar (TTK m.478) ve imtiyazlı pay sahipleri özel kurulu (TTK m.454) ile şirketteki bazı paylara, diğer paylardan farklı ve üstün haklar, koruma mekanizmaları tanınmıştır. Bu çalışma kapsamında imtiyazlı paylar ve imtiyazlı pay sahipleri özel kurulu; 6102 sayılı Türk Ticaret Kanunu'ndaki (TTK) hükümler, mukayeseli hukuktaki düzenlemeler, öğreti görüşleri, Yargıtay kararları ve uygulamadaki sorunlar ele alınarak incelenmiştir. Konumuz ile ilgili tartışmalı hususlar, kanun ve yargı kararlarıyla netlik kazanması beklenen durumlar irdelenerek yeni bir bakış açısı kazandırmak amaçlanmıştır. Bu doğrultuda ''Anonim Şirketlerde İmtiyazlı Paylar ve İmtiyazlı Pay Sahipleri Özel Kurulu'' başlıklı tezimiz dört bölüm olarak hazırlanmıştır. ''İmtiyazlı Paylar'' başlıklı birinci bölümde, imtiyazlı pay kavramı, benzer kavramlar ve anonim şirketlere hakim olan ilkeler ile mukayese edilerek imtiyazlı pay ilkeleri çerçevesinde incelenmiştir. ''İmtiyazlı Pay Çeşitleri'' başlıklı ikinci bölümde, imtiyazlı pay çeşitleri incelenerek, bölümün ana omurgasını oluşturacak şekilde uygulamada en çok tartışılan hususlar olan, oy hakkında imtiyazlı paylar ve yönetim kurulunda temsil edilme hakkında imtiyazlı paylar irdelenmiştir. ''İmtiyazlı Pay Sahipleri Özel Kurulu'' başlıklı üçüncü bölümde imtiyazlı pay sahipleri özel kurulu kavramı, oluşturulma amacı, hukuki niteliği, mukayeseli hukukta imtiyazlı paylar ve imtiyazlı pay sahipleri özel kurulu, imtiyazlı pay sahipleri özel kurulunun toplanma şartları, toplanma süreci, toplanmasını gerektiren kararlar ve toplanmasına gerek olmayan durumlar ele alınarak incelenmiştir. ''İmtiyazlı Pay Sahipleri Özel Kurul Kararlarının Hukuki Etkisi, İptali ve Hükümsüzlüğü'' başlıklı dördüncü bölümde ise imtiyazlı pay sahipleri özel kurulu kararlarına karşı hukuki koruma mekanizmaları incelenmiştir. In joint-stock companies, which have an important function in the free market, privileged shares are created to provide new capital to the company or to maintain the control of the existing shareholders. In the Turkish Commercial Code No. 6102, privileged shares (TTK m. 478) and the special assembly of privileged shareholders (TTK m. 454) are regulated, granting certain shares in the company different and superior rights and protection mechanisms compared to other shares. With in the scope of this study, privileged shares and the special assembly of privileged shareholders have been examined by addressing the provisions of the Turkish Commercial Code No. 6102, comparative law regulations, doctrinal views, Supreme Court decisions, and practical issues. By examining the controversial issues related to our topic and the situations expected to gain clarity through laws and judicial decisions, it is aimed to provide a new perspective. In this context, our thesis titled "Special Shares and Special Shareholders in Joint-Stock Companies" has been prepared in four sections. In the first chapter titled "Preferred Shares," the concept of preferred shares was examined within the framework of preferred share principles by comparing it with similar concepts and the principles governing joint-stock companies. In the second section titled "Types of Preferred Shares," the various types of preferred shares are examined, focusing on the most debated issues in practice, namely, preferred shares with voting rights and preferred shares with representation on the board of directors, which form the main backbone of the section. In the third section titled "Special Assembly of Preferred Shareholders," the concept of the special assembly of preferred shareholders, its purpose of establishment, legal nature, preferred shares in comparative law, and the special assembly of preferred shareholders, the conditions for convening the special assembly of preferred shareholders, the process of convening, decisions requiring a meeting , and situations where a meeting is not necessary have been examined. In the fourth section titled "Legal Effect, Annulment, and Nullity of Preferred Shareholders Special Assembly Decisions," the legal protection mechanisms against the decisions of the preferred shareholders' special assembly are examined.

Unlocking Africa's trade potential: Boosting regional markets and reducing risks - United Nations Conference on Trade and Development (United Nations, 2025)
Economic Development in Africa Report 2024